A 3D In Vivo Model for Studying Human Renal Cystic Tissue and Mouse Kidney Slices - Bichlmayer, Eva Marie; Mahl, Lina; Hesse, Leo; Pion, Eric; Haller, Victoria; Moehwald, Andreas; Hackl, Christina; Werner, Jens M.; Schlitt, Hans J.; Schwarz, Siegfried; Kainz, Philipp; Brochhausen, Christoph; et al. (Cells, 2022)
(1) Background: Autosomal dominant polycystic kidney disease (ADPKD) is a frequent monogenic disorder that leads to progressive renal cyst growth and renal failure. Strategies to inhibit cyst growth in non-human cyst models have often failed in clinical trials. There is a significant need for models that enable studies of human cyst growth and drug trials. (2) Methods: Renal tissue from ADPKD patients who received a nephrectomy as well as adult mouse kidney slices were cultured on a chorioallantoic membrane (CAM) for one week. The cyst volume was monitored by microscopic and CT-based applications. The weight and angiogenesis were quantified. Morphometric and histological analyses were performed after the removal of the tissues from the CAM. (3) Results: The mouse and human renal tissue mostly remained vital for about one week on the CAM. The growth of cystic tissue was evaluated using microscopic and CT-based volume measurements, which correlated with weight and an increase in angiogenesis, and was accompanied by cyst cell proliferation. (4) Conclusions: The CAM model might bridge the gap between animal studies and clinical trials of human cyst growth, and provide a drug-testing platform for the inhibition of cyst enlargement. Real-time analyses of mouse kidney tissue may provide insights into renal physiology and reduce the need for animal experiments.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 3D in vivo model; ADPKD; chorioallantoic membrane (CAM) model; human renal cystic tissue; mouse kidney slices; polycystic kidney disease

AA amyloidosis in inflammatory active malignant paraganglioma - Ihne, Sandra; Kircher, Malte; Papagianni, Aikaterini; Goetze, Oliver; Morbach, Caroline; Werner, Rudolf A.; Zeller, Daniel; Sommer, Claudia; Rosenwald, Andreas; Amann, Kerstin Ute; Linke, Reinhold P.; Lapa, Constantin; et al. (Amyloid-Journal of Protein Folding Disorders, 2022)
CRIS-Team WoS Importer:2022-02-11

A collagen-binding protein enables molecular imaging of kidney fibrosis in vivo - Baues, Maike; Klinkhammer, Barbara M.; Ehling, Josef; Gremse, Felix; van Zandvoort, Marc A.M.J.; Reutelingsperger, Chris P.M.; Daniel, Christoph; Amann, Kerstin Ute; Bábíčková, Janka; Kiessling, Fabian; Floege, Jürgen; Lammers, Twan; et al. (Kidney International, 2019)
Pathological deposition of collagen is a hallmark of kidney fibrosis. To illustrate this process we employed multimodal optical imaging to visualize and quantify collagen deposition in murine models of kidney fibrosis (ischemia-reperfusion or unilateral ureteral obstruction) using the collagen-binding adhesion protein CNA35. For in vivo imaging, we used hybrid computed tomography-fluorescence molecular tomography and CNA35 labeled with the near-infrared fluorophore Cy7. Upon intravenous injection, CNA35-Cy7 accumulation was significantly higher in fibrotic compared to non-fibrotic kidneys. This difference was not detected for a non-specific scrambled version of CNA35-Cy7. Ex vivo, on kidney sections of mice and patients with renal fibrosis, CNA35-FITC co-localized with fibrotic collagen type I and III, but not with the basement membrane collagen type IV. Following intravenous injection, CNA35-FITC bound to both interstitial and perivascular fibrotic areas. In line with this perivascular accumulation, we observed significant perivascular fibrosis in the mouse models and in biopsy sections from patients with chronic kidney disease using computer-based morphometry quantification. Thus, molecular imaging of collagen using CNA35 enabled specific non-invasive quantification of kidney fibrosis. Collagen imaging revealed significant perivascular fibrosis as a consistent component next to the more commonly assessed interstitial fibrosis. Our results lay the basis for further probe and protocol optimization towards the clinical translation of molecular imaging of kidney fibrosis.
CRIS-Team Scopus Importer:2019-12-17
Keywords: chronic kidney disease (CKD); collagen; extracellular matrix; molecular imaging; non-invasive imaging; renal fibrosis

Activated ERK1/2 increases CD44 in glomerular parietal epithelial cells leading to matrix expansion - Roeder, Sebastian S.; Barnes, Taylor J.; Lee, Jonathan S.; Kato, India; Eng, Diana G.; Kaverina, Natalya V.; Sunseri, Maria W.; Daniel, Christoph; Amann, Kerstin Ute; Pippin, Jeffrey W.; Shankland, Stuart J. (Kidney International, 2017)
The glycoprotein CD44 is barely detected in normal mouse and human glomeruli, but is increased in glomerular parietal epithelial cells following podocyte injury in focal segmental glomerulosclerosis (FSGS). To determine the biological role and regulation of CD44 in these cells, we employed an in vivo and in vitro approach. Experimental FSGS was induced in CD44 knockout and wild-type mice with a cytotoxic podocyte antibody. Albuminuria, focal and global glomerulosclerosis (periodic acid-Schiff stain), and collagen IV staining were lower in CD44 knockout compared with wild-type mice with FSGS. Parietal epithelial cells had lower migration from Bowman's capsule to the glomerular tuft in CD44 knockout mice with disease compared with wild type mice. In cultured murine parietal epithelial cells, overexpressing CD44 with a retroviral vector encoding CD44 was accompanied by significantly increased collagen IV expression and parietal epithelial cell migration. Because our results showed de novo co-staining for activated ERK1/2 (pERK) in parietal epithelial cells in experimental FSGS, and also in biopsies from patients with FSGS, two in vitro strategies were employed to prove that pERK regulated CD44 levels. First, mouse parietal epithelial cells were infected with a retroviral vector for the upstream kinase MEK-DD to increase pERK, which was accompanied by increased CD44 levels. Second, in CD44-overexpressing parietal epithelial cells, decreasing pERK with U0126 was accompanied by reduced CD44. Finally, parietal epithelial cell migration was higher in cells with increased and reduced in cells with decreased pERK. Thus, pERK is a regulator of CD44 expression, and increased CD44 expression leads to a pro-sclerotic and migratory parietal epithelial cell phenotype.
EVALuna2:25535

Activation of the receptor for advanced glycation end products induces nuclear inhibitor of protein phosphatase-1 suppression - Liebisch, Marita; Bondeva, Tzvetanka; Franke, Sybille; Daniel, Christoph; Amann, Kerstin Ute; Wolf, Gunter (Kidney International, 2014)
The activation of the receptor for advanced glycation end products (RAGE) is involved in the development of diabetic nephropathy. Analysis of protein phosphatase-1 indicated that advanced glycation end products did not affect its expression, but increased its phosphatase activity. Using differential display analysis we previously demonstrated that stimulation of RAGE in podocytes modulates the expression of numerous genes, among others nuclear inhibitor of protein phosphatase-1 (NIPP1). Here we found that silencing of NIPP1 induced podocyte hypertrophy, cell cycle arrest, and significantly increased protein phosphatase-1 activity. NIPP1 downregulation was associated with increased p27(Kip1) protein expression. Reporter assays revealed a transcriptional activation of nuclear factor-?B in podocytes after suppression of NIPP1. The protein level of NIPP1 was also significantly reduced in podocytes of diabetic mice. Blocking the RAGE in vivo by a soluble analog elevated the NIPP1 protein in podocytes of diabetic mice. Thus, activation of the RAGE by advanced glycation end products or other ligands suppresses NIPP1 expression in diabetic nephropathy, contributes to podocyte hypertrophy, and glomerular inflammation.
EVALuna2:25459

Acute interstitial nephritis after vaccination with BNT162b2 - Rieckmann, Sonja; Seibert, Felix S.; Hogeweg, Maximilian; Bertram, Sebastian; Doevelaar, Adrian A.N.; Amann, Kerstin Ute; Babel, Nina; Westhoff, Timm H. (Journal of Nephrology, 2022)
CRIS-Team Scopus Importer:2022-03-18
Keywords: BNT162b2; COVID-19; Interstitial nephritis; Kidney injury; Vaccination

Acute Kidney Allograft Injury Following Vitamin C Administration for Septic Shock - Mahling, Moritz; Köppen, Michael; Mühlbacher, Thomas; Amann, Kerstin Ute; Königsrainer, Alfred; Heyne, Nils; Häberle, Helene; Nadalin, Silvio; Guthoff, Martina (Kidney International Reports, 2020)
CRIS-Team Scopus Importer:2020-11-20

Acute respiratory and renal failure in a 20-year-old man - Heissner, K.; Riessen, R.; Horger, M.; Amann, Kerstin Ute; Haap, M. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2015)
EVALuna2:25474

Adhesion GPCR Gpr126 (Adgrg6) Expression Profiling in Zebrafish, Mouse, and Human Kidney. - Cazorla-Vázquez, Salvador; Kösters, Peter; Bertz, Simone; Pfister, Frederick; Daniel, Christoph; Dedden, Mark; Zundler, Sebastian; Jobst-Schwan, Tilman; Amann, Kerstin Ute; Engel, Felix (Cells, 2023)
Adhesion G protein-coupled receptors (aGPCRs) comprise the second-largest class of GPCRs, the most common target for approved pharmacological therapies. aGPCRs play an important role in development and disease and have recently been associated with the kidney. Several aGPCRs are expressed in the kidney and some aGPCRs are either required for kidney development or their expression level is altered in diseased kidneys. Yet, general aGPCR function and their physiological role in the kidney are poorly understood. Here, we characterize in detail Gpr126 (Adgrg6) expression based on RNAscope® technology in zebrafish, mice, and humans during kidney development in adults. Gpr126 expression is enriched in the epithelial linage during nephrogenesis and persists in the adult kidney in parietal epithelial cells, collecting ducts, and urothelium. Single-cell RNAseq analysis shows that gpr126 expression is detected in zebrafish in a distinct ionocyte sub-population. It is co-detected selectively with slc9a3.2, slc4a4a, and trpv6, known to be involved in apical acid secretion, buffering blood or intracellular pH, and to maintain high cytoplasmic Ca2+ concentration, respectively. Furthermore, gpr126-expressing cells were enriched in the expression of potassium transporter kcnj1a.1 and gcm2, which regulate the expression of a calcium sensor receptor. Notably, the expression patterns of Trpv6, Kcnj1a.1, and Gpr126 in mouse kidneys are highly similar. Collectively, our approach permits a detailed insight into the spatio-temporal expression of Gpr126 and provides a basis to elucidate a possible role of Gpr126 in kidney physiology.
EVALuna2:539836
Keywords: adhesion GPCR; kidney development; Gpr126; parietal epithelial cell; collecting duct; urothelium; ionocytes; zebrafish; RNAscope

Adhesion G Protein-Coupled Receptor Gpr126 (Adgrg6) Expression Profiling in Diseased Mouse, Rat, and Human Kidneys - Kösters, Peter; Cazorla Vázquez, Salvador; Krüger, René; Daniel, Christoph; Vonbrunn, Eva; Amann, Kerstin Ute; Engel, Felix (Cells, 2024)
Uncovering the function of understudied G protein-coupled receptors (GPCRs) provides a wealth of untapped therapeutic potential. The poorly understood adhesion GPCR Gpr126 (Adgrg6) is widely expressed in developing kidneys. In adulthood, Gpr126 expression is enriched in parietal epithelial cells (PECs) and epithelial cells of the collecting duct and urothelium. Whether Gpr126 plays a role in kidney disease remains unclear. Here, we characterized Gpr126 expression in diseased kidneys in mice, rats, and humans. RT-PCR data show that Gpr126 expression is altered in kidney disease. A quantitative RNAscope® analysis utilizing cell type-specific markers revealed that Gpr126 expression upon tubular damage is mainly increased in cell types expressing Gpr126 under healthy conditions as well as in cells of the distal and proximal tubules. Upon glomerular damage, an increase was mainly detected in PECs. Notably, Gpr126 expression was upregulated in an ischemia/reperfusion model within hours, while upregulation in a glomerular damage model was only detected after weeks. An analysis of kidney microarray data from patients with lupus nephritis, IgA nephropathy, focal segmental glomerulosclerosis (FSGS), hypertension, and diabetes as well as single-cell RNA-seq data from kidneys of patients with acute kidney injury and chronic kidney disease indicates that GPR126 expression is also altered in human kidney disease. In patients with FSGS, an RNAscope® analysis showed that GPR126 mRNA is upregulated in PECs belonging to FSGS lesions and proximal tubules. Collectively, we provide detailed insights into Gpr126 expression in kidney disease, indicating that GPR126 is a potential therapeutic target.
CRIS-Team Scopus Importer:2024-05-31
Keywords: adhesion GPCR; collecting duct; focal segmental glomerulosclerosis; Gpr126; human; kidney disease; parietal epithelial cell; RNAscope; urothelium

Afferent neurons of the kidney with impaired firing pattern in inflammation – role of sodium currents? - Lale, Nena; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Pflügers Archiv: European Journal of Physiology, 2023)
Peripheral neurons with renal afferents exhibit a predominantly tonic firing pattern of higher frequency that is reduced to low frequencies (phasic firing pattern) in renal inflammation. We wanted to test the hypothesis that the reduction in firing activity during inflammation is due to high-activity tonic neurons switching from higher to low frequencies depending on altered sodium currents. We identified and cultivated afferent sensory neurons with renal projections from the dorsal root ganglia (Th11-L2). Cultivated neurons were incubated with the chemokine CXCL1 (1,5 nmol/ml) for 12 h. We characterized neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., < 5 APs upon stimulation in the current clamp. Their membrane currents were investigated in a voltage clamp. Data analyzed: renal vs. non-renal and tonic vs. phasic neurons. Renal afferent neurons exposed to CXCL1 showed a decrease in tonic firing pattern (CXCL1: 35,6% vs. control: 57%, P < 0.05). Na+ and K+ currents were not different between control renal and non-renal DRG neurons. Phasic neurons exhibited higher Na+ and K+ currents than tonic resulting in shorter APs (3.7 ± 0.3 vs. 6.1 ± 0.6 ms, P < 0.01). In neurons incubated with CXCL1, Na+ and K+ peak current density increased in phasic (Na+: − 969 ± 47 vs. − 758 ± 47 nA/pF, P < 0.01; K+: 707 ± 22 vs. 558 ± 31 nA/pF, P < 0.01), but were unchanged in tonic neurons. Phasic neurons exposed to CXCL1 showed a broader range of Na+ currents ([− 365– − 1429 nA] vs. [− 412– − 4273 nA]; P < 0.05) similar to tonic neurons. After CXCL1 exposure, significant changes in phasic neurons were observed in sodium activation/inactivation as well as a wider distribution of Na+ currents characteristic of tonic neurons. These findings indicate a subgroup of tonic neurons besides mere tonic or phasic neurons exists able to exhibit a phasic activity pattern under pathological conditions.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Chemokine; Firing pattern; Phasic; Renal afferent nerve; Sodium currents; Tonic; Voltage-gated sodium channels

AFFERENT PEPTIDERGIC NERVE FIBERS - IMPORTANCE FOR THE SALT METABOLISM BEYOND THE KIDNEYS? - Ditting, Tilmann; Rodionova, Kristina; Reeh, Peter; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Ott, Christianroland; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Afferent renal innervation in anti-Thy1.1 nephritis in rats - Rodionova, Kristina; Veelken, Roland; Hilgers, Karl Friedrich; Paulus, Eva Maria; Linz, Peter; Fischer, Michael J.M.; Schenker, Martina; Reeh, Peter; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; et al. (American Journal of Physiology-Renal Physiology, 2020)
Afferent renal nerves exhibit a dual function controlling central sympathetic outflow via afferent electrical activity and influencing intrarenal immunological processes by releasing peptides such as calcitonin gene-related peptide (CGRP). We tested the hypothesis that increased afferent and efferent renal nerve activity occur with augmented release of CGRP in anti-Thy1.1 nephritis, in which enhanced CGRP release exacerbates inflammation. Nephritis was induced in Sprague-Dawley rats by intravenous injection of OX-7 antibody (1.75 mg/kg), and animals were investigated neurophysiologically, electrophysiologically, and pathomorphologically 6 days later. Nephritic rats exhibited proteinuria (169.3 ± 10.2 mg/24 h) with increased efferent renal nerve activity (14.7 ± 0.9 bursts/s vs. control 11.5 ± 0.9 bursts/s, n = 11, P < 0.05). However, afferent renal nerve activity (in spikes/s) decreased in nephritis (8.0 ± 1.8 Hz vs. control 27.4 ± 4.1 Hz, n = 11, P < 0.05). In patch-clamp recordings, neurons with renal afferents from nephritic rats showed a lower frequency of high activity following electrical stimulation (43.4% vs. 66.4% in controls, P < 0.05). In vitro assays showed that renal tissue from nephritic rats exhibited increased CGRP release via spontaneous (14 ± 3 pg/mL vs. 6.8 ± 2.8 pg/ml in controls, n = 7, P < 0.05) and stimulated mechanisms. In nephritic animals, marked infiltration of macrophages in the interstitium (26 ± 4 cells/mm2) and glomeruli (3.7 ± 0.6 cells/glomerular cross-section) occurred. Pretreatment with the CGRP receptor antagonist CGRP8-37 reduced proteinuria, infiltration, and proliferation. In nephritic rats, it can be speculated that afferent renal nerves lose their ability to properly control efferent sympathetic nerve activity while influencing renal inflammation through increased CGRP release.
CRIS-Team Scopus Importer:2020-11-13
Keywords: afferent renal neerves; calcitonin gene-related peptide; renal inflammation; renal innervation; sympathetic innervation

AFFERENT RENAL NERVE PATHWAYS IN RATS - RESPONSIVENESS TO HIGH SALT INTAKE - Rodionova, Kristina; Ditting, Tilmann; Fahrmeier, Franziska; Ott, Chirstian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

A High Fat Diet During Pregnancy and Lactation Induces Cardiac and Renal Abnormalities in GLUT4 +/- Male Mice - Kruse, Michael; Fiallo, Ariana; Tao, Jianling; Susztak, Katalin; Amann, Kerstin Ute; Katz, Ellen B.; Charron, Maureen J. (Kidney & Blood Pressure Research, 2017)
Altered nutrients during the in utero (IU) and/or lactation (L) period predispose offspring to cardio-renal diseases in adulthood. This study investigates the effect of a high fat diet (HFD) fed to female mice during IU/L on gene expression patterns associated with heart and kidney failure and hypertension in male offspring.Female wild type (WT) mice were fed either a HFD or control chow (C) prior to mating with males with a genetic heterozygous deletion of GLUT4 (G4+/-, a model of peripheral insulin resistance and hypertension) and throughout IU/L. After weaning male offspring were placed on a standard rodent chow until 24 weeks of age.All offspring exposed to a maternal HFD showed increased heart and kidney weight and reduced cardiac insulin responsiveness. G4+/- offspring on a HFD displayed early hypertension associated with increased renal gene expression of renin and the AT1- receptors compared to G4+/- on a C diet. This group showed decreased cardiac expression of key genes involved in fatty acid oxidation compared to WT on a C diet.These results indicate an interaction between a HFD diet and genotype during early life development that can enhance susceptibility to cardio-renal diseases later in life.
EVALuna2:25542

Akute Nierenschädigung bei Leberinsuffizienz – Fall 10/2016 - Werner, Christoph R.; Wagner, Verena; Sipos, Bence; Büttner-Herold, Maike; Amann, Kerstin Ute; Haap, Michael; Malek, Nisar P.; Bitzer, Michael; Artunc, Ferruh (Deutsche Medizinische Wochenschrift, 2016)
History and admission findings: We report on a 76-year-old man presenting with painless jaundice who developed dialysis-dependent acute kidney injury. Investigations: Biliary tract was examined with endoscopy, in addition kidney biopsy was performed. Diagnosis, treatment and course: A stenosing process could be seen in the biliary tract, leading to stent implantation. However, jaundice did not resolve. Kidney biopsy revealed bile casts indicating cholemic nephropathy. After switch of concomitant medication, hyperbilirubinemia resolved and kidney function was completely restored. Conclusion: Cholestatic liver disease can cause acute kidney injury by formation of bile casts in the tubuli defining cholemic nephropathy. Resolution of cholestasis can restore kidney functio
EVALuna2:25551

Alkali therapy protects renal function, suppresses inflammation, and improves cellular metabolism in kidney disease - Pastor Arroyo, Eva Maria; Yassini, Nima; Sakiri, Elif; Russo, Giancarlo; Bourgeois, Soline; Mohebbi, Nilufar; Amann, Kerstin Ute; Joller, Nicole; Wagner, Carsten A.; Imenez Silva, Pedro Henrique (Clinical Science, 2022)
Chronic kidney disease (CKD) affects approximately 10-13% of the population worldwide and halting its progression is a major clinical challenge. Metabolic acidosis is both a consequence and a possible driver of CKD progression. Alkali therapy counteracts these effects in CKD patients, but underlying mechanisms remain incompletely understood. Here we show that bicarbonate supplementation protected renal function in a murine CKD model induced by an oxalate-rich diet. Alkali therapy had no effect on the aldosterone-endothelin axis but promoted levels of the anti-aging protein klotho; moreover, it suppressed adhesion molecules required for immune cell invasion along with reducing T-helper cell and inflammatory monocyte invasion. Comparing transcriptomes from the murine crystallopathy model and from human biopsies of kidney transplant recipients (KTRs) suffering from acidosis with or without alkali therapy unveils parallel transcriptome responses mainly associated with lipid metabolism and oxidoreductase activity. Our data reveal novel pathways associated with acidosis in kidney disease and sensitive to alkali therapy and identifies potential targets through which alkali therapy may act on CKD and that may be amenable for more targeted therapies.
CRIS-Team Scopus Importer:2022-05-06
Keywords: acid-base balance; alkali therapy; chronic kidney disease; crystal nephropathy; inflammation; metabolism

ALLOGRAFT INFILTRATION AND MENINGOENCEPHALITIS BY SARS-COV-2 IN A PANCREAS-KIDNEY TRANSPLANT RECIPIENT - Doevelaar, A.; Seibert, F.; Bauer, F.; Stervbo, U.; Anft, M.; Rohn, B.; Winnekendonk, G.; Dittmer, U.; Schenker, P.; Amann, Kerstin Ute; Zgoura, P.; Viebahn, R.; et al. (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

Allograft infiltration and meningoencephalitis by SARS-CoV-2 in a pancreas-kidney transplant recipient - Westhoff, Timm H.; Seibert, Felix S.; Bauer, Frederic; Stervbo, Ulrik; Anft, Moritz; Doevelaar, Adrian A. N.; Rohn, Benjamin J.; Winnekendonk, Guido; Dittmer, Ulf; Schenker, Peter; Vonbrunn, Eva; Amann, Kerstin Ute; et al. (American Journal of Transplantation, 2020)
Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) preferentially affects epithelia of the upper and lower respiratory tract. Thus, impairment of kidney function has been primarily attributed until now to secondary effects such as cytokine release or fluid balance disturbances. We provide evidence that SARS-CoV-2 can directly infiltrate a kidney allograft. A 69-year-old male, who underwent pancreas-kidney transplantation 13 years previously, presented to our hospital with coronavirus disease 2019 (COVID-19) pneumonia and impaired pancreas and kidney allograft function. Kidney biopsy was performed showing tubular damage and an interstitial mononuclear cell infiltrate. Reverse transcriptase polymerase chain reaction from the biopsy specimen was positive for SARS-CoV-2. In-situ hybridization revealed SARS-CoV-2 RNA in tubular cells and the interstitium. Subsequently, he had 2 convulsive seizures. Magnetic resonance tomography suggested meningoencephalitis, which was confirmed by SARS-CoV-2 RNA transcripts in the cerebrospinal fluid. The patient had COVID-19 pneumonia, meningoencephalitis, and nephritis. SARS-CoV-2 binds to its target cells through angiotensin-converting enzyme 2, which is expressed in a broad variety of tissues including the lung, brain, and kidney. SARS-CoV-2 thereby shares features with other human coronaviruses including SARS-CoV that were identified as pathogens beyond the respiratory tract as well. The present case should provide awareness that extrapulmonary symptoms in COVID-19 may be attributable to viral infiltration of diverse organs.
CRIS-Team Scopus Importer:2020-09-11

Alternative Splicing in Mechanically Stretched Podocytes as a Model of Glomerular Hypertension - Mattias, Francescapaola; Tsoy, Olga; Hammer, Elke; Gress, Alexander; Simm, Stefan; Lio, Chit Tong; Ameling, Sabine; Amann, Kerstin Ute; Dreher, Leonie; Wenzel, Ulrich; Kacprowski, Tim; List, Markus; et al. (Journal of the American Society of Nephrology, 2025)
Background: Alterations in pre-mRNA splicing are crucial to the pathophysiology of various diseases. However, the effects of alternative splicing of mRNA on podocytes in hypertensive nephropathy are still unknown. The Sys-CARE project aimed to identify alternative splicing events involved in the development and progression of glomerular hypertension. Methods: Murine podocytes were exposed to mechanical stretch, after which proteins and mRNA were analyzed by proteomics, RNA sequencing and several bioinformatic alternative splicing tools. Results: Using transcriptomic and proteomic analysis, we identified significant changes in gene expression and protein abundance due to mechanical stretch. RNA-Seq identified over 3,000 alternative spliced genes after mechanical stretch, including all types of alternative splicing events. Among these, 17 genes exhibited an alternative splicing event across four different splicing analysis tools. From this group, we focused on Myl6, a component of the myosin protein complex, and Shroom3, an actin-binding protein essential for podocyte function. We identified two Shroom3 isoforms with significant expression changes under mechanical stretch, which was validated by qRT-PCR and in situ hybridization. Additionally, we observed an expression switch of two Myl6 isoforms after mechanical stretch, accompanied by an alteration in the C-terminal amino acid sequence. Conclusions: A comprehensive RNA-Seq analysis of mechanically stretched podocytes identified novel potential podocyte-specific biomarkers and highlighted significant alternative splicing events, notably in the mRNA of Shroom3 and Myl6.
CRIS-Team Scopus Importer:2025-06-06

Amyloid fibril structure from the vascular variant of systemic AA amyloidosis - Banerjee, Sambhasan; Baur, Julian; Daniel, Christoph; Pfeiffer, Peter Benedikt; Hitzenberger, Manuel; Kuhn, Lukas; Wiese, Sebastian; Bijzet, Johan; Haupt, Christian; Amann, Kerstin Ute; Zacharias, Martin; Hazenberg, Bouke P.C.; et al. (Nature Communications, 2022)
Systemic AA amyloidosis is a debilitating protein misfolding disease in humans and animals. In humans, it occurs in two variants that are called ‘vascular’ and ‘glomerular’, depending on the main amyloid deposition site in the kidneys. Using cryo electron microscopy, we here show the amyloid fibril structure underlying the vascular disease variant. Fibrils purified from the tissue of such patients are mainly left-hand twisted and contain two non-equal stacks of fibril proteins. They contrast in these properties to the fibrils from the glomerular disease variant which are right-hand twisted and consist of two structurally equal stacks of fibril proteins. Our data demonstrate that the different disease variants in systemic AA amyloidosis are associated with different fibril morphologies.
CRIS-Team Scopus Importer:2022-12-02

ANCA-positive IgA nephropathy in a patient with ANA-positive long-standing rheumatoid arthritis and type 1 diabetes. - Krasselt, Marco; Halbritter, Jan; Amann, Kerstin Ute; Baerwald, Christoph G.; Seifert, Olga (Clinical and Experimental Rheumatology, 2020)
EVALuna2:421408

ANCA-positive IgA nephropathy in a patient with ANA-positive long-standing rheumatoid arthritis and type 1 diabetes - Krasselt, Marco; Halbritter, Jan; Amann, Kerstin Ute; Baerwald, Christoph; Seifert, Olga (Clinical and Experimental Rheumatology, 2020)
CRIS-Team Scopus Importer:2020-06-05

ANCA-positive vasculitis as a secondary autoimmune disease after autologous stem cell transplantation for systemic sclerosis: a case report - Schmalzing, M; Amann, Kerstin Ute; Tony, H-P (Clinical and Experimental Rheumatology, 2014)
Autologous stem cell transplantation (SCT) is increasingly used to treat autoimmune diseases (AD), in particular systemic sclerosis (SSc). Secondary autoimmune diseases are a known complication after autologous stem cell transplantations for any cause. A 43-year-old man had received an autologous stem cell transplantation for an aggressive diffuse cutaneous SSc. After mobilisation with cyclophosphamide and Granulocyte-Colony-Stimulating Factor stem cells were CD34-selected. The patient received a conditioning regimen with cyclophosphamide and Antithymocyte globulin. He had an excellent response with the modified Rodnan Skin Score decreasing from 34 to 3. One year and 4 months after SCT mild erythrocyturia without acanthocytes and proteinuria were seen for the first time on routine urinalysis. During the following year erythrocyturia increased to 131 erythrocytes /?l and protein excretion to 628 mg/g creatinine. At that time, acanthocytes of 25% finally could be detected. Due to the clearly nephritic constellation in urinalysis a renal biopsy was performed, which revealed mild global and focal-segmental sclerosing and focal-segmental proliferative glomerulonephritis without any signs of a IgA-nephropathy. The result was compatible with a renal manifestation of a small-vessel vasculitis. During the following laboratory workup ANCA of a perinuclear pattern with specificity for myeloperoxidase in high titers could be detected. Therefore the diagnosis of a p-ANCA-positive glomerulonephritis was established. As treatment, the patient received Rituximab, which turned out to be effective. We provide the first report of a patient who developed a p-ANCA-associated vasculitis after autologous stem cell transplantation for an autoimmune disease, namely systemic sclerosis.
EVALuna2:25472

Angiostatic immune reaction in colorectal carcinoma: Impact on survival and perspectives for antiangiogenic therapy - Naschberger, Elisabeth; Croner, Roland S.; Merkel, Susanne; Dimmler, Arno; Tripal, Philipp; Amann, Kerstin Ute; Kremmer, Elisabeth; Brueckl, Wolfgang M.; Papadopoulos, Thomas; Hohenadl, Christine; Hohenberger, Werner; Stürzl, Michael (International Journal of Cancer, 2008)
Angiogenesis and inflammation are the 2 major stroma reactions in colorectal carcinoma (CRC). Guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation. Therefore, we hypothesized that GBP-1 may be a biomarker of intrinsic angiostasis associated with an improved outcome in CRC patients. GBP-1 was strongly expressed in endothelial cells and immune cells in the desmoplastic stroma of 32% of CRC as determined by immunohistochemical investigation of 388 sporadic CRC. Cancer-related 5-year survival was highly significant (p < 0.001) increased (16.2%) in patients with GBP-1-positive CRC. Multivariate analysis showed that GBP-1 is an independent prognostic factor indicating a reduction of the relative risk of cancer-related death by the half (p = 0.032). A comparative transcriptome analysis (22,215 probe sets) of GBP-1-positive (n = 12) and -negative (n = 12) tumors showed that particularly IFN-γ-induced genes including the major antiangiogenic chemokines CXCL9, CXCL10 and CXCL11 were coexpressed with GBP-1. Altogether our findings indicated that GBP-1 may be a novel biomarker and an active component of a Th-1-like angiostatic immune reaction in CRC. This reaction may affect patient's response to antiangiogenic therapy and the identification of such tumors may provide a novel criterion for patient selection. Moreover, the induction of a Th-1-like angiostatic immune reaction may be a promising approach for the clinical treatment of CRC. © 2008 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Colorectal carcinoma; Guanylate binding protein-1; Inflammation; Interferon-γ

Angiotensin II type 1a receptor-deficient mice develop angiotensin II-induced oxidative stress and DNA damage without blood pressure increase - Zimnol, Anna; Amann, Kerstin Ute; Mandel, Philipp; Hartmann, Christina; Schupp, Nicole (American Journal of Physiology-Renal Physiology, 2017)
Hypertensive patients have an increased risk to develop kidney cancer. We have shown in vivo, that besides elevating blood pressure, angiotensin II causes DNA damage dose-dependently. Here, the role of blood pressure in the formation of DNA damage is studied. Mice lacking one of the two murine angiotensin II type 1 receptor (AT1R) subtypes, AT1aR, were equipped with osmotic minipumps, delivering angiotensin II during 28 days. Parameters of oxidative stress and DNA damage of kidneys and hearts of AT1aR-knockout mice were compared to wildtype (C57BL/6) mice receiving angiotensin II, and additionally, to wildtype (WT) mice treated with candesartan, an antagonist of both AT1R-subtypes. In WT mice, angiotensin II induced hypertension, reduced kidney function and led to a significant formation of reactive oxygen species (ROS). Furthermore, genomic damage was markedly increased in this group. All these responses to angiotensin II could be attenuated by concurrent administration of candesartan. In AT1aR-deficient mice treated with angiotensin II, systolic pressure was not increased, and renal function was not affected. However, angiotensin II still led to an increase of ROS in kidneys and hearts of these animals. Additionally, genomic damage in the form of double-strand breaks, was significantly induced in kidneys of AT1aR-deficient mice. Our results show that angiotensin II induced ROS production and DNA damage even without the presence of AT1aR and independently of blood pressure changes.
EVALuna2:25539

A noninvasive diagnostic approach to retrospective donor HLA typing in kidney transplant patients using urine - Bach, Christian; Knaup, Karl; Herrmann, Markus; Krumbiegel, Mandy; Pfister, Frederick; Büttner-Herold, Maike; Steffen, Martin; Zecher, Daniel; Lopau, Kai; Schneider, Karen; Dieterle, Anne; Amann, Kerstin Ute; et al. (Transplant International, 2021)
Antibody-mediated rejection (AMR) is a major obstacle to long-term kidney transplantation. AMR is mostly caused by donor specific HLA antibodies, which can arise before or any time after transplantation. Incomplete donor HLA typing and unavailability of donor DNA regularly preclude the assessment of donor-specificity of circulating anti-HLA antibodies. In our centre, this problem arises in approximately 20% of all post-transplant HLA-antibody assessments. We demonstrate that this diagnostic challenge can be resolved by establishing donor renal tubular cell cultures from recipient´s urine as a source of high-quality donor DNA. DNA was then verified for genetic origin and purity by fluorescence in situ hybridization and short tandem repeat analysis. Two representative cases highlight the diagnostic value of this approach which is corroborated by analysis of ten additional patients. The latter were randomly sampled from routine clinical care patients with available donor DNA as controls. In all 12 cases, we were able to perform full HLA typing of the respective donors confirmed by cross-comparison to results from the stored 10 donor DNAs. We propose that this noninvasive diagnostic approach for HLA typing in kidney transplant patients is valuable to determine donor specificity of HLA antibodies, which is important in clinical assessment of suspected AMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; HLA typing; HLA-antibody post-transplantation; rejection

A novel urinary proteomics classifier for non-invasive evaluation of interstitial fibrosis and tubular atrophy in chronic kidney disease - Catanese, Lorenzo; Siwy, Justyna; Mavrogeorgis, Emmanouil; Amann, Kerstin Ute; Mischak, Harald; Beige, Joachim; Rupprecht, Harald (Proteomes, 2021)
Non-invasive urinary peptide biomarkers are able to detect and predict chronic kidney disease (CKD). Moreover, specific urinary peptides enable discrimination of different CKD etiologies and offer an interesting alternative to invasive kidney biopsy, which cannot always be performed. The aim of this study was to define a urinary peptide classifier using mass spectrometry technology to predict the degree of renal interstitial fibrosis and tubular atrophy (IFTA) in CKD patients. The urinary peptide profiles of 435 patients enrolled in this study were analyzed using capillary electrophoresis coupled with mass spectrometry (CE-MS). Urine samples were collected on the day of the diagnostic kidney biopsy. The proteomics data were divided into a training (n = 200) and a test (n = 235) cohort. The fibrosis group was defined as IFTA ≥ 15% and no fibrosis as IFTA < 10%. Statistical comparison of the mass spectrometry data enabled identification of 29 urinary peptides with differential occurrence in samples with and without fibrosis. Several collagen fragments and peptide fragments of fetuinA and others were combined into a peptidomic classifier. The classifier separated fibrosis from non-fibrosis patients in an independent test set (n = 186) with area under the curve (AUC) of 0.84 (95% CI: 0.779 to 0.889). A significant correlation of IFTA and FPP_BH29 scores could be observed Rho = 0.5, p < 0.0001. We identified a peptidomic classifier for renal fibrosis containing 29 peptide fragments corresponding to 13 different proteins. Urinary proteomics analysis can serve as a noninvasive tool to evaluate the degree of renal fibrosis, in contrast to kidney biopsy, which allows repeated measurements during the disease course.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Biomarkers; Fibrosis; IFTA; Peptides; Urine

Anti-BAFF treatment interferes with humoral responses in a model of renal transplantation in rats - Steines, Louisa; Poth, Helen; Schuster, Antonia; Geissler, Edward K.; Amann, Kerstin Ute; Banas, Bernhard; Bergler, Tobias (Transplantation, 2019)
BACKGROUND: B cell activating factor (BAFF) is associated with donor-specific antibodies (DSA) and poorer outcomes after renal transplantation (RTx). We examined the effects of anti-BAFF treatment on B cells, expression of costimulatory molecules and cytokines, germinal centers (GCs) and DSA formation in a RTx model in rats. METHODS: Anti-BAFF antibody was injected on days 3, 17, 31 and 45 after allogeneic RTx. Rats received reduced dose cyclosporine A (CsA) for 28 or 56 days to allow chronic rejection and DSA formation. Leukocytes, B cell subsets and DSA were measured using flow cytometry; expression of cytokines and costimulatory molecules was measured by qRT-PCR, and GCs and T follicular helper (TfH) were assessed using immunohistochemistry. Rejection was evaluated by a nephropathologist. RESULTS: Anti-BAFF treatment reduced the frequency of B cells in allografts and spleen. Naïve B cells were strongly reduced by anti-BAFF treatment in all compartments. mRNA expression of IL-6 and the costimulatory molecules CD40 and ICOS ligand was significantly reduced in anti-BAFF-treated rats. GCs were smaller and plasmablast/plasma cell numbers lower in anti-BAFF-treated rats, which was reflected by less DSA in certain IgG subclasses. CONCLUSIONS: Anti-BAFF treatment interferes with humoral responses at multiple levels in this model of allogeneic RTx.
EVALuna2:205573

Aprotinin prevents proteolytic epithelial sodium channel (ENaC) activation and volume retention in nephrotic syndrome - Bohnert, Bernhard N.; Menacher, Martina; Janessa, Andrea; Woern, Matthias; Schork, Anja; Daiminger, Sophie; Kalbacher, Hubert; Haering, Hans-Ulrich; Daniel, Christoph; Amann, Kerstin Ute; Sure, Florian; Bertog, Marko; et al. (Kidney International, 2018)
Volume retention in nephrotic syndrome has been linked to activation of the epithelial sodium channel (ENaC) by proteolysis of its ?-subunit following urinary excretion of serine proteases such as plasmin. Here we tested whether pharmacological inhibition of urinary serine protease activity might protect from ENaC activation and volume retention in nephrotic syndrome. Urine from both nephrotic mice (induced by doxorubicin injection) and nephrotic patients exhibited high aprotinin-sensitive serine protease activity. Treatment of nephrotic mice with the serine protease inhibitor aprotinin by means of subcutaneous sustained-release pellets normalized urinary serine protease activity and prevented sodium retention, as did treatment with the ENaC inhibitor amiloride. In the kidney cortex from nephrotic mice, immunofluorescence revealed increased apical ?-ENaC staining, normalized by aprotinin treatment. In Xenopus laevis oocytes heterologously expressing murine ENaC, aprotinin had no direct inhibitory effect on channel activity but prevented proteolytic channel activation. Thus, our study shows that volume retention in experimental nephrotic syndrome is related to proteolytic ENaC activation by proteasuria and can be prevented by treatment with aprotinin. Hence, inhibition of urinary serine protease activity might become a therapeutic approach to treat patients with nephrotic-range proteinuri
EVALuna2:25560

Artificial intelligence in kidney transplant pathology Künstliche Intelligenz in der Nierentransplantationspathologie - Bülow, Roman David; Lan, Yu Chia; Amann, Kerstin Ute; Boor, Peter (Die Pathologie, 2024)
Background: Artificial intelligence (AI) systems have showed promising results in digital pathology, including digital nephropathology and specifically also kidney transplant pathology. Aim: Summarize the current state of research and limitations in the field of AI in kidney transplant pathology diagnostics and provide a future outlook. Materials and methods: Literature search in PubMed and Web of Science using the search terms “deep learning”, “transplant”, and “kidney”. Based on these results and studies cited in the identified literature, a selection was made of studies that have a histopathological focus and use AI to improve kidney transplant diagnostics. Results and Conclusion: Many studies have already made important contributions, particularly to the automation of the quantification of some histopathological lesions in nephropathology. This likely can be extended to automatically quantify all relevant lesions for a kidney transplant, such as Banff lesions. Important limitations and challenges exist in the collection of representative data sets and the updates of Banff classification, making large-scale studies challenging. The already positive study results make future AI support in kidney transplant pathology appear likely.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Computer assistance; Datenintegration; Deep learning; Histomorphometry; Kidney transplantation

Assessment and Risk Prediction of Chronic Kidney Disease and Kidney Fibrosis Using Non-Invasive Biomarkers. - Rupprecht, Harald; Catanese, Lorenzo; Amann, Kerstin Ute; Hengel, Felicitas E.; Huber, Tobias B.; Latosinska, Agnieszka; Lindenmeyer, Maja T.; Mischak, Harald; Siwy, Justyna; Wendt, Ralph; Beige, Joachim (International Journal of Molecular Sciences, 2024)
Effective management of chronic kidney disease (CKD), a major health problem worldwide, requires accurate and timely diagnosis, prognosis of progression, assessment of therapeutic efficacy, and, ideally, prediction of drug response. Multiple biomarkers and algorithms for evaluating specific aspects of CKD have been proposed in the literature, many of which are based on a small number of samples. Based on the evidence presented in relevant studies, a comprehensive overview of the different biomarkers applicable for clinical implementation is lacking. This review aims to compile information on the non-invasive diagnostic, prognostic, and predictive biomarkers currently available for the management of CKD and provide guidance on the application of these biomarkers. We specifically focus on biomarkers that have demonstrated added value in prospective studies or those based on prospectively collected samples including at least 100 subjects. Published data demonstrate that several valid non-invasive biomarkers of potential value in the management of CKD are currently available.
EVALuna2:566232

Association of Blood Donor-derived Cell-free DNA Levels with Banff Scores and Histopathological Lesions in Kidney Allograft Biopsies: Results from an Observational Study - Akifova, Aylin; Budde, Klemens; Choi, Mira; Amann, Kerstin Ute; Büttner-Herold, Maike; Oellerich, Michael; Beck, Julia; Bornemann-Kolatzki, Kirsten; Schütz, Ekkehard; Bachmann, Friederike; Halleck, Fabian; Schrezenmeier, Eva V.; et al. (Transplantation Direct, 2025)
Background. Donor-derived cell-free DNA (dd-cfDNA) is an emerging biomarker of kidney allograft injury, mainly investigated in the context of rejection. However, the dd-cfDNA dynamics in other graft pathologies merit further investigation. Methods. In this single-center observational study, we prospectively collected dd-cfDNA at indication biopsies. To evaluate the association between dd-cfDNA and different histological patterns, we correlated absolute and relative dd-cfDNA (thresholds of 50 copies/mL and 0.5%, respectively) with the Banff 2022 lesion scores and the assigned diagnoses. Results. We examined 151 dd-cfDNA paired biopsies in 131 kidney transplant recipients and found significantly higher absolute dd-cfDNA levels in antibody-mediated rejection (n, median, IQR: 45, 63 copies/mL, 42-89), microvascular inflammation (MVI) without donor-specific antibodies or C4d-deposition (6, 102 copies/mL, 61-134), mixed rejection (8, 140 copies/mL, 77-171), and BK virus-Associated nephropathy (6, 213 copies/mL, 83-298) compared with glomerulonephritis (20, 12 copies/mL, 8-18), calcineurin toxicity (19, 10 copies/mL, 7-16), interstitial fibrosis/tubular atrophy (12, 10 copies/mL, 9-16) and normal histology (6, 9 copies/mL, 7-16). In the multivariable analysis, absolute and relative dd-cfDNA correlated with the peritubular capillaritis (ptc), glomerulitis (g), and tubulitis (t) scores. In the receiver operating characteristic analysis, absolute dd-cfDNA showed best discrimination for MVI of any cause (area under the curve [AUC] 0.88, sensitivity 0.71, specificity 0.86, positive predictive value [PPV] 0.76, negative predictive value [NPV] 0.82), followed by antibody-mediated rejection including mixed rejection (AUC 0.85, sensitivity 0.72, specificity 0.83, PPV 0.69, NPV 0.84), and overall rejection (AUC 0.83, sensitivity 0.66, specificity 0.85, PPV 0.76, NPV 0.77). T cell-mediated rejection was only detectable by dd-cfDNA when associated with vascular lesions. Conclusions. Altogether, we conclude that dd-cfDNA-release is not limited to rejection-related injury phenotypes and is mainly driven by MVI in kidney allografts.
CRIS-Team Scopus Importer:2025-05-02

Association of donor hypertension and recipient renal function in living donor kidney transplantation: A single-center retrospective study - Dienemann, Thomas; Schellenberg, Jana; Heller, Katharina; Daniel, Christoph; Amann, Kerstin Ute; Hilgers, Karl Friedrich; Schiffer, Mario; Weidemann, Alexander (Clinical Transplantation, 2019)
Transplant centers now accept living donors with well-controlled hypertension. Little is known whether hypertension in living donors affects recipient's kidney function. We aimed to examine potential differences in kidneys from hypertensive donors compared to normotensive donors with respect to renal function over 36 months and histologic findings at transplantation (T0) and 12 months after transplantation (T1). Retrospective single-center analysis of 174 living donor-recipient pairs (age > 18; transplantation date 1/2008-3/2016). Hypertension in donors was defined as being on antihypertensive medication. All biopsies were assessed by the same blinded, experienced renal pathologist. Biopsies were scored for glomerulosclerosis, IFTA, and arteriosclerosis. Regression models were used to examine the relationship of donor hypertension with renal function and histologic changes. Hypertensive donors were significantly older than normotensive donors. Chronic changes such as tubular atrophy and atherosclerosis were more evident in kidneys from hypertensive donors at T0 as well as T1. Donor hypertension was independently associated with histologic changes at T0 and T1 but not with renal function over the follow period. Despite more pronounced histologic changes in kidneys from hypertensive living donors, these grafts exhibited a similar functional outcome. However, they subsequently might be at a greater risk and warrant thorough follow-up care.
CRIS-Team WoS Importer:2019-09-27

AT II Receptor Blockade and Renal Denervation: Different Interventions with Comparable Renal Effects? - Rodionova, Kristina; Hindermann, Martin; Hilgers, Karl Friedrich; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Kidney & Blood Pressure Research, 2021)
Background: Angiotensin II (Ang II) and the renal sympathetic nervous system exert a strong influence on renal sodium and water excretion. We tested the hypothesis that already low doses of an Ang II inhibitor (candesartan) will result in similar effects on tubular sodium and water reabsorption in congestive heart failure (CHF) as seen after renal denervation (DNX). Methods: Measurement of arterial blood pressure, heart rate (HR), renal sympathetic nerve activity (RSNA), glomerular filtration rate (GFR), renal plasma flow (RPF), urine volume, and urinary sodium. To assess neural control of volume homeostasis, 21 days after the induction of CHF via myocardial infarction rats underwent volume expansion (0.9% NaCL; 10% body weight) to decrease RSNA. CHF rat and controls with or without DNX or pretreated with the Ang II type-1 receptor antagonist candesartan (0.5 ug i.v.) were studied. Results: CHF rats excreted only 68 + 10.2% of the volume load (10% body weight) in 90 min. CHF rats pretreated with candesartan or after DNX excreted from 92 to 103% like controls. Decreases of RSNA induced by volume expansion were impaired in CHF rats but unaffected by candesartan pointing to an intrarenal drug effect. GFR and RPF were not significantly different in controls or CHF. Conclusion: The prominent function of increased RSNA - retaining salt and water - could no longer be observed after renal Ang II receptor blockade in CHF rats.
CRIS-Team WoS Importer:2021-06-11
Keywords: Renal sympathetic innervation; Angiotensin II; Congestive heart failure; Renal nerve ablation; Renal function

Basic nephropathology for pathologists—part 1: Kidney biopsy—inflammation and immune complexes Grundlagen der Nierenpathologie für Pathologen – Teil 1: Nierenbiopsie – Inflammation und Immunkomplexe - Büttner-Herold, Maike; Gaspert, Ariana; Amann, Kerstin Ute (Pathologe, 2022)
The assessment of kidney biopsies is mainly confined to specialized centres. However, sometimes a kidney biopsy is submitted to a general pathologist, and in addition peritumorous renal parenchyma in tumour nephrectomies can have concomitant non-neoplastic renal disease. Here we present a survey of inflammatory and immunologic changes in all renal compartments, which may in part indicate the need of prompt therapeutic intervention such as in vasculitis, glomerulonephritis and interstitial nephritis. It is important to take into account that renal involvement of vasculitis is mainly centred in glomeruli and only to a much lesser extent in arteries, and that the frequently observed interstitial inflammation very often is an epiphenomenon of another primary kidney disease and not an independent disease process. Typical renal patterns of injury are emphasised.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Biopsy; Differential diagnosis; Immune complexes; Inflammation; Microscopy

Batf-dependent Th17 cells critically regulate IL-23 driven colitis-associated colon cancer - Punkenburg, Elise; Vogler, Tina; Büttner, Maike; Amann, Kerstin Ute; Waldner, Maximilian; Atreya, Raja; Abendroth, Benjamin; Mudter, Jonas; Merkel, Susanne; Gallmeier, Eike; Rose-John, Stefan; Neurath, Markus; et al. (Gut, 2016)
IBDs have an increased risk for development of colorectal cancer (CRC). Here, we aimed at the characterisation of the functional role of Th17-associated transcription factors in sporadic and colitis-associated colon cancer in vivo.We used mice deficient or transgenic for the activating protein 1 family member basic leucine zipper transcription factor ATF-like (Batf) to evaluate the role of Th17 cells during sporadic and inflammation-induced colon carcinogenesis. We also studied the expression of Batf and ROR?t in patients with IBD and CRC.Batf but not retinoic acid-related orphan receptor ?t(ROR?t) expression was significantly increased together with interleukin (IL) 23 expression in UC but not in Crohn's disease (CD) tissue samples. In CRC also Batf but not ROR?t expression was increased and its expression correlated with the IL-23 and IL-23 receptor (IL-23R) expression. Finally, Batf but not ROR?t was coexpressed with IL-17a, IL-23R and IL-6 within CRC-infiltrating CD4(+) T cells. Functional studies in mice revealed that Batf-dependent T cells are crucial regulators of sporadic and inflammation-induced CRC. Colitis-associated Batf(-/-) tumours lacked IL-17a(+)IL-23R(+)IL-6(+)CD4(+) T cells, hence displaying characteristics reminiscent of human CRC-infiltrating CD4(+) T cells. Strikingly, Batf(-/-) tumours contained low IL-23 but high IL-17a expression levels. Tumour formation and intratumoral IL-23 expression could be restored by administration of Hyper-IL-6 consisting of IL-6 and soluble IL-6 receptor.Batf-dependent IL-23R(+)IL-6(+)CD4(+) Th17 cells critically control IL-23 driven colitis-associated tumour formation and the progression of sporadic colon tumours. Batf-dependent IL-23R(+) T cells represent a potential future therapeutic target limiting CRC progression.
EVALuna2:2026

BDNF: mRNA expression in urine cells of patients with chronic kidney disease and its role in kidney function - Endlich, Nicole; Lange, Tim; Kuhn, Jana; Klemm, Paul; Kotb, Ahmed M.; Siegerist, Florian; Kindt, Frances; Lindenmeyer, Maja T.; Cohen, Clemens D.; Kuss, Andreas W.; Nath, Neetika; Rettig, Rainer; et al. (Journal of Cellular and Molecular Medicine, 2018)
Podocyte loss and changes to the complex morphology are major causes of chronic kidney disease (CKD). As the incidence is continuously increasing over the last decades without sufficient treatment, it is important to find predicting biomarkers. Therefore, we measured urinary mRNA levels of podocyte genes NPHS1, NPHS2, PODXL and BDNF, KIM-1, CTSL by qRT-PCR of 120 CKD patients. We showed a strong correlation between BDNF and the kidney injury marker KIM-1, which were also correlated with NPHS1, suggesting podocytes as a contributing source. In human biopsies, BDNF was localized in the cell body and major processes of podocytes. In glomeruli of diabetic nephropathy patients, we found a strong BDNF signal in the remaining podocytes. An inhibition of the BDNF receptor TrkB resulted in enhanced podocyte dedifferentiation. The knockdown of the orthologue resulted in pericardial oedema formation and lowered viability of zebrafish larvae. We found an enlarged Bowman's space, dilated glomerular capillaries, podocyte loss and an impaired glomerular filtration. We demonstrated that BDNF is essential for glomerular development, morphology and function and the expression of BDNF and KIM-1 is highly correlated in urine cells of CKD patients. Therefore, BDNF mRNA in urine cells could serve as a potential CKD biomarker.
EVALuna2:156717

Biallelic ANKS6 mutations cause late-onset ciliopathy with chronic kidney disease through YAP dysregulation - Schwarz, Hannah; Popp, Bernt; Airik, Rannar; Torabi Sarijalo, Nasrin; Knaup, Karl; Stoeckert, Johanna; Wiech, Thorsten; Amann, Kerstin Ute; Wiesmann da Silva Reis, André; Schiffer, Mario; Schueler, Markus; Wiesener, Michael (Human Molecular Genetics, 2022)
Nephronophthisis-related ciliopathies (NPHP-RC) comprises a group of inherited kidney diseases, caused by mutations in genes encoding proteins localizing to primary cilia. NPHP-RC represents one of the most frequent monogenic causes of renal failure within the first three decades of life, but its molecular disease mechanisms remain unclear. Here, we identified biallelic ANKS6 mutations in two affected siblings with late-onset chronic kidney disease by whole-exome sequencing. We employed patient-derived fibroblasts generating an in vitro model to study the precise biological impact of distinct human ANKS6 mutations, completed by immunohistochemistry studies on renal biopsy samples. Functional studies using patient-derived cells showed an impaired integrity of the ciliary inversin compartment with reduced cilia length. Further analyses demonstrated that ANKS6 deficiency leads to a dysregulation of Hippo-signaling through nuclear yes-associated protein (YAP) imbalance and disrupted ciliary localization of YAP. In addition, an altered transcriptional activity of canonical Wnt target genes and altered expression of non-phosphorylated (active) beta-catenin and phosphorylated glycogen synthase kinase 3 beta were observed. Upon ciliation, ANKS6 deficiency revealed a deranged subcellular localization and expression of components of the endocytic recycling compartment. Our results demonstrate that ANKS6 plays a key role in regulating the Hippo pathway, and ANKS6 deficiency is linked to dysregulation of signaling pathways. Our study provides molecular clues in understanding pathophysiological mechanisms of NPHP-RC and may offer new therapeutic targets.
CRIS-Team WoS Importer:2022-05-13

Biallelic Expression of Mucin-1 in Autosomal Dominant Tubulointerstitial Kidney Disease: Implications for Nongenetic Disease Recognition - Knaup, Karl; Hackenbeck, Thomas; Popp, Bernt; Stoeckert, Johanna; Wenzel, Andrea; Büttner-Herold, Maike; Pfister, Frederick; Schüler, Markus; Seven, Didem; May, Annette M.; Halbritter, Jan; Gröne, Hermann Josef; et al. (Journal of the American Society of Nephrology, 2018)
BACKGROUND: Providing the correct diagnosis for patients with tubulointerstitial kidney disease and secondary degenerative disorders, such as hypertension, remains a challenge. The autosomal dominant tubulointerstitial kidney disease (ADTKD) subtype caused by MUC1 mutations (ADTKD-MUC1) is particularly difficult to diagnose, because the mutational hotspot is a complex repeat domain, inaccessible with routine sequencing techniques. Here, we further evaluated SNaPshot minisequencing as a technique for diagnosing ADTKD-MUC1 and assessed immunodetection of the disease-associated mucin 1 frameshift protein (MUC1-fs) as a nongenetic technique. METHODS: We re-evaluated detection of MUC1 mutations by targeted repeat enrichment and SNaPshot minisequencing by haplotype reconstruction via microsatellite analysis in three independent ADTKD-MUC1 families. Additionally, we generated rabbit polyclonal antibodies against MUC1-fs and evaluated immunodetection of wild-type and mutated allele products in human kidney biopsy specimens. RESULTS: The detection of MUC1 mutations by SNaPshot minisequencing was robust. Immunostaining with our MUC1-fs antibodies and an MUC1 antibody showed that both proteins are readily detectable in human ADTKD-MUC1 kidneys, with mucin 1 localized to the apical membrane and MUC1-fs abundantly distributed throughout the cytoplasm. Notably, immunohistochemical analysis of MUC1-fs expression in clinical kidney samples facilitated reliable prediction of the disease status of individual patients. CONCLUSIONS: Diagnosing ADTKD-MUC1 by molecular genetics is possible, but it is technically demanding and labor intensive. However, immunohistochemistry on kidney biopsy specimens is feasible for nongenetic diagnosis of ADTKD-MUC1 and therefore, a valid method to select families for further diagnostics. Our data are compatible with the hypothesis that specific molecular effects of MUC1-fs underlie the pathogenesis of this disease.
EVALuna2:34428

Bi-nucleation of podocytes is uniformly accompanied by foot processes widening in renal disease - Muehldorfer, Johanna; Pfister, Eva; Buettner-Herold, Maike; Klewer, Monika; Amann, Kerstin Ute; Daniel, Christoph (Nephrology Dialysis Transplantation, 2017)
Podocytes are terminally differentiated glomerular cells expressing a highly complex architecture and lacking the ability to proliferate. However, during renal injury or stress these cells can re-enter into the cell cycle but fail to divide. As a consequence, bi- and multi-nucleated podocytes can be identified in renal biopsies from patients with various kidney diseases. It is still unclear whether the occurrence of such cells is dependent on or correlates with renal damage and if bi- or multi-nucleation results in ultrastructural alterations such as e.g. foot process effacement. Therefore, we investigated the frequency, correlation with clinical parameters and morphological consequences of podocyte bi- or multi-nucleation in a cohort of 377 patients suffering from different renal diseases.Renal biopsies from patients with minimal change disease (MCD; n = 93), IgA-glomerulonephritis (IgA-GN, n = 95), lupus nephritis (LN; n = 90) and diabetic nephropathy (DN; n = 99) were investigated for the occurrence of bi-nucleated or multi-nucleated podocytes using semi-thin sections and light-microscopy at 1000× magnification. The frequency of bi-nucleation and multi-nucleation in podocytes was correlated with clinical parameters and markers of renal injury. In addition, ultrastructural morphological features associated with podocyte bi- or multi-nucleation were analysed by scanning transmission electron microscopy at various magnifications.Ultrastructural analysis of podocyte nuclear morphology revealed a broad spectrum of nuclear appearances. Therefore, podocytes were classified in cells with mono-nucleated, lobulated, potential bi-nucleated, symmetrically bi-nucleated, asymmetrically bi-nucleated and multi-nucleated nuclear morphology. In 65-80% of all investigated glomeruli only mono-nuclear podocytes were identified. The highest frequency of bi-nucleated podocytes was found in patients with IgA-GN (18.6%) and the lowest in patients with DN (5.6%). The proportion of bi-nucleated podocytes with asymmetric nuclear morphology was about 50% of all bi-nucleated podocytes and independent of the underlying renal disease. In addition, ultrastructural analysis by electron microscopy showed significant widening of foot processes in bi-nucleated compared with mono-nucleated podocytes. Interestingly, foot process width of podocytes with lobulated nuclei was also significantly increased compared with podocytes with normal mono-nuclear morphology. Furthermore, podocyte density per glomerular area was significantly lower in glomeruli with bi-nucleated podocytes. Due to the relatively low frequency of bi- and multi-nucleated podocytes, correlations with clinical parameters were weak and dependent on renal disease.The frequency of bi-nucleated podocytes was highest in IgA-GN but can also be observed in all investigated renal diseases. In podocytes with altered nuclear morphology particularly in bi- and multi-nucleated podocytes ultrastructural analysis of podocytes revealed significant widening of foot processes as a potential maladaptive structural consequence.
EVALuna2:25559

BKPYV-SPECIFIC T CELLS REDUCE VIRAL LOAD IN A PRIMARY TUBULAR CELL MODEL - Wasielewski, E.; Lippler, Susanne; Knaup, Karl; Gary, Regina; Aigner, Michael; Kremer, Anna-Lena; Pfister, Felix; Amann, Kerstin Ute; Schiffer, Mario; Mackensen, Andreas; Wiesener, Michael (TRANSPLANT INTERNATIONAL, 2021)
CRIS-Team WoS Importer:2021-10-15

Blood group-specific apheresis in combination with daratumumab as a rescue therapy of acute antibody-mediated rejection in a case of ABO- and human leukocyte antigen-incompatible kidney transplantation - Süsal, Can C.; Kraft, Leonie; Ender, Andrea; Süsal, Caner; Schwenger, Amelie; Amann, Kerstin Ute; Böhmig, Georg A.; Schwenger, Vedat (SAGE Open Medical Case Reports, 2023)
We report a case of antibody-mediated rejection treated with the human CD38 monoclonal antibody daratumumab in a 58-year-old female patient with end-stage kidney disease due to autosomal dominant polycystic kidney disease who received an ABO- and human leukocyte antigen antibody-incompatible living donor kidney transplant. The patient experienced an episode of severe antibody-mediated rejection within the first week of transplantation. Blood-group-antibody selective immunoadsorption in combination with administration of four doses of daratumumab (each 1800 mg s.c.) led to a persistent decrease of ABO- and more interestingly donor-specific human leukocyte antigen antibody reactivity and resulted in clinical and histopathological remission with full recovery of graft function, which has remained stable until post-transplant day 212. This case illustrates the potential of targeting CD38 in antibody-mediated rejection.
CRIS-Team Scopus Importer:2023-11-24
Keywords: antibody-mediated rejection; blood-group incompatibility; Case report; daratumumab; HLA incompatibility; kidney transplantation; living-donor transplantation; rejection therapy

Blunted transcriptional response to skeletal muscle ischemia in rats with chronic kidney disease: potential role for impaired ischemia-induced angiogenesis - Heiß, Rafael; Fahlbusch, Fabian B.; Jacobi, Johannes; Daniel, Christoph; Ekici, Arif Bülent; Cordasic, Nada; Amann, Kerstin Ute; Hilgers, Karl Friedrich; Hartner, Andrea (Physiological Genomics, 2017)
Chronic kidney disease (CKD) is associated with increased cardiovascular morbidity and mortality. Previous studies indicated an impairment of ischemia-induced angiogenesis in skeletal muscle of rats with CKD. We performed a systematic comparison of early gene expression in response to ischemia in rats with or without CKD to identify potential molecular mechanisms underlying impaired angiogenesis in CKD. CKD was induced in male rats by 5/6 nephrectomy (SNX); control rats were sham operated (sham). Eight weeks later, ischemia of the right limb was induced by ligation and resection of the femoral artery. Rats were sacrificed 24 hours after the onset of ischemia, and RNA was extracted from the musculus soleus of the ischemic and the nonischemic hindlimb. To identify differentially expressed transcripts, RNA was analyzed employing Affymetrix GeneChip Rat Genome 230 2.0 Arrays. RT-PCR analysis of selected genes was performed to validate observed changes. Hindlimb ischemia up-regulated 239 genes in CKD and 299 genes in control rats (66% overlap) whereas only a few genes were down-regulated (14 in CKD and 34 in controls), compared with the non-ischemic limb of the same animals. Comparison between the ischemic limbs of CKD and controls revealed down-regulation of 65 genes in CKD; 37 of these genes were also among the ischemia-induced genes in controls. Analysis of functional groups (other than angiogenesis) pointed to genes involved in leukocyte recruitment and fatty acid metabolism. Transcript expression profiling points to a relatively small number of differentially expressed genes which may underlie the impaired post-ischemic angiogenesis in CKD.
EVALuna2:3946

BRONJ-related jaw bone is associated with increased Dlx-5 and suppressed osteopontin-implication in the site-specific alteration of angiogenesis and bone turnover by bisphosphonates - Wehrhan, Falk; Amann, Kerstin Ute; Moebius, Patrick; Weber, Manuel; Preidl, Raimund; Ries, Jutta; Stockmann, Philipp (Clinical Oral Investigations, 2015)
Site-specific suppression of bone remodelling has been implicated in bisphosphonate-(BP)-related osteonecrosis of the jaws (BRONJ). Due to the origin of jaw bone from cranial neural crest, osseous differentiation is regulated specifically by the antagonizing BMP-2-downstream-transcription factors Msx-1 and Dlx-5. Osteopontin has been implicated in bone remodelling and angiogenesis. The osteoblast and osteoclast progenitor proliferation mediating Msx-1 has been demonstrated to be suppressed in BRONJ. In vitro BPs were shown to increase Dlx-5 and to suppress osteopontin expression. This study targeted Dlx-5 and osteopontin in BRONJ-related and BP-exposed jaw bone compared with healthy jaw bone samples at protein- and messenger RNA (mRNA) level, since increased Dlx-5 and suppressed osteopontin might account for impaired bone turnover in BRONJ.Fifteen BRONJ-exposed, 15 BP-exposed and 20 healthy jaw bone samples were processed for real-time reverse transcription polymerase chain reaction (RT-PCR) and for immunohistochemistry. Targeting Dlx-5, osteopontin and glyceraldehyde 3-phosphate dehydrogenase mRNA was extracted, quantified by the LabChip-method, followed by quantitative RT-PCR. For immunohistochemistry, an autostaining-based alkaline phosphatase antialkaline phosphatase (APAPP) staining kit was used. Semiquantitative assessment was performed measuring the ratio of stained cells/total number of cells (labelling index, Bonferroni adjustment).The labelling index was significant decreased for osteopontin (p < 0.017) and significantly increased for Dlx-5 (p < 0.021) in BRONJ samples. In BRONJ specimens, a significant fivefold decrease in gene expression for osteopontin (p < 0.015) and a significant eightfold increase in Dlx-5 expression (p < 0.012) were found.BRONJ-related suppression of bone turnover is consistent with increased Dlx-5 expression and with suppression of osteopontin. The BP-related impaired BMP-2-Msx-1-Dlx-5 axis might explain the jaw bone specific alteration by BP.The findings of this study help to explain the restriction of RONJ to craniofacial bones. BRONJ might serve as a model of disease elucidating the specific signal transduction of neural crest cell-derived bone structures in health and disease.
EVALuna2:24383

Bruton’s tyrosine kinase inhibition attenuates disease progression by reducing renal immune cell invasion in mice with hemolytic-uremic syndrome - Kroeller, Sarah; Wissuwa, Bianka; Dennhardt, Sophie; Krieg, Nadine; Thiemermann, Christoph; Daniel, Christoph; Amann, Kerstin Ute; Gunzer, Florian; Coldewey, Sina M. (Frontiers in Immunology, 2023)
Hemolytic-uremic syndrome (HUS) can occur as a complication of an infection with Shiga-toxin (Stx)-producing Escherichia coli. Patients typically present with acute kidney injury, microangiopathic hemolytic anemia and thrombocytopenia. There is evidence that Stx-induced renal damage propagates a pro-inflammatory response. To date, therapy is limited to organ-supportive strategies. Bruton’s tyrosine kinase (BTK) plays a pivotal role in recruitment and function of immune cells and its inhibition was recently shown to improve renal function in experimental sepsis and lupus nephritis. We hypothesized that attenuating the evoked immune response by BTK-inhibitors (BTKi) ameliorates outcome in HUS. We investigated the effect of daily oral administration of the BTKi ibrutinib (30 mg/kg) and acalabrutinib (3 mg/kg) in mice with Stx-induced HUS at day 7. After BTKi administration, we observed attenuated disease progression in mice with HUS. These findings were associated with less BTK and downstream phospholipase-C-gamma-2 activation in the spleen and, subsequently, a reduced renal invasion of BTK-positive cells including neutrophils. Only ibrutinib treatment diminished renal invasion of macrophages, improved acute kidney injury and dysfunction (plasma levels of NGAL and urea) and reduced hemolysis (plasma levels of bilirubin and LDH activity). In conclusion, we report here for the first time that BTK inhibition attenuates the course of disease in murine HUS. We suggest that the observed reduction of renal immune cell invasion contributes – at least in part – to this effect. Further translational studies are needed to evaluate BTK as a potential target for HUS therapy to overcome currently limited treatment options.
CRIS-Team Scopus Importer:2023-03-24
Keywords: acalabrutinib; acute kidney injury; animal model; Bruton’s tyrosine kinase; hemolytic-uremic syndrome; ibrutinib; inflammation

Can Gene Expression Analysis in Zero-Time Biopsies Predict Kidney Transplant Rejection? - Vonbrunn, Eva; Angeloni, Miriam; Büttner-Herold, Maike; Müller-Deile, Janina; Heller, Katharina M.; Bleich, Erik; Söllner, Stefan; Amann, Kerstin Ute; Ferrazzi, Fulvia; Daniel, Christoph (Frontiers in Medicine, 2022)
Zero-time biopsies are taken to determine the quality of the donor organ at the time of transplantation. Histological analyses alone have so far not been able to identify parameters that allow the prediction of subsequent rejection episodes or graft survival. This study investigated whether gene expression analyses of zero-time biopsies might support this prediction. Using a well-characterized cohort of 26 zero-time biopsies from renal transplant patients that include 4 living donor (LD) and 22 deceased donor (DD) biopsies that later developed no rejection (Ctrl, n = 7), delayed graft function (DGF, n = 4), cellular (T-cell mediated rejection; TCMR, n = 8), or antibody-mediated rejection (ABMR, n = 7), we analyzed gene expression profiles for different types of subsequent renal transplant complication. To this end, RNA was isolated from formalin-fixed, paraffin-embedded (FFPE) sections and gene expression profiles were quantified. Results were correlated with transplant data and B-cell, and plasma cell infiltration was assessed by immunofluorescence microscopy. Both principal component analysis and clustering analysis of gene expression data revealed marked separation between LDs and DDs. Differential expression analysis identified 185 significant differentially expressed genes (adjusted p < 0.05). The expression of 68% of these genes significantly correlated with cold ischemia time (CIT). Furthermore, immunoglobulins were differentially expressed in zero-time biopsies from transplants later developing rejection (TCMR + ABMR) compared to non-rejected (Ctrl + DGF) transplants. In addition, immunoglobulin expression did not correlate with CIT but was increased in transplants with previous acute renal failure (ARF). In conclusion, gene expression profiles in zero-time biopsies derived from LDs are markedly different from those of DDs. Pre-transplant ARF increased immunoglobulin expression, which might be involved in triggering later rejection events. However, these findings must be confirmed in larger cohorts and the role of early immunoglobulin upregulation in zero-biopsies needs further clarification.
CRIS-Team Scopus Importer:2022-04-29
Keywords: inflammation; kidney transplantation; mRNA expression; outcome; zero-time biopsy

Cardiovascular changes in the NZB/W F1 mouse model of lupus nephritis - Böhme, Romy; Daniel, Christoph; Ferrazzi, Fulvia; Angeloni, Miriam; Ekici, Arif Bülent; Winkler, Thomas; Hilgers, Karl Friedrich; Wellmann, Ute; Voll, Reinhard E.; Amann, Kerstin Ute (Frontiers in Cardiovascular Medicine, 2023)
Background: Patients with systemic lupus erythematosus (SLE), an autoimmune disease, have a higher risk of cardiovascular (CV) disease and death. In addition, up to 40%–50% of SLE patients develop lupus nephritis (LN) and chronic kidney disease, which is an additional CV risk factor. Thus, the individual contributions of LN and other SLE-specific factors to CV events are unclear. Methods: In this study, we investigated the effect of LN on the development of CV changes using the female NZBxNZW F1 (NZB/W) mouse model of lupus-like disease, with female NZW mice as controls. Standard serologic, morphologic, immunohistologic, and molecular analyses were performed. In a separate group of NZB/W mice, systolic blood pressure (BP) was measured during the course of the disease using tail plethysmography. Results: Our data show marked CV changes in NZB/W mice, i.e., increased heart weight, hypertrophy of the left ventricle (LV) and septum, and increased wall thickness of the intramyocardial arteries and the aorta, which correlated with the progression of renal damage, but not with the age of the mice. In addition, systolic BP was increased in NZB/W mice only when kidney damage progressed and proteinuria was present. Pathway analysis based on gene expression data revealed a significant upregulation of the response to interferon beta in NZB/W mice with moderate kidney injury compared with NZB mice. Furthermore, IFI202b and IL-6 mRNA expression is correlated with CV changes. Multiple linear regression analysis demonstrated serum urea as a surrogate marker of kidney function and IFI202b expression as an independent predictor for LV wall thickness. In addition, deposition of complement factors CFD and C3c in hearts from NZB/W mice was seen, which correlated with the severity of kidney disease. Conclusions: Thus, we postulate that the pathogenesis of CV disease in SLE is affected by renal impairment, i.e., LN, but it can also be partly influenced by lupus-specific cardiac expression of pro-inflammatory factors and complement deposition.
CRIS-Team Scopus Importer:2023-08-18
Keywords: autoimmune disease; cardiovascular disease; IL-15; interferon-related; renal disease; systemic lupus erythematosus

Case Report: Pediatric Renal Sarcoidosis and Prognostic Factors in Reviewed Cases - Klaus, Richard; Jansson, Annette Friederike; Griese, Matthias; Seeman, Tomas; Amann, Kerstin Ute; Lange-Sperandio, Bärbel (Frontiers in Pediatrics, 2021)
Background: Pediatric sarcoidosis is a complex inflammatory disorder with multisystemic manifestations. Kidney involvement in children is rare, and prognostic factors are unknown. Case Report and Methods: We report the case of a 16-year-old girl with multiorgan sarcoidosis and renal involvement. The patient presented with tubulointerstitial nephritis, acute kidney injury (AKI), chest CT disseminated noduli, granulomatous iridocyclitis, giant-cell sialadenitis, and arthralgia. The kidney biopsy revealed non-granulomatous interstitial nephritis. Treatment consisted of initial high-dose methylprednisolone pulse followed by oral prednisolone and methotrexate. Full remission was achieved. In addition, we performed a literature review using PubMed and analyzed data on pediatric renal sarcoidosis cases. Results: We identified 36 cases of pediatric sarcoidosis with renal involvement on presentation and data on the end-of-follow-up glomerular filtration rate (GFR). The data from the literature review showed that renal involvement was slightly more prevalent in males (60%). AKI was present in most of the described patients (84%). Oral prednisolone was used in 35 of 36 cases; in more severe cases, other immunosuppressants were used. We newly identified renal concentration impairment and granulomatous interstitial nephritis as factors with a clear trend toward GFR loss at the end of follow-up, emphasizing the importance of kidney biopsy in symptomatic patients. In contrast, higher GFR at presentation and hypercalcemia were rather favorable factors. According to the identified predictive factors, our patient has a good prognosis and is in remission. Conclusion: The factors indicating a trend toward an unfavorable renal outcome in pediatric sarcoidosis are renal concentration impairment and granulomatous interstitial nephritis at presentation, while a higher GFR is beneficial.
CRIS-Team Scopus Importer:2021-10-08
Keywords: acute kidney injury; case report; prognostic factor analysis; sarcoidosis; tubulointerstitial nephritis

Caspase-8 regulates TNF-α-induced epithelial necroptosis and terminal ileitis - Günther, Claudia; Martini, Eva; Amann, Kerstin Ute; Weigmann, Benno; Neumann, Helmut; Waldner, Maximilian; Tenzer, Stefan; Neurath, Markus; Becker, Christoph; et al. (Nature, 2011)
Dysfunction of the intestinal epithelium is believed to result in the excessive translocation of commensal bacteria into the bowel wall that drives chronic mucosal inflammation in Crohn's disease, an incurable inflammatory bowel disease in humans characterized by inflammation of the terminal ileum. In healthy individuals, the intestinal epithelium maintains a physical barrier, established by the tight contact of cells. Moreover, specialized epithelial cells such as Paneth cells and goblet cells provide innate immune defence functions by secreting mucus and antimicrobial peptides, which hamper access and survival of bacteria adjacent to the epithelium. Epithelial cell death is a hallmark of intestinal inflammation and has been discussed as a possible pathogenic mechanism driving Crohn's disease in humans. However, the regulation of epithelial cell death and its role in intestinal homeostasis remain poorly understood. Here we demonstrate a critical role for caspase-8 in regulating necroptosis of intestinal epithelial cells (IECs) and terminal ileitis. Mice with a conditional deletion of caspase-8 in the intestinal epithelium (Casp8(ΔIEC)) spontaneously developed inflammatory lesions in the terminal ileum and were highly susceptible to colitis. Casp8(ΔIEC) mice lacked Paneth cells and showed reduced numbers of goblet cells, indicating dysregulated antimicrobial immune cell functions of the intestinal epithelium. Casp8(ΔIEC) mice showed increased cell death in the Paneth cell area of small intestinal crypts. Epithelial cell death was induced by tumour necrosis factor (TNF)-α, was associated with increased expression of receptor-interacting protein 3 (Rip3; also known as Ripk3) and could be inhibited on blockade of necroptosis. Lastly, we identified high levels of RIP3 in human Paneth cells and increased necroptosis in the terminal ileum of patients with Crohn's disease, suggesting a potential role of necroptosis in the pathogenesis of this disease. Together, our data demonstrate a critical function of caspase-8 in regulating intestinal homeostasis and in protecting IECs from TNF-α-induced necroptotic cell death.

CD101 inhibits the expansion of colitogenic T cells - Schey, Regina; Dornhoff, H.; Baier, J. L. C.; Purtak, M.; Opoka, R.; Koller, A. K.; Atreya, Raja; Rau, Tilman; Daniel, Christoph; Amann, Kerstin Ute; Bogdan, Christian; Mattner, Jochen (Mucosal Immunology, 2016)
CD101 exerts negative-costimulatory effects in vitro, but its function in vivo remains poorly defined. CD101 is abundantly expressed on lymphoid and myeloid cells in intestinal tissues, but absent from naïve splenic T cells. Here, we assessed the impact of CD101 on the course of inflammatory bowel disease (IBD). Using a T-cell transfer model of chronic colitis, we found that in recipients of naïve T cells from CD101(+/+) donors up to 30% of the recovered lymphocytes expressed CD101, correlating with an increased interleukin (IL)-2-mediated FoxP3 expression. Transfer of CD101(-/-) T cells caused more severe colitis and was associated with an expansion of IL-17-producing T cells and an enhanced expression of IL-2R?/? independently of FoxP3. The co-transfer of naïve and regulatory T cells (Treg) protected most effectively from colitis, when both donor and recipient mice expressed CD101. Although the expression of CD101 on T cells was sufficient for Treg-function and the inhibition of T-cell proliferation, sustained IL-10 production required additional CD101 expression by myeloid cells. Finally, in patients with IBD a reduced CD101 expression on peripheral and intestinal monocytes and CD4(+) T cells correlated with enhanced IL-17 production and disease activity. Thus, CD101 deficiency is a novel marker for progressive colitis and potential target for therapeutic intervention.
EVALuna2:2051

CD107a+ (LAMP-1) Cytotoxic CD8+ T-Cells in Lupus Nephritis Patients - Wiechmann, Anika; Wilde, Benjamin; Tyczynski, Bartosz; Amann, Kerstin Ute; Abdulahad, Wayel H.; Kribben, Andreas; Lang, Karl Sebastian; Witzke, Oliver; Dolff, Sebastian (Frontiers in Medicine, 2021)
Cytotoxic CD8+ T-cells play a pivotal role in the pathogenesis of systemic lupus erythematosus (SLE). The aim of this study was to investigate the role of CD107a (LAMP-1) on cytotoxic CD8+ T-cells in SLE-patients in particular with lupus nephritis. Peripheral blood of SLE-patients (n = 31) and healthy controls (n = 21) was analyzed for the expression of CD314 and CD107a by flow cytometry. Kidney biopsies of lupus nephritis patients were investigated for the presence of CD8+ and C107a+ cells by immunohistochemistry and immunofluorescence staining. The percentages of CD107a+ on CD8+ T-cells were significantly decreased in SLE-patients as compared to healthy controls (40.2 ± 18.5% vs. 47.9 ± 15.0%, p = 0.02). This was even more significant in SLE-patients with inactive disease. There was a significant correlation between the percentages of CD107a+CD8+ T-cells and SLEDAI. The evaluation of lupus nephritis biopsies showed a significant number of CD107a+CD8+ T-cells mainly located in the peritubular infiltrates. The intrarenal expression of CD107a+ was significantly correlated with proteinuria. These results demonstrate that CD8+ T-cells of patients with systemic lupus erythematosus have an altered expression of CD107a which seems to be associated with disease activity. The proof of intrarenal CD107a+CD8+ suggests a role in the pathogenesis of lupus nephritis.
CRIS-Team Scopus Importer:2021-04-16
Keywords: CD107a; cytotoxic T-cells; LAMP-1; lupus nephritis; SLE

CD161a-positive natural killer (NK) cells and α-smooth muscle actin-positive myofibroblasts were upregulated by extrarenal DPP4 in a rat model of acute renal rejection - Schmid, Franziska; Mayer, Carolin; Büttner-Herold, Maike; von Hörsten, Stephan; Amann, Kerstin Ute; Daniel, Christoph (Diabetes Research and Clinical Practice, 2021)
Aims: Systemic inhibition of dipeptidyl peptidase 4 (DPP4) showed a protective effect in several transplant models. Here we assessed the specific role of extrarenal DPP4 in renal transplant rejection. Methods: Kidneys from wildtype (wt) F344 rats were either transplanted in wt Dark Agouti or congenic rats not expressing DPP4. The remaining, not transplanted donor kidney served as healthy controls. To investigate early inflammatory events rats were sacrificed 3 days after transplantation and kidneys were evaluated for inflammatory cells, capillary rarefaction, proliferation, apoptosis and myofibroblasts by immunohistochemistry. Results: Capillary ERG-1-positive endothelial cells were significantly more abundant in renal cortex when transplanted into DPP4 deficient compared to wt recipients. In contrast, TGF-ß and myofibroblasts were reduced by more than 25% in kidneys transplanted into DPP4 deficient compared to wt recipients. Numbers of CD161a-positive NK-cells were significantly lower in allografts in DPP4 deficient compared to wt recipients. Numbers of all other investigated immune cells were not affected by the lack of extrarenal DPP4. Conclusion: In early transplant rejection extrarenal DPP4 is involved in the recruitment of NK-cells and early fibrosis. Beneficial effects were less pronounced than reported for systemic DPP4 inhibition, indicating that renal DPP4 is an important player in transplantation-mediated injury.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Extrarenal DPP4; Fibrosis; Inflammation; Renal transplantation

CD163+ M2c-like macrophages predominate in renal biopsies from patients with lupus nephritis - Olmes, Gregor; Buettner-Herold, Maike; Ferrazzi, Fulvia; Distel, Luitpold; Amann, Kerstin Ute; Daniel, Christoph (Arthritis Research & Therapy, 2015)
The role of macrophages in the pathogenesis of lupus nephritis, in particular their differentiation to a certain subtype (e.g., M1- or M2-like) modulating the inflammatory reaction, is unknown. Here we investigated whether the differentiation in M1- or M2-like macrophages depends on the stage of lupus nephritis and whether this correlates with clinical parameters.Using immunohistochemical analysis we analyzed renal biopsies from 68 patients with lupus nephritis (ISN/RPS classes II-V) for infiltration with M1-like (iNOS+/CD68+), M2a-like (CD206+/CD68+), M2c-like macrophages (CD163+/CD68+), and FoxP3+ regulatory T-cells. In addition, clinical parameters at the time of renal biopsy, i.e., blood pressure, proteinuria and serum urea were correlated with the macrophage infiltration using the Spearman test.The mean number of CD68+ macrophages was related to the diagnosed ISN/RPS class, showing the highest macrophage infiltration in biopsies with diffuse class IV and the lowest number in ISN/RPS class V. In all ISN/RPS classes we detected more M2c-like CD163+/CD68+ than M2a-like CD206+/CD68+ cells, while M1-macrophages played only a minor role. Cluster analysis using macrophage subtype numbers in different renal compartments revealed three main clusters showing cluster 1 dominated by class V. Clusters 2 and 3 were dominated by lupus class IV indicating that this class can be further differentiated by its macrophage population. The number of tubulointerstitial FoxP3+ cells correlated with all investigated macrophage subtypes showing the strongest association to numbers of M2a-like macrophages. Kidney function, as assessed by serum creatinine and serum urea, correlated positively with the number of total CD68+, M2a-like and M2c-like macrophages in the tubulointerstitium. In addition, total CD68+ and M2c-like macrophage numbers highly correlated with Austin activity score. Interestingly, in hypertensive lupus patients only the number of M2a-like macrophages was significantly increased compared to biopsies from normotensive lupus patients.M2-like macrophages are the dominant subpopulation in human lupus nephritis and particularly, M2a subpopulations were associated with disease progression, but their role in disease progression remains unclear.
EVALuna2:9308

CD22 x Siglec-G Double-Deficient Mice Have Massively Increased B1 Cell Numbers and Develop Systemic Autoimmunity - Jellusova, Julia; Wellmann, Ute; Amann, Kerstin Ute; Winkler, Thomas; Nitschke, Lars (Journal of Immunology, 2010)
CD22 and Siglec-G are inhibitory coreceptors for BCR-mediated signaling. Although CD22-deficient mice show increased calcium signaling in their conventional B2 cells and a quite normal B cell maturation, Siglec-G-deficient mice have increased calcium mobilization just in B1 cells and show a large expansion of the 131 cell population. Neither CD22-deficient, nor Siglec-G-deficient mice on a pure C57BL/6 or BALB/c background, respectively, develop autoimmunity. Using Siglec-G X CD22 double-deficient mice, we addressed whether Siglec-G and CD22 have redundant functions. Siglec-G X CD22 double-deficient mice show elevated calcium responses in both B1 cells and B2 cells, increased serum IgM levels and an enlarged population of B1 cells. The enlargement of 131 cell numbers is even higher than in Siglecg(-/-) mice. This expansion seems to happen at the expense of B2 cells, which are reduced in absolute cell numbers, but show an activated phenotype. Furthermore, Siglec-G X CD22 double-deficient mice show a diminished immune response to both thymus-dependent and thymus-independent type 11 Ags. In contrast, B cells from Siglec-G X CD22 double-deficient mice exhibit a hyperproliferative response to stimulation with several TLR ligands. Aged Siglec-G X CD22 double-deficient mice spontaneously develop anti-DNA and antinuclear autoantibodies. These resulted in a moderate form of immune complex glomerulonephritis. These results show that Siglec-G and CD22 have partly compensatory functions and together are crucial in maintaining the B cell tolerance. The Journal of Immunology, 2010, 184: 3618-3627.

Cell cycle re-entry sensitizes podocytes to injury induced death - Hagen, Manuel; Pfister, Eva; Kosel, Andrea; Shankland, Stuart; Pippin, Jeffrey; Amann, Kerstin Ute; Daniel, Christoph (Cell Cycle, 2016)
Podocytes are terminally differentiated renal cells, lacking the ability to regenerate by proliferation. However, during renal injury, podocytes re-enter into the cell cycle but fail to divide. Earlier studies suggested that re-entry into cell cycle results in loss of podocytes, but a direct evidence for this is lacking. Therefore, we established an in vitro model to test the consequences of re-entry into the cell cycle on podocyte survival. A mouse immortalized podocyte cell line was differentiated to non-permissive podocytes and stimulated with e.g. growth factors. Stimulated cells were analyzed for mRNA-expression or stained for cell cycle analysis using flow cytometry and immunocytofluorescence microscopy. After stimulation to re-entry into cell cycle, podocytes were stressed with puromycin aminonucleoside (PAN) and analyzed for survival. During permissive stage more than 40% of immortalized podocytes were in the S-phase. In contrast, S-phase in non-permissive differentiated podocytes was reduced to 5%. Treatment with b-FGF dose dependently induced re-entry into cell cycle increasing the number of podocytes in the S-phase to 10.7% at an optimal bFGF dosage of 10 ng/ml. Forty eight hours after stimulation with bFGF the number of bi-nucleated podocytes significantly increased. A secondary injury stimulus significantly reduced podocyte survival preferentially in bi-nucleated podocytes In conclusion, stimulation of podocytes using bFGF was able to induce re-entry of podocytes into the cell cycle and to sensitize the cells for cell death by secondary injuries. Therefore, this model is appropriate for testing new podocyte protective substances that can be used for therapy.
EVALuna:32169

Cellular FLICE-like inhibitory protein secures intestinal epithelial cell survival and immune homeostasis by regulating caspase-8. - Günther, Claudia; Martini, Eva; He, Guiwei; Amann, Kerstin Ute; He, You-Wen; Neurath, Markus; Becker, Christoph; et al. (Gastroenterology, 2013)
The intestinal epithelium generates a barrier that protects mammals from potentially harmful intestinal contents, such as pathogenic bacteria. Dysregulation of epithelial cell death has been implicated in barrier dysfunction and in the pathogenesis of intestinal inflammation. We investigated mechanisms of cell-death regulation in the intestinal epithelium of mice. Conditional knockout mice (either inducible or permanent) with deletion of cellular FLICE-inhibitory protein (cFlip) or caspase-8 in the intestinal epithelium were analyzed by histology and high-resolution endoscopy. We assessed the effects of cFlip or caspase-8 deficiency on intestinal homeostasis. Expression of cFlip in the intestinal epithelium was required for constitutive activation of caspase-8 under steady-state conditions. Intestinal expression of cFlip was required for development; disruption of the gene encoding cFlip from the intestinal epithelium (cFlip(fl/fl) VillinCre(+) mice) resulted in embryonic lethality. When cFlip was deleted from the intestinal epithelium of adult mice (cFlip(iΔIEC) mice), the animals died within a few days from severe tissue destruction, epithelial cell death, and intestinal inflammation. Death of cFlip-depleted intestinal epithelial cells was regulated extrinsically and required the presence of death receptor ligands, such as tumor necrosis factor-α and CD95 ligand, but was independent of receptor-interacting protein 3. cFlip deficiency was associated with strong up-regulation of caspase-8 and caspase-3 activity and excessive apoptosis in intestinal crypts. cFlip is required for intestinal tissue homeostasis in mice. It controls the level of activation of caspase-8 to promote survival of intestinal epithelial cells. BACKGROUND & AIMS METHODS RESULTS CONCLUSIONS
Keywords: CASP8; CFLAR; Fadd; Fadd-Like Apoptosis Regulator; Fas-associated protein with death domain; IEC; NEMO; NF-κB essential modulator; Rip; TNF; TUNEL; cFLIP; cellular FLICE-like inhibitory protein; intestinal epithelial cell; receptor interacting protein; terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick-end labeling; tumor necrosis factor

Cellular stress induces erythrocyte assembly on intravascular von Willebrand factor strings and promotes microangiopathy - Nicolay, Jan P.; Thorn, Verena; Daniel, Christoph; Amann, Kerstin Ute; Siraskar, Balasaheb; Lang, Florian; Hillgruber, Carina; Goerge, Tobias; Hoffmann, Stefan; Gorzelanny, Christian; Huck, Volker; Mess, Christian; et al. (Scientific Reports, 2018)
Microangiopathy with subsequent organ damage represents a major complication in several diseases. The mechanisms leading to microvascular occlusion include von Willebrand factor (VWF), notably the formation of ultra-large von Willebrand factor fibers (ULVWFs) and platelet aggregation. To date, the contribution of erythrocytes to vascular occlusion is incompletely clarified. We investigated the platelet-independent interaction between stressed erythrocytes and ULVWFs and its consequences for microcirculation and organ function under dynamic conditions. In response to shear stress, erythrocytes interacted strongly with VWF to initiate the formation of ULVWF/erythrocyte aggregates via the binding of Annexin V to the VWF A1 domain. VWF-erythrocyte adhesion was attenuated by heparin and the VWF-specific protease ADAMTS13. In an in vivo model of renal ischemia/reperfusion injury, erythrocytes adhered to capillaries of wild-type but not VWF-deficient mice and later resulted in less renal damage. In vivo imaging in mice confirmed the adhesion of stressed erythrocytes to the vessel wall. Moreover, enhanced eryptosis rates and increased VWF binding were detected in blood samples from patients with chronic renal failure. Our study demonstrates that stressed erythrocytes have a pronounced binding affinity to ULVWFs. The discovered mechanisms suggest that erythrocytes are essential for the pathogenesis of microangiopathies and renal damage by actively binding to ULVWFs.
EVALuna:34419

Changes in glomerular parietal epithelial cells in mouse kidneys with advanced age - Roeder, Sebastian S.; Stefanska, Ania; Eng, Diana G.; Kaverina, Natalya; Sunseri, Maria W.; Mcnicholas, Bairbre A.; Rabinovitch, Peter; Engel, Felix; Daniel, Christoph; Amann, Kerstin Ute; Lichtnekert, Julia; Pippin, Jeffrey W.; et al. (American Journal of Physiology-Renal Physiology, 2015)
Kidney aging is accompanied by characteristic changes in the glomerulus, but little is known about the effect of aging on glomerular parietal epithelial cells (PECs), nor if the characteristic glomerular changes in humans and rats also occur in very old mice. Accordingly, a descriptive analysis was undertaken in 27-mo-old C57B6 mice, considered advanced age. PEC density was significantly lower in older mice compared with young mice (aged 3 mo), and the decrease was more pronounced in juxtamedullary glomeruli compared with outer cortical glomeruli. In addition to segmental and global glomerulosclerosis in older mice, staining for matrix proteins collagen type IV and heparan sulfate proteoglycan were markedly increased in Bowman's capsules of older mouse glomeruli, consistent with increased extracellular matrix production by PECs. De novo staining for CD44, a marker of activated and profibrotic PECs, was significantly increased in aged glomeruli. CD44 staining was more pronounced in the juxtamedullary region and colocalized with phosphorylated ERK. Additionally, a subset of aged PECs de novo expressed the epithelial-to-mesenchymal transition markers ?-smooth muscle and vimentin, with no changes in epithelial-to-mesenchymal transition markers E-cadherin and ?-catenin. The mural cell markers neural/glial antigen 2, PDGF receptor-?, and CD146 as well as Notch 3 were also substantially increased in aged PECs. These data show that mice can be used to better understand the aging kidney and that PECs undergo substantial changes, especially in juxtamedullary glomeruli, that may participate in the overall decline in glomerular structure and function with advancing age.
EVALuna2:25490

Characteristic morphological changes in anti-VEGF therapy induced glomerular microangiopathy - Pfister, Frederick; Amann, Kerstin Ute; Daniel, Christoph; Klewer, Monika; Büttner, Anke; Büttner-Herold, Maike (Histopathology, 2018)
BACKGROUND: Thrombotic microangiopathy (TMA) is a microvascular pathology caused by several drugs used in cancer therapy. Agents targeting vascular endothelial growth factor (VEGF) have increasingly been used in therapy of advanced malignancies and have been found to induce renal TMA and proteinuria. However, histomorphological changes in human biopsies in this setting and the underlying mechanism are not yet fully understood. METHODS: Renal biopsies of 15 patients with anti-VEGF therapy (aVEGF) evaluated between 2013 and 2017 at a single centre were morphologically characterized using light microscopy, electron microscopy and immunohistochemistry (IgA, IgG, IgM, C1q, C3) and compared to cases with acute TMA caused by atypical haemolytic uramic syndrome or hypertension. Morphological overlap with immune-complex and cryoglobulinemic membranoproliferative glomerulonephritis, diabetic glomerulopathy and pre-emclapsia induced glomerulopathy were discussed. RESULTS: Segmental glomerular capillary microaneurysms and segmental hyalinosis were typical morphological features of aVEGF therapy induced glomerular microangiopathy, whereas fibrin or platelet thrombi or fragmented erythrocytes were rarely found or absent. aVEGF therapy associated microangiopathy was diffusely distributed in the glomeruli, spared pre-glomerular vessels, and showed morphological characteristics of chronic TMA. In individual cases, aVEGF therapy induced glomerular microangiopathy was accompanied by immune-complex glomerulonephritis. CONCLUSION: aVEGF therapy induced glomerular microangiopathy has a characteristic morphology and clinical presentation that helps to differentiate it from other causes of TMA. Awareness of these light microscopic findings allows identification of aVEGF therapy as a trigger of renal disease in critically ill cancer patients and therefore might help in deciding on further therapy. This article is protected by copyright. All rights reserved.
EVALuna2:34420

Characterization of Glomerular Sox9+ Cells in Anti-Glomerular Basement Membrane Nephritis in the Rat - Prochnicki, Ania; Amann, Kerstin Ute; Wegner, Michael; Sock, Elisabeth; Pfister, Eva; Shankland, Stuart; Pippin, Jeffrey; Daniel, Christoph (American Journal of Pathology, 2018)
Mechanisms of glomerular crescent formation and podocyte repair processes are still unclear. Therefore, we investigated the expression of the transcription factor Sox9 as a potential marker of a subpopulation of parietal epithelial cells (PECs) with potential regenerative properties. Glomerular Sox9 expression was characterized in detail in a rat anti-glomerular basement membrane (GBM) nephritis model using immunofluorescence and confocal laser scanning microscopy. In healthy kidneys Sox9 is expressed in a subpopulation of PECs restricted to approximately 20% to 50% of PEC nuclei and was highly conserved in all investigated species. During rat anti-GBM nephritis the number of glomerular Sox9+ cells increased and was associated with proliferation activity. In nephritic glomeruli Sox9 expression was not restricted to Bowman's capsule lining but was also found on cells of the glomerular tuft. Nearly all Sox9+ cells also expressed the PEC marker Pax8, whereas endothelial cells, mesangial cells, macrophages, and T lymphocytes lacked Sox9 expression. At the margins of crescents Sox9+/Pax8+ cells additionally expressed podocyte markers. In contrast, in sclerotic lesions a minority of Sox9+/Pax8+ cells expressed the myofibroblast marker α-smooth muscle actin. In glomerular Sox9+ cells Jagged 1 was up-regulated. During anti-GBM nephritis Sox9+ PECs proliferate and migrate onto the glomerular tuft. Future studies are needed to confirm the origin of Sox9+ cells from PECs and differentiation in both podocytes and/or myofibroblasts.
EVALuna2:35393

Checkpoint kinase Chk2 controls renal Cyp27b1 expression, calcitriol formation, and calcium-phosphate metabolism - Fahkri, Hajar; Zhang, Bingbing; Fajol, Abul; Hernando, Nati; Elvira, Bernat; Mannheim, Julia G.; Pichler, Bernd J.; Daniel, Christoph; Amann, Kerstin Ute; Hirao, Atsushi; Haight, Jillian; Mak, Tak W.; et al. (Pflügers Archiv: European Journal of Physiology, 2015)
Checkpoint kinase 2 (Chk2) is the main effector kinase of ataxia telangiectasia mutated (ATM) and responsible for cell cycle regulation. ATM signaling has been shown to upregulate interferon-regulating factor-1 (IRF-1), a transcription factor also expressed in the kidney. Calcitriol (1,25 (OH)2D3), a major regulator of mineral metabolism, is generated by 25-hydroxyvitamin D 1?-hydroxylase in the kidney. Since 25-hydroxyvitamin D 1?-hydroxylase expression is enhanced by IRF-1, the present study explored the role of Chk2 for calcitriol formation and mineral metabolism. Chk2-deficient mice (chk2 (-/-)) were compared to wild-type mice (chk2 (+/+)). Transcript levels of renal 25-hydroxyvitamin D 1?-hydroxylase, Chk2, and IRF-1 were determined by RT-PCR; Klotho expression by Western blotting; bone density by ?CT analysis; serum or plasma 1,25 (OH)2D3, PTH, and C-terminal FGF23 concentrations by immunoassays; and serum, fecal, and urinary calcium and phosphate concentrations by photometry. The renal expression of IRF-1 and 25-hydroxyvitamin D 1?-hydroxylase as well as serum 1,25 (OH)2D3 and FGF23 levels were significantly lower in chk2 (-/-) mice compared to chk2 (+/+) mice. Plasma PTH was not different between the genotypes. Renal calcium and phosphate excretion were significantly higher in chk2 (-/-) mice than in chk2 (+/+) mice despite hypophosphatemia and normocalcemia. Bone density was not different between the genotypes. We conclude that Chk2 regulates renal 25-hydroxyvitamin D 1?-hydroxylase expression thereby impacting on calcium and phosphate metabolism.
EVALuna2:25469

Chronic Kidney Disease and Coronary Artery Disease: JACC State-of-the-Art Review - Sarnak, Mark J.; Amann, Kerstin Ute; Bangalore, Sripal; Cavalcante, João L.; Charytan, David M.; Craig, Jonathan C.; Gill, John S.; Hlatky, Mark A.; Jardine, Alan G.; Landmesser, Ulf; Newby, L. Kristin; Herzog, Charles A.; et al. (Journal of the American College of Cardiology, 2019)
Chronic kidney disease (CKD) is a major risk factor for coronary artery disease (CAD). As well as their high prevalence of traditional CAD risk factors, such as diabetes and hypertension, persons with CKD are also exposed to other nontraditional, uremia-related cardiovascular disease risk factors, including inflammation, oxidative stress, and abnormal calcium-phosphorus metabolism. CKD and end-stage kidney disease not only increase the risk of CAD, but they also modify its clinical presentation and cardinal symptoms. Management of CAD is complicated in CKD patients, due to their likelihood of comorbid conditions and potential for side effects during interventions. This summary of the Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference on CAD and CKD (including end-stage kidney disease and transplant recipients) seeks to improve understanding of the epidemiology, pathophysiology, diagnosis, and treatment of CAD in CKD and to identify knowledge gaps, areas of controversy, and priorities for research.
CRIS-Team Scopus Importer:2019-10-01
Keywords: acute coronary syndromes; calcification; chronic kidney disease; coronary artery disease; revascularization

Chronic kidney disease and valvular heart disease: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference - Marwick, Thomas H.; Amann, Kerstin Ute; Bangalore, Sripal; Cavalcante, João L.; Charytan, David M.; Craig, Jonathan C.; Gill, John S.; Hlatky, Mark A.; Jardine, Alan G.; Landmesser, Ulf; Newby, L. Kristin; Herzog, Charles A.; et al. (Kidney International, 2019)
Chronic kidney disease (CKD) is a major risk factor for valvular heart disease (VHD). Mitral annular and aortic valve calcifications are highly prevalent in CKD patients and commonly lead to valvular stenosis and regurgitation, as well as complications including conduction system abnormalities and endocarditis. VHD, especially mitral regurgitation and aortic stenosis, is associated with significantly reduced survival among CKD patients. Knowledge related to VHD in the general population is not always applicable to CKD patients because the pathophysiology may be different, and CKD patients have a high prevalence of comorbid conditions and elevated risk for periprocedural complications and mortality. This Kidney Disease: Improving Global Outcomes (KDIGO) review of CKD and VHD seeks to improve understanding of the epidemiology, pathophysiology, diagnosis, and treatment of VHD in CKD by summarizing knowledge gaps, areas of controversy, and priorities for research.
CRIS-Team Scopus Importer:2019-09-24
Keywords: aortic stenosis; chronic kidney disease; end-stage kidney disease; mitral annular calcification; valvular heart disease

CIDP, myasthenia gravis, and membranous glomerulonephritis - three autoimmune disorders in one patient: a case report - Bolz, Saskia; Totzeck, Andreas; Amann, Kerstin Ute; Stettner, Mark; Kleinschnitz, Christoph; Hagenacker, Tim (BMC Neurology, 2018)
BACKGROUND: We present a patient fulfilling the electrophysiological criteria for definite chronic inflammatory demyelinating polyneuropathy (CIDP), antibody-positive myasthenia gravis (MG), and membranous glomerulonephritis (MGN) confirmed by biopsy. To our knowledge, this is the first case of the concomitant appearance of these three autoimmune diseases in a single patient. CASE REPRESENTATION: A 42-year-old Caucasian male presented with rapidly progressive gait disturbance, distal weakness of the lower extremities, ascending hypoesthesia, impaired fine motor skills, and beginning cranial nerve palsy showing dysarthrophonia, facial paralysis, and eye movement abnormalities and was diagnosed as rapid onset (atypical) CIDP. After 3 months, the patient complained of increasing physical exhaustion, reduction of his walking distance, worsening of the residual dysphagia, and dysarthria with an inability to swallow. AChR antibodies (17.0 nmol/L, RF < 0.4) and titin antibodies were positive and repetitive nerve stimulation showed an abnormal decrement matching the criteria of myasthenia gravis. Over time the patient developed severe acute-on-chronic renal failure with high-grade proteinuria resulting in generalized edema followed by secondary hyperparathyroidism and dialysis-dependent renal failure. Renal biopsy confirmed beginning anti-phospholipase A2 receptor antibody membranous nephropathy. CONCLUSION: All three diseases are of autoimmune origin with distinctive immunopathogenetic mechanisms. The present case of CIDP, MG, and MGN occurring in one patient indicates a common underlying immune mechanism in these distinct conditions, including the involvement of autoantibodies and T cells.
EVALuna2:205570

Clinical Course of an Early Childhood-Onset Granulomatosis with Polyangiitis - Krasselt, Marco; Pierer, Matthias; Amann, Kerstin Ute; Bachmann, Anette; Lindner, Tom H. (Deutsche Medizinische Wochenschrift, 2017)
History A 26-year-old male patient presented with an eight-week history of unspecific symptoms such as weight loss and fever. Besides, he also suffered from haemoptysis, cough, and arthralgia. Since the age of twelve years, the patient has been treated for Wegner's granulomatosis. At the age of 20 years he received a kidney transplant which failed only four years later. Investigations The relapse we clinically suspected was confirmed by CT scan showing bilateral pulmonary manifestations. Moreover, we found highly positive antibodies against proteinase 3. Treatment and course After an induction therapy using Glucocorticoids and Rituximab, accompanied by plasmapheresis, the patient's clinical condition showed a marked improvement. We were able to discharge him continuing the treatment in an outpatient setting. Conclusion Childhood-onset GPA is a life-threatening disease and often characterized by recurring relapses as well as a significantly reduced quality of life for the patient.
EVALuna2:25540

Coding practice in national and regional kidney biopsy registries - Dendooven, Amélie; Peetermans, Han; Helbert, Mark; Nguyen, Tri Q.; Marcussen, Niels; Nagata, Michio; Gesualdo, Loreto; Perkowska-Ptasinska, Agnieszka; Capusa, Cristina; López-Gómez, Juan M.; Geddes, Colin; Abdul-Hamid, Myrurgia A.; et al. (BMC Nephrology, 2021)
Background: Kidney biopsy registries all over the world benefit research, teaching and health policy. Comparison, aggregation and exchange of data is however greatly dependent on how registration and coding of kidney biopsy diagnoses are performed. This paper gives an overview over kidney biopsy registries, explores how these registries code kidney disease and identifies needs for improvement of coding practice. Methods: A literature search was undertaken to identify biopsy registries for medical kidney diseases. These data were supplemented with information from personal contacts and from registry websites. A questionnaire was sent to all identified registries, investigating age of registries, scope, method of coding, possible mapping to international terminologies as well as self-reported problems and suggestions for improvement. Results: Sixteen regional or national kidney biopsy registries were identified, of which 11 were older than 10 years. Most registries were located either in Europe (10/16) or in Asia (4/16). Registries most often use a proprietary coding system (12/16). Only a few of these coding systems were mapped to SNOMED CT (1), older SNOMED versions (2) or ERA-EDTA PRD (3). Lack of maintenance and updates of the coding system was the most commonly reported problem. Conclusions: There were large gaps in the global coverage of kidney biopsy registries. Limited use of international coding systems among existing registries hampers interoperability and exchange of data. The study underlines that the use of a common and uniform coding system is necessary to fully realize the potential of kidney biopsy registries.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Coding; Kidney biopsy registry; Nephropathology; Renal pathology; Systematic review

COL4A5-p.Gly624Asp is the Predominant Variant in Europe Associated With a Mild Alport Syndrome Phenotype - Krüger, Bastian M.; Jens, Annika; Neuhaus, Anna; Ćomić, Jasmina; Berutti, Riccardo; de Fallois, Jonathan; Petzold, Friederike; Münch, Johannes; Kowald, Jan; Lindner, Tom H.; Budde, Klemens; Brüning, Klara K.; et al. (Kidney International Reports, 2025)
Introduction: Pathogenic variants in COL4A3–5 are common causes of inherited kidney disease. The clinical presentation extends from classical Alport syndrome (AS) to focal segmental glomerulosclerosis (FSGS) without extrarenal manifestation. In this study, we aimed to assess the genetic and phenotypic spectrum, along with the associated natural histories, in a cohort of patients with AS from 3 tertiary centers in Central Europe. Methods: A total of 210 patients with disease causing variants in one of the COL4A3–5 genes were characterized and evaluated for genotype-phenotype correlations. In addition, 48 COL4A5-p.Gly624Asp carriers were analyzed for replication and pooled analysis. Results: COL4A5-p.Gly624Asp was by far the most common variant, accounting for 16% of all genetic diagnoses. These patients presented with overall milder renal phenotypes than patients with other COL4A5 missense variants and COL4A5 glycine-missense variants after age- and sex-matching. In patients lacking a wild-type allele (X-Linked AS [XLAS] males and autosomal recessive AS [ARAS]), histological AS was most frequently observed in kidney biopsies, and truncating variants were associated with increased disease severity. Conversely, in patients with a wild-type allele present (XLAS females and autosomal dominant AS [ADAS]), FSGS was more frequently observed. Predicted protein truncation was not inferior to missense alterations in terms of renal survival. Conclusion: The predominance of the European COL4A5 founder variant p.Gly624Asp allowed for the creation of the largest cohort of patients with an identical Alport variant to date, confirming the more favorable renal prognosis specific to this amino acid change. Allelic and gene dosage effects drive phenotypic differences and should be incorporated into future risk models.
CRIS-Team Scopus Importer:2025-04-01
Keywords: alport syndrome; chronic kidney disease; COL4A3; COL4A4; COL4A5; collagen type IV

Colony-stimulating factor-1: a potential biomarker for lupus nephritis - Menke, Julia; Amann, Kerstin Ute; Cavagna, Lorenzo; Blettner, Maria; Weinmann, Arndt; Schwarting, Andreas; Kelley, Vicki R. (Journal of the American Society of Nephrology, 2015)
A noninvasive means to predict the onset and recurrence of lupus nephritis (LN) before overt renal injury is needed to optimize and individualize treatment. Colony-stimulating factor-1 (CSF-1) is expressed by kidney tubules at the onset of LN, increases with disease progression, and spills into the circulation in lupus-prone mice. We tested the hypothesis that amplified expression of CSF-1 detected in the serum or urine correlates with intrarenal CSF-1 expression and histopathology (increased macrophage accumulation, activity indices) and clinical kidney disease activity and predicts the onset and recurrence of nephritis in patients with systemic lupus erythematosus (SLE). We found increased serum or urine CSF-1 levels in patients with cutaneous, serositis, and musculoskeletal disease; however, the increase in CSF-1 levels was far greater in LN. Moreover, an elevation in serum or urine CSF-1 levels correlated with increasing intrarenal CSF-1 expression and histopathology. By longitudinally tracking patients, we found that elevated serum CSF-1 heralded the initial onset of disease, and a rise in serum or urine CSF-1 predicted recurrences of LN before clinical evidence of glomerular dysfunction and conventional serologic measures, even in patients with other manifestations of SLE. These findings indicate that serial monitoring for a rise in serum or urine CSF-1 levels in patients with SLE reflects kidney histopathology and may predict renal disease activity and the onset and recurrence of LN more accurately than conventional laboratory measures.
EVALuna2:25483

Comparison of different normalization strategies for the analysis of glomerular microRNAs in IgA nephropathy - Bockmeyer, Clemens L.; Saeuberlich, Karen; Wittig, Juliane; Esser, Marc; Röder, Sebastian; Vester, Udo; Hoyer, Peter F.; Agustian, Putri A.; Zeuschner, Philip; Amann, Kerstin Ute; Daniel, Christoph; Becker, Jan U. (Scientific Reports, 2016)
Small nucleolar RNAs (snoRNAs) have been used for normalization in glomerular microRNA (miRNA) quantification without confirmation of validity. Our aim was to identify glomerular reference miRNAs in IgA nephropathy. We compared miRNAs in human paraffin-embedded renal biopsies from patients with cellular-crescentic IgA-GN (n = 5; crescentic IgA-GN) and non-crescentic IgA-GN (n = 5; IgA-GN) to mild interstitial nephritis without glomerular abnormalities (controls, n = 5). Laser-microdissected glomeruli were used for expression profiling of 762 miRNAs by low-density TaqMan arrays (cards A and B). The comparison of different normalization methods (GeNormPlus, NormFinder, global mean and snoRNAs) in crescentic IgA-GN, IgA-GN and controls yielded similar results. However, levels of significance and the range of relative expression differed. In median, two normalization methods demonstrated similar results. GeNormPlus and NormFinder gave different top ranked reference miRNAs. Stability ranking for snoRNAs varied between cards A and B. In conclusion, we suggest the geometric mean of the most stable reference miRNAs found in GeNormPlus (miR-26b-5p), NormFinder (miR-28-5p) and snoRNAs (RNU44) as reference. It should be considered that significant differences could be missed using one particular normalization method. As a starting point for glomerular miRNA studies in IgA nephropathy we provide a library of miRNAs.
EVALuna2:25525

Complement 9 in amyloid deposits - Lux, Annelie; Gottwald, Juliane; Behrens, Hans-Michael; Daniel, Christoph; Amann, Kerstin Ute; Roecken, Christoph (Amyloid-Journal of Protein Folding Disorders, 2021)
Amyloidosis is a disease group caused by pathological aggregation and deposition of peptides in diverse tissue sites. Apart from the fibril protein, amyloid deposits frequently enclose non-fibrillar constituents. In routine diagnostics, we noticed the presence of complement 9 (C9) in amyloid. Based on this observation, we systematically explored the occurrence of C9 in amyloid. Apolipoprotein E (apoE), caspase 3 and complement 3 (C3) served as controls. From the Amyloid Registry Kiel, we retrieved 118 formalin-fixed and paraffin-embedded tissue samples, including eight different amyloid- and 18 different tissue types. The expression patterns were assessed immunohistochemically in relation to amyloid deposits. A literature search on proteomic data was performed. Amyloid deposits stained for C9 and apoE in 117 (99.2%) and 112 of 118 (94.9%) cases, respectively. A homogeneous immunostaining of the entire amyloid deposits was found in 75.4% (C9) and 61.9% (apoE) of the cases. Caspase 3 and C3 were present only in 22 (19.3%) of 114 and 20 (36%) of 55 assessable cases, respectively. Caspase 3 and C3 immunostaining rarely covered substantial areas of the amyloid deposits. The literature search on proteomic data confirmed the frequent detection of apoE and the occurrence of C9 and C3 in amyloid deposits. No data were found regarding caspase 3. Our findings demonstrate the ubiquitous, spatial and specific enrichment of C9 in amyloid deposits irrespective of amyloid-, organ- or tissue type. Our findings lend support to the hypothesis that amyloidosis might activate the complement cascade, which could lead to the formation of the membrane attack complex and cell death.
CRIS-Team WoS Importer:2021-06-11

Complement Activation in Kidneys of Patients With COVID-19 - Pfister, Frederick; Vonbrunn, Eva; Ries, Tajana; Jäck, Hans-Martin; Überla, Klaus; Lochnit, Günter; Sheriff, Ahmed; Herrmann, Martin; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2021)
Most patients who became critically ill following infection with COVID-19 develop severe acute respiratory syndrome (SARS) attributed to a maladaptive or inadequate immune response. The complement system is an important component of the innate immune system that is involved in the opsonization of viruses but also in triggering further immune cell responses. Complement activation was seen in plasma adsorber material that clogged during the treatment of critically ill patients with COVID-19. Apart from the lung, the kidney is the second most common organ affected by COVID-19. Using immunohistochemistry for complement factors C1q, MASP-2, C3c, C3d, C4d, and C5b-9 we investigated the involvement of the complement system in six kidney biopsies with acute kidney failure in different clinical settings and three kidneys from autopsy material of patients with COVID-19. Renal tissue was analyzed for signs of renal injury by detection of thrombus formation using CD61, endothelial cell rarefaction using the marker E-26 transformation specific-related gene (ERG-) and proliferation using proliferating cell nuclear antigen (PCNA)-staining. SARS-CoV-2 was detected by in situ hybridization and immunohistochemistry. Biopsies from patients with hemolytic uremic syndrome (HUS, n = 5), severe acute tubular injury (ATI, n = 7), zero biopsies with disseminated intravascular coagulation (DIC, n = 7) and 1 year protocol biopsies from renal transplants (Ctrl, n = 7) served as controls. In the material clogging plasma adsorbers used for extracorporeal therapy of patients with COVID-19 C3 was the dominant protein but collectin 11 and MASP-2 were also identified. SARS-CoV-2 was sporadically present in varying numbers in some biopsies from patients with COVID-19. The highest frequency of CD61-positive platelets was found in peritubular capillaries and arteries of COVID-19 infected renal specimens as compared to all controls. Apart from COVID-19 specimens, MASP-2 was detected in glomeruli with DIC and ATI. In contrast, the classical pathway (i.e. C1q) was hardly seen in COVID-19 biopsies. Both C3 cleavage products C3c and C3d were strongly detected in renal arteries but also occurs in glomerular capillaries of COVID-19 biopsies, while tubular C3d was stronger than C3c in biopsies from COVID-19 patients. The membrane attack complex C5b-9, demonstrating terminal pathway activation, was predominantly deposited in COVID-19 biopsies in peritubular capillaries, renal arterioles, and tubular basement membrane with similar or even higher frequency compared to controls. In conclusion, various complement pathways were activated in COVID-19 kidneys, the lectin pathway mainly in peritubular capillaries and in part the classical pathway in renal arteries whereas the alternative pathway seem to be crucial for tubular complement activation. Therefore, activation of the complement system might be involved in the worsening of renal injury. Complement inhibition might thus be a promising treatment option to prevent deregulated activation and subsequent collateral tissue injury.
CRIS-Team Scopus Importer:2021-03-05
Keywords: complement—immunological term; COVID-19; endothelial injury; kidney; lectin pathway activation

Complement Activation via the Lectin and Alternative Pathway in Patients With Severe COVID-19 - Niederreiter, Janina; Eck, Christine; Ries, Tajana; Hartmann, Arndt; Märkl, Bruno; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2022)
Complement plays an important role in the direct defense to pathogens, but can also activate immune cells and the release of pro-inflammatory cytokines. However, in critically ill patients with COVID-19 the immune system is inadequately activated leading to severe acute respiratory syndrome (SARS) and acute kidney injury, which is associated with higher mortality. Therefore, we characterized local complement deposition as a sign of activation in both lungs and kidneys from patients with severe COVID-19. Using immunohistochemistry we investigated deposition of complement factors C1q, MASP-2, factor D (CFD), C3c, C3d and C5b-9 as well as myeloperoxidase (MPO) positive neutrophils and SARS-CoV-2 virus particles in lungs and kidneys from 38 patients who died from COVID-19. In addition, tissue damage was analyzed using semi-quantitative scores followed by correlation with complement deposition. Autopsy material from non-COVID patients who died from cardiovascular causes, cerebral hemorrhage and pulmonary embolism served as control (n=8). Lung injury in samples from COVID-19 patients was significantly more pronounced compared to controls with formation of hyaline membranes, thrombi and edema. In addition, in the kidney tubular injury was higher in these patients and correlated with lung injury (r=0.361*). In autopsy samples SARS-CoV-2 spike protein was detected in 22% of the lungs of COVID-19 patients but was lacking in kidneys. Complement activation was significantly stronger in lung samples from patients with COVID-19 via the lectin and alternative pathway as indicated by deposition of MASP-2, CFD, C3d and C5b9. Deposits in the lung were predominantly detected along the alveolar septa, the hyaline membranes and in the alveolar lumina. In the kidney, complement was significantly more deposited in patients with COVID-19 in peritubular capillaries and tubular basement membranes. Renal COVID-19-induced complement activation occurred via the lectin pathway, while activation of the alternative pathway was similar in both groups. Furthermore, MPO-positive neutrophils were found in significantly higher numbers in lungs and kidneys of COVID-19 patients and correlated with local MASP-2 deposition. In conclusion, in patients who died from SARS-CoV-2 infection complement was activated in both lungs and kidneys indicating that complement might be involved in systemic worsening of the inflammatory response. Complement inhibition might thus be a promising treatment option to prevent deregulated activation and subsequent collateral tissue injury in COVID-19.
CRIS-Team Scopus Importer:2022-03-11
Keywords: autopsy; complement deposition; COVID-19; kidney; lectin pathway; lung

Complement Factor H-Related 5-Hybrid Proteins Anchor Properdin and Activate Complement at Self-Surfaces - Chen, Qian; Manzke, Melanie; Hartmann, Andrea; Büttner, Maike; Amann, Kerstin Ute; Pauly, Diana; Wiesener, Michael; Skerka, Christine; Zipfel, Peter F. (Journal of the American Society of Nephrology, 2016)
C3 glomerulopathy (C3G) is a severe kidney disease for which no specific therapy exists. The causes of C3G are heterogeneous, and defective complement regulation is often linked to C3G pathogenesis. Copy number variations in the complement factor H-related (CFHR) gene cluster on chromosome 1q32 and CFHR5 mutant proteins associate with this disease. Here, we identified CFHR5 as a pattern recognition protein that binds to damaged human endothelial cell surfaces and to properdin, the human complement activator. We found the two N-terminal short consensus repeat domains of CFHR5 contact properdin and mediate dimer formation. These properdin-binding segments are duplicated in two mutant CFHR5 proteins, CFHR2-CFHR5Hyb from German patients with C3G and CFHR5Dup from Cypriot patients with C3G. Each of these mutated proteins assembled into large multimeric complexes and, compared to CFHR5, bound damaged human cell surfaces and properdin with greater intensity and exacerbated local complement activation. This enhanced surface binding and properdin recruitment was further evidenced in the mesangia of a transplanted and explanted kidney from a German patient with a CFHR2-CFHR5Hyb protein. Enhanced properdin staining correlated with local complement activation with C3b and C5b-9 deposition on the mesangial cell surface in vitro This gain of function in complement activation for two disease-associated CFHR5 mutants describes a new disease mechanism of C3G, which is relevant for defining appropriate treatment options for this disorder.
EVALuna2:3837

Complement factor H-related hybrid protein deregulates complement in dense deposit disease - Chen, Qian; Wiesener, Michael; Eberhardt, Hannes U.; Hartmann, Andrea; Uzonyi, Barbara; Kirschfink, Michael; Amann, Kerstin Ute; Büttner, Maike; Goodship, Tim; Hugo, Christian; Skerka, Christine; Zipfel, Peter F. (Journal of Clinical Investigation, 2014)
The renal disorder C3 glomerulopathy with dense deposit disease (C3G-DDD) pattern results from complement dysfunction and primarily affects children and young adults. There is no effective treatment, and patients often progress to end-stage renal failure. A small fraction of C3G-DDD cases linked to factor H or C3 gene mutations as well as autoantibodies have been reported. Here, we examined an index family with 2 patients with C3G-DDD and identified a chromosomal deletion in the complement factor H-related (CFHR) gene cluster. This deletion resulted in expression of a hybrid CFHR2-CFHR5 plasma protein. The recombinant hybrid protein stabilized the C3 convertase and reduced factor H-mediated convertase decay. One patient was refractory to plasma replacement and exchange therapy, as evidenced by the hybrid protein quickly returning to pretreatment plasma levels. Subsequently, complement inhibitors were tested on serum from the patient for their ability to block activity of CFHR2-CFHR5. Soluble CR1 restored defective C3 convertase regulation; however, neither eculizumab nor tagged compstatin had any effect. Our findings provide insight into the importance of CFHR proteins for C3 convertase regulation and identify a genetic variation in the CFHR gene cluster that promotes C3G-DDD. Monitoring copy number and sequence variations in the CFHR gene cluster in C3G-DDD and kidney patients with C3G-DDD variations will help guide treatment strategies.
EVALuna2:3659

Complement Inhibition in Kidney Transplantation: Where Are We Now? - Vonbrunn, Eva; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Biodrugs, 2022)
Kidney transplantation is a life-saving strategy for patients with end-stage renal disease. Although progress has been made in the field of transplantation medicine in recent decades in terms of surgical techniques and immunosuppression, long-term organ survival remains a challenge. Also, for reasons of organ shortage, there is an unmet need for new therapeutic approaches to improve the long-term survival of transplants. There is increasing evidence that the complement system plays a crucial role in various pathological events after transplantation, including ischemia/reperfusion injury as well as rejection episodes. The complement system is part of the innate immune system and plays a crucial role in the defense against pathogens but is also involved in tissue homeostasis. However, the tightly regulated complement system can become dysregulated or activated by non-infectious stimuli, then targeting the organism’s own cells and leading to inflammatory tissue damage that exacerbates injury. In this review, we will highlight the role of the complement system after transplantation and discuss ongoing and potential therapeutic approaches.
CRIS-Team Scopus Importer:2022-12-23

Complement in Renal Disease as a Potential Contributor to Arterial Hypertension - Fischer, Lisa-Maren; Fichte, Laura A.; Büttner-Herold, Maike; Ferrazzi, Fulvia; Amann, Kerstin Ute; Benz, Kerstin; Daniel, Christoph (Kidney & Blood Pressure Research, 2021)
Objective: Complement deposition is prevalent in kidney biopsies of patients with arterial hypertension and hypertensive nephropathy, but an association of hypertension and complement deposition or involvement of complement in the pathogenesis of hypertensive nephropathy has not been shown to date. Methods: In this study, we analyzed complement C1q and C3c deposition in a rat model of overload and hypertension by subtotal nephrectomy (SNX) and in archival human renal biopsies from 217 patients with known hypertension and 91 control patients with no history of hypertension using semiquantitative scoring of C1q and C3c immunohistochemistry and correlation with parameters of renal function. To address whether complement was only passively deposited or actively expressed by renal cells, C1q and C3 mRNA expression were additionally analyzed. Results: Glomerular C1q and C3c complement deposition were significantly higher in kidneys of hypertensive SNX rats and hypertensive compared to nonhypertensive patients. Mean arterial blood pressure (BP) in SNX rats correlated well with the amount of glomerular C1q and C3c deposition and with left ventricular weight, as an indirect parameter of high BP. Quantitative mRNA analysis showed that C3 was not only deposited but also actively produced by glomerular cells of hypertensive SNX rats and in human renal biopsies. Of note, in patients CKD-stage correlated significantly with the intensity of glomerular C3c staining, but not with that of C1q. Conclusion: Renal complement deposition correlated with experimental hypertension as well as the presence of hypertension in a variety of renal diseases. To answer the question, if and how exactly renal complement is causative for the pathogenesis of arterial hypertension in men, further studies are needed.
CRIS-Team WoS Importer:2021-06-11
Keywords: Kidney; Complement deposition; Hypertension; Renal disease

Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, Kristina; Fiedler, Christian; Günther, Franziska; Grouzmann, Eric; Neuhuber, Winfried; Fischer, Michael; Ott, Christian; Linz, Peter; Freisinger, Wolfgang; Heinlein, Sonja; Schmidt, Stefan; Schmieder, Roland; et al. (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.
EVALuna2:3840

Consensus definitions for glomerular lesions by light and electron microscopy: recommendations from a working group of the Renal Pathology Society - Haas, Mark; Seshan, Surya V.; Barisoni, Laura; Amann, Kerstin Ute; Bajema, Ingeborg M.; Becker, Jan Ulrich; Joh, Kensuke; Ljubanovic, Danica; Roberts, Ian S.D.; Roelofs, Joris J.; Sethi, Sanjeev; Zeng, Caihong; et al. (Kidney International, 2020)
Over the past 2 decades, scoring systems for multiple glomerular diseases have emerged, as have consortia of pathologists and nephrologists for the study of glomerular diseases, including correlation of pathologic findings with clinical features and outcomes. However, one important limitation faced by members of these consortia and other renal pathologists and nephrologists in both investigative work and routine practice remains a lack of uniformity and precision in clearly defining the morphologic lesions on which the scoring systems are based. In response to this issue, the Renal Pathology Society organized a working group to identify the most frequently identified glomerular lesions observed by light microscopy and electron microscopy, review the literature to capture the published definitions most often used for each, and determine consensus terms and definitions for each lesion in a series of online and in-person meetings. The defined lesions or abnormal findings are not specific for any individual disease or subset of diseases, but rather can be applied across the full spectrum of glomerular diseases and within the context of the different scoring systems used for evaluating and reporting these diseases. In addition to facilitating glomerular disease research, standardized terms and definitions should help harmonize reporting of medical kidney diseases worldwide and lead to more-precise diagnoses and improved patient care.
CRIS-Team Scopus Importer:2020-11-06
Keywords: electron microscopy; glomerulonephritis; glomerulus; kidney biopsy; renal pathology

Correction to: Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis (Strahlentherapie und Onkologie, (2019), 195, 1, (52-61), 10.1007/s00066-018-1382-3) - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2020)
The original version of this article unfortunately contained a mistake. The correct version of the Acknowledgements is given below: Acknowledgements This study was supported by the ELAN-Fond (University of Erlangen-Nürnberg). The authors thank Carsten Kronauer and Florian Obstmeier for conducting the immunohistochemical staining and detecting the expression of mediators.
CRIS-Team Scopus Importer:2020-01-21

Correlation of enhanced thrombospondin-1 expression, TGF-β signalling and proteinuria in human type-2 diabetic nephropathy - Hohenstein, Bernd; Daniel, Christoph; Hausknecht, Birgit; Boehmer, Kirsten; Riess, Regine; Amann, Kerstin Ute; Hugo, Christian (Nephrology Dialysis Transplantation, 2008)
Background. Activation of the thrombospondin-1 (TSP-1)-TGF-β pathway by glucose and the relevance of TSP-1-dependent activation of TGF-β for renal matrix expansion, renal fibrosis and sclerosis have previously been demonstrated by our group in in vivo and in vitro studies. Design and methods. We investigated renal biopsies (n = 40) and clinical data (n = 30) of patients with diabetic nephropathy. Ten kidneys without evidence of renal disease served as controls. Glomerular and cortical expression of TSP-1, p-smad2/3, fibrosis and glomerular sclerosis (PAS) were assessed by immunhistochemical staining and related with clinical data. Results. Glomerular (g) and cortical (c) TSP-1 were increased during diabetic nephropathy (g: 2.62 ± 2.65; c: 4.5 ± 4.2) compared to controls (g: 0.67 ± 0.7; c: 1.5 ± 1.2). P-smad2/3 was significantly increased (g: 16.7 ± 12.9; c: 148.7 ± 92.8) compared to controls (g: 7.1 ± 3.6; c: 55 ± 25; P < 0.05). TSP-1 was coexpressed with p-smad2/3 as an indicator of TGF-β activation. TSP-1 correlated with enhanced tubulointerstitial p-smad2/3 positivity (r = 0.39 and r = 0.4, P < 0.05) and glomerular p-smad2/3 correlated with proteinuria (r = 0.35, P < 0.05). Conclusions. In summary, the present study suggests a functional activity of the TSP-1/TGF-β axis, especially in the tubulointerstitium of patients with diabetic nephropathy. The positive correlation of glomerular p-smad2/3 positivity with proteinuria further supports the importance of the TSP-1/TGF-β system as a relevant mechanism for progression of human type-2 diabetic nephropathy. © The Author [2008].
Created from Fastlane, Scopus look-up
Keywords: Diabetic nephropathy; Proteinuria; TGF-β; TSP-1; Tubulointerstitium

Correlation of Hif1a expression of primary oral squamous cell carcinomas with histomorphologic parameters and macrophage polarization - Wehrhan, Falk; Möbius, Patrick; Amann, Kerstin Ute; Geppert, Carol-Immanuel; Preidl, Raimund; Ries, Jutta; Neukam, Friedrich Wilhelm; Weber, Manuel (2018)
EVALuna2:34066

Correlations Between Interleukin-11 Expression and Hypertensive Kidney Injury in a Rat Model of Renovascular Hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Dambietz, Thomas; Veelken, Roland; Amann, Kerstin Ute; Hartner, Andrea; Hilgers, Karl Friedrich (American Journal of Hypertension, 2020)
BACKGROUND: Interleukin-11 (IL-11) is a pleiotropic cytokine of the interleukin-6 family. Recent studies revealed its crucial role in the development of cardiovascular fibrosis. In this study we examined IL-11 expression levels in the heart and the kidney exposed to high blood pressure in renovascular hypertensive rats and their correlations to fibrotic markers and kidney injury. METHODS: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats. IL-11 expression was measured by real-time polymerase chain reaction in the left ventricle and the right kidney. The correlation of cardiac IL-11 expression with biomarkers of renal fibrosis was assessed. We further investigated IL-11 expression in 2K1C rats grouped into rats with malignant vs. nonmalignant hypertension (distinguishing criteria: weight loss, number of fibrinoid necrosis, and onion skin lesions). RESULTS: Thirty-five days after clipping, mean arterial pressure was significantly increased in 2K1C. Renal IL-11 expression was elevated in 2K1C. In the heart there was only a trend toward higher IL-11 expression in 2K1C. IL-11 in the kidney in 2K1C correlated with the expression of transforming growth factor (TGF)-β1/2, collagens, fibronectin, osteopontin, as well as tissue inhibitors of metalloprotease 1/2. There were also correlations of IL-11 with tissue collagen expansion, number of activated fibroblasts and serum creatinine, but no correlation with mean arterial pressure. Renal expression of IL-11 was highest in rats with malignant hypertension. CONCLUSIONS: Renal IL-11 expression of renovascular hypertensive rats is markedly increased and correlates with profibrotic markers and loss of function and might therefore serve as a biomarker for the severity of hypertensive nephrosclerosis.
CRIS-Team Scopus Importer:2020-04-14
Keywords: blood pressure; hypertension; interleukin-11 (IL-11); malignant hypertension; renal fibrosis; two-kidney one-clip renovascular hypertension (2K1C)

Corrigendum: Complement activation via the lectin and alternative pathway in patients with severe COVID-19(Front. Immunol., (2022), 13, (835156), 10.3389/fimmu.2022.835156) - Niederreiter, Janina; Eck, Christine; Ries, Tajana; Hartmann, Arndt; Märkl, Bruno; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2023)
In the published article, information in the Acknowledgments was mistakenly not included in the publication. A correction has been made to Acknowledgments:
CRIS-Team Scopus Importer:2023-10-20
Keywords: autopsy; complement deposition; COVID-19; kidney; lectin pathway; lung

COVID-19 effects on the kidney. - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV‑2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV‑2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
EVALuna2:421391

COVID-19 effects on the kidney - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV-2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV-2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
CRIS-Team WoS Importer:2021-02-19

COVID-19 und Nierenbefall - Amann, Kerstin Ute; Boor, P.; Wiech, T. (Nephrologe, 2020)
Apart from the pulmonary disease, acute kidney injury is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could also be detected in renal tissue. Patients with chronic kidney disease and on dialysis as well as kidney transplantation patients represent a particularly vulnerable population. The increasing number of patients infected with SARS-CoV‑2 has aroused increased interest in the exact pathophysiology and morphology of kidney damage as well as the direct detection of the virus in the kidneys, which in contrast to the lungs is overall more difficult to perform. Meanwhile, data from several large autopsy and kidney biopsy studies are now available. While the detection of SARS-CoV‑2 RNA in tissue leads to consistently reproducible results, the use of electron microscopy for visualization of the virus is critically discussed due to various artefacts. The exact and direct effects of SARS-CoV‑2 on the kidneys are not yet known in detail and are currently the focus of intensive research.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Acute renal insufficiency; Acute tubular injury; Chronic kidney disease; Coronavirus; Virus detection

Critical size defect regeneration using PEG-mediated BMP-2 gene delivery and the use of cell occlusive barrier membranes - the osteopromotive principle revisited - Wehrhan, Falk; Amann, Kerstin Ute; Molenberg, Aart; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2013)
Objective: The objective of this study was to investigate if osseous regeneration can be accelerated by involvement of periosteal tissue. Bone defect regeneration could be accelerated by the involvement of periosteal tissue if osteogenic cell signalling is maintained within the defect. It was questioned if local cell-mediated BMP-2 gene delivery makes a cell occlusive membrane dispensable during bone critical size defect regeneration. Methods: PEG matrix (degradation time 10 days) and PEG membrane (degradation time 120 days) were used in the pig calvarial model. Cylindrical (1 × 1 cm) critical size defects (CSD) (9 per animal; 20 animals) were filled with: (i) particulated autologous bone, covered with PEG membrane (group 1); (ii) HA/TCP, covered with PEG membrane (group 2); (iii) HA/TCP, mixed with PEG matrix (group 3); and (iv) HA/TCP mixed with BMP-2-transfected osteoblasts and PEG matrix (group 4). BMP-2/4 gene transfer: liposomal in vitro transfection of BMP-2/V5-tag fusion-protein. Quantitative histomorphometry (toluidine blue staining) after 2, 4 and 12 weeks assessed bone formation. Semiquantitative immunohistochemistry estimated the expression of BMP-2, V5-tag, Runx-2 and Sox9. Results: PEG matrix embedded BMP-2 expressing cells presented higher bone formation (P < 0.05) than HA/TCP + PEG matrix defect filling or PEG membrane covering (HA/TCP filling) after 12 weeks. Highest expression of BMP-2, Runx-2 and lowest expression of fibrous tissue marker Sox9 was seen in the BMP-2 group. Conclusion: PEG matrix embedded BMP-2 expressing cells are capable to maintain osteogenic signalling and to accelerate osseous defect regeneration in absence of a cell occlusive membrane. © 2012 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: BMP; Bone regeneration; Gene transfer; Hydrogel; Immunohistochemistry; Osteogenesis

CSF2-dependent monocyte education in the pathogenesis of ANCA-induced glomerulonephritis - Rousselle, Anthony; Sonnemann, Janis; Amann, Kerstin Ute; Mildner, Alexander; Lodka, Dorte; Kling, Lovis; Bieringer, Markus; Schneider, Udo; Leutz, Achim; Enghard, Philipp; Kettritz, Ralph; Schreiber, Adrian (Annals of the Rheumatic Diseases, 2022)
Objectives Myeloid cell activation by antineutrophil cytoplasmic antibody (ANCA) is pivotal for necrotising vasculitis, including necrotising crescentic glomerulonephritis (NCGN). In contrast to neutrophils, the contribution of classical monocyte (CM) and non-classical monocyte (NCM) remains poorly defined. We tested the hypothesis that CMs contribute to antineutrophil cytoplasmic antibody-associated vasculitis (AAV) and that colony-stimulating factor-2 (CSF2, granulocyte-macrophage colony-stimulating factor (GM-CSF)) is an important monocyte-directed disease modifier. Methods Myeloperoxidase (MPO)-immunised MPO-/- mice were transplanted with haematopoietic cells from wild-type (WT) mice, C-C chemokine receptor 2 (CCR2)(-/-) mice to abrogate CM, or transcription factor CCAAT-enhancer-binding protein beta (C/EBP beta)(-/-) mice to reduce NCM, respectively. Monocytes were stimulated with CSF2, and CSF2 receptor subunit beta (CSF2rb)-deficient mice were used. Urinary monocytes and CSF2 were quantified and kidney Csf2 expression was analysed. CSF2-blocking antibody was used in the nephrotoxic nephritis (NTN) model. Results Compared with WT mice, CCR2(-/-) chimeric mice showed reduced circulating CM and were protected from NCGN. C/EBP beta(-/-) chimeric mice lacked NCM but developed NCGN similar to WT chimeric mice. Kidney and urinary CSF2 were upregulated in AAV mice. CSF2 increased the ability of ANCA-stimulated monocytes to generate interleukin-1 beta and to promote T(H)17 effector cell polarisation. CSF2rb(-/-) chimeric mice harboured reduced numbers of kidney T(H)17 cells and were protected from NCGN. CSF2 neutralisation reduced renal damage in the NTN model. Finally, patients with active AAV displayed increased urinary CM numbers, CSF2 levels and expression of GM-CSF in infiltrating renal cells. Conclusions CMs but not NCMs are important for inducing kidney damage in AAV. CSF2 is a crucial pathological factor by modulating monocyte proinflammatory functions and thereby T(H)17 cell polarisation.
CRIS-Team WoS Importer:2022-04-29

Cyclosporine A responsive congenital nephrotic syndrome with single heterozygous variants in NPHS1, NPHS2, and PLCE1 - Eichinger, Anna; Ponsel, Sabine; Bergmann, Carsten; Guenthner, Roman; Hoefele, Julia; Amann, Kerstin Ute; Lange-Sperandio, Baerbel (Pediatric Nephrology, 2018)
BACKGROUND: Congenital nephrotic syndrome (CNS) is primarily a monogenetic disease, with the majority of cases due to changes in five different genes: the nephrin (NPHS1), podocin (NPHS2), Wilms tumor 1 (WT1), laminin ß2 (LAMB2), and phospholipase C epsilon 1 (PLCE1, NPHS3) gene. Usually CNS is not responsive to immunosuppressive therapy, but treatment with ACE inhibitors, AT1 receptor blockade and/or indomethacin can reduce proteinuria. If the disease progresses to end-stage renal disease, kidney transplantation is the therapy of choice. CASE-DIAGNOSIS: Here, we present the case of a 4-month-old girl with congenital nephrotic syndrome. Upon admission, the patient presented with life-threatening anasarca, hypoalbuminemia, proteinuria, and impaired growth. There was no evidence of an infectious or immunological etiology. The genetic evaluation revealed a heterozygous variant in NPHS1 (p.Arg207Trp), in NPHS2 (p.Ser95Phe) as well as in PLCE1 (p.Ala1045Ser) and did not explain CNS. In addition to daily parenteral albumin infusions plus furosemide, a pharmacological antiproteinuric therapy was started to reduce protein excretion. Based on the genetic results, immunosuppressive therapy with prednisolone was initiated, but without response. However, following cyclosporine A treatment, the patient achieved complete remission and now has good renal function, growth, and development. CONCLUSIONS: A profound search for the cause of CNS is necessary but has its limitations. The therapeutic strategy should be adapted when the etiology remains unclear.
EVALuna2:34430

Daratumumab for the treatment of refractory ANCA-associated vasculitis - Ostendorf, Lennard; Burns, Marie; Wagner, Dimitrios Laurin; Enghard, Philipp; Amann, Kerstin Ute; Mei, Henrik; Eckardt, Kai-Uwe; Seelow, Evelyn; Schreiber, Adrian (RMD Open, 2023)
Objective Treatment-refractory antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a life-threatening condition without evidence-based treatment options. One emerging treatment option for several antibody-mediated autoimmune diseases is the anti-CD38 antibody daratumumab, which depletes autoantibody-secreting plasma cells.Methods We treated two patients with severe life-threatening AAV with renal and pulmonary manifestation despite induction therapy with rituximab and cyclophosphamide with four to eight doses of 1800 mg daratumumab. We followed clinical and immunological responses.Results The first patient with myeloperoxidase-ANCA-positive microscopic polyangiitis had resolution of pneumonitis and pleuritis and stabilisation of kidney function after daratumumab. The second patient with proteinase 3-ANCA-positive granulomatosis with polyangiitis, diffuse alveolar haemorrhage necessitating extracorporeal membrane oxygenation (ECMO) and acute kidney failure, requiring kidney replacement therapy, was weaned off ECMO, mechanical ventilation and dialysis and discharged home after daratumumab. Clinical improvement was paralleled by a strong reduction in serum ANCA levels as well as total IgG, indicating depletion of plasma cells. Apart from the depletion of CD38+ natural killer cells, blood leucocyte levels were not notably influenced by daratumumab. Only mild adverse events, such as hypogammaglobulinaemia and an upper respiratory tract infection occurred.Conclusion Daratumumab was safe and effective in inducing remission in two patients with severe treatment-refractory AAV, warranting prospective clinical trials to establish safety and efficacy.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Autoimmune Diseases; Systemic vasculitis; Treatment

Darbepoetin alpha reduces oxidative stress and chronic inflammation in atherosclerotic lesions of apo e deficient mice in experimental renal failure - Arend, Nicole; Hilgers, Karl Friedrich; Campean, Valentina; Karpe, Britta; Cordasic, Nada; Klanke, Bernd; Amann, Kerstin Ute (PLoS ONE, 2014)
Cardiovascular morbidity and mortality is very important in patients with chronic renal failure. This occurs even in mild impairment of renal function and may be related to oxidative stress and chronic inflammation. The nephrectomized apo E knockout mouse is an accepted model for evaluating atherosclerosis in renal dysfunction. Erythropoietin derivates showed anti-oxidative and anti-inflammatory effects. Therefore, this study evaluates the effects of Darbepoetin on markers of oxidative stress and chronic inflammation in atherosclerotic lesions in apo E knockout mice with renal dysfunction.Apo E knockout mice underwent unilateral (Unx, n = 20) or subtotal (Snx, n = 26) nephrectomy or sham operation (Sham, n = 16). Mice of each group were either treated with Darbepoetin or saline solution, a part of Snx mice received a tenfold higher dose of Darbepoetin. The aortic plaques were measured and morphologically characterized. Additional immunhistochemical analyses were performed on tissue samples taken from the heart and the aorta.Both Unx and Snx mice showed increased expression of markers of oxidative stress and chronic inflammation. While aortic plaque size was not different, Snx mice showed advanced plaque stages when compared to Unx mice. Darbepoetin treatment elevated hematocrit and lowered Nitrotyrosin as one marker of oxidative stress, inflammation in heart and aorta, plaque stage and in the high dose even plaque cholesterol content. In contrast, there was no influence of Darbepoetin on aortic plaque size; high dose Darbepoetin treatment resulted in elevated renal serum parameters.Darbepoetin showed some protective cardiovascular effects irrespective of renal function, i.e. it improved plaque structure and reduced some signs of oxidative stress and chronic inflammation without affecting plaque size. Nevertheless, the dose dependent adverse effects must be considered as high Darbepoetin treatment elevated serum urea. Elevation of hematocrit might be a favorable effect in anemic Snx animals but a thrombogenic risk in Sham animals.
EVALuna2:3673

Deceased Donor Kidney Transplantation in the Eurotransplant Senior Program (ESP): A Single-Center Experience from 2008 to 2013 - Jacobi, Johannes; Beckmann, Sophie; Heller, Katharina; Hilgers, Karl Friedrich; Apel, Hendrik; Spriewald, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Annals of Transplantation, 2016)
BACKGROUND The aim of this study was to evaluate the outcome after transplantation of deceased allografts in donor/recipient pairs aged >=65 years enrolled in the Eurotransplant Senior Program (ESP). MATERIAL AND METHODS In this retrospective cohort study we evaluated data from 89 patients transplanted under the ESP protocol from 2008 to 2013. Outcome parameters included graft and patient survival, rate of biopsy-proven acute rejections (BPAR), peri- and post-operative complications, tumor development, development of donor-specific antibodies (DSA), and the prognostic role of preimplantation biopsies. RESULTS One-year patient and allograft survival rates were 92.1% and 84.3%, respectively. During follow-up, 23 (26%) patients died; the major cause of death was sepsis, followed by cardiovascular events and malignancies. BPAR episodes were frequent within the first year ( 33%) and overall were less common in patients treated with tacrolimus. Post-transplant malignancies were seen in 15 (17%) patients. During follow-up, 16 (18%) patients developed DSA; patients with delayed graft function (DGF) were more likely to develop DSA (p=0.029). A higher preimplantation biopsy score was associated with DGF but did not predict later graft outcome. CONCLUSIONS The results highlight increased risks in ESP transplant candidates and the importance of careful surveillance of this patient group.
EVALuna2:3834

Deceased donor urinary Dickkopf-3 associates with future allograft function following kidney transplantation - Fallois, Jonathan de; Günzel, Anna; Daniel, Christoph; Stumpf, Julian; Busch, Martin; Pein, Ulrich; Paliege, Alexander; Amann, Kerstin Ute; Wiech, Thorsten; Hantmann, Elena; Wolf, Gunter; Pfeifer, Felix; et al. (American Journal of Transplantation, 2024)
Predicting future kidney allograft function is challenging. Novel biomarkers, such as urinary Dickkopf-3 (uDKK3), may help guide donor selection and improve allograft outcomes. In this prospective multicenter pilot trial, we investigated whether donor uDKK3 reflects organ quality and is associated with future allograft function. We measured uDKK3/crea ratios (uDKK3/crea) from 95 deceased and 46 living kidney donors. Prenephrectomy uDKK3/crea levels were 100× higher in deceased than in living donors (9888 pg/mg vs 113 pg/mg; P < .001). Among deceased donor transplantations, recipients were stratified by their corresponding uDKK3/crea donor levels ranging below (group A, n = 68) or above (group B, n = 65) median. The primary end point of best estimated glomerular filtration rate (eGFR) within the first 3 months after kidney transplantation was superior in group A (56.3 mL/min/1.73 m2) than that in group B (44.2 mL/min/1.73 m2; P = .0139). Second, the composite clinical end point consisting of death, allograft failure or eGFR decline >50% occurred less frequent in group A. By mixed linear regression modeling, donor uDKK3/crea remained an independent predictor of eGFR after transplantation, with a slope of −4.282 mL/min/1.73 m2 per logarithmic increase in donor uDKK3/crea. In summary, uDKK3 may serve as a noninvasive, donor-dependent biomarker for assessing organ quality and future allograft function.
CRIS-Team Scopus Importer:2024-10-18
Keywords: biomarker; DKK3; donor; kidney transplantation; recipient

Development and Evaluation of a Semi-automated Segmentation Tool and a Modified Ellipsoid Formula for Volumetric Analysis of the Kidney in Non-contrast T2-Weighted MR Images - Seuß, Hannes; Janka, Rolf Matthias; Pruemmer, Marcus; Hammon, Rebecca; Theis, Ragnar; Sandmair, Martin; Amann, Kerstin Ute; Bäuerle, Tobias; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Journal of Digital Imaging, 2017)
Volumetric analysis of the kidney parenchyma provides additional information for the detection and monitoring of various renal diseases. Therefore the purposes of the study were to develop and evaluate a semi-automated segmentation tool and a modified ellipsoid formula for volumetric analysis of the kidney in non-contrast T2-weighted magnetic resonance (MR)-images. Three readers performed semi-automated segmentation of the total kidney volume (TKV) in axial, non-contrast-enhanced T2-weighted MR-images of 24 healthy volunteers (48 kidneys) twice. A semi-automated threshold-based segmentation tool was developed to segment the kidney parenchyma. Furthermore, the three readers measured renal dimensions (length, width, depth) and applied different formulas to calculate the TKV. Manual segmentation served as a reference volume. Volumes of the different methods were compared and time required was recorded. There was no significant difference between the semi-automatically and manually segmented TKV (p = 0.31). The difference in mean volumes was 0.3 ml (95% confidence interval (CI), -10.1 to 10.7 ml). Semi-automated segmentation was significantly faster than manual segmentation, with a mean difference = 188 s (220 vs. 408 s); p < 0.05. Volumes did not differ significantly comparing the results of different readers. Calculation of TKV with a modified ellipsoid formula (ellipsoid volume × 0.85) did not differ significantly from the reference volume; however, the mean error was three times higher (difference of mean volumes -0.1 ml; CI -31.1 to 30.9 ml; p = 0.95). Applying the modified ellipsoid formula was the fastest way to get an estimation of the renal volume (41 s). Semi-automated segmentation and volumetric analysis of the kidney in native T2-weighted MR data delivers accurate and reproducible results and was significantly faster than manual segmentation. Applying a modified ellipsoid formula quickly provides an accurate kidney volume.
EVALuna2:14622

Diabetes mellitus negatively affects peri-implant bone formation in the diabetic domestic pig - von Wilmowsky, Cornelius; Stockmann, Philipp; Harsch, Igor; Amann, Kerstin Ute; Metzler, Philipp; Lutz, Rainer; Möst, Tobias; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Journal of Clinical Periodontology, 2011)
Aim: Diabetes mellitus is classified as a relative contraindication for implant treatment, and higher failure rates have been seen in diabetic patients. The aim of the present study was to investigate the effect of diabetes on peri-implant bone formation in an animal model of human bone repair. Materials and Methods: Diabetes was induced by an intra-venous application of streptozotocin (90 mg/kg) in 15 domestic pigs. Implants were placed after significant histopathological changes in the hard and soft tissues were verified. The bone-implant contact (BIC), peri-implant bone mineral density (BMD), and expression of collagen type-I and osteocalcin proteins were qualitatively evaluated 4 and 12 weeks after implantation. Fifteen animals served as healthy controls. Results: Diabetes caused pathological changes in the soft and hard tissues. The BIC and BMD were significantly reduced in the diabetic group after 4 and 12 weeks. Collagen type-I was increased in the diabetic group at both time points, whereas osteocalcin was reduced in the diabetic group. Conclusions: Poorly controlled diabetes negatively affects peri-implant bone formation and bone mineralization. These findings have to be taken into consideration for diabetic patients with an indication for implant therapy. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: bone; diabetes; implants; osseointegration; pig

Diagnostic impact of percutaneous renal biopsy - Kitterer, Daniel; Guerzing, Katharina; Segerer, Stephan; Alscher, M. Dominik; Amann, Kerstin Ute; Braun, Niko; Latus, Joerg (Clinical Nephrology, 2015)
Ultrasound-guided percutaneous renal biopsy (PRB) is an important diagnostic tool for nephrologists. Athough widely used and without question of pivotal importance for the diagnosis of renal diseases, little systematic data regarding standardized indications, outcomes, or consequences for this procedure are available. The aim of this study was to compare the clinically suspected diagnosis with the morphological results and the potential impact of PRB on the treatment of the patient.205 patients who underwent PRB of the native kidney within a 4-year period were included in this retrospective analysis. The biopsy results (BR), discharge diagnosis (DD), and the suspected diagnoses (SD) of the attending nephrologists prior to biopsy were documented.Mean age of the patients was 58 (range 44 - 77) years. The majority of patients (61%) received PRB during an acute disease phase, whereas 39% had elective PRB. Percutaneous biopsy of the native kidney led to a discharge diagnosis in 92% of the patients, with low complication rates (with 3 out of 205 patients had major bleeding complications). In 2/3, the nephrologists were correct with the suspected diagnosis prior to the biopsy. In 74% of the biopsies, a disease was identified that was potentially responsive to treatment modification.In summary, PRB was found to be a safe procedure that confirmed the suspected clinical diagnosis in two thirds of patients. As one third of the histopathological analyses demonstrated a non-suspected disease, the biopsies were of major importance for the correct treatment of the patients.
EVALuna2:25522

Differences in kidney-specific DPP-4 inhibition by linagliptin and sitagliptin - Luippold, Gerd; Mark, Michael; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (Diabetes Research and Clinical Practice, 2018)
The two dipeptidyl peptidase (DPP)-4 inhibitors, linagliptin and sitagliptin, were shown to exert different binding kinetics in vitro. Twenty-four hours after oral dosing particularly in vivo inhibition of renal-specific DPP-4 activity was more sustained in Sprague Dawley rats after exposure to linagliptin than it was after sitagliptin.
EVALuna2:34421

DIFFERENT FORMS OF AFFERENT NERVE INPUT IN CARDIAC AND RENAL DISEASE IN RATS? - Rodionova, Kristina; Ditting, Tilmann; Pickny, Lisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Differential Diagnosis of Interstitial Allograft Rejection and BKV Nephropathy by T-cell Receptor Sequencing - Stervbo, Ulrik; Nienen, Mikalai; Hecht, Jochen; Viebahn, Richard; Amann, Kerstin Ute; Westhoff, Timm H.; Babel, Nina (Transplantation, 2020)
CRIS-Team Scopus Importer:2020-04-10

Differentiating primary and secondary FSGS using non-invasive urine biomarkers. - Catanese, Lorenzo; Siwy, Justyna; Wendt, Ralph; Amann, Kerstin Ute; Beige, Joachim; Hendry, Bruce; Mischak, Harald; Mullen, William; Paterson, Ian; Schiffer, Mario; Wolf, Michael; Rupprecht, Harald (Clinical Kidney Journal, 2024)
BACKGROUND: Focal segmental glomerulosclerosis (FSGS) is divided into genetic, primary (p), uncertain cause, and secondary (s) forms. The subclasses differ in management and prognosis with differentiation often being challenging. We aimed to identify specific urine proteins/peptides discriminating between clinical and biopsy-proven pFSGS and sFSGS. METHODS: Sixty-three urine samples were collected in two different centers (19 pFSGS and 44 sFSGS) prior to biopsy. Samples were analysed using capillary electrophoresis-coupled mass spectrometry. For biomarker definition, datasets of age-/sex-matched normal controls (NC, n = 98) and patients with other chronic kidney diseases (CKDs, n = 100) were extracted from the urinary proteome database. Independent specificity assessment was performed in additional data of NC (n = 110) and CKD (n = 170). RESULTS: Proteomics data from patients with pFSGS were first compared to NC (n = 98). This resulted in 1179 biomarker (P < 0.05) candidates. Then, the pFSGS group was compared to sFSGS, and in a third step, pFSGS data were compared to data from different CKD etiologies (n = 100). Finally, 93 biomarkers were identified and combined in a classifier, pFSGS93. Total cross-validation of this classifier resulted in an area under the receiving operating curve of 0.95. The specificity investigated in an independent set of NC and CKD of other etiologies was 99.1% for NC and 94.7% for CKD, respectively. The defined biomarkers are largely fragments of different collagens (49%). CONCLUSION: A urine peptide-based classifier that selectively detects pFSGS could be developed. Specificity of 95%-99% could be assessed in independent samples. Sensitivity must be confirmed in independent cohorts before routine clinical application.
EVALuna2:552743

DISRUPTION OF TFH:B CELL CROSSTALK PREVENTS ANTIBODY-MEDIATED REJECTION IN AN EXPERIMENTAL KIDNEY TRANSPLANT MODEL - Steines, L.; Poth, H.; Schuster, A.; Amann, Kerstin Ute; Banas, B.; Bergler, T. (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

Disruption of Tfh:B Cell Interactions Prevents Antibody-Mediated Rejection in a Kidney Transplant Model in Rats: Impact of Calcineurin Inhibitor Dose - Steines, Louisa; Poth, Helen; Schuster, Antonia; Amann, Kerstin Ute; Banas, Bernhard; Bergler, Tobias (Frontiers in Immunology, 2021)
We aimed to investigate the mechanisms of humoral immune activation in ABMR using a MHC-mismatched rat kidney transplant model. We applied low dose cyclosporine A (loCNI) to allow donor-specific antibody (DSA) formation and rejection and high dose cyclosporine A (hiCNI) for non-rejection. DSA and leukocyte subsets were measured by flow cytometry. Germinal centers (GC), T follicular helper cells (Tfh), plasma cells and interleukin-21 (IL-21) expression were analyzed by immunofluorescence microscopy. Expression of important costimulatory molecules and cytokines was measured by qRT-PCR. Allograft rejection was evaluated by a nephropathologist. We found that DSA formation correlated with GC frequency and expansion, and that GC size was linked to the number of activated Tfh. In hiCNI, GC and activated Tfh were virtually absent, resulting in fewer plasma cells and no DSA or ABMR. Expression of B cell activating T cell cytokine IL-21 was substantially inhibited in hiCNI, but not in loCNI. In addition, hiCNI showed lower expression of ICOS ligand and IL-6, which stimulate Tfh differentiation and maintenance. Overall, Tfh:B cell crosstalk was controlled only by hiCNI treatment, preventing the development of DSA and ABMR. Additional strategies targeting Tfh:B cell interactions are needed for preventing alloantibody formation and ABMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; B cell activation; calcineurin inhibitor; donor-specific antibodies; kidney transplantation; T follicular helper cells

Divergent roles of haptoglobin and hemopexin deficiency for disease progression of Shiga-toxin-induced hemolytic-uremic syndrome in mice - Pirschel, Wiebke; Mestekemper, Antonio N.; Wissuwa, Bianka; Krieg, Nadine; Kröller, Sarah; Daniel, Christoph; Gunzer, Florian; Tolosano, Emanuela; Bauer, Michael; Amann, Kerstin Ute; Heinemann, Stefan H.; Coldewey, Sina M. (Kidney International, 2022)
Thrombotic microangiopathy, hemolysis and acute kidney injury are typical clinical characteristics of hemolytic-uremic syndrome (HUS), which is predominantly caused by Shiga-toxin–producing Escherichia coli. Free heme aggravates organ damage in life-threatening infections, even with a low degree of systemic hemolysis. Therefore, we hypothesized that the presence of the hemoglobin- and the heme-scavenging proteins, haptoglobin and hemopexin, respectively impacts outcome and kidney pathology in HUS. Here, we investigated the effect of haptoglobin and hemopexin deficiency (haptoglobin-/-, hemopexin-/-) and haptoglobin treatment in a murine model of HUS-like disease. Seven-day survival was decreased in haptoglobin-/- (25%) compared to wild type mice (71.4%), whereas all hemopexin-/- mice survived. Shiga-toxin–challenged hemopexin-/- mice showed decreased kidney inflammation and attenuated thrombotic microangiopathy, indicated by reduced neutrophil recruitment and platelet deposition. These observations were associated with supranormal haptoglobin plasma levels in hemopexin-/- mice. Low dose haptoglobin administration to Shiga-toxin–challenged wild type mice attenuated kidney platelet deposition and neutrophil recruitment, suggesting that haptoglobin at least partially contributes to the beneficial effects. Surrogate parameters of hemolysis were elevated in Shiga-toxin–challenged wild type and haptoglobin-/- mice, while signs for hepatic hemoglobin degradation like heme oxygenase-1, ferritin and CD163 expression were only increased in Shiga-toxin–challenged wild type mice. In line with this observation, haptoglobin-/- mice displayed tubular iron deposition as an indicator for kidney hemoglobin degradation. Thus, haptoglobin and hemopexin deficiency plays divergent roles in Shiga-toxin–mediated HUS, suggesting haptoglobin is involved and hemopexin is redundant for the resolution of HUS pathology.
CRIS-Team Scopus Importer:2022-03-25
Keywords: acute kidney injury; haptoglobin; hemolysis; hemolytic-uremic syndrome; hemopexin; iron homeostasis; Shiga toxin

Diverse molecular causes of unsolved autosomal dominant tubulointerstitial kidney diseases - Wopperer, Florian; Knaup, Karl; Stanzick, Kira J.; Schneider, Karen; Jobst-Schwan, Tilman; Ekici, Arif Bülent; Uebe, Steffen; Wenzel, Andrea; Schliep, Stefan; Schürfeld, Carsten; Seitz, Randolf; Bernhardt, Wanja; et al. (Kidney International, 2022)
Autosomal Dominant Tubulointerstitial Kidney Disease (ADTKD) is caused by mutations in one of at least five genes and leads to kidney failure usually in mid adulthood. Throughout the literature, variable numbers of families have been reported, where no mutation can be found and therefore termed ADTKD-not otherwise specified. Here, we aim to clarify the genetic cause of their diseases in our ADTKD registry. Sequencing for all known ADTKD genes was performed, followed by SNaPshot minisequencing for the dupC (an additional cytosine within a stretch of seven cytosines) mutation of MUC1. A virtual panel containing 560 genes reported in the context of kidney disease (nephrome) and exome sequencing were then analyzed sequentially. Variants were validated and tested for segregation. In 29 of the 45 registry families, mutations in known ADTKD genes were found, mostly in MUC1. Sixteen families could then be termed ADTKD-not otherwise specified, of which nine showed diagnostic variants in the nephrome (four in COL4A5, two in INF2 and one each in COL4A4, PAX2, SALL1 and PKD2). In the other seven families, exome sequencing analysis yielded potential disease associated variants in novel candidate genes for ADTKD; evaluated by database analyses and genome-wide association studies. For the great majority of our ADTKD registry we were able to reach a molecular genetic diagnosis. However, a small number of families are indeed affected by diseases classically described as a glomerular entity. Thus, incomplete clinical phenotyping and atypical clinical presentation may have led to the classification of ADTKD. The identified novel candidate genes by exome sequencing will require further functional validation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: ADTKD; Alport syndrome; exome; MITKD; MUC1; UMOD

Do ANCAs make the difference in lupus nephritis? - Amann, Kerstin Ute (Kidney International, 2017)
There has been much debate as to whether the distinction between lupus nephritis class IV-S and class IV-G is clinically relevant and whether antineutrophil cytoplasmic antibodies are pathomechanistically involved because they have been associated with the more necrotic and pauci-inflammatory phenotype of lupus nephritis that is more often seen in class IV-S. Recent data show that antineutrophil cytoplasmic antibody positivity indeed influences the histological pattern of lupus nephritis and is associated with worse baseline renal function and more active lupus serology.
EVALuna2:25558

Donor acute kidney injury and short-term graft outcome in renal transplantation - Jacobi, Johannes; Rebhan, Dirk; Heller, Katharina; Velden, Joachim; Hilgers, Karl Friedrich; Wullich, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Clinical Transplantation, 2014)
With increased waiting times for kidney transplantation, marginal organs from expanded criteria donors (ECD) are increasingly offered for allocation. In addition to ECD status, donors may have suffered from acute kidney injury (AKI) prior to organ procurement.In this retrospective cohort study, we studied short-term allograft function in 517 kidney transplants performed between the years 2008-2014. Recipients of allografts from deceased organ donors were categorized as standard criteria donors (SCD) or ECD with or without AKI defined by RIFLE criteria.Of 382 deceased donations, 174 (45.5%) were classified as ECD and 63 (16.5%) fulfilled AKI criteria. Donor creatinine on hospital admission was similar, whereas creatinine before organ procurement differed (p < 0.001). Despite these differences, serum creatinine and eGFR at discharge and after one yr showed only minor differences between kidneys with or without AKI. In multivariate linear regression analyses, donor AKI was not a predictor of one-yr allograft function.Given the poor prognosis of dialysis patients and the increase in waiting time, kidneys from SCD and ECD donors with AKI should be allocated for transplantation. In case of ECD donors with AKI, recipients should be informed about the possibility of permanent non-function or early graft loss.
EVALuna2:3714

Double-Sided Graphene-Enhanced Raman Scattering and Fluorescence Quenching in Hybrid Biological Structures - Sarau, George; Daniel, Christoph; Heilmann, Martin; Leuchs, Gerd; Amann, Kerstin Ute; Christiansen, Silke H. (Advanced Materials Technologies, 2021)
Due to their large contact and loading surfaces as well as high sensitivities to chemical changes, graphene-based materials (GBMs) are increasingly being employed into novel nanomedicine technologies. Here biomolecule-monolayer graphene-kidney tissue hybrid structures are studied using mapping micro-Raman and fluorescence spectroscopies. Because in this configuration graphene interacts with molecules on both sides, a double-sided graphene-enhanced Raman scattering (GERS) effect up to approximate to 10.1 is found for biomolecules adsorbed on graphene and amino acids in the kidney tissue below graphene. Moreover, graphene causes an efficient autofluorescence quenching (FLQ) up to approximate to 20% emitted by the kidney tissue. Despite the complexity of such layered materials, the intriguing simultaneous occurrence of double-sided GERS (a new development of GERS) and FLQ phenomena can be well explained by suitable molecular structure and energy level alignment between molecules and graphene. These result in effective charge transfer mediated by non-covalent interactions as indicated by correlative strain, doping, and defect analyses in graphene based on the Raman data and energy level calculations. Last, the advantages of using graphene over standard photobleaching are demonstrated. This work can be extended to other macromolecular entities toward integrating GBMs in versatile drug delivery, imaging, and sensing devices.
CRIS-Team WoS Importer:2021-08-13

DPP4-INHIBITOR LINAGLIPTIN ACCELERATES RESOLUTION OF CRESCENT FORMATION IN A RAT MODEL OF ANTI-GBM GLOMERULONEPHRITIS - Mayer, Anna-Lena; Ebert, Nadja; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-08-21

Dysfunction of the key ferroptosis-surveilling systems hypersensitizes mice to tubular necrosis during acute kidney injury - Tonnus, Wulf; Meyer, Claudia; Steinebach, Christian; Belavgeni, Alexia; von Mässenhausen, Anne; Gonzalez, Nadia Zamora; Maremonti, Francesca; Gembardt, Florian; Himmerkus, Nina; Latk, Markus; Locke, Sophie; Marschner, Julian; et al. (Nature Communications, 2021)
Acute kidney injury (AKI) is morphologically characterized by a synchronized plasma membrane rupture of cells in a specific section of a nephron, referred to as acute tubular necrosis (ATN). Whereas the involvement of necroptosis is well characterized, genetic evidence supporting the contribution of ferroptosis is lacking. Here, we demonstrate that the loss of ferroptosis suppressor protein 1 (Fsp1) or the targeted manipulation of the active center of the selenoprotein glutathione peroxidase 4 (Gpx4cys/-) sensitize kidneys to tubular ferroptosis, resulting in a unique morphological pattern of tubular necrosis. Given the unmet medical need to clinically inhibit AKI, we generated a combined small molecule inhibitor (Nec-1f) that simultaneously targets receptor interacting protein kinase 1 (RIPK1) and ferroptosis in cell lines, in freshly isolated primary kidney tubules and in mouse models of cardiac transplantation and of AKI and improved survival in models of ischemia-reperfusion injury. Based on genetic and pharmacological evidence, we conclude that GPX4 dysfunction hypersensitizes mice to ATN during AKI. Additionally, we introduce Nec-1f, a solid inhibitor of RIPK1 and weak inhibitor of ferroptosis.
CRIS-Team Scopus Importer:2021-08-06

Early Ultrastructural Changes in Biopsies From Patients With Symptomatic CKD of Uncertain Etiology - Daniel, Christoph; Enghard, Philipp; Ratnatunga, Neelakanthi; Wijetunge, Sulochana; Wazil, A. W.M.; Zwiener, Christian; Barth, Johannes; Chandrajith, Rohana; Klewer, Monika; Eckardt, Kai-Uwe; Amann, Kerstin Ute; Freund, Paul; et al. (Kidney International Reports, 2023)
Introduction: Although the investigation of chronic kidney disease of uncertain etiology (CKDu) has identified many possible influencing factors in recent years, the exact pathomechanism of this disease remains unclear. Methods: In this study, we collected 13 renal biopsies from patients with symptomatic CKDu (Sym-CKDu) from Sri Lanka with well-documented clinical and socioeconomic factors. We performed light microscopy and electron microscopic evaluation for ultrastructural analysis, which was compared with 100 biopsies from German patients with 20 different kidney diseases. Results: Of the 13 Sri Lankan patients, 12 were men (92.3%), frequently employed in agriculture (50%), and experienced symptoms such as feeling feverish (83.3%), dysuria (83.3%), and arthralgia (66.6%). Light microscopic evaluation using activity and chronicity score revealed that cases represented early stages of CKDu except for 2 biopsies, which showed additional signs of diabetes. Most glomeruli showed only mild changes, such as podocyte foot process effacement on electron microscopy. We found a spectrum of early tubulointerstitial changes including partial loss of brush border in proximal tubules, detachment of tubular cells, enlarged vacuoles, and mitochondrial swelling associated with loss of cristae and dysmorphic lysosomes with electron-dense aggregates. None of these changes occurred exclusively in Sym-CKDu; however, they were significantly more frequent in these cases than in the control cohort. Conclusion: In conclusion, our findings confirm the predominant and early alterations of tubular structure in CKDu that can occur without significant glomerular changes. The ultrastructural changes do not provide concrete evidence of the cause of CKDu but were significantly more frequent in Sym-CKDu than in the controls.
CRIS-Team Scopus Importer:2023-03-17
Keywords: chronic kidney disease of uncertain etiology (CKDu); lysosomal alteration; mitochondrial swelling; renal biopsy; transmission electron microscopy; tubular injury

Eculizumab in Pediatric Dense Deposit Disease - Oosterveld, Michiel J. S.; Garrelfs, Mark R.; Hoppe, Bernd; Florquin, Sandrine; Roelofs, Joris J. T. H.; Van Den Heuvel, L. P.; Amann, Kerstin Ute; Davin, Jean-Claude; Bouts, Antonia H. M.; Schriemer, Pietrik J.; Groothoff, Jaap W. (Clinical Journal of the American Society of Nephrology, 2015)
Dense deposit disease (DDD), a subtype of C3 glomerulopathy, is a rare disease affecting mostly children. Treatment options are limited. Debate exists whether eculizumab, a monoclonal antibody against complement factor C5, is effective in DDD. Reported data are scarce, especially in children.The authors analyzed clinical and histologic data of five pediatric patients with a native kidney biopsy diagnosis of DDD. Patients received eculizumab as therapy of last resort for severe nephritic or nephrotic syndrome with alternative pathway complement activation; this therapy was given only when the patients had not or only marginally responded to immunosuppressive therapy. Outcome measures were kidney function, proteinuria, and urine analysis.In all, seven disease episodes were treated with eculizumab (six episodes of severe nephritic syndrome [two of which required dialysis] and one nephrotic syndrome episode). Median age at treatment start was 8.4 (range, 5.9-13) years. For three treatment episodes, eculizumab was the sole immunosuppressive treatment. In all patients, both proteinuria and renal function improved significantly within 12 weeks of treatment (median urinary protein-to-creatinine ratio of 8.5 [range, 2.2-17] versus 1.1 [range, 0.2-2.0] g/g, P<0.005, and eGFR of 58 [range, 17-114] versus 77 [range, 50-129] ml/min per 1.73 m(2), P<0.01). A striking finding was the disappearance of leukocyturia within 1 week after the first eculizumab dose in all five episodes with leukocyturia at treatment initiation.In this case series of pediatric patients with DDD, eculizumab treatment was associated with reduction in proteinuria and increase in eGFR. Leukocyturia resolved within 1 week of initiation of eculizumab treatment. These results underscore the need for a randomized trial of eculizumab in DDD.
EVALuna2:25493

EFFECTS OF NEUROGENIC CGRP ON RENAL AFFERENT PEPTIDERGIC NEURONS - Veelken, Roland; Raschke, Giulia; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Rodionova, Kristina (2018)
EVALuna2:204843

Einfluss des Klimawandels auf Infektionskrankheiten in der Nephrologie - Kraft, Leonie; Schmidt-Chanasit, Jonas; Paul, Gregor; Amann, Kerstin Ute; Latus, Jörg (Die Nephrologie, 2023)
Climate change is one of the most important challenges of our time. While at first sight the danger seems to emanate from extreme weather situations and natural disasters, the risk of a possible increase or change in the pathogen spectrum of infectious diseases should not be ignored. We do not yet know much about the spread of infectious diseases due to global warming. Most scenarios are derived from statistical climate models and what the future will look like is difficult to estimate. In addition, the lack of epidemiological data and different mandatory reporting of infectious diseases make the risk assessment more difficult. Furthermore, the spread of infectious diseases is not only dependent on higher temperatures. Changes in the use of agricultural land, socioeconomic factors with population growth and migration, access to clean drinking water, and innovations in the healthcare and reporting systems will continue to change the pattern of infectious diseases. Infectious diseases will affect the nephrology community in different ways in the coming years and decades. Some, such as hantavirus infections, are obvious as acute kidney injury is characteristic for this disease. Others have an indirect effect, through septic or prerenal kidney injury or because most of the patients belong to vulnerable groups and are particularly in need of protection. In the case of febrile illnesses, many of the diseases mentioned should be considered as differential diagnoses in the future, even without a suitable travel history.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Arbovirus infections; Global warming; Kidney injury; Metazoonoses; Vector-borne pathogens

Einführung in die Nierenpathologie - Büttner-Herold, Maike; Amann, Kerstin Ute (Die Pathologie, 2024)
In recent decades, nephropathology has developed worldwide as a subspeciality of pathology, which requires special methodological and technical equipment to process the material and specific clinical and pathological expertise to interpret the findings. These special requirements mean that nephropathology is not available at all pathology institutes, but is carried out on a large scale in a few highly specialised centres. The history of nephropathology, or in a narrower sense the specialised histopathological examination of kidney biopsies, began in 1958 with the first use or performance of a kidney biopsy [1]. It thus replaced the practice of urinalysis, which had been common since the Middle Ages, as a diagnostic tool for kidney diseases. Specialised techniques such as immunofluorescence or immunohistology but also electron microscopy are required to assess specific renal changes, for which the examination of renal biopsies is one of the few remaining routine applications today. In Germany and German-speaking countries, the discipline developed thanks to the work of outstanding people in the field of pathology who were primarily involved in this discipline and had the necessary technical and human resources in their laboratories to ensure that these biopsies could be analysed.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Electron microscopy; Immunohistology; Light microscopy; Renal biopsy; Renal specimens

Elastin imaging enables noninvasive staging and treatment monitoring of kidney fibrosis - Sun, Qinxue; Baues, Maike; Klinkhammer, Barbara M.; Ehling, Josef; Djudjaj, Sonja; Drude, Natascha; Daniel, Christoph; Amann, Kerstin Ute; Kramann, Rafael; Kim, Hyojin; Saez-Rodriguez, Julio; Weiskirchen, Ralf; et al. (Science Translational Medicine, 2019)
Fibrosis is the common endpoint and currently the best predictor of progression of chronic kidney diseases (CKDs). Despite several drawbacks, biopsies remain the only available means to specifically assess the extent of renal fibrosis. Here, we show that molecular imaging of the extracellular matrix protein elastin allows for noninvasive staging and longitudinal monitoring of renal fibrosis. Elastin was hardly expressed in healthy mouse, rat, and human kidneys, whereas it was highly up-regulated in cortical, medullar, and perivascular regions in progressive CKD. Compared to a clinically relevant control contrast agent, the elastin-specific magnetic resonance imaging agent ESMA specifically detected elastin expression in multiple mouse models of renal fibrosis and also in fibrotic human kidneys. Elastin imaging allowed for repetitive and reproducible assessment of renal fibrosis, and it enabled longitudinal monitoring of therapeutic interventions, accurately capturing anti-fibrotic therapy effects. Last, in a model of reversible renal injury, elastin imaging detected ensuing fibrosis not identifiable via routine assessment of kidney function. Elastin imaging thus has the potential to become a noninvasive, specific imaging method to assess renal fibrosis.
CRIS-Team WoS Importer:2019-04-16

Elevated n-3/n-6 PUFA ratio in early life diet reverses adverse intrauterine kidney programming in female rats - Voggel, Jenny; Fink, Gregor; Zelck, Magdalena; Wohlfarth, Maria; Post, Julia M.; Bindila, Laura; Rauh, Manfred; Amann, Kerstin Ute; Alcazar, Miguel A. Alejandre; Doetsch, Joerg; Nuesken, Kai-Dietrich; Nuesken, Eva (Journal of Lipid Research, 2022)
Intrauterine growth restriction (IUGR) predisposes to chronic kidney disease via activation of proinflammatory pathways, and omega-3 PUFAs (n-3 PUFAs) have anti-inflammatory properties. In female rats, we investigated 1) how an elevated di-etary n-3/n-6 PUFA ratio (1:1) during postnatal kidney development modifies kidney phospholipid (PL) and arachidonic acid (AA) metabolite content and 2) whether the diet counteracts adverse molecular pro-tein signatures expected in IUGR kidneys. IUGR was induced by bilateral uterine vessel ligation or intra-uterine stress through sham operation 3.5 days before term. Control (C) offspring were born after uncom-promised pregnancy. On postnatal (P) days P2-P39, rats were fed control (n-3/n-6 PUFA ratio 1:20) or n-3 PUFA intervention diet (N3PUFA; ratio 1:1). Plasma parameters (P33), kidney cortex lipidomics and pro-teomics, as well as histology (P39) were studied. We found that the intervention diet tripled PL-DHA content (PC 40:6; P < 0.01) and lowered both PL-AA content (PC 38:4 and lyso-phosphatidylcholine 20:4; P < 0.05) and AA metabolites (HETEs, dihydrox-yeicosatrienoic acids, and epoxyeicosatrienoic acids) to 25% in all offspring groups. After ligation, our network analysis of differentially expressed proteins identified an adverse molecular signature indicating inflammation and hypercoagulability. N3PUFA diet reversed 61 protein alterations (P < 0.05), thus miti-gating adverse IUGR signatures. In conclusion, an elevated n-3/n-6 PUFA ratio in early diet strongly reduces proinflammatory PLs and mediators while increasing DHA-containing PLs regardless of prior intrauterine conditions. Counteracting a proin-flammatory hypercoagulable protein signature in young adult IUGR individuals through early diet intervention may be a feasible strategy to prevent developmentally programmed kidney damage in later life.
CRIS-Team WoS Importer:2022-12-02

End-stage renal disease after sarcoma therapy - case 3/2014 - Baumann, D.; Amann, Kerstin Ute; Schlatter, E.; Ciarimboli, G.; Kopp, H. G.; Müller, M.; Kluba, T.; Bakos, G.; Steinke, I.; Bunz, H.; Weyrich, P.; Artunc, F. (Deutsche Medizinische Wochenschrift, 2014)
A 67-year-old male patient developed progressive renal failure following successful treatment of a soft tissue sarcoma that comprised surgical resection after neoadjuvant radiochemotherapy with the application of doxorubicin (cumulative dose 180 mg/m²) and ifosfamide (cumulative dose 33 g/m²).Plasma creatinine concentration was elevated to 4.5 mg/dl. Upon detection of glucosuria and ?1-microglobulinuria renal biopsy was performed.Histologic analysis revealed massively injured tubules that could be explained by a toxic effect of ifosfamide. Glomeruli were not affected and appeared normal. After two months of conservative therapy, the patient developed an uremic syndrome requiring hemodialysis. Ever since kidney function did not recover albeit preserved diuresis.Ifosfamide can cause end-stage renal disease by a tubulotoxic effect that may be the result of a selective intracellular uptake into the proximal tubule via the human organic cation transporter 2 (OCT2).
EVALuna2:25473

Engineering of vascularized transplantable bone tissues: induction of axial vascularization in an osteoconductive matrix using an arteriovenous loop. - Kneser, Ulrich; Polykandriotis, Elias; Ohnolz, Jan; Heidner, Kristina; Grabinger, Lucia; Euler, Simon; Amann, Kerstin Ute; Heß, Andreas; Brune, Kay; Greil, Peter; Stürzl, Michael; Horch, Raymund E. (Tissue Engineering -Larchmont, 2006)
This study demonstrates for the first time successful vascularization of solid porous matrices by means of an AV loop. Injection of osteogenic cells into axially prevascularized matrices may eventually create functional bioartificial bone tissues for reconstruction of large defects. Vascularization remains an obstacle to engineering of larger volume bone tissues. Our aim was to induce axial vascularization in a processed bovine cancellous bone (PBCB) matrix using an arteriovenous (AV) loop (artery, vein graft, and vein). Custom-made PBCB discs (9 x 5 mm) were implanted into rats. In group A (n = 19), the matrices were inserted into microsurgically constructed AV loops between the femoral vessels using a vein graft from the contralateral side. In group B (n = 19), there was no vascular carrier. The matrices were encased in isolation chambers. After 2, 4, and 8 weeks, the animals were perfused with India ink via the abdominal aorta. Matrices were explanted and subjected to histological and morphometric analysis. Results were compared with intravital dynamic micro & magnetic resonance imaging and scanning electron microscopy images of vascular corrosion replicas. In group A, significant vascularization of the matrix had occurred by the 8th week. At this time, vascular remodeling with organization into vessels of different sizes was evident. Blood vessels originated from all 3 zones of the AV loop. Group A was significantly superior to group B in terms of vascular density and vascularization kinetics. DISCUSSION INTRODUCTION METHODS RESULTS

Epidemiology, molecular, and genetic methodologies to evaluate causes of CKDu around the world: report of the Working Group from the ISN International Consortium of Collaborators on CKDu - Anand, Shuchi; Caplin, Ben; Gonzalez-Quiroz, Marvin; Schensul, Stephen L.; Bhalla, Vivek; Parada, Xavier; Nanayakkara, Nishantha; Fire, Andrew; Levin, Adeera; Friedman, David J.; Aguilar-Gonzalez, Angie; Abbot, Kevin; et al. (Kidney International, 2019)
CRIS-Team WoS Importer:2019-12-06

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

Erratum to: ‘Inhibition of the renal apical sodium dependent bile acid transporter prevents cholemic nephropathy in mice with obstructive cholestasis’ [J Hepatol (2024) 80:268-281, (S0168827823052352), (10.1016/j.jhep.2023.10.035)] - Ghallab, Ahmed; González, Daniela; Strängberg, Ellen; Hofmann, Ute; Myllys, Maiju; Hassan, Reham; Hobloss, Zaynab; Brackhagen, Lisa; Begher-Tibbe, Brigitte; Duda, Julia C.; Drenda, Carolin; Kappenberg, Franziska; et al. (Journal of Hepatology, 2025)
In this article, owing to a typesetter error, the supplementary video files were incorrectly named. This has now been updated online. The publisher apologises for any inconvenience caused.
CRIS-Team Scopus Importer:2025-04-01

Essential role of DNA-PKcs and plasminogen for the development of doxorubicin-induced glomerular injury in mice - Bohnert, Bernhard N.; Gonzalez-Menendez, Irene; Dörffel, Thomas; Schneider, Jonas C.; Xiao, Mengyun; Janessa, Andrea; Kalo, M. Zaher; Fehrenbacher, Birgit; Schaller, Martin; Casadei, Nicolas; Amann, Kerstin Ute; Daniel, Christoph; et al. (Disease Models & Mechanisms, 2021)
Susceptibility to doxorubicin-induced nephropathy (DIN), a toxic model for the induction of proteinuria in mice, is related to the single-nucleotide polymorphism (SNP) C6418T of the Prkdc gene encoding for the DNA-repair enzyme DNA-PKcs. In addition, plasminogen (Plg) has been reported to play a role in glomerular damage. Here, we investigated the interdependence of both factors for the development of DIN. Genotyping confirmed the SNP of the Prkdc gene in C57BL/6 (PrkdcC6418/C6418) and 129S1/SvImJ (PrkdcT6418/T6418) mice. Intercross of heterozygous 129SB6F1 mice led to 129SB6F2 hybrids with Mendelian inheritance of the SNP. After doxorubicin injection, only homozygous F2 mice with PrkdcT6418/T6418 developed proteinuria. Genetic deficiency of Plg (Plg-/-) in otherwise susceptible 129S1/SvImJ mice led to resistance to DIN. Immunohistochemistry revealed glomerular binding of Plg in Plg+/+ mice after doxorubicin injection involving histone H2B as Plg receptor. In doxorubicin-resistant C57BL/6 mice, Plg binding was absent. In conclusion, susceptibility to DIN in 129S1/SvImJ mice is determined by a hierarchical two-hit process requiring the C6418T SNP in the Prkdc gene and subsequent glomerular binding of Plg.
CRIS-Team Scopus Importer:2021-10-15
Keywords: DNA-pkcs; Doxorubicin; Nephropathy; Plasminogen; Prkdc

Ethylene glycol poisoning - Garibashvili, Tamara; Roeder, Maximilian; Pfluegler, Carolin; Breckner, Martin; Amann, Kerstin Ute; Heckmann, Josef G. (Practical Neurology, 2022)
CRIS-Team WoS Importer:2022-10-21

Experimental renal transplantation in rats improves cardiac dysfunction caused by chronic kidney disease while LVH persists - Hagmayer, Linda; Mayer, Christina; Ebert, Nadja; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Cardiovascular Medicine, 2023)
Background: Chronic kidney disease (CKD) causes congestive heart failure (CHF) with systolic dysfunction and left ventricular hypertrophy (LVH), which is a major contributor to increased mortality in CKD patients. It remains unclear whether cardiovascular changes that occur during the course of CKD can be reversed when renal function is restored by transplantation. Methods: To investigate this, chronic kidney disease was established in F344 rats by subtotal nephrectomy (SNx) for 8 weeks, followed by transplantation of a functional kidney from an isogenic F344 donor. SNx rats without transplantation and sham-operated animals served as controls. Renal function was assessed before and throughout the experiment. In addition, cardiac ultrasound was performed at weeks 0, 8, 12 and 16. At the end of the experiment, intra-arterial blood pressure was measured and kidneys and hearts were histologically and molecularly examined. Results: Eight weeks after SNx, rats developed marked renal dysfunction associated with significant glomerulosclerosis and tubulointerstitial fibrosis, but also an increase in left ventricular mass. After transplantation, renal function normalized but relative heart weight and ventricular mass as assessed by ultrasound scans showed no reduction compared with SNx controls. However, left ventricular wall thickness, fractional shortening and ejection fraction was normalized by renal transplantation. At 8 weeks after kidney transplantation, cardiac expression of BNP and FGF23 was also at levels comparable to healthy controls, whereas these factors were significantly increased in SNx rats. Cardiac fibrosis, as measured by fibronectin mRNA expression, was completely normalized, whereas cardiac fibronectin protein was still slightly but not significantly increased in transplanted animals compared to controls. In addition, the myofibroblast marker collagen 1, as assessed by immunohistochemistry, was significantly increased in SNx rats and also normalized by renal transplantation. Interestingly, CD68+ macrophages were significantly reduced in the hearts of SNx rats and in transplanted animals at slightly higher levels compared to controls. Conclusion: Restoration of renal function by kidney transplantation normalized early cardiac changes at most functional and molecular levels, but did not completely reverse LVH. However, further studies are needed to determine whether restoration of renal function can also reverse LVH at a later time point.
CRIS-Team Scopus Importer:2023-08-11
Keywords: cardiac hypertrophy; chronic kidney disease; FGF23; fibrosis; renal tranplantation

Expression of transforming growth factor beta 1-related signaling proteins in irradiated vessels - Preidl, Raimund; Moebius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Wehrhan, Falk (Strahlentherapie und Onkologie, 2015)
Microvascular free tissue transfer is a standard method in head and neck reconstructive surgery. However, previous radiotherapy of the operative region is associated with an increased incidence in postoperative flap-related complications and complete flap loss. As transforming growth factor beta (TGF-?) 1 and galectin-3 are well known markers in the context of fibrosis and lectin-like oxidized low-density lipoprotein 1 (LOX-1) supports vascular atherosclerosis, the aim of this study was to evaluate the expression of TGF-?1 and related markers as well as LOX-1 in irradiated vessels.To evaluate the expression of galectin-3, Smad 2/3, TGF-?1, and LOX-1, 20 irradiated and 20 nonirradiated arterial vessels were used for immunohistochemical staining. We semiquantitatively assessed the ratio of stained cells/total number of cells (labeling index).Expression of galectin-3, Smad 2/3, and TGF-?1 was significantly increased in previously irradiated vessels compared with nonirradiated controls. Furthermore, LOX-1 was expressed significantly higher in irradiated compared with nonirradiated vessels.Fibrosis-related proteins like galectin-3, Smad 2/3, and TGF-?1 are upregulated after radiotherapy and support histopathological changes leading to vasculopathy of the irradiated vessels. Furthermore, postoperative complications in irradiated patients can be explained by increased endothelial dysfunction caused by LOX-1 in previously irradiated patients. Consequently, not only TGF-?1 but also galectin-3inhibitors may decrease complications after microsurgical tissue transfer.
EVALuna2:24387

Factor inhibiting HIF limits the expression of hypoxia-inducible genes in podocytes and distal tubular cells - Schödel, Johannes; Bohr, Daniela; Klanke, Bernd; Schley, Gunnar; Schlötzer-Schrehardt, Ursula; Warnecke, Christina; Kurtz, Armin; Amann, Kerstin Ute; Eckardt, Kai-Uwe; Willam, Carsten (Kidney International, 2010)
The two hypoxia-inducible factors (HIF-1α and HIF-2α) are transcription factors that regulate the response to hypoxia. Recently, the factor inhibiting HIF (FIH1) was identified as a molecular oxygen-dependent dioxygenase that blunts the transcriptional activity of HIF and has also been implicated in HIF-dependent and-independent hypoxia responses. Interestingly, HIF accumulation in the kidney has been shown to confer renal protection and to also cause glomerular injury or enhance renal fibrosis. In order to better understand the regulation of hypoxia-inducible genes, we determined the expression of FIH1 in the kidney and its functional role in isolated renal cells. FIH1 was expressed only in distal tubules and in podocytes, thus showing a very distinct expression pattern, partially overlapping with sites of HIF-1α expression. In tubular cells, RNA silencing of FIH1 caused transcriptional activation of HIF target genes during hypoxia. In contrast, FIH1 silencing in podocytes enhanced transcription of hypoxia-inducible genes in an HIF-independent manner. Using the anti-Thy.1 rat model of glomerulonephritis, we found a gradual decrease of glomerular FIH1 expression during disease progression paralleled by an increase in hypoxia-inducible genes including CXCR4, a mediator of glomerular inflammation. Thus, FIH1 appears to be a suppressor of oxygen-dependent genes in the kidney, operating through HIF-dependent and-independent mechanisms. © 2010 International Society of Nephrology.
CRIS-Team Scopus Importer:2024-05-13
Keywords: cell biology and structure; hypoxia; immunohistochemistry; podocyte; tubule cells

Fatal Puumala Hantavirus Infection in a Patient with Common Variable Immunodeficiency (CVID) - Steininger, Philipp; Herbst, Larissa; Bihlmaier, Karl; Willam, Carsten; Koerper, Sixten; Schrezenmeier, Hubert; Klueter, Harald; Pfister, Frederick; Amann, Kerstin Ute; Weiss, Sabrina; Krueger, Detlev H.; Zimmermann, Robert; et al. (Microorganisms, 2023)
Puumala hantavirus (PUUV) infections usually show a mild or moderate clinical course, but may sometimes also lead to life-threatening disease. Here, we report on a 60-year-old female patient with common variable immunodeficiency (CVID) who developed a fatal PUUV infection with persistent renal failure, thrombocytopenia, and CNS infection with impaired consciousness and tetraparesis. Hantavirus-specific antibodies could not be detected due to the humoral immunodeficiency. Diagnosis and virological monitoring were based on the quantitative detection of PUUV RNA in blood, cerebrospinal fluid, bronchial lavage, and urine, where viral RNA was found over an unusually extended period of one month. Due to clinical deterioration and virus persistence, treatment with ribavirin was initiated. Additionally, fresh frozen plasma (FFP) from convalescent donors with a history of PUUV infection was administered. Despite viral clearance, the clinical condition of the patient did not improve and the patient died on day 81 of hospitalization. This case underlines the importance of the humoral immune response for the course of PUUV disease and illustrates the need for PCR-based virus diagnostics in those patients. Due to its potential antiviral activity, convalescent plasma should be considered in the therapy of severe hantavirus diseases.
CRIS-Team Scopus Importer:2023-03-10
Keywords: common variable immunodeficiency; convalescent plasma; encephalitis; Puumala hantavirus; ribavirin

Fibronectin is up-regulated in podocytes by mechanical stress - Kliewe, Felix; Kaling, Sören; Lötzsch, Henriette; Artelt, Nadine; Schindler, Maximilian; Rogge, Henrik; Schröder, Sindy; Scharf, Christian; Amann, Kerstin Ute; Daniel, Christoph; Lindenmeyer, Maja T.; Cohen, Clemens D.; et al. (The FASEB Journal, 2019)
Hypertension is one of the central causes of kidney damage. In the past it was shown that glomerular hypertension leads to morphologic changes of podocytes and effacement and is responsible for detachment of these postmitotic cells. Because we have shown that podocytes are mechanosensitive and respond to mechanical stress by reorganization of the actin cytoskeleton in vitro, we look for mechanotransducers in podocytes. In this study, we demonstrate that the extracellular matrix protein fibronectin (Fn1) might be a potential candidate. The present study shows that Fn1 is essential for the attachment of podocytes during mechanical stress. By real-time quantitative PCR as well as by liquid chromatography-mass spectrometry, we found a significant up-regulation of Fn1 caused by mechanical stretch (3 d, 0.5 Hz, and 5% extension). To study the role of Fn1 in cultured podocytes under mechanical stress, Fn1 was knocked down (Fn1 KD) by a specific small interfering RNA. Additionally, we established a Fn1 knockout (KO) podocyte cell line (Fn1 KO) by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9). During mechanical stress, a significant loss of podocytes (>80%) was observed in Fn1 KD as well as Fn1 KO podocytes compared with control cells. Furthermore, Fn1 KO podocytes showed a significant down-regulation of the focal adhesion proteins talin, vinculin, and paxillin and a reduced cell spreading, indicating an important role of Fn1 in adhesion. Analyses of kidney sections from patients with diabetic nephropathy have shown a significant up-regulation of FN1 in contrast to control biopsies. In summary, we show that Fn1 plays an important role in the adaptation of podocytes to mechanical stress.-Kliewe, F., Kaling, S., Lötzsch, H., Artelt, N., Schindler, M., Rogge, H., Schröder, S., Scharf, C., Amann, K., Daniel, C., Lindenmeyer, M. T., Cohen, C. D., Endlich, K., Endlich, N. Fibronectin is up-regulated in podocytes by mechanical stress.
EVALuna2:204845
Keywords: Fn1; extracellular matrix; hypertension; mechanical load; diabetic nephropathy

First report from the German COVID-19 autopsy registry - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; Knüchel, Ruth; et al. (The Lancet Regional Health - Europe, 2022)
Background: Autopsies are an important tool in medicine, dissecting disease pathophysiology and causes of death. In COVID-19, autopsies revealed e.g., the effects on pulmonary (micro)vasculature or the nervous system, systemic viral spread, or the interplay with the immune system. To facilitate multicentre autopsy-based studies and provide a central hub supporting autopsy centres, researchers, and data analyses and reporting, in April 2020 the German COVID-19 Autopsy Registry (DeRegCOVID) was launched. Methods: The electronic registry uses a web-based electronic case report form. Participation is voluntary and biomaterial remains at the respective site (decentralized biobanking). As of October 2021, the registry included N=1129 autopsy cases, with 69271 single data points including information on 18674 available biospecimens gathered from 29 German sites. Findings: In the N=1095 eligible records, the male-to-female ratio was 1·8:1, with peaks at 65-69 and 80-84 years in males and >85 years in females. The analysis of the chain of events directly leading to death revealed COVID-19 as the underlying cause of death in 86% of the autopsy cases, whereas in 14% COVID-19 was a concomitant disease. The most common immediate cause of death was diffuse alveolar damage, followed by multi-organ failure. The registry supports several scientific projects, public outreach and provides reports to the federal health authorities, leading to legislative adaptation of the German Infection Protection Act, facilitating the performance of autopsies during pandemics. Interpretation: A national autopsy registry can provide multicentre quantitative information on COVID-19 deaths on a national level, supporting medical research, political decision-making and public discussion. Funding: German Federal Ministries of Education and Research and Health. Hintergrund: Obduktionen sind ein wichtiges Instrument in der Medizin, um die Pathophysiologie von Krankheiten und Todesursachen zu untersuchen. Im Rahmen von COVID-19 wurden durch Obduktionen z.B. die Auswirkungen auf die pulmonale Mikrovaskulatur, das Nervensystem, die systemische Virusausbreitung, und das Zusammenspiel mit dem Immunsystem untersucht. Um multizentrische, auf Obduktionen basierende Studien zu erleichtern und eine zentrale Anlaufstelle zu schaffen, die Obduktionszentren, Forscher sowie Datenanalysen und -berichte unterstützt, wurde im April 2020 das deutsche COVID-19-Autopsieregister (DeRegCOVID) ins Leben gerufen. Methoden: Das elektronische Register verwendet ein webbasiertes elektronisches Fallberichtsformular. Die Teilnahme ist freiwillig und das Biomaterial verbleibt am jeweiligen Standort (dezentrales Biobanking). Im Oktober 2021 umfasste das Register N=1129 Obduktionsfälle mit 69271 einzelnen Datenpunkten, die Informationen über 18674 verfügbare Bioproben enthielten, die von 29 deutschen Standorten gesammelt wurden. Ergebnisse: In den N=1095 ausgewerteten Datensätzen betrug das Verhältnis von Männern zu Frauen 1,8:1 mit Spitzenwerten bei 65-69 und 80-84 Jahren bei Männern und >85 Jahren bei Frauen. Die Analyse der Sequenz der unmittelbar zum Tod führenden Ereignisse ergab, dass in 86 % der Obduktionsfälle COVID-19 die zugrunde liegende Todesursache war, während in 14 % der Fälle COVID-19 eine Begleiterkrankung war. Die häufigste unmittelbare Todesursache war der diffuse Alveolarschaden, gefolgt von Multiorganversagen. Das Register unterstützt mehrere wissenschaftliche Projekte, die Öffentlichkeitsarbeit und liefert Berichte an die Bundesgesundheitsbehörden, was zu einer Anpassung des deutschen Infektionsschutzgesetzes führte und die Durchführung von Obduktionen in Pandemien erleichtert. Interpretation: Ein nationales Obduktionsregister kann multizentrische quantitative Informationen über COVID-19-Todesfälle auf nationaler Ebene liefern und damit die medizinische Forschung, die politische Entscheidungsfindung und die öffentliche Diskussion unterstützen. Finanzierung: Bundesministerien für Bildung und Forschung und für Gesundheit.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Autopsy; Cause of Death; COVID-19; Registry; SARS-CoV-2

First Treatment of Relapsing Rapidly Progressive IgA Nephropathy With Eculizumab After Living Kidney Donation: A Case Report - Herzog, A. L.; Wanner, C.; Amann, Kerstin Ute; Lopau, K. (Transplantation Proceedings, 2017)
IgA nephropathy (IGAN) rarely can present as a crescent and progressive form leading to end-stage renal disease (ESRD) in a short period of time. Recurrence of IGAN after kidney transplantation is frequent, and complement components such as C3, C4d, and C5 seem to be involved. We present a case of a young male patient with ESRD caused by rapidly progressive IGAN and who demonstrated rapid recurrence of crescentic IGAN after kidney donation.In September 2014, a 28-year-old male patient was hospitalized due to IGAN with 60% of crescents. Cyclophosphamide, steroids, and plasmapheresis did not prevent ESRD. After 8 months of peritoneal dialysis, the patient received a blood group-compatible living donor kidney from his 57-year-old mother. Immunosuppression consisted of tacrolimus, mycophenolic acid, and steroids without induction therapy. Acute graft failure occurred 2 months later, and graft biopsy results revealed recurrence of crescentic IGAN. Cyclophosphamide was added to tacrolimus and steroid treatment, but graft function could not be restored despite viable kidney tissue in repeated biopsy specimens. Rescue therapy with 4 single doses of eculizumab was introduced while hemodialysis had already been initiated. After a cumulative dose of 1800 mg of eculizumab, kidney function did not recover.In this case, eculizumab was not effective in treating IGAN recurrence after transplantation. Therapy was started late when hemodialysis had already been initiated; an earlier start of therapy might be more effective.
EVALuna2:25549

Four subunits (αβγδ) of the epithelial sodium channel (ENaC) are expressed in the human eye in various locations - Krüger, Bettina; Schlötzer-Schrehardt, Ursula; Härteis, Silke; Zenkel, Matthias; Chankiewitz, Verena E.; Amann, Kerstin Ute; Kruse, Friedrich; Korbmacher, Christoph (Investigative Ophthalmology & Visual Science, 2012)
The epithelial sodium channel (ENaC) is typically expressed in sodium-absorbing epithelia. Several reports suggest that ENaC is also expressed in ocular tissues and may play a role in aqueous humor secretion and glaucoma. However, the precise localization of ENaC in the human eye is still unclear. Here, the authors studied ENaC expression in 12 normal human donor eyes and in six eyes of patients with glaucoma.Quantitative real-time PCR was used to investigate the expression of ?-, ?-, ?-, and ?-ENaC transcripts in ocular tissues. In addition, the authors performed immunohistochemical studies using recently generated antibodies against human ?- and ?-ENaC.At the mRNA level, all four ENaC subunits were found to be expressed in a wide range of ocular tissues from normal and glaucomatous human eyes, with the cornea, ciliary body, iris, and retina showing the highest expression levels. At the protein level, ?- and ?-ENaC subunits showed distinct distribution patterns and could be immunolocalized primarily to the cell membranes of epithelial cells of the cornea and to the conjunctiva, iris, ciliary body, lens, and retinal pigment epithelium but also to vascular endothelial cells, smooth muscle cells, stromal cells, and retinal neurons. The authors found no altered mRNA level of any subunit in glaucomatous eyes.All four ENaC subunits (????) are expressed in the normal human eye, with distinct localization of subunits possibly reflecting different functional states of the channel. The (patho-)physiological roles of ENaC in the various localizations in the eye remain to be determined.
EVALuna2:4482

Gastrointestinal involvement in granulomatosis with polyangiitis and microscopic polyangiitis: histological features and outcome - Latus, Joerg; Koetter, Ina; Fritz, Peter; Kimmel, Martin; Biegger, Dagmar; Ott, German; Stange, Eduard F.; Amann, Kerstin Ute; Alscher, Dominik M.; Braun, Niko (International Journal of Rheumatic Diseases, 2014)
Gastrointestinal (GI) involvement in patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) is rare.Medical charts of seven patients with GPA and MPA and GI involvement were reviewed regarding clinical presentation, outcome, diagnostic tools and therapy. Second, the cellular composition of the inflammatory infiltrate associated with the vascular lesions in histological samples (ileum, colon, rectum, duodenum) were investigated to identify possible treatment targets. Immunohistochemistry was done with antibodies against CD20, CD3 and CD34. Samples from a healthy control group (n = 15) were used for comparison.Mean age at onset of the first symptoms of vasculitis was 48 ± 21.3 years. At time of diagnosis GI symptoms were present in five out of seven patients (71%) and occurred during relapse of the vasculitis in two patients (29%). All patients had abdominal pain, four of seven (57%) had an acute kidney injury and three patients required renal replacement therapy. At the time of diagnosis five of seven patients (71%) required surgery and mean Birmingham Vasculitis Activity Score (BVAS) on admission was high (26.3 ± 7.7). Regarding outcome, one patient died due to gastrointestinal bleeding. Histological analysis showed significantly higher expression of CD3 in this patient compared to the control group (P = 0.02). Analysis of expression of CD20 and CD34 showed no statistically significant differences between patients with GPA and MPA with GI involvement compared to the control group.GI involvement in GPA and MPA is rare. Therapy directed at T cells might be an alternative treatment option.
EVALuna2:25467

Gene variants of unknown significance in Fabry disease: Clinical characteristics of c.376A>G (p.Ser126Gly) - Lau, Kolja; Ueceyler, Nurcan; Cairns, Tereza; Lorenz, Lora; Sommer, Claudia; Schindehuette, Magnus; Amann, Kerstin Ute; Wanner, Christoph; Nordbeck, Peter (Molecular Genetics and Genomic Medicine, 2022)
Background: Anderson-Fabry disease (FD) is an X-linked lysosomal storage disorder with varying organ involvement and symptoms, depending on the underlying mutation in the alpha-galactosidase A gene (HGNC: GLA). With genetic testing becoming more readily available, it is crucial to precisely evaluate pathogenicity of each genetic variant, in order to determine whether there is or might be not a need for FD-specific therapy in affected patients and relatives at the time point of presentation or in the future.
CRIS-Team WoS Importer:2022-03-11

Geochemical Characteristics of Groundwater Consumed by Patients with Chronic Kidney Disease with Unknown Aetiology in the Crystalline Dry Zone Terrain of Sri Lanka - Chandrajith, Rohana; Nanayakkara, Nishantha; Zwiener, Christian; Daniel, Christoph; Amann, Kerstin Ute; Barth, Johannes (Exposure and Health, 2023)
Quality of drinking water has become a significant concern with chronic kidney disease of uncertain aetiology (CKDu), particularly in the dry zone regions of Sri Lanka. In this study, groundwaters consumed by biopsy-proven CKDu patients were assessed for identifying possible hydrogeochemical risk factors because histopathological observations are still considered the best method for identifying CKDu cases. Major anions, cations, and 22 trace elements in groundwater were measured in addition to dissolved organic carbon (DOC) and its isotope ratios (expressed as δ13CDOC). Variations of groundwater quality were monitored monthly in five selected wells. The data were compared with a non-endemic region with a similar climatic and socio-economic background. Groundwater used by CKDu cases is predominantly of the Ca–Mg–HCO3 type. Over 88% of the samples showed excess hardness, while 44% showed high fluoride (F−) contents (> 0.60 mg/L). These two parameters are noticeably different compared to groundwater from non-endemic regions with similar geoenvironmental backgrounds. The dissolved organic carbon (DOC) content varied from 0.06 to 0.30 mmol/L with a mean value of 0.15 mmol/L in CKDu wells. In most cases, known nephrotoxic trace elements such as As, Pb, Cd, and U were found to be lower than 0.01 µg/L. Seasonally, F− and Si4+ (as H4SiO4) content fluctuated, even though monsoon rain inputs did not seem to alter the geochemical composition. Principal component analysis (PCA) indicated that the dissolution of aquifer minerals and ion exchange processes are most likely responsible for the groundwater geochemistry in the study terrain. This study highlights the importance of F−, hardness (Ca2+ + Mg2+), and Si4+ in groundwaters of CKDu-related tropical terrains. The synergetic impact of these parameters needs further systematic studies, ideally combined with animal models, to unravel the aetiological mechanisms of CKDu.
CRIS-Team Scopus Importer:2023-04-14
Keywords: CKDu; Dissolved organic carbon; Environmental-nephrotoxin; Fluoride; Silica; Water hardness; Water isotopes

Glomerular Endothelial Cell-Derived microRNA-192 Regulates Nephronectin Expression in Idiopathic Membranous Glomerulonephritis. - Müller-Deile, Janina; Sopel, Nina; Ohs, Alexandra; Rose, Victoria; Gröner, Marwin; Wrede, Christoph; Hegermann, Jan; Daniel, Christoph; Amann, Kerstin Ute; Zahner, Gunther; Schiffer, Mario (Journal of the American Society of Nephrology, 2021)
BACKGROUND: Autoantibodies binding to podocyte antigens cause idiopathic membranous glomerulonephritis (iMGN). However, it remains elusive how autoantibodies reach the subepithelial space because the glomerular filtration barrier (GFB) is size selective and almost impermeable for antibodies. METHODS: Kidney biopsies from patients with iMGN, cell culture, zebrafish, and mouse models were used to investigate the role of nephronectin (NPNT) regulating microRNAs (miRs) for the GFB. RESULTS: Glomerular endothelial cell (GEC)-derived miR-192-5p and podocyte-derived miR-378a-3p are upregulated in urine and glomeruli of patients with iMGN, whereas glomerular NPNT is reduced. Overexpression of miR-192-5p and morpholino-mediated npnt knockdown induced edema, proteinuria, and podocyte effacement similar to podocyte-derived miR-378a-3p in zebrafish. Structural changes of the glomerular basement membrane (GBM) with increased lucidity, splitting, and lamellation, especially of the lamina rara interna, similar to ultrastructural findings seen in advanced stages of iMGN, were found. IgG-size nanoparticles accumulated in lucidity areas of the lamina rara interna and lamina densa of the GBM in npnt-knockdown zebrafish models. Loss of slit diaphragm proteins and severe structural impairment of the GBM were further confirmed in podocyte-specific Npnt knockout mice. GECs downregulate podocyte NPNT by transfer of miR-192-5p-containing exosomes in a paracrine manner. CONCLUSIONS: Podocyte NPNT is important for proper glomerular filter function and GBM structure and is regulated by GEC-derived miR-192-5p and podocyte-derived miR-378a-3p. We hypothesize that loss of NPNT in the GBM is an important part of the initial pathophysiology of iMGN and enables autoantigenicity of podocyte antigens and subepithelial immune complex deposition in iMGN.
EVALuna2:483425

GOLD, SILVER, AND BRONZE WITH HIS FATHERS KIDNEY: A LIVING-DONOR KIDNEY TRANSPLANT IN A FAMILY WITH AUTOSOMAL ALPORT SYNDROME - Petzold, Friederike; Bachmann, Anette; Amann, Kerstin Ute; Lindner, Tom H.; Helmchen, Udo; Bergmann, Carsten; Halbritter, Jan (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-11-26

G Protein-coupled Estrogen Receptor Protects from Atherosclerosis - Meyer, Matthias R.; Fredette, Natalie C.; Howard, Tamara A.; Hu, Chelin; Ramesh, Chinnasamy; Daniel, Christoph; Amann, Kerstin Ute; Arterburn, Jeffrey B.; Barton, Matthias; Prossnitz, Eric R. (Scientific Reports, 2014)
Coronary atherosclerosis and myocardial infarction in postmenopausal women have been linked to inflammation and reduced nitric oxide (NO) formation. Natural estrogen exerts protective effects on both processes, yet also displays uterotrophic activity. Here, we used genetic and pharmacologic approaches to investigate the role of the G protein-coupled estrogen receptor (GPER) in atherosclerosis. In ovary-intact mice, deletion of gper increased atherosclerosis progression, total and LDL cholesterol levels and inflammation while reducing vascular NO bioactivity, effects that were in some cases aggravated by surgical menopause. In human endothelial cells, GPER was expressed on intracellular membranes and mediated eNOS activation and NO formation, partially accounting for estrogen-mediated effects. Chronic treatment with G-1, a synthetic, highly selective small molecule agonist of GPER, reduced postmenopausal atherosclerosis and inflammation without uterotrophic effects. In summary, this study reveals an atheroprotective function of GPER and introduces selective GPER activation as a novel therapeutic approach to inhibit postmenopausal atherosclerosis and inflammation in the absence of uterotrophic activity.
EVALuna2:25485

Grundlagen der Nierenpathologie für Pathologen – Teil 2, Nichtentzündliche Veränderungen - Gaspert, Ariana; Büttner-Herold, Maike; Amann, Kerstin Ute (Die Pathologie, 2023)
The evaluation of kidney biopsies for specific renal diseases or kidney transplant biopsies is mainly restricted to specialized centers. Lesions in nonneoplastic renal tissue in partial nephrectomies or nephrectomies due to renal tumors, especially noninflammatory, ischemic, vascular changes or diabetic nephropathy can be of greater prognostic significance than the tumor itself in patients with a localized tumor and good tumor-associated survival. In this part of basic nephropathology for pathologists, the most common noninflammatory lesions of the vascular, glomerular and tubulo-interstitial compartment are discussed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Diabetic nephropathy; Differential diagnosis; Hypertension; Nephropathy; Thrombotic microangiopathy

Guanylate-binding protein 1 expression from embryonal endothelial progenitor cells reduces blood vessel density and cellular apoptosis in an axially vascularised tissue-engineered construct - Bleiziffer, Oliver; Hammon, Matthias; Arkudas, Andreas; Taeger, Christian; Beier, Justus; Amann, Kerstin Ute; Naschberger, Elisabeth; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (BMC Biotechnology, 2012)
Background: Guanylate binding protein-1 (GBP-1) is a large GTPase which is actively secreted by endothelial cells. It is a marker and intracellular inhibitor of endothelial cell proliferation, migration, and invasion. We previously demonstrated that stable expression of GBP-1 in murine endothelial progenitor cells (EPC) induces their premature differentiation and decreases their migration capacity in vitro and in vivo. The goal of the present study was to assess the antiangiogenic capacity of EPC expressing GBP-1 (GBP-1-EPC) and their impact on blood vessel formation in an axially vascularized 3-D bioartificial construct in vivo.Results: Functional in vitro testing demonstrated a significant increase in VEGF secretion by GBP-1-EPC after induction of cell differentiation. Undifferentiated GBP-1-EPC, however, did not secrete increased levels of VEGF compared to undifferentiated control EPC expressing an empty vector (EV-EPC). In our In vivo experiments, we generated axially vascularized tissue-engineered 3-D constructs. The new vascular network arises from an arterio-venous loop (AVL) embedded in a fibrin matrix inside a separation chamber. Total surface area of the construct as calculated from cross sections was larger after transplantation of GBP-1-EPC compared to control EV-EPC. This indicated reduced formation of fibrovascular tissue and less resorption of fibrin matrix compared to constructs containing EV-EPC. Most notably, the ratio of blood vessel surface area over total construct surface area in construct cross sections was significantly reduced in the presence of GBP-1-EPC. This indicates a significant reduction of blood vessel density and thereby inhibition of blood vessel formation from the AVL constructs caused by GBP-1. In addition, GBP-1 expressed from EPC significantly reduced cell apoptosis compared to GBP-1-negative controls.Conclusion: Transgenic EPC expressing the proinflammatory antiangiogenic GTPase GBP-1 can reduce blood vessel density and inhibit apoptosis in a developing bioartificial vascular network and may become a new powerful tool to manipulate angiogenetic processes in tissue engineering and other pathological conditions such as tumour angiogenesis. © 2012 Bleiziffer et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Endothelial progenitor cells; Guanylate-binding protein 1; In vivo tissue engineering

Hemophagocytic lymphohistiocytosis and thrombotic microangiopathy after parvovirus B19 infection and renal transplantation: a case report - Steffen, C. J.; Koch, N.; Eckardt, K. U.; Amann, Kerstin Ute; Seelow, E.; Schreiber, A. (BMC Nephrology, 2021)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening disease characterized by hyperactivation of the immune system that causes hypercytokinemia and potentially multi organ failure. HLH can occur in patients with underlying rheumatic or autoinflammatory disorders. Additionally, HLH can develop in patients during infections or malignancies without a known genetic predisposition. Case presentation: We herein report a patient, who presented with fever, both acute kidney and liver injury, anemia, thrombocytopenia and HSV stomatitis. HLH was diagnosed based on clinical criteria and qPCR revealed an acute parvovirus B19 infection as potential underlying infectious trigger. Treatment was started with both IVIG and dexamethasone. Subsequently, kidney biopsy demonstrated TMA. Conclusions: In rare cases both HLH and aHUS can occur simultaneously in a patient as a consequence of viral infections. Insights from this unusual case might help physicians understand this complex symptom constellation.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Atypical hemorrhagic uremic syndrome (aHUS); Case report; Hemophagocytic Lymphohistiocytosis (HLH); Parvovirus B19

Heterozygosity of mitogen-activated protein kinase organizer 1 ameliorates diabetic nephropathy and suppresses epithelial-to-mesenchymal transition-like changes in db/db mice - Loeffler, Ivonne; Liebisch, Marita; Daniel, Christoph; Amann, Kerstin Ute; Wolf, Gunter (Nephrology Dialysis Transplantation, 2017)
Progressive diabetic nephropathy (DN) is characterized by tubulointerstitial fibrosis that is caused by accumulation of extracellular matrix. Induced by several factors, matrix-producing myofibroblasts may to some extent originate from tubular cells by epithelial-to-mesenchymal transition (EMT). Although previous data document that activation of hypoxia-inducible factor (HIF) signalling can be renoprotective in acute kidney disease, this issue remains controversial in chronic kidney injury. Here, we studied whether DN and EMT-like changes are ameliorated in a mouse model of type 2 diabetes mellitus with increased stability and activity of the HIF.We used db/db mice that were crossed with transgenic mice expressing reduced levels of mitogen-activated protein kinase organizer 1 (MORG1), a scaffold protein interacting with prolyl hydroxylase domain 3 (PHD3), because of deletion of one MORG1 allele.We found significantly reduced nephropathy in diabetic MORG1 +/- heterozygous mice compared with the diabetic wild-types ( db/db XMORG1 +/+ ). Furthermore, we demonstrated that EMT-like changes in the tubulointerstitium of diabetic wild-type MORG1 +/+ mice are present, whereas diabetic mice with reduced expression of MORG1 showed significantly fewer EMT-like changes.These findings reveal that a deletion of one MORG1 allele inhibits the development of DN in db/db mice. The data suggest that the diminished interstitial fibrosis in these mice is a likely consequence of suppressed EMT-like changes.
EVALuna2:25538

HIF activation protects from acute kidney injury - Weidemann, Alexander; Bernhardt, Wanja M.; Klanke, Bernd; Daniel, Christoph; Buchholz, Björn; Campean, Valentina; Amann, Kerstin Ute; Warnecke, Christina; Wiesener, Michael Sean; Eckardt, Kai-Uwe; Willam, Carsten (Journal of the American Society of Nephrology, 2008)
The contribution of hypoxia to cisplatin-induced renal tubular injury is controversial. Because the hypoxia-inducible factor (HIF) pathway is a master regulator of adaptation to hypoxia, we measured the effects of cisplatin on HIF accumulation in vitro and in vivo, and tested whether hypoxic preconditioning is protective against cisplatin-induced injury. We found that cisplatin did not stabilize HIF-1 alpha protein in vitro or in vivo under normoxic conditions. However, hypoxic preconditioning of cisplatin-treated proximal tubular cells in culture reduced apoptosis in an HIF-1 alpha-dependent fashion and increased cell proliferation as measured by BrdU incorporation. In vivo, rats preconditioned with carbon monoxide before cisplatin administration had significantly better renal function than rats kept in normoxic conditions throughout. Moreover, the histomorphological extent of renal damage and tubular apoptosis was reduced by the preconditional treatment. Therefore, development of pharmacologic agents to induce renal HIF might provide a new approach to ameliorate cisplatin-induced nephrotoxicity.

High frequency of autoantibody-secreting cells and long-lived plasma cells within inflamed kidneys of NZB/W F1 lupus mice - Starke, Charlotte; Frey, Silke; Wellmann, Ute; Urbonaviciute, Vilma; Herrmann, Martin; Amann, Kerstin Ute; Schett, Georg; Winkler, Thomas; Voll, Reinhard E. (European Journal of Immunology, 2011)
Autoantibodies to double-stranded (ds) DNA represent a serological hallmark of systemic lupus erythematosus (SLE) and may critically contribute to the pathogenesis of lupus nephritis. Self-reactive antibodies might be partially produced by long-lived plasma cells (PCs), which mainly reside within the bone marrow and spleen. In contrast to short-lived PCs, long-lived PCs are extremely resistant to therapy and may sustain refractory disease courses. Recently, antibody-secreting cells were found within the inflamed kidneys of New Zealand black/white (NZB/W) F1 lupus mice as well as of patients with SLE. To analyze the longevity of the IgG-producing cells present in nephritic kidneys of NZB/W F1 mice we performed in vivo BrdU-labeling. We identified a higher frequency of long-lived than short-lived renal PCs, indicating that survival niches for long-lived PCs also exist within inflamed kidneys. Using ELISPOT assays, we found that on average 31% of renal IgG-producing cells reacted with dsDNA and 24% with nucleolin. Moreover, the frequencies of IgG-secreting cells specific for the autoantigens dsDNA and nucleolin were higher in the kidneys compared with those in the spleen and bone marrow.
Keywords: Autoantibody-secreting cells; Autoimmunity; Long-lived plasma cells; Lupus nephritis

High RIPK3 expression is associated with a higher risk of early kidney transplant failure - Wahida, Adam; Schmaderer, Christoph; Büttner-Herold, Maike; Branca, Caterina; Donakonda, Sainitin; Haberfellner, Flora; Torrez, Carlos; Schmitz, Jessica; Schulze, Tobias; Seibt, Tobias; Öllinger, Rupert; Engleitner, Thomas; et al. (iScience, 2023)
Renal ischemia-reperfusion injury (IRI) is associated with reduced allograft survival, and each additional hour of cold ischemia time increases the risk of graft failure and mortality following renal transplantation. Receptor-interacting protein kinase 3 (RIPK3) is a key effector of necroptosis, a regulated form of cell death. Here, we evaluate the first-in-human RIPK3 expression dataset following IRI in kidney transplantation. The primary analysis included 374 baseline biopsy samples obtained from renal allografts 10 minutes after onset of reperfusion. RIPK3 was primarily detected in proximal tubular cells and distal tubular cells, both of which are affected by IRI. Time-to-event analysis revealed that high RIPK3 expression is associated with a significantly higher risk of one-year transplant failure and prognostic for one-year (death-censored) transplant failure independent of donor and recipient associated risk factors in multivariable analyses. The RIPK3 score also correlated with deceased donation, cold ischemia time and the extent of tubular injury.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Molecular biology; Nephrology

High Sodium Diet - Role in Renal Sympathodepression - Rodionova, Kristina; Ditting, Tilmann; Fahrmeier, Franziska; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (FASEB JOURNAL, 2020)
CRIS-Team WoS Importer:2020-10-16

Histomorphology and pathogenesis of diabetic nephropathy Histomorphologie und Pathogenese der diabetischen Nephropathie - Amann, Kerstin Ute; Daniel, Christoph (Nephrologe, 2020)
Diabetes mellitus and organ involvement or associated diseases are a medical problem worldwide with an ever increasing incidence and prevalence, not only in western countries. Diabetes mellitus must be taken seriously particularly because the incidence in children and young adults is increasing in a threatening way. It is estimated that in the USA by 2025 every third individual born in 2000 will suffer from diabetes, which in the long term will drastically reduce the life expectation of the population. In addition to cardiovascular diseases, such as high blood pressure, coronary heart disease and stroke, the renal involvement in diabetes mellitus, the so-called diabetic nephropathy (DN) in particular represents an increasing and serious problem. In Germany DN now represents with approximately 35% the leading single course by far of end-stage renal disease. This article deals with the pathogenesis and morphology of DN with a special emphasis on new treatment principles.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Diabetes mellitus; DPP‑4; Kidney; Pathogenesis; SGLT1

Hypoxia inducible factor stabilization improves defective ischemia-induced angiogenesis in a rodent model of chronic kidney disease - Schellinger, Isabel Nahal; Cordasic, Nada; Panesar, Julian; Buchholz, Björn; Jacobi, Johannes; Hartner, Andrea; Klanke, Bernd; Jakubiczka-Smorag, Joanna; Burzlaff, Nicolai; Heinze, Eva; Warnecke, Christina; Raaz, Uwe; et al. (Kidney International, 2017)
Chronic kidney disease (CKD) is associated with increased risk and worse prognosis of cardiovascular disease, including peripheral artery disease. An impaired angiogenic response to ischemia may contribute to poor outcomes of peripheral artery disease in patients with CKD. Hypoxia inducible factors (HIF) are master regulators of angiogenesis and therefore represent a promising target for therapeutic intervention. To test this we induced hind-limb ischemia in rats with CKD caused by 5/6 nephrectomy and administered two different treatments known to stabilize HIF protein in vivo: carbon monoxide and a pharmacological inhibitor of prolyl hydroxylation 2-(1-chloro-4- hydroxyisoquinoline-3-carboxamido) acetate (ICA). Expression levels of pro-angiogenic HIF target genes (Vegf, Vegf-r1, Vegf-r2, Ho-1) were measured by qRT-PCR. Capillary density was measured by CD31 immunofluorescence staining and HIF expression was evaluated by immunohistochemistry. Capillary density in ischemic skeletal muscle was significantly lower in CKD animals compared to sham controls. Rats with CKD showed significantly lower expression of HIF and all measured pro-angiogenic HIF target genes, including VEGF. Both HIF stabilizing treatments rescued HIF target gene expression in animals with CKD and led to significantly higher ischemia-induced capillary sprouting compared to untreated controls. ICA was effective regardless of whether it was administered before or after induction of ischemia and led to a HIF expression in skeletal muscle. Thus, impaired ischemia-induced angiogenesis in rats with CKD can be improved by HIF stabilization, even if started after onset of ischemia.
EVALuna2:3925
Keywords: cardiovascular disease; chronic kidney disease; hypoxia

Hypoxia-inducible protein 2 is a novel lipid droplet protein and a specific target gene of hypoxia-inducible factor-1 - Gimm, Tina; Wiese, Melanie; Teschemacher, Barbara; Deggerich, Anke; Schödel, Johannes; Knaup, Karl; Hackenbeck, Thomas; Hellerbrand, Claus; Amann, Kerstin Ute; Wiesener, Michael; Höning, Stefan; Eckardt, Kai-Uwe; et al. (The FASEB Journal, 2010)
Hypoxia-inducible protein 2 (HIG2) has been implicated in canonical Wnt signaling, both as target and activator. The potential link between hypoxia and an oncogenic signaling pathway might play a pivotal role in renal clear-cell carcinoma characterized by constitutive activation of hypoxia-inducible factors (HIFs), and hence prompted us to analyze HIG2 regulation and function in detail. HIG2 was up-regulated by hypoxia and HIF inducers in all cell types and mouse organs investigated and abundantly expressed in renal clear-cell carcinomas. Promoter analyses, gel shifts, and siRNA studies revealed that HIG2 is a direct and specific target of HIF-1, but not responsive to HIF-2. Surprisingly, HIG2 was not secreted, and HIG2 overexpression neither stimulated proliferation nor activated Wnt signaling. Instead, we show that HIG2 decorates the hemimembrane of lipid droplets, whose number and size increase on hypoxic inhibition of fatty acid β-oxidation, and colocalizes with the lipid droplet proteins adipophilin and TIP47. Normoxic overexpression of HIG2 was sufficient to increase neutral lipid deposition in HeLa cells and stimulated cytokine expression. HIG2 could be detected in atherosclerotic arteries and fatty liver disease, suggesting that this ubiquitously inducible HIF-1 target gene may play an important functional role in diseases associated with pathological lipid accumulation. © FASEB.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Gene expression; Lipid metabolism; Promoter; Renal clear-cell carcinoma

Hypoxia-inducible transcription factors stabilization in the thick ascending limb protects against ischemic acute kidney injury - Schley, Gunnar; Klanke, Bernd; Schödel, Johannes; Forstreuter, Frauke; Shukla, Deepa; Kurtz, Armin; Amann, Kerstin Ute; Wiesener, Michael; Rosen, Seymour; Eckardt, Kai-Uwe; Maxwell, Patrick H.; Willam, Carsten (Journal of the American Society of Nephrology, 2011)
Hypoxia-inducible transcription factors (HIF) protect cells against oxygen deprivation, and HIF stabilization before ischemia mitigates tissue injury. Because ischemic acute kidney injury (AKI) often involves the thick ascending limb (TAL), modulation of HIF in this segment may be protective. Here, we generated mice with targeted TAL deletion of the von Hippel-Lindau protein (Vhl), which mediates HIF degradation under normoxia, using Tamm-Horsfall protein (Thp)-driven Cre expression. These mice showed strong expression of HIF-1α in TALs but no changes in kidney morphology or function under control conditions. Deficiency of Vhl in the TAL markedly attenuated proximal tubular injury and preserved TAL function following ischemia-reperfusion, which may be partially a result of enhanced expression of glycolytic enzymes and lactate metabolism. These results highlight the importance of the thick ascending limb in the pathogenesis of AKI and suggest that pharmacologically targeting the HIF system may have potential to prevent and mitigate AKI. Copyright © 2011 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2024-05-13

Hypoxia regulates the sperm associated antigen 4 (SPAG4) via HIF, which is expressed in renal clear cell carcinoma and promotes migration and invasion in vitro - Knaup, Karl; Monti, Juliana; Hackenbeck, Thomas; Jobst-Schwan, Tilman; Klanke, Bernd; Schietke, Ruth Elisabeth; Wacker, Ingrid; Behrens, Jürgen; Amann, Kerstin Ute; Eckardt, Kai-Uwe; Warnecke, Christina; Wiesener, Michael (Molecular Carcinogenesis, 2014)
Hypoxia leads to the upregulation of a variety of genes mediated largely via the hypoxia inducible transcription factor (HIF). Prominent HIF-regulated target genes such as the vascular endothelial growth factor (VEGF), the glucose transporter 1 (Glut-1), or erythropoietin (EPO) help to assure survival of cells and organisms in a low oxygenated environment. Here, we are the first to report the hypoxic regulation of the sperm associated antigen 4 (SPAG4). SPAG4 is a member of the cancer testis (CT) gene family and to date little is known about its physiological function or its involvement in tumor biology. A number of CT family candidate genes are therefore currently being investigated as potential cancer markers, due to their predominant testicular expression pattern. We analyzed RNA and protein expression by RNAse protection assay, immunoflurescent as well as immunohistological stainings. To evaluate the influence of SPAG4 on migration and invasion capabilities, siRNA knockdown as well as transient overexpression was performed prior to scratch or invasion assay analysis. The hypoxic regulation of SPAG4 is clearly mediated in a HIF-1 and VHL dependent manner. We furthermore show upregulation of SPAG4 expression in human renal clear cell carcinoma (RCC) and co-localization within the nucleolus in physiological human testis tissue. SPAG4 knockdown reduces the invasion capability of RCC cells in vitro and overexpression leads to enhancement of tumor cell migration. Together, SPAG4 could possibly play a role in the invasion capability and growth of renal tumors and could represent an interesting target for clinical intervention. © 2013 Wiley Periodicals, In
EVALuna2:3620

Idiopathic granulomatous interstitial nephritis and isolated renal sarcoidosis: Two diagnoses of exclusion - Janssen, Ulf; Naderi, Shirin; Amann, Kerstin Ute (SAGE Open Medicine, 2021)
Granulomatous interstitial nephritis is a rare finding in renal biopsy caused by drugs, infections, and inflammatory or autoimmune diseases. Idiopathic cases account for 18% of granulomatous interstitial nephritis in native kidneys. Sarcoidosis and drugs are the most common causes of granulomatous interstitial nephritis in Western countries, while in India tuberculosis prevails. Few cases of renal sarcoidosis without extrarenal involvement, that is, isolated renal sarcoidosis, have been reported. The diagnostic criteria of isolated renal sarcoidosis remain, however, unclear. Extrarenal sarcoidosis and other etiologies of granulomatous interstitial nephritis, in particular drug-related, have to be excluded. Some of these patients may develop extrarenal manifestations during follow-up. Changes in calcium and vitamin D metabolism are frequently observed in renal sarcoidosis and support its diagnosis. While non-necrotizing granulomas are a feature of sarcoidosis and drug-induced granulomatous interstitial nephritis, they also prevail in tuberculosis-associated granulomatous interstitial nephritis. Granulomatous interstitial nephritis caused by sarcoidosis and drugs usually responds to steroid therapy. A poor response to steroids may indicate an infectious etiology such as tuberculosis and should lead to a review of the initial diagnosis. This article gives an overview of the various etiologies of granulomatous interstitial nephritis, their frequency and histopathological characteristics, as well as potential biomarkers associated with renal sarcoidosis.
CRIS-Team WoS Importer:2021-09-17

Imaging mass spectrometry analysis of renal amyloidosis biopsies reveals protein co-localization with amyloid deposits - Casadonte, Rita; Kriegsmann, Mark; Deininger, Soeren-Oliver; Amann, Kerstin Ute; Paape, Rainer; Belau, Eckhard; Suckau, Detlev; Fuchser, Jens; Beckmann, Janine; Becker, Michael; Kriegsmann, Joerg (Analytical and Bioanalytical Chemistry, 2015)
Amyloidosis is a heterogeneous group of protein misfolding diseases characterized by deposition of amyloid proteins. The kidney is frequently affected, especially by immunoglobulin light chain (AL) and serum amyloid A (SAA) amyloidosis as the most common subgroups. Current diagnosis relies on histopathological examination, Congo red staining, or electron microscopy. Subtyping is done by immunohistochemistry; however, commercially available antibodies lack specificity. The purpose of this study was to identify and map amyloid proteins in formalin-fixed paraffin-embedded tissue sections using matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI IMS) coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis in an integrated workflow. Renal amyloidosis and non-amyloidosis biopsies were processed for histological and MS analysis. Mass spectra corresponding to the congophilic areas were directly linked to the histological and MS images for correlation studies. Peptides for SAA and AL were detected by MALDI IMS associated to Congo red-positive areas. Sequence determination of amyloid peptides by LC-MS/MS analysis provided protein distribution and identification. Serum amyloid P component, apolipoprotein E, and vitronectin proteins were identified in both AA and AL amyloidosis, showing a strong correlation with Congo red-positive regions. Our findings highlight the utility of MALDI IMS as a new method to type amyloidosis in histopathological routine material and characterize amyloid-associated proteins that may provide insights into the pathogenetic process of amyloid formation.
EVALuna2:25521

Immune monitoring facilitates the clinical decision in multifocal COVID-19 of a pancreas-kidney transplant patient - Babel, Nina; Anft, Moritz; Blazquez-Navarro, Arturo; Doevelaar, Adrian A.N.; Seibert, Felix S.; Bauer, Frederic; Rohn, Benjamin J.; Hoelzer, Bodo; Thieme, Constantin J.; Roch, Toralf; Meister, Toni L.; Pfaender, Stephanie; et al. (American Journal of Transplantation, 2020)
The optimal management in transplant recipients with coronavirus disease 2019 (COVID-19) remains uncertain. The main concern is the ability of immunosuppressed patients to generate sufficient immunity for antiviral protection. Here, we report on immune monitoring facilitating a successful outcome of severe severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-associated pneumonia, meningoencephalitis, gastroenteritis, and acute kidney and pancreas graft failure in a pancreas-kidney transplant recipient. Despite the very low numbers of circulating B, NK, and T cells identified in follow-up, a strong SARS-CoV-2 reactive T cell response was observed. Importantly, we detected T cells reactive to Spike, Membrane, and Nucleocapsid proteins of SARS-CoV-2 with majority of T cells showing polyfunctional proinflammatory Th1 phenotype at all analyzed time points. Antibodies against Spike protein were also detected with increasing titers in follow-up. Neutralization tests confirmed their antiviral protection. A correlation between cellular and humoral immunity was observed underscoring the specificity of demonstrated data. We conclude that analyzing the kinetics of nonspecific and SARS-CoV-2-reactive cellular and humoral immunity can facilitate the clinical decision on immunosuppression adjustment and allow successful outcome as demonstrated in the current clinical case. Although the antiviral protection of the detected SARS-CoV-2-reactive T cells requires further evaluation, our data prove an ability mounting a strong SARS-CoV-2-reactive T cell response with functional capacity in immunosuppressed patients.
CRIS-Team Scopus Importer:2020-09-18

(Immuno‑)Pathology of drug side effects in the kidney - Pfister, F.; Büttner-Herold, Maike; Amann, Kerstin Ute (Pathologe, 2018)
Nephrotoxicity or renal side effects of drugs are frequent and may vary in their clinical presentation. Various types of acute and chronic kidney disease are known to develop as a consequence or side effect of a long list of drugs with nephrotoxicity most commonly being associated with injury in the tubulointerstitial compartment. In addition, drug-induced glomerular and vascular disease have also been reported, either as the result of direct cellular injury or immune-mediated injury to glomerular or endothelial cells. From a clinical point of view it is important to recognize such drug-induced nephropathies early in order to prevent or adequately treat them to favour kidney recovery and to avoid long-lasting negative consequences for kidney function.This article will focus on the typical morphology and pathogenesis of some frequent drug-induced renal diseases.
EVALuna2:204840

Immunosuppression with cyclosporine versus tacrolimus shows distinctive nephrotoxicity profiles within renal compartments - Demirci, Hasan; Popovic, Suncica; Dittmayer, Carsten; Yilmaz, Duygu Elif; El-Shimy, Ismail Amr; Mülleder, Michael; Hinze, Christian; Su, Mingzhen; Mertins, Philipp; Kirchner, Marieluise; Osmanodja, Bilgin; Paliege, Alexander; et al. (Acta Physiologica, 2024)
Aim: Calcineurin inhibitors (CNIs) are the backbone for immunosuppression after solid organ transplantation. Although successful in preventing kidney transplant rejection, their nephrotoxic side effects contribute to allograft injury. Renal parenchymal lesions occur for cyclosporine A (CsA) as well as for the currently favored tacrolimus (Tac). We aimed to study whether chronic CsA and Tac exposures, before reaching irreversible nephrotoxic damage, affect renal compartments differentially and whether related pathogenic mechanisms can be identified. Methods: CsA and Tac were administered chronically in wild type Wistar rats using osmotic minipumps over 4 weeks. Functional parameters were controlled. Electron microscopy, confocal, and 3D-structured illumination microscopy were used for histopathology. Clinical translatability was tested in human renal biopsies. Standard biochemical, RNA-seq, and proteomic technologies were applied to identify implicated molecular pathways. Results: Both drugs caused significant albeit differential damage in vasculature and nephron. The glomerular filtration barrier was more affected by Tac than by CsA, showing prominent deteriorations in endothelium and podocytes along with impaired VEGF/VEGFR2 signaling and podocyte-specific gene expression. By contrast, proximal tubule epithelia were more severely affected by CsA than by Tac, revealing lysosomal dysfunction, enhanced apoptosis, impaired proteostasis and oxidative stress. Lesion characteristics were confirmed in human renal biopsies. Conclusion: We conclude that pathogenetic alterations in the renal compartments are specific for either treatment. Considering translation to the clinical setting, CNI choice should reflect individual risk factors for renal vasculature and tubular epithelia. As a step in this direction, we share protein signatures identified from multiomics with potential pathognomonic relevance.
CRIS-Team Scopus Importer:2024-06-28
Keywords: calcineurin inhibitor nephropathy; multiomics; pore endothelium; proximal tubule; unfolded protein response; VEGF

Impact of Consensus Definitions on Identification of Glomerular Lesions by Light and Electron Microscopy - Haas, Mark; Mirocha, James; Amann, Kerstin Ute; Bajema, Ingeborg M.; Barisoni, Laura; Becker, Jan Ulrich; Jennette, J. Charles; Joh, Kenuske; Ljubanovic, Danica Galesic; Roberts, Ian S.D.; Roelofs, Joris J.; Sethi, Sanjeev; et al. (Kidney International Reports, 2021)
Introduction: In 2020, a working group of 13 renal pathologists published consensus definitions for 47 individual glomerular lesions found on light microscopy (LM) and 47 glomerular lesions and 9 normal structures found on electron microscopy (EM). Methods: To test the impact of these definitions on identification of these lesions and structures, 2 surveys were circulated to all members of the Renal Pathology Society (RPS), each having 32 images (19 LM, 13 EM) and accompanying questions with 5 multiple-choice answers, one being the consensus choice of the working group. The first survey (survey 1 [S1]), answered by 297 RPS members, was sent in September 2020, before publication of the consensus definitions. The second (survey 2 [S2]), with images of the same lesions and structures (but not the same images) and the same questions and multiple choices in different order, was sent in April 2020, 5 months after the publication of the definitions. Results: S2 was taken by 181 RPS members; 64% also took S1 and 61% reported having read the definitions paper (def. paper). Mean agreement with the consensus answers increased modestly between the 2 surveys (65.2% vs. 72.0%, P = 0.097); the increase was greater and significant when only respondents to S2 who read the def. paper were considered (65.2% vs. 74.8%, P = 0.026). Furthermore, in S2 agreement with consensus answers was greater among respondents who read this paper versus those who did not (66.9% vs. 74.8%, P < 0.0001). Conclusions: Publication of the consensus definitions modestly improved interobserver agreement in identification of glomerular lesions.
CRIS-Team Scopus Importer:2021-11-26
Keywords: electron microscopy; glomerulonephritis; glomerulus; kidney biopsy; renal pathology

IMPACT OF DONOR HYPERTENSION AND HISTOLOGIC CHANGES IN LIVING DONOR KIDNEY TRANSPLANTATION: A SINGLE CENTER RETROSPECTIVE STUDY - Dienemann, Thomas; Schellenberg, J.; Heller, K.; Daniel, Christoph; Amann, Kerstin Ute; Weidemann, A. (2018)
EVALuna2:204841

Impact of phosphorus restriction and vitamin D-substitution on secondary hyperparathyroidism in a proteinuric mouse model - Bohnert, Bernhard N.; Daniel, Christoph; Amann, Kerstin Ute; Voelkl, Jakob; Alesutan, Ioana; Lang, Florian; Heyne, Nils; Haering, Hans-Ulrich; Artunc, Ferruh (Kidney & Blood Pressure Research, 2015)
Since the discovery of FGF23, secondary hyperparathyroidism (SHPT) in renal disease has been considered to result primarily from phosphorus retention rather than vitamin D deficiency. However, the impact of phosphorus restriction and vitamin D supplementation on SHPT is still ill defined.We investigated the development of SHPT in a doxorubicin-induced proteinuric mouse model and tested different treatment strategies including a low phosphorus diet and substitution with native or active vitamin D in 129 S1/SvImJ wild-type mice.Development of SHPT at day 30 was strongly related to the magnitude of induced proteinuria. In mice with a proteinuria <100 mg/mg creatinine, SHPT was mild (PTH increase 2.4-fold), and serum levels of FGF23, phosphate and urea remained almost stable, whereas mice with heavy proteinuria (>100 mg/mg creatinine) developed marked SHPT (PTH increase 10.1-fold) accompanied by massive increase in FGF23 (27.0-fold increase), hyperphosphatemia (1.8-fold increase), renal failure (7.3-fold urea increase) and depletion of both 25-OH vitamin D and 1,25-OH vitamin D. Substitution with native or active vitamin D was unable to suppress SHPT, whereas a low-phosphorus diet (Pi content 0.013%) completely suppressed SHPT in mice with both mild and heavy proteinuria.The development of SHPT resulted from phosphate retention in this proteinuric model and could completely be suppressed with a low-phosphorus diet.
EVALuna2:25491

IMPACT OF SAMPLING SIDE OF PERITONEAL BIOPSIES ON PERITONEAL THICKNESS AND HISTOPATHOLOGICAL DIAGNOSIS - A QUANTITATIVE HISTOLOGICAL STUDY IN BODY DONORS - Eden, Gabriele; Pfister, Frederick; Kielstein, Heike; Amann, Kerstin Ute; Kielstein, Jan T. (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-11-26

Impaired Neovascularization and Reduced Capillary Supply in the Malignant vs. Non-malignant Course of Experimental Renovascular Hypertension - Jagusch, Lisa Gudrun; Cordasic, Nada; Amann, Kerstin Ute; Veelken, Roland; Jacobi, Johannes; Hilgers, Karl Friedrich; Hartner, Andrea (Frontiers in Physiology, 2016)
Malignant hypertension develops in some cases of hypertension but not in others. We hypothesized that an impaired neovascularization and a reduced capillary supply characterizes the malignant course of experimental hypertension. Two-kidney, one-clip renovascular hypertension was induced in rats; controls (sham) were sham operated. To distinguish malignant hypertension from non-malignant hypertension, we considered two factors: weight loss, and the number of typical vascular lesions (onion skin lesions and fibrinoid necroses) per kidney section of the nonclipped kidney. Animals in the upper half for both criteria were defined as malignant hypertensives. After 5 weeks, mean arterial blood pressure was elevated to the same degree in malignant hypertension and non-malignant hypertension whereas plasma renin and aldosterone were significantly higher in malignant hypertensives. The expression of plasminogen activator inhibitor-1 was elevated (up to 14-fold) in non-malignant but significantly more increased (up to 36-fold) in malignant hypertensive rats, compared to sham. As a bioassay for neovascularization, the area of granulation tissue ingrowth in polyvinyl discs (implanted subcutaneously) was reduced in malignant hypertension compared to non-malignant hypertension and sham, while there was no difference between non-malignant hypertension and sham. The number of renal and left ventricular capillaries was significantly lower in malignant hypertension compared to non-malignant hypertension, as was the number of proliferating endothelial cells. We conclude that an impaired neovascularization and capillarization occurs in malignant renovascular hypertension but not in the non-malignant course of the disease despite comparable blood pressure levels. This might contribute to the unique vascular lesions and progressive target organ damage observed in malignant hypertension.
EVALuna2:3914

Increased malignancy of oral squamous cell carcinomas (oscc) is associated with macrophage polarization in regional lymph nodes - an immunohistochemical study - Wehrhan, Falk; Buettner-Herold, Maike; Hyckel, Peter; Moebius, Patrick; Preidl, Raimund; Distel, Luitpold; Ries, Jutta; Amann, Kerstin Ute; Schmitt, Christian; Neukam, Friedrich Wilhelm; Weber, Manuel (BMC Cancer, 2014)
It is largely accepted that specific immunological parameters in solid malignancies are associated with patient's prognosis. Recently a correlation of macrophage polarization with histomorphological parameters could also be shown in oral squamous cell carcinoma (oscc). The observed tumor derived peripheral immune tolerance could be associated with the macrophage polarization in regional tumor draining lymph nodes.So far there are no studies analyzing the macrophage polarization in cervical lymph nodes of oscc patients. In the present study we aimed to correlate macrophage polarization in different anatomical lymph node compartments of patients diagnosed with oscc with histopathologic parameters of the primary tumor (T-, N-, L-, V-, Pn-status, grading).Tumor free (n = 37) and metastatic (n = 17) lymph nodes of T1 and T2 oscc patients were processed for immunohistochemistry to detect CD68, CD11c, CD163 and MRC1 positive cells. Samples were digitized using whole slide imaging and the number of cells expressing the aforementioned markers in the region of interest quantitatively analyzed.The malignancy of the primary tumor (defined by T-, L-, Pn-status, grading) correlated with the lymph node macrophage polarization. L1 and Pn1 tumor cases displayed a significantly (p < 0.05) decreased M1 and increased M2 polarization in the sinus of the lymph nodes. G3 cases presented a significantly (p < 0.05) increased M2 polarization in the sinus compared to G2 cases. T2 tumors had significantly (p < 0.05) increased M2 polarization in the interfollicular zone of regional lymph nodes compared to T1 tumors. Metastatic and non-metastatic lymph nodes did not differ regarding their macrophage polarization.The current study revealed for the first time an influence of oscc on the macrophage polarization in regional lymph nodes. Markers of malignant behavior in the primary tumor were associated with a shift of macrophage polarization in lymph nodes from the anti-tumoral M1 type to the tumor-promoting M2 type. As tumor free and metastatic lymph nodes did not differ in terms of their macrophage polarization pattern, there must be other factors influencing the location for lymph node metastasis formation.
EVALuna2:18175

In Deutschland erworbene West-Nil-Virusinfektion bei einem nierentransplantierten Patienten - Karrasch, Matthias; Pein, Ulrich; Fritz, Annekathrin; Lange, Danica; Moritz, Stefan; Amann, Kerstin Ute; Schmidt-Chanasit, Jonas; Cadar, Daniel; Tappe, Dennis; Gabriel, Martin (Deutsche Medizinische Wochenschrift, 2021)
Background West-Nile-Virus (WNV) is a widely distributed flavivirus that is mainly transmitted between birds through different mosquito species (e.g. Culex, Aedes), but may also be transmitted to mammals including humans. WNV causes a spectrum of disease, ranging from asymptomatic infection to encephalitis in a minority of cases. Risk factors for severe disease are older age, cardiovascular disease and an immunocompromised state. Medical History and Clinical Examination Here we report about a 60-year-old male patient who was referred to the University Hospital of Halle (Saale) with severe fever two years after kidney transplantation due to hypertensive nephropathy. No infection focus could be found and by day 6 in the course of his illness the patient developed neurologic symptoms and viral encephalitis was suspected. Treatment and course The patient was initially treated with aciclovir. After initial reduction of immunosuppression, coincident graft dysfunction was treated with methylprednisolon. WNV-infection was suspected due to recent emerging human cases in the nearby area of the city of Leipzig. WNV lineage 2 was detected in the patient's urine by RT-PCR and seroconversion with presence of anti WNV IgM and IgG could be demonstrated. Consecutively, aciclovir treatment was stopped. The patient fully recovered and the transplanted kidney regained adequate function. Kidney biopsy did not reveal gross rejection of the transplant. Conclusion This case highlights the need to consider rarer causes of illness like WNV-infection particularly in risk groups for more severe outcomes of infectious disease. WNV may be detected by PCR in the blood and cerebrospinal fluid early in the course of infection but it is also excreted for a prolonged period of time in the urine. Seroconversion to anti WNV IgG and IgM may be shown but serologic cross-reactivity among members of the flaviviridae family must be considered.
CRIS-Team Scopus Importer:2021-04-16
Keywords: encephalitis; kidney; menigoencephalitis; transplantation; west nile virus

Inhibition of the renal apical sodium dependent bile acid transporter prevents cholemic nephropathy in mice with obstructive cholestasis - Ghallab, Ahmed; González, Daniela; Strängberg, Ellen; Hofmann, Ute; Myllys, Maiju; Hassan, Reham; Hobloss, Zaynab; Brackhagen, Lisa; Begher-Tibbe, Brigitte; Duda, Julia C.; Drenda, Carolin; Kappenberg, Franziska; et al. (Journal of Hepatology, 2024)
Background & Aims: Cholemic nephropathy (CN) is a severe complication of cholestatic liver diseases for which there is no specific treatment. We revisited its pathophysiology with the aim of identifying novel therapeutic strategies. Methods: Cholestasis was induced by bile duct ligation (BDL) in mice. Bile flux in kidneys and livers was visualized by intravital imaging, supported by MALDI mass spectrometry imaging and liquid chromatography-tandem mass spectrometry. The effect of AS0369, a systemically bioavailable apical sodium-dependent bile acid transporter (ASBT) inhibitor, was evaluated by intravital imaging, RNA-sequencing, histological, blood, and urine analyses. Translational relevance was assessed in kidney biopsies from patients with CN, mice with a humanized bile acid (BA) spectrum, and via analysis of serum BAs and KIM-1 (kidney injury molecule 1) in patients with liver disease and hyperbilirubinemia. Results: Proximal tubular epithelial cells (TECs) reabsorbed and enriched BAs, leading to oxidative stress and death of proximal TECs, casts in distal tubules and collecting ducts, peritubular capillary leakiness, and glomerular cysts. Renal ASBT inhibition by AS0369 blocked BA uptake into TECs and prevented kidney injury up to 6 weeks after BDL. Similar results were obtained in mice with humanized BA composition. In patients with advanced liver disease, serum BAs were the main determinant of KIM-1 levels. ASBT expression in TECs was preserved in biopsies from patients with CN, further highlighting the translational potential of targeting ASBT to treat CN. Conclusions: BA enrichment in proximal TECs followed by oxidative stress and cell death is a key early event in CN. Inhibiting renal ASBT and consequently BA enrichment in TECs prevents CN and systemically decreases BA concentrations. Impact and implications: Cholemic nephropathy (CN) is a severe complication of cholestasis and an unmet clinical need. We demonstrate that CN is triggered by the renal accumulation of bile acids (BAs) that are considerably increased in the systemic blood. Specifically, the proximal tubular epithelial cells of the kidney take up BAs via the apical sodium-dependent bile acid transporter (ASBT). We developed a therapeutic compound that blocks ASBT in the kidneys, prevents BA overload in tubular epithelial cells, and almost completely abolished all disease hallmarks in a CN mouse model. Renal ASBT inhibition represents a potential therapeutic strategy for patients with CN.
CRIS-Team Scopus Importer:2024-02-02
Keywords: bile cast nephropathy; bile duct ligation; Cholestasis; intravital imaging; kidney injury

In-situ analysis of mast cells and dendritic cells in coronary atherosclerosis in chronic kidney disease (CKD) - Wachter, David; Neureiter, D.; Campean, Valentina; Hilgers, Karl Friedrich; Buettner-Herold, M.; Daniel, Christoph; Benz, Kerstin; Amann, Kerstin Ute (Histology and Histopathology, 2018)
AIMS: Mast cells (MC) and dendritic cells (DC) have immune modulatory function and can influence T-cell activity. Both cell types have been found in atherosclerotic plaques and are thought to play an important role for plaque stability. Compared to matched segments of the non-renal population, patients with chronic kidney disease (CKD) show a more pronounced and more aggressive course of atherosclerosis with higher plaque calcification and significantly higher complications rates. It was the aim of this study to analyze the number and localization of MCs and DCs, macrophages, T- and B-cells as well as the expression of markers of inflammation such as CRP and NFκB in calcified and non-calcified atherosclerotic plaques of patients with CKD and control patients. METHODS: Fifty coronary atherosclerotic plaques from patients with endstage CKD (CKD, n=25) and control (n=25) patients were categorized according to the Stary classification and investigated using immunohistochemistry (markers for MC, DC, T, B, macrophage and NFκB). Expression was analyzed separately for the complete plaque area as well as for the different plaque subregions and correlations were analyzed. RESULTS: We found only very few DCs and MCs per lesion area with slightly increased numbers in calcified plaques. MCs per plaque area were significantly more frequent in CKD than in control patients and this was independent of plaque calcification. MCs were most frequently found in the shoulder and basis of the plaque. DCs per plaque area were significantly less in calcified plaques of CKD compared to control patients. In control, but not in CKD patients, DCs were significantly more frequent in calcified than in non-calcified plaques. Within the plaques DCs were similarly distributed between all 4 subregions. CONCLUSIONS: Coronary atherosclerotic plaques of CKD patients showed a significantly higher number of MCs whereas DCs were less frequent compared to control patients particularly if plaques were calcified. These findings might indicate a potential proinflammatory role of MCs, but not of DCs in atherosclerotic lesions of CKD patients, adding another characteristic of advanced atherosclerosis in these patients.
EVALuna2:34422

INTERLEUKIN-21-A NEW PLAYER IN ALLOGRAFT REJECTION? - Steines, L.; Friedmann, J.; Schuster, A.; Poth, H.; Amann, Kerstin Ute; Banas, B.; Bergler, T. (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

Intracranial hemorrhage in COVID-19 patients during extracorporeal membrane oxygenation for acute respiratory failure: a nationwide register study report - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Meybohm, Patrick; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; et al. (Critical Care, 2022)
Background: In severe cases, SARS-CoV-2 infection leads to acute respiratory distress syndrome (ARDS), often treated by extracorporeal membrane oxygenation (ECMO). During ECMO therapy, anticoagulation is crucial to prevent device-associated thrombosis and device failure, however, it is associated with bleeding complications. In COVID-19, additional pathologies, such as endotheliitis, may further increase the risk of bleeding complications. To assess the frequency of bleeding events, we analyzed data from the German COVID-19 autopsy registry (DeRegCOVID). Methods: The electronic registry uses a web-based electronic case report form. In November 2021, the registry included N = 1129 confirmed COVID-19 autopsy cases, with data on 63 ECMO autopsy cases and 1066 non-ECMO autopsy cases, contributed from 29 German sites. Findings: The registry data showed that ECMO was used in younger male patients and bleeding events occurred much more frequently in ECMO cases compared to non-ECMO cases (56% and 9%, respectively). Similarly, intracranial bleeding (ICB) was documented in 21% of ECMO cases and 3% of non-ECMO cases and was classified as the immediate or underlying cause of death in 78% of ECMO cases and 37% of non-ECMO cases. In ECMO cases, the three most common immediate causes of death were multi-organ failure, ARDS and ICB, and in non-ECMO cases ARDS, multi-organ failure and pulmonary bacterial ± fungal superinfection, ordered by descending frequency. Interpretation: Our study suggests the potential value of autopsies and a joint interdisciplinary multicenter (national) approach in addressing fatal complications in COVID-19.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Autopsy; Bleeding events; COVID-19; ECMO; Intracranial bleeding; Registry

INTRARENAL HIGH SALT ADMINISTRATION CAUSES TONIC INHIBITION OF RENAL SYMPATHETIC NERVE ACTIVITY (RSNA) - Hindermann, Martin; Rodionova, Kristina; Dietz, Amelie; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Veelken, Roland (2018)
EVALuna2:204842

Intravital imaging reveals glomerular capillary distension and endothelial and immune cell activation early in Alport syndrome - Gyarmati, Georgina; Shroff, Urvi Nikhil; Izuhara, Audrey; Hou, Xiaogang; Da Sacco, Stefano; Sedrakyan, Sargis; Lemley, Kevin V.; Amann, Kerstin Ute; Perin, Laura; Peti-Peterdi, Janos (JCI Insight, 2022)
Alport syndrome (AS) is a genetic disorder caused by mutations in type IV collagen that lead to defective glomerular basement membrane, glomerular filtration barrier (GFB) damage, and progressive chronic kidney disease. While the genetic basis of AS is well known, the molecular and cellular mechanistic details of disease pathogenesis have been elusive, hindering the development of mechanism-based therapies. Here, we performed intravital multiphoton imaging of the local kidney tissue microenvironment in a X-linked AS mouse model to directly visualize the major drivers of AS pathology. Severely distended glomerular capillaries and aneurysms were found accompanied by numerous microthrombi, increased glomerular endothelial surface layer (glycocalyx) and immune cell homing, GFB albumin leakage, glomerulosclerosis, and interstitial fibrosis by 5 months of age, with an intermediate phenotype at 2 months. Renal histology in mouse or patient tissues largely failed to detect capillary aberrations. Treatment of AS mice with hyaluronidase or the ACE inhibitor enalapril reduced the excess glomerular endothelial glycocalyx and blocked immune cell homing and GFB albumin leakage. This study identified central roles of glomerular mechanical forces and endothelial and immune cell activation early in AS, which could be therapeutically targeted to reduce mechanical strain and local tissue inflammation and improve kidney function.
CRIS-Team Scopus Importer:2022-01-28

Is Early Complement Activation in Renal Transplantation Associated with Later Graft Outcome? - Bobka, Steffen; Ebert, Nadja; Koertvely, Eloed; Jacobi, Johannes; Wiesener, Michael; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: Complement activation is important in post-transplantation renal injury, but data on its role as predictor of transplant outcome/complications when assessed in donor kidneys are lacking. METHODS: In human renal transplant biopsies with delayed graft function (DGF, n=12), antibody mediated rejection (ABMR, n=8), T-cell mediated rejection (TCMR, n=11), 1 year protocol biopsies (control, n=10) and corresponding zero-biopsies we performed immunohistochemical analyses of 6 complement factors using FFPE sections and correlated the findings with kidney function, as assessed by serum creatinine, and morphological changes including interstitial fibrosis and tubular atrophy (IF/TA). RESULTS: In DGF, TCMR and ABMR significant complement deposition was observed, which was less pronounced in corresponding zero-biopsies. Zero-biopsies with subsequent ABMR showed glomerular complement factor D and C3c expression. Moreover, glomerular C3c and C9 and tubular MASP-2 and Collectin-11 expression in zero-biopsies significantly correlated with serum creatinine at diagnosis of DGF, TCMR or ABMR. Glomerular C1q was significantly increased in ABMR, but not in DGF and TCMR. In contrast, peritubular C1q was significantly enhanced in DGF and TCMR compared to zero-biopsies. Using C3d as a surrogate marker for complement activity we could confirm that stained complement factors are frequently associated with complement activity. CONCLUSION: Complement deposition strongly correlated with histopathological changes observed in renal transplants. All 3 complement pathways were operational in biopsies with DGF, TCMR and ABMR albeit with differential abundance and localization. Since complement deposition in zero-biopsies correlated with graft function and morphological changes, early specific complement inhibition in renal transplantation may be a new therapeutic option to prevent graft loss.
EVALuna2:35394

Janus kinase 3 regulates renal 25-hydroxyvitamin D 1?-hydroxylase expression, calcitriol formation, and phosphate metabolism - Umbach, Anja T.; Zhang, Bingbing; Daniel, Christoph; Fajol, Abul; Velic, Ana; Hosseinzadeh, Zohreh; Bhavsar, Shefalee K.; Bock, C-Thomas; Kandolf, Reinhard; Pichler, Bernd J.; Amann, Kerstin Ute; Foeller, Michael; et al. (Kidney International, 2015)
Calcitriol, a powerful regulator of phosphate metabolism and immune response, is generated by 25-hydroxyvitamin D 1?-hydroxylase in the kidney and macrophages. Renal 1?-hydroxylase expression is suppressed by Klotho and FGF23, the expression of which is stimulated by calcitriol. Interferon ? (INF?) regulates 1?-hydroxylase expression in macrophages through transcription factor interferon regulatory factor-1. INF?-signaling includes Janus kinase 3 (JAK3) but a role of JAK3 in the regulation of 1?-hydroxylase expression and mineral metabolism has not been shown. Thus, the impact of JAK3 deficiency on calcitriol formation and phosphate metabolism was measured. Renal interferon regulatory factor-1 and 1?-hydroxylase transcript levels, serum calcitriol and FGF23 levels, intestinal phosphate absorption as well as absolute and fractional renal phosphate excretion were significantly higher in jak3 knockout than in wild-type mice. Coexpression of JAK3 increased the phosphate-induced current in renal sodium-phosphate cotransporter-expressing Xenopus oocytes. Thus, JAK3 is a powerful regulator of 1?-hydroxylase expression and phosphate transport. Its deficiency leads to marked derangement of phosphate metabolism.
EVALuna2:25470

Key role of renal biopsy in management of progressive chronic kidney disease in liver graft recipients - Welker, Martin-Walter; Weiler, Nina; Bechstein, Wolf Otto; Herrmann, Eva; Betz, Christoph; Schoeffauer, Mark; Zeuzem, Stefan; Sarrazin, Christoph; Amann, Kerstin Ute; Jung, Oliver (Journal of Nephrology, 2018)
AIMS: Chronic kidney disease (CKD) is a common complication after liver transplantation (LT). The etiology of CKD is broad and may only be assessed accurately by renal histology. The current study aimed to analyze the safety of renal biopsy in daily clinical practice as well as its usefulness regarding management of CKD after LT. METHODS: We performed a retrospective analysis of clinical data and renal biopsies obtained from patients with severe renal impairment (overt proteinuria, progressive deterioration of renal function) after LT with respect to safety, etiology of renal disease, and therapeutic consequences. RESULTS: Renal biopsies were obtained from 14 patients at median (minimum-maximum) 3 (0.2-12) years after LT. No major complications associated with renal biopsy were observed. Histomorphological alterations were varied (nephrosclerosis, n = 5; IgA-glomerulonephritis, n = 4; tenofovir-associated nephropathy, membranoproliferative glomerulonephritis type 1, membranous glomerulonephritis, amyloid A amyloidosis, and calcineurin inhibitor nephropathy, n = 1, respectively). The diagnosis of specific renal diseases other than calcineurin-inhibitor nephrotoxicity facilitated specific treaments and avoided unnecessary modification of immunosuppression in the majority of patients. CONCLUSIONS: Renal biopsy in patients with CKD after LT seems safe and may offer specific therapeutic options. Furthermore, unnecessary changes of immunosuppression can be avoided in a considerable number of patients.
EVALuna2:34431

Key role of renal biopsy in management of progressive chronic kidney disease in liver graft recipients - Welker, Martin-Walter; Weiler, Nina; Bechstein, Wolf Otto; Herrmann, Eva; Betz, Christoph; Schoeffauer, Mark; Zeuzem, Stefan; Sarrazin, Christoph; Amann, Kerstin Ute; Jung, Oliver (Journal of Nephrology, 2019)
Aims Chronic kidney disease (CKD) is a common complication after liver transplantation (LT). The etiology of CKD is broad and may only be assessed accurately by renal histology. The current study aimed to analyze the safety of renal biopsy in daily clinical practice as well as its usefulness regarding management of CKD after LT.
CRIS-Team WoS Importer:2019-02-27

Kidney injury is independent of endothelial HIF-1? - Kalucka, Joanna; Schley, Gunnar; Georgescu, Adela; Klanke, Bernd; Roessler, Susanne; Baumgartl, Jasmin; Velden, Joachim; Amann, Kerstin Ute; Willam, Carsten; Johnson, Randall S.; Eckardt, Kai-Uwe; Weidemann, Alexander (Journal of Molecular Medicine, 2015)
Hypoxia-inducible transcription factors (HIFs) control cellular adaptation to low oxygen. In the kidney, activation of HIF is beneficial during injury; however, the specific contribution of HIF-1? in renal endothelial cells (EC) remains elusive. Since EC display tissue-specific heterogeneity, we investigated how HIF-1? affects key functions of glomerular EC in vitro and its contribution to renal development and pathophysiological adaptation to acute or chronic renal injury in vivo. Loss of HIF-1? in glomerular EC induces hypoxic cell death and reduces hypoxic adhesion of macrophages in vitro. In vivo, HIF-1? expression in EC in mouse kidneys is detectable but limited. Accordingly, EC-specific ablation of HIF-1? does not lead to developmental or phenotypical abnormalities in the kidney. Renal function and expression of adhesion molecules during acute ischemic kidney injury is independent of HIF-1? in EC. Likewise, inflammation and development of fibrosis after unilateral ureteric obstruction is not influenced by endothelial HIF-1?. Taken together, although HIF-1? exerts effects on glomerular EC in vitro, endothelial HIF-1? does not influence renal development and pathophysiological adaptation to kidney injury in vivo. This implies a profound difference of the hypoxic response of the renal vascular bed compared to other organs, such as the heart. This has implications for the development of pharmacological strategies targeting the endothelial hypoxic response pathways.HIF-1? controls hypoxic survival and adhesion on endothelial cells (EC) in vitro. In vivo, HIF-1? expression in renal EC is low. Deletion of HIF-1? in EC does not affect kidney development and function in mice. Renal function after acute and chronic kidney injury is independent of HIF-1? in EC. Data suggest organ-specific regulation of HIF-1? function in EC.
EVALuna2:3772

Kidney transplantation after rescue allocation-meticulous selection yields the chance for excellent outcome - Assfalg, Volker; Misselwitz, Svea; Renders, Lutz; Hüser, Norbert; Novotny, Alexander; Jäger, Carsten; Büttner-Herold, Maike; Amann, Kerstin Ute; Schmaderer, Christoph; Heemann, Uwe; Wen, Ming; Haberfellner, Flora; et al. (Nephrology Dialysis Transplantation, 2021)
BACKGROUND: The small number of organ donors forces transplant centres to consider potentially suboptimal kidneys for transplantation. Eurotransplant established an algorithm for rescue allocation (RA) of kidneys repeatedly declined or not allocated within 5 h after procurement. Data on the outcomes and benefits of RA are scarce to date. METHODS: We conducted a retrospective 8-year analysis of transplant outcomes of RA offers based on our in-house criteria catalogue for acceptance and decline of organs and potential recipients. RESULTS: RA donors and recipients were both older compared with standard allocation (SA). RA donors more frequently had a history of hypertension, diabetes or fulfilled expanded criteria donor key parameters. RA recipients had poorer human leucocyte antigen (HLA) matches and longer cold ischaemia times (CITs). However, waiting time was shorter and delayed graft function, primary non-function and biopsy-proven rejections were comparable to SA. Five-year graft and patient survival after RA were similar to SA. In multivariate models accounting for confounding factors, graft survival and mortality after RA and SA were comparable as well. CONCLUSIONS: Facing relevant comorbidities and rapid deterioration with the risk of being removed from the waiting list, kidney transplantation after RA was identified to allow for earlier transplantation with excellent outcome. Data from this survey propose not to reject categorically organs from multimorbid donors with older age and a history of hypertension or diabetes to aim for the best possible HLA matching and to carefully calculate overall expected CIT.
CRIS-Team Scopus Importer:2021-03-19
Keywords: allocation; kidney; outcome; rescue; transplantation

Knockdown of ApoL1 in Zebrafish Larvae Affects the Glomerular Filtration Barrier and the Expression of Nephrin - Kotb, Ahmed M.; Simon, Ole; Blumenthal, Antje; Vogelgesang, Silke; Dombrowski, Frank; Amann, Kerstin Ute; Zimmermann, Uwe; Endlich, Karlhans; Endlich, Nicole (PLoS ONE, 2016)
APOL1, a secreted high-density lipoprotein, is expressed in different human tissues. Genetic variants of APOL1 are described to be associated with the development of end stage renal diseases in African Americans. In human kidney, APOL1 is mainly expressed in podocytes that are responsible for proper blood filtration. Since mice do not express ApoL1, the zebrafish is an ideal model to study the role of ApoL1. Injection of morpholinos against zApoL1 into zebrafish eggs and larvae, respectively, induces severe edema indicating a leakage of the filtration barrier. This was demonstrated in zApoL1 knockdown larvae by intravascular injection of fluorescently-labeled 10- and 500-kDa dextrans and by clearance of the vitamin D-binding protein from the circulation. Immunohistochemistry and RT-PCR revealed the reduction of nephrin, a podocyte-specific protein essential for blood filtration. Coinjection of human nephrin mRNA rescued the zApoL1 knockdown induced phenotype. Reduced APOL1 and nephrin levels were also found in biopsies of patients suffering from end stage renal diseases. Our results demonstrate that zApoL1 is essential for proper blood filtration in the zebrafish glomerulus and that zApoL1 affects the expression of nephrin.
EVALuna2:25517

Lack of intestinal epithelial atg7 affects paneth cell granule formation but does not compromise immune homeostasis in the gut. - Günther, Claudia; Martini, Eva; Waldner, Maximilian; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph; et al. (Clinical & Developmental Immunology, 2012)
Genetic polymorphisms of autophagy-related genes have been associated with an increased risk to develop inflammatory bowel disease (IBD). Autophagy is an elementary process participating in several cellular events such as cellular clearance and nonapoptotic programmed cell death. Furthermore, autophagy may be involved in intestinal immune homeostasis due to its participation in the digestion of intracellular pathogens and in antigen presentation. In the present study, the role of autophagy in the intestinal epithelial layer was investigated. The intestinal epithelium is essential to maintain gut homeostasis, and defects within this barrier have been associated with the pathogenesis of IBD. Therefore, mice with intestinal epithelial deletion of Atg7 were generated and investigated in different mouse models. Knockout mice showed reduced size of granules and decreased levels of lysozyme in Paneth cells. However, this was dispensable for gut immune homeostasis and had no effect on susceptibility in mouse models of experimentally induced colitis.

Lessons for the clinical nephrologist: recurrence of nephrotic syndrome induced by SARS-CoV-2 - Doevelaar, Adrian A.N.; Hölzer, Bodo; Seibert, Felix S.; Bauer, Frederic; Stervbo, Ulrik; Rohn, Benjamin J.; Zgoura, Panagiota; Schenker, Peter; Vonbrunn, Eva; Amann, Kerstin Ute; Viebahn, Richard; Babel, Nina; et al. (Journal of Nephrology, 2020)
SARS-CoV-2 is characterized by a multiorgan tropism including the kidneys. Recent autopsy series indicated that SARS-CoV-2 can infect both tubular and glomerular cells. Whereas tubular cell infiltration may contribute to acute kidney injury, data on a potential clinical correlative to glomerular affection is rare. We describe the first case of nephrotic syndrome in the context of COVID-19 in a renal transplant recipient. A 35 year old male patient received a kidney allograft for primary focal segmental glomerulosclerosis (FSGS). Three months posttransplant a recurrence of podocytopathy was successfully managed by plasma exchange, ivIG, and a conversion from tacrolimus to belatacept (initial proteinuria > 6 g/l decreased to 169 mg/l). Six weeks later he was tested positive for SARS-CoV-2 and developed a second increase of proteinuria (5.6 g/l). Renal allograft biopsy revealed diffuse podocyte effacement and was positive for SARS-CoV-2 in RNA in-situ hybridation indicating a SARS-CoV-2 associated recurrence of podocytopathy. Noteworthy, nephrotic proteinuria resolved spontaneously after recovering from COVID-19. The present case expands the spectrum of renal involvement in COVID-19 from acute tubular injury to podocytopathy in renal transplant recipients. Thus, it may be wise to test for SARS-CoV-2 prior to initiation of immunosuppression in new onset glomerulopathy during the pandemic.
CRIS-Team Scopus Importer:2020-09-18
Keywords: COVID-19; Podocytopathy; SARS-CoV-2

Light chain proximal tubulopathy in the spectrumof B-cell dyscrasia induced renal disease - Buettner-Herold, M.; Chuva, T.; Minuth, Kaija; Pfister, F.; Daniel, C.; Klewer, M.; Buttner, A.; Ferrazzi, F.; Bertz, S.; Amann, Kerstin Ute (2018)
EVALuna2:34617

Light Chain Restriction in Proximal Tubules—Implications for Light Chain Proximal Tubulopathy - Büttner-Herold, Maike; Krieglstein, Nathalie; Chuva, Teresa; Minuth, Kaija; Pfister, Frederick; Daniel, Christoph; Klewer, Monika; Büttner, Anke; Ferrazzi, Fulvia; Bertz, Simone; Amann, Kerstin Ute (Frontiers in Medicine, 2022)
Monoclonal gammopathy (MG) causes various nephropathies, which may suffice for cytoreductive therapy even in the absence of diagnostic criteria for multiple myeloma or B-cell non-Hodgkin lymphoma. The aim of this study was to better understand the significance of light chain (LC) restriction or crystals (LC-R/C) in proximal tubules in the spectrum of LC-induced nephropathies. A consecutive cohort of 320 renal specimens with a history of B-cell dyscrasia was characterized. Special attention was paid to immunohistochemical LC restriction in proximal tubules, tubular crystals or constipation, and ultrastructural findings. Complementary cell culture experiments were performed to assess the role of LC concentrations in generating LC restriction. Light chain restriction or crystals in proximal tubules was found in a quarter of analyzed cases (81/316) and was associated with another LC-induced disease in 70.4% (57/81), especially LC cast-nephropathy (cast-NP) and interstitial myeloma infiltration. LC restriction without significant signs of acute tubular injury was observed in 11.1% (9/81). LC-R/C was not associated with inferior renal function compared to the remainder of cases, when cases with accompanying cast-NP were excluded. Besides crystals, cloudy lysosomes were significantly associated with LC-R/C on an ultrastructural level. In summary, LC-R/C is frequent and strongly associated with cast-NP, possibly indicating that a high load of clonal LC is responsible for this phenomenon, supported by the observation that LC restriction can artificially be generated in cell culture. This and the lack of significant tubular injury in a subgroup imply that in part LC-R/C is a tubular trafficking phenomenon rather than an independent disease process.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cast nephropathy; light chain restriction; monoclonal gammopathies of renal significance; renal tubule; tubular crystals

Lineage-associated connexin 43 expression in bisphosphonate-exposed rat bones - Preidl, Raimund; Amann, Kerstin Ute; Weber, Manuel; Schiller, Martin; Ringler, Manuela; Ries, Jutta; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Journal of Cranio-Maxillofacial Surgery, 2021)
Expression of signaling proteins in bone cells depends on their embryological mesoderm-derived (e.g. tibia) or cranial neural crest (CNC)-derived (e.g. jaw) origin. Connexin 43 (Cx43) is a gap junction protein that plays an essential role in the mode of action of bisphosphonates (BP). This study aimed to investigate Cx43 expression and the influence of BP application on mesoderm- and CNC-derived bone. Using a rat model, molar extraction and tibia osteotomy with (Group 4) or without (Group 3) previous BP application was performed. Untreated (Group 1) and animals selectively treated with BPs (Group 2) served as controls. Cx43 expression was immunohistochemically determined 12 and 16 weeks postoperatively via a labeling index. Cx43 expression in CNC-derived bone was significantly higher compared with mesodermal bone. BP application decreased Cx43 expression; however, detected expression levels were still higher in jawbone (Group 2 tibia vs jaw: 5.83 ± 5.06 vs 23.52 ± 6.42; p = 0.007). During bone healing after surgical intervention (Group 3) there were no expression differences between tibia and jawbone. BP treatment prior to surgery resulted in significantly lower Cx43 expression in CNC-derived compared with tibia bone (Group 4 tibia vs jaw: 56.84 ± 15.57 vs 16.40 ± 5.66; p < 0.01). Increased Cx43 expression in jaw compared with tibia bone is in line with their embryological origins. A significant Cx43 suppression in jawbone after BP application and surgery might contribute to the selectively altered osseous turnover and development of MRONJ in CNC-derived bone.
CRIS-Team Scopus Importer:2021-03-12
Keywords: Bisphosphonate; Jawbone; Medication-related osteonecrosis of the jaw (MRONJ)

LONGITUDINAL INTRAINDIVIDUAL CHANGES OF PERITONEAL HISTOLOGY OVER TIME IN 37 PERITONEAL DIALYSIS PATIENTS - Aziz, Alan; Kielstein, Jan T.; Pfister, Frederick; Amann, Kerstin Ute; Eden, Gabriele (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-07-22

Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2019)
BACKGROUND: Microvascular free flap reconstruction has become a standard technique in head and neck reconstructive surgery. Pre-operative radiotherapy is associated with a higher incidence of free flap malperfusion and the need for operative revision. Irradiated vessels present characteristic histomorphological and structural changes. Alterations in endothelial cells of irradiated arteries remain incompletely investigated especially with regard to long-term changes in endothelial dysfunction supporting an intraluminal pro-thrombotic and pro-inflammatory milieu. METHODS: Endothelial expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E‑ and P‑selectin, endothelial NO-synthase (eNOS), thrombomodulin and plasminogen activator inhibitor-1 (PAI-1) in irradiated and non-irradiated arteries was analysed using immunohistochemistry and Remmele scale grading. The average radiation dose was 58.7 ± 7.0 Gy; the time interval between end of radiation and tissue sampling was 106.0 ± 86.8 months. RESULTS: Endothelial expression of ICAM-1, VCAM-1, E‑ and P‑selectin as well as PAI-1 was significantly increased in previously irradiated arteries compared with non-irradiated controls, whereas thrombomodulin and eNOS expression did not show any differences. However, when comparing non-irradiated free flap arteries with irradiated arteries from the head and neck area in respective individuals, eNOS expression was significantly lower in irradiated vessels whereas ICAM-1, VCAM-1, E‑/p-Selectin and PAI-1 showed significantly higher expression levels. CONCLUSION: There is ongoing endothelial dysfunction in terms of increased expression of pro-thrombotic and pro-inflammatory markers in irradiated arteries even years after radiotherapy. Treating this endothelial dysfunction might reduce the complication rates associated with microvascular free flap reconstructions in irradiated patients.
EVALuna2:35426

Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis Langzeit-Endothelfunktionsstörung in bestrahlten Gefäßen: immunhistochemische Analyse - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2019)
Background: Microvascular free flap reconstruction has become a standard technique in head and neck reconstructive surgery. Pre-operative radiotherapy is associated with a higher incidence of free flap malperfusion and the need for operative revision. Irradiated vessels present characteristic histomorphological and structural changes. Alterations in endothelial cells of irradiated arteries remain incompletely investigated especially with regard to long-term changes in endothelial dysfunction supporting an intraluminal pro-thrombotic and pro-inflammatory milieu. Methods: Endothelial expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E‑ and P‑selectin, endothelial NO-synthase (eNOS), thrombomodulin and plasminogen activator inhibitor-1 (PAI-1) in irradiated and non-irradiated arteries was analysed using immunohistochemistry and Remmele scale grading. The average radiation dose was 58.7 ± 7.0 Gy; the time interval between end of radiation and tissue sampling was 106.0 ± 86.8 months. Results: Endothelial expression of ICAM-1, VCAM-1, E‑ and P‑selectin as well as PAI-1 was significantly increased in previously irradiated arteries compared with non-irradiated controls, whereas thrombomodulin and eNOS expression did not show any differences. However, when comparing non-irradiated free flap arteries with irradiated arteries from the head and neck area in respective individuals, eNOS expression was significantly lower in irradiated vessels whereas ICAM-1, VCAM-1, E‑/p-Selectin and PAI-1 showed significantly higher expression levels. Conclusion: There is ongoing endothelial dysfunction in terms of increased expression of pro-thrombotic and pro-inflammatory markers in irradiated arteries even years after radiotherapy. Treating this endothelial dysfunction might reduce the complication rates associated with microvascular free flap reconstructions in irradiated patients.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Endothelial dysfunction; Free tissue flaps; Radiation dosage; Radiotherapy; Reconstructive surgery

Loss of Survivin in Intestinal Epithelial Progenitor Cells Leads to Mitotic Catastrophe and Breakdown of Gut Immune Homeostasis - Martini, Eva; Wittkopf, Nadine; Günther, Claudia; Leppkes, Moritz; Okada, Hitoshi; Watson, Alastair J.; Podstawa, Eva; Backert, Ingo; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph (Cell Reports, 2016)
A tightly regulated balance of proliferation and cell death of intestinal epithelial cells (IECs) is essential for maintenance of gut homeostasis. Survivin is highly expressed during embryogenesis and in several cancer types, but little is known about its role in adult gut tissue. Here, we show that Survivin is specifically expressed in transit-amplifying cells and Lgr5(+) stem cells. Genetic loss of Survivin in IECs resulted in destruction of intestinal integrity, mucosal inflammation, and death of the animals. Survivin deletion was associated with decreased epithelial proliferation due to defective chromosomal segregation. Moreover, Survivin-deficient animals showed induced phosphorylation of p53 and H2AX and increased levels of cell-intrinsic apoptosis in IECs. Consequently, induced deletion of Survivin in Lgr5(+) stem cells led to cell death. In summary, Survivin is a key regulator of gut tissue integrity by regulating epithelial homeostasis in the stem cell niche.
EVALuna2:2058

Loss of the collagen IV modifier prolyl 3-hydroxylase 2 causes thin basement membrane nephropathy - Aypek, Hande; Krisp, Christoph; Lu, Shun; Liu, Shuya; Kylies, Dominik; Kretz, Oliver; Wu, Guochao; Moritz, Manuela; Amann, Kerstin Ute; Benz, Kerstin; Tong, Ping; Hu, Zheng Mao; et al. (Journal of Clinical Investigation, 2022)
The glomerular filtration barrier (GFB) produces primary urine and is composed of a fenestrated endothelium, a glomerular basement membrane (GBM), podocytes, and a slit diaphragm. Impairment of the GFB leads to albuminuria and microhematuria. The GBM is generated via secreted proteins from both endothelial cells and podocytes and is supposed to majorly contribute to filtration selectivity. While genetic mutations or variations of GBM components have been recently proposed to be a common cause of glomerular diseases, pathways modifying and stabilizing the GBM remain incompletely understood. Here, we identified prolyl 3-hydroxylase 2 (P3H2) as a regulator of the GBM in an a cohort of patients with albuminuria. P3H2 hydroxylates the 3′ of prolines in collagen IV subchains in the endoplasmic reticulum. Characterization of a P3h2ΔPod mouse line revealed that the absence of P3H2 protein in podocytes induced a thin basement membrane nephropathy (TBMN) phenotype with a thinner GBM than that in WT mice and the development of microhematuria and microalbuminuria over time. Mechanistically, differential quantitative proteomics of the GBM identified a significant decrease in the abundance of collagen IV subchains and their interaction partners in P3h2ΔPod mice. To our knowledge, P3H2 protein is the first identified GBM modifier, and loss or mutation of P3H2 causes TBMN and focal segmental glomerulosclerosis in mice and humans.
CRIS-Team Scopus Importer:2022-05-20

Macrophage and osteoclast polarization in bisphosphonate associated necrosis and osteoradionecrosis - Wehrhan, Falk; Möbius, Patrick; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Weber, Manuel (Journal of Cranio-Maxillofacial Surgery, 2017)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a complication of antiresorptive therapy with nitrogen-containing bisphosphonates (BP). With various suggestions as to pathogenesis, the etiology of BRONJ is not sufficiently understood. Osteoclasts and their precursors, that is, macrophages, are the main target cells of BP. BP can repolarize regeneration- and healing-associated M2 macrophages towards the tissue destructive M1-type. The current study aims to elucidate differences in macrophage and osteoclast polarization in BRONJ, osteoradionecrosis (ORN) and healthy control specimens.A total of 39 jaw bone samples (18 BRONJ, 8 ORN and 13 healthy controls) were processed for immunohistochemistry to detect CD68-, CD11c- and CD163-positive cells. Macrophages and osteoclasts were distinguished on the basis of morphological differences. Samples were digitized, and the macrophage and osteoclast cell counts were quantitatively analyzed.In jaw bone affected by BRONJ, a significantly increased macrophage infiltration and M1 polarization of macrophages can be seen. The density of CD68-expressing osteoclasts is significantly increased in BRONJ specimens compared to ORN and to healthy controls.A bisphosphonate-derived shift of macrophage polarization towards M1-polarized macrophages might impair bone tissue homeostasis and thus contribute to the pathogenesis of BRONJ. The observed increase in osteoclast density might be caused by BP-induced prolonged osteoclast survival.
EVALuna2:24431

Macrophage-Induced Pro-Fibrotic Gene Expression in Tubular Cells after Ischemia/Reperfusion Is Paralleled but Not Directly Mediated by C5a/C5aR1 Signaling - Bleich, Erik; Vonbrunn, Eva; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Life, 2024)
Ischemia/reperfusion (I/R) is inevitable during kidney transplantation and causes acute kidney injury (AKI), which affects immediate outcome and leads to chronic changes such as fibrotic remodeling of the graft. We investigated pro-fibrotic signaling after I/R, focusing on the complement component and receptor C5a/C5aR1 and macrophage/tubule crosstalk. Male Dark Agouti rats were subjected to I/R and their kidneys were harvested 10 min, 6 h, 24 h, 3 days, 5 days and 8 weeks after reperfusion. The development of renal fibrosis was assessed by the detection of Vimentin (VIM), α-smooth muscle actin (α-SMA) and collagen by immunohistochemistry and Sirius Red staining, respectively. The characterization of C5a/C5aR1 activity and C5aR1+ cells was performed by multiplex mRNA analysis, ELISA, immunofluorescence flow cytometry and in situ hybridization in animal models and cell culture analyses. In the cell culture experiments, we focused on macrophage/tubule cell crosstalk in co-culture experiments and mimicked in vivo conditions by hypoxia/reoxygenation and supplementation with C5a. Already 6–24 h after the induction of I/R in the rat model, C5a concentration in the plasma was significantly increased compared to the control. The matrix components VIM and α-SMA peaked on day 5 and declined after 8 weeks, when an increase in collagen was detected using Sirius Red. In contrast to early I/R-induced C5a activation, renal C5ar1 expression was maximal at day 5 and C5 expression increased until week 8, indicating that the renal upregulation of expression is not required for early complement activation. C5aR1 mRNA was detected in neutrophils and macrophages, but not in proximal tubular cells in the injured kidneys. The macrophage/tubular cell co-culture experiments showed that macrophages were mainly responsible for the increased expression of fibrosis-associated genes in tubule cells (ACTA2, VIM, SNAI1, TGFB1 and FGF-2), and hypoxia/reoxygenation had a partially enhancing effect. A direct pro-fibrotic effect of C5a was not observed. Increased TGF-ß levels were dependent on the differentiation of macrophages to the M2 subtype. In conclusion, the early activation of mesenchymal markers in tubular epithelial cells leads to long-term fibrotic remodeling characterized by VIM expression and driven by TGF-ß-dependent macrophage/tubular crosstalk. The chemoattractive properties of complement C5a may contribute to the recruitment of pro-fibrotic macrophages.
CRIS-Team Scopus Importer:2024-09-06
Keywords: complement C5a; fibrosis; ischemia/reperfusion; macrophage/tubular crosstalk

Macrophage polarisation changes within the time between diagnostic biopsy and tumour resection in oral squamous cell carcinomas-an immunohistochemical study - Weber, Manuel; Moebius, P.; Büttner-Herold, M.; Amann, Kerstin Ute; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (British Journal of Cancer, 2015)
The prognosis of solid malignancies has been shown to depend on immunological parameters, such as macrophage polarisation (M1/M2). Recently, it was reported that preoperative oral surgery leads to a worsening of oral squamous cell carcinomas (OSCC) prognosis. Diagnostic incision biopsies are oral surgery procedures that might lead to healing-associated M2 macrophage polarisation with a potential negative influence on tumour biology. No studies have compared macrophage polarisation in OSCC biopsies and tumour specimens.Preoperative diagnostic incision biopsies (n=25) and tumour resection specimens (n=34) of T1/T2 OSCC were processed for immunohistochemistry to detect CD68-, CD11c-, CD163- and MRC1-positive cells. Samples were digitised using whole-slide imaging, and the expression of macrophage markers was quantitatively analysed.Carcinoma tissues obtained during OSCC tumour resections showed a significantly (P<0.05) increased CD163 cell count (M2 macrophages) compared with tissues obtained during preoperative incision biopsies. Additionally, the CD163/CD68 ratio (an indicator of M2 polarisation) was significantly (P<0.05) higher in tumour resection specimens than in biopsies.This study revealed for the first time an increase in M2 polarisation in samples obtained during OSCC tumour resection surgery compared with preoperative incision biopsies. The biopsy-induced tissue trauma might explain the observed shift in macrophage polarisation towards the tumour-promoting M2 type and could lead to accelerated tumour progression.
EVALuna2:24401

Macrophage subpopulations in pediatric patients with lupus nephritis and other inflammatory diseases affecting the kidney. - Sandersfeld, Mira; Büttner-Herold, Maike; Ferrazzi, Fulvia; Amann, Kerstin Ute; Benz, Kerstin; Daniel, Christoph (Arthritis Research & Therapy, 2024)
BACKGROUND: Macrophages play an important role in the pathogenesis of lupus nephritis (LN), but less is known about macrophage subtypes in pediatric LN. Here we compared renal inflammation in LN with other inflammatory pediatric kidney diseases and assessed whether inflammation correlates with clinical parameters. METHODS: Using immunofluorescence microscopy, we analyzed renal biopsies from 20 pediatric patients with lupus nephritis (ISN/RPS classes II-V) and pediatric controls with other inflammatory kidney diseases for infiltration with M1-like (CD68 + /CD206 - , CD68 + /CD163 -), M2a-like (CD206 + /CD68 +), and M2c-like macrophages (CD163 + /CD68 +) as well as CD3 + T-cells, CD20 + B-cells, and MPO + neutrophilic granulocytes. In addition, the correlation of macrophage infiltration with clinical parameters at the time of renal biopsy, e.g., eGFR and serum urea, was investigated. Macrophage subpopulations were compared with data from a former study of adult LN patients. RESULTS: The frequency of different macrophage subtypes in biopsies of pediatric LN was dependent on ISN/RPS class and showed the most pronounced M1-like macrophage infiltration in patients with LN class IV, whereas M2c-like macrophages were most abundant in class III and IV. Interestingly, on average, only half as many macrophages were found in renal biopsies of pediatric LN compared to adult patients with LN. The distribution of frequencies of macrophage subpopulations, however, was different for CD68 + CD206 + (M2a-like) but comparable for CD68 + CD163 - (M1-like) CD68 + CD163 + (M2c-like) cells in pediatric and adult patients. Compared to other inflammatory kidney diseases in children, fewer macrophages and other inflammatory cells were found in kidney biopsies of LN. Depending on the disease, the frequency of individual immune cell types varied, but we were unable to confirm disease-specific inflammatory signatures in our study due to the small number of pediatric cases. Worsened renal function, measured as elevated serum urea and decreased eGFR, correlated particularly strongly with the number of CD68 + /CD163 - M1-like macrophages and CD20 + B cells in pediatric inflammatory kidney disease. CONCLUSION: Although M1-like macrophages play a greater role in pediatric LN patients than in adult LN patients, M2-like macrophages appear to be key players and are more abundant in other pediatric inflammatory kidney diseases compared to LN.
EVALuna2:552742

Management of spontaneous enophthalmos due to silent sinus syndrome: a case report - Nkenke, Emeka; Alexiou, Christoph; Iro, Heinrich; Amann, Kerstin Ute; Kirchner, Thomas; Häusler, Gerd; Neukam, Friedrich Wilhelm; Holbach, Benedict (International Journal of Oral and Maxillofacial Surgery, 2005)
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.manage

Marine alkaloid Monanchocidin a overcomes drug resistance by induction of autophagy and lysosomal membrane permeabilization - Dyshlovoy, Sergey A.; Hauschild, Jessica; Amann, Kerstin Ute; Tabakmakher, Ksenia M.; Venz, Simone; Walther, Reinhard; Guzii, Alla G.; Makarieva, Tatiana N.; Shubina, Larisa K.; Fedorov, Sergey N.; Stonik, Valentin A.; Bokemeyer, Carsten; et al. (Oncotarget, 2015)
Monanchocidin A (MonA) is a novel alkaloid recently isolated from the marine sponge Monanchora pulchra. The compound reveals cytotoxic activity in genitourinary cancers including cisplatin-sensitive and -resistant germ cell tumor (GCT) cell lines, hormone-sensitive and castration-resistant prostate carcinoma cell lines and different bladder carcinoma cell lines. In contrast, non-malignant cells were significantly less sensitive. MonA is highly synergistic with cisplatin in GCT cells. Induction of autophagy at lower and lysosomal membrane permeabilization (LMP) at higher concentrations were identified as the dominating modes of action. Cytotoxicity and protein degradation could be inhibited by 3-methyladenine, an inhibitor of autophagy. LMP was confirmed by loss of acridine orange staining of lysosoms and by release of cathepsin B. In conclusion, MonA exerts cytotoxic activity by mechanisms different from "classical" apoptosis, and could be a promising new compound to overcome resistance to standard therapies in genitourinary malignancies.
EVALuna2:25492

Marine compound rhizochalinin shows high in vitro and in vivo efficacy in castration resistant prostate cancer - Dyshlovoy, Sergey A.; Otte, Katharina; Alsdorf, Winfried H.; Hauschild, Jessica; Lange, Tobias; Venz, Simone; Bauer, Christiane K.; Baehring, Robert; Amann, Kerstin Ute; Mandanchi, Ramin; Schumacher, Udo; Schroeder-Schwarz, Jennifer; et al. (Oncotarget, 2016)
Development of drug resistance is an inevitable phenomenon in castration-resistant prostate cancer (CRPC) cells requiring novel therapeutic approaches. In this study, efficacy and toxicity of Rhizochalinin (Rhiz) - a novel sphingolipid-like marine compound - was evaluated in prostate cancer models, resistant to currently approved standard therapies. In vitro activity and mechanism of action of Rhiz were examined in the human prostate cancer cell lines PC-3, DU145, LNCaP, 22Rv1, and VCaP. Rhiz significantly reduced cell viability at low micromolar concentrations showing most pronounced effects in enzalutamide and abiraterone resistant AR-V7 positive cells. Caspase-dependent apoptosis, inhibition of pro-survival autophagy, downregulation of AR-V7, PSA and IGF-1 expression as well as inhibition of voltage-gated potassium channels were identified as mechanisms of action. Remarkably, Rhiz re-sensitized AR-V7 positive cells to enzalutamide and increased efficacy of taxanes.In vivo activity and toxicity were evaluated in PC-3 and 22Rv1 NOD SCID mouse xenograft models using i.p. administration. Rhiz significantly reduced growth of PC-3 and 22Rv1 tumor xenografts by 27.0% (p = 0.0156) and 46.8% (p = 0.047) compared with controls with an increased fraction of tumor cells showing apoptosis secondary to Rhiz exposure. In line with the in vitro data, Rhiz was most active in AR-V7 positive xenografts in vivo. In animals, no severe side effects were observed.In conclusion, Rhiz is a promising novel marine-derived compound characterized by a unique combination of anticancer properties. Its further clinical development is of high impact for patients suffering from drug resistant prostate cancer especially those harboring AR-V7 mediated resistance to enzalutamide and abiraterone.
EVALuna2:25524

Mechanisms of everolimus‐induced glomerulosclerosis after glomerular injury in the rat - Daniel, Christoph; Renders, L.; Amann, Kerstin Ute; Schulze-Lohoff, Eckhard; Hauser, Ingeborg A.; Hugo, Christian (American Journal of Transplantation, 2005)
Despite the lack of nephrotoxicity, adverse effects of the new antiproliferative immunosuppressant everolimus have been reported. By varying time point and dose of everolimus treatment as well as the degree of glomerular injury, the specific conditions and potential mechanisms leading to adverse actions in the anti-Thy1 model have been determined. Only the combination of early and high-dose everolimus treatment (1-3 mg/kg bw) with a severe glomerular lesion ('full-dose' anti-Thy1 model) caused adverse effects with a high mortality rate, progressive apoptosis, crescent formation and glomerulosclerosis. In contrast, either later start or low-dose (0.3 mg/kg bw) therapy or treatment of a less severe lesion ('reduced dose' anti-Thy1 model) appeared to be relatively safe for the glomerular architecture. The adverse effects of everolimus were linked to its marked inhibition of endothelial cell, but not necessarily mesangial cell proliferation. In addition, everolimus markedly inhibited the angiogenic cytokine vascular endothelial growth factor in nephritic glomeruli in vivo. These experimental results suggest special caution regarding the use of everolimus in all situations of severe glomerular cell injury requiring extensive capillary repair, where at least adaption to a low dose needs to be considered. Copyright © Blackwell Munksgaard 2005.
Created from Fastlane, Scopus look-up
Keywords: Anti-Thy1 model; Glomerular endothelial cell proliferation; Glomerular regeneration; Rapamycin derivative everolimus; Renal microvascular injury

Membranoproliferative glomerulonephritis and C3 glomerulopathy - Hohenstein, B.; Amann, Kerstin Ute; Menne, J. (Internist, 2019)
Based on an increasingly better pathophysiological understanding over the last 10 years, in 2010 a new classification of glomerulonephritis with dominant or codominant C3 deposits was introduced and the predominant subgoup was termed C3 glomerulopathy (C3G). In the current classification, immune complex mediated membranoproliferative glomerulonephritis (IC-MPGN) and C3 glomerulopathy (C3G) form a disease spectrum which is very heterogeneous in terms of pathophysiology and the clinical course. Recent evidence suggests that IC-MPGN and C3G share more pathophysiological aspects with respect to secondary causes, autoantibodies and genetic aspects than had been suggested with the creation of the new classification. Knowledge of the underlying pathophysiology is important for guiding the diagnostic steps for clarification of secondary causes. Comprehensive complement analysis, accompanied by antibody screening and genetic analysis, should be consistently carried out. Although not systematically validated in clinical trials, the published evidence provides a robust foundation for the use of available treatment approaches for these diseases that are often rapidly progressive and often return after renal transplantation.
EVALuna2:102223

Mild Salt-Sensitive Hypertension in Genetically Determined Low Nephron Number is Associated with Chloride but Not Sodium Retention - Benz, Kerstin; Schlote, Julia; Daniel, Christoph; Kopp, Christoph; Dahlmann, Anke; Schröder, Agnes; Cordasic, Nada; Klanke, Bernd; Hilgers, Karl Friedrich; Titze, Jens; Amann, Kerstin Ute (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: One potential pathomechanism how low nephron number leads to hypertension in later life is altered salt handling. We therefore evaluated changes in electrolyte and water content in wildtype (wt) and GDNF+/- mice with a 30% reduction of nephron number. METHODS: 32 GDNF+/- and 36 wt mice were fed with low salt (LSD, 0.03%, normal drinking water) or high salt (HSD, 4%, 0.9% drinking water) diet for 4 weeks. Blood pressure was continuously measured by telemetry in a subgroup. At the end of the experiment and after standardized ashing processes electrolyte- and water contents of the skin and the total body were determined. RESULTS: We found higher blood pressure in high salt treated GDNF+/-compared to wt mice. Of interest, we could not confirm an increase in total-body sodium as predicted by prevailing explanations, but found increased total body and skin chloride that interestingly correlated with relative kidney weight. CONCLUSION: We hereby firstly report significant total body and skin chloride retention in salt sensitive hypertension of GDNF+/-mice with genetically determined lower nephron number. Thus, in contrast to the prevailing opinion our data argue for the involvement of non-volume related mechanisms.
EVALuna2:34423

Modeling Hemolytic-Uremic Syndrome: In-Depth Characterization of Distinct Murine Models Reflecting Different Features of Human Disease - Dennhardt, Sophie; Pirschel, Wiebke; Wissuwa, Bianka; Daniel, Christoph; Gunzer, Florian; Lindig, Sandro; Medyukhina, Anna; Kiehntopf, Michael; Rudolph, Wolfram W.; Zipfel, Peter F.; Gunzer, Matthias; Figge, Marc Thilo; et al. (Frontiers in Immunology, 2018)
Diarrhea-positive hemolytic-uremic syndrome (HUS) is a renal disorder that results from infections with Shiga-toxin (Stx)-producing Escherichia coli. The aim of this study was to establish well-defined refined murine models of HUS that can serve as preclinical tools to elucidate molecular mechanisms of disease development. C57BL/6J mice were subjected to different doses of Stx2 purified from an E. coli O157:H7 patient isolate. Animals received 300 ng/kg Stx2 and were sacrificed on day 3 to establish an acute model with fast disease progression. Alternatively, mice received 25 ng/kg Stx2 on days 0, 3, and 6, and were sacrificed on day 7 to establish a subacute model with moderate disease progression. Indicated by a rise in hematocrit, we observed dehydration despite volume substitution in both models, which was less pronounced in mice that underwent the 7-day regime. Compared with sham-treated animals, mice subjected to Stx2 developed profound weight loss, kidney dysfunction (elevation of plasma urea, creatinine, and neutrophil gelatinase-associated lipocalin), kidney injury (tubular injury and loss of endothelial cells), thrombotic microangiopathy (arteriolar microthrombi), and hemolysis (elevation of plasma bilirubin, lactate dehydrogenase, and free hemoglobin). The degree of complement activation (C3c deposition), immune cell invasion (macrophages and T lymphocytes), apoptosis, and proliferation were significantly increased in kidneys of mice subjected to the 7-day but not in kidneys of mice subjected to the 3-day regime. However, glomerular and kidney volume remained mainly unchanged, as assessed by 3D analysis of whole mount kidneys using CD31 staining with light sheet fluorescence microscopy. Gene expression analysis of kidneys revealed a total of only 91 overlapping genes altered in both Stx2 models. In conclusion, we have developed two refined mouse models with different disease progression, both leading to hemolysis, thrombotic microangiopathy, and acute kidney dysfunction and damage as key clinical features of human HUS. While intrarenal changes (apoptosis, proliferation, complement deposition, and immune cell invasion) mainly contribute to the pathophysiology of the subacute model, prerenal pathomechanisms (hypovolemia) play a predominant role in the acute model. Both models allow the further study of the pathomechanisms of most aspects of human HUS and the testing of distinct novel treatment strategies.
EVALuna2:34424

Molecular diagnosis of kidney transplant failure based on urine - Wiesener, Antje; Knaup, Karl; Büttner-Herold, Maike; Dieterle, Anne; Stoeckert, Johanna; Riedl, Bernhard; Morath, Christian; Wald, Alexandra; Vondran, Florian; Braun, Felix; Schödel, Johannes; Schüler, Markus; et al. (American Journal of Transplantation, 2020)
In light of the organ shortage, there is a great responsibility to assess postmortal organs for which procurement has been consented and to increase the life span of transplanted organs. The former responsibility has moved many centers to accept extended criteria organs. The latter responsibility requires an exact diagnosis and, if possible, omission of the harmful influence on the transplant. We report the course of a kidney transplant that showed a steady decline of function over a decade, displaying numerous cysts of different sizes. Clinical workup excluded the most frequent causes of chronic transplant failure. The filed allocation documents mentioned the donor's disease of oral-facial-digital syndrome, a rare ciliopathy, which can also affect the kidney. Molecular diagnosis was performed by culturing donor tubular cells from the recipient ' s urine more than 10 years after transplantation. Next-generation panel sequencing with DNA from tubular urinary cells revealed a novel truncating mutation in OFD1, which sufficiently explains the features of the kidney transplants, also found in the second kidney allograft. Despite this severe donor disease, lifesaving transplantation with good long-term outcome was enabled for 5 recipients.
CRIS-Team WoS Importer:2020-01-31

MOLECULAR DIAGNOSIS OF KIDNEY TRANSPLANT FAILURE BY THE URINE - Knaup, Karl; Wiesener, A.; Buettner-Herold, M.; Dieterle, A.; Morath, C.; Vondran, F. W. R.; Wald, A.; Braun, F.; Schüler, Markus; Schödel, Johannes; Schiffer, Mario; Reis, André; et al. (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

Molecular weight and molar substitution are more important in HES-induced renal impairment than concentration after hemorrhagic and septic shock - Simon, T P; Thiele, C; Schuerholz, T; Fries, M; Stadermann, F; Haase, G; Amann, Kerstin Ute; Marx, G (Minerva Anestesiologica, 2015)
Clinical studies have raised concerns about the safety of 6% hydroxyethylstarch (HES) 130/0.42, but the pathomechanisms of this renal impairment remain unknown. To evaluate the effects of different HES concentrations, molar substitutions and molecular weights in HES-induced renal impairment, we used a porcine two-hit model that combined haemorrhagic and septic shock.We conducted a prospective, randomised, double-blinded, controlled study in a university animal laboratory. Thirty anaesthetised and ventilated pigs were randomised to receive volume replacement therapy using 6% HES130/0.42, 6% HES200/0.5, 10% HES130/0.42 or 10% HES200/0.5, all dissolved in 0.9% NaCl rather than 0.9% NaCl alone. First, we bled the animals until they reached half of their baseline mean arterial pressure (MAP) for 45 minutes followed by fluid resuscitation. As a second hit, sepsis was induced using an Escherichia coli-laden clot 6 hours after haemorrhagic shock. Volume resuscitation started with a delay of two hours and a central venous pressure goal of 12 mmHg.At the end of the study, the groups showed no difference in cardiac output or MAP, but the volume balance (mL/kg BW) was significantly higher in the 0.9% NaCl group (346±90; P<=0.05) than in the other groups (6% HES130, 125±26; 6% HES200, 105±15; 10% HES130, 114±17; 10% HES200, 96±23). Creatinine clearance (mL/min) was significantly lower in the 6% HES200 (26±33) and 10% HES200 (15±18) groups compared to the 0.9% NaCl group (104±46; P<=0.05) but not in the HES 130 formulations (6% HES130: 64±51; 10% HES130: 58±38) at the end of the study.In this porcine two-hit shock model, treatment with 0.9% NaCl, HES 130/0.42 or HES 200/0.5 led to a similar maintenance of haemodynamic values. Despite this similar maintenance of the haemodynamic values, volume replacement with 6% and 10% HES 200/0.5 led to an accumulation of HES, higher colloid osmotic pressure and significantly reduced renal function after haemorrhagic and septic shock. These facts support the presumption that not the concentration but the degree of substitution and the molecular weight play a decisive role in HES-induced renal impairment.
EVALuna2:25475

MONITORING OF GENERAL IMMUNE STATUS AND SARS-COV-2 REACTIVE T-CELL AND HUMORAL IMMUNITY FACILITATES THE CLINICAL DECISION IN A SEVERE SARS-COV-2-ASSOCIATED PNEUMONIA, MENINGOENCEPHALITIS AND GASTROENTERITIS IN A PANCREAS-KIDNEY TRANSPLANT PATIENT - Babel, N.; Stervbo, U.; Seibert, F.; Bauer, F.; Anft, M.; Rohn, B.; Winnekendonk, G.; Dittmer, U.; Schenker, P.; Amann, Kerstin Ute; Viebahn, R.; Westhoff, T. (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

Multiplex gene analysis reveals T-cell and antibody-mediated rejection-specific upregulation of complement in renal transplants - Vonbrunn, Eva; Ries, Tajana; Söllner, Stefan; Müller-Deile, Janina; Büttner, Maike; Amann, Kerstin Ute; Daniel, Christoph (Scientific Reports, 2021)
In renal transplantation, complement is involved in ischemia reperfusion injury, graft rejection and dysfunction. However, it is still unclear how induction of complement and its activation are initiated. Using allograft biopsies of a well-characterized cohort of 28 renal transplant patients with no rejection (Ctrl), delayed graft function (DGF), acute T-cell-mediated (TCMR) or antibody-mediated rejection (ABMR) we analyzed differences in complement reaction. For that mRNA was isolated from FFPE sections, quantified with a multiplex gene expression panel and correlated with transplant conditions and follow-up of patients. Additionally, inflammatory cells were quantified by multiplex immunohistochemistry. In allograft biopsies with TCMR and ABMR gene expression of C1QB was 2-4 fold elevated compared to Ctrl. In TCMR biopsies, mRNA counts of several complement-related genes including C1S, C3, CFB and complement regulators CFH, CR1 and SERPING1 were significantly increased compared to Ctrl. Interestingly, expression levels of about 75% of the analyzed complement related genes correlated with cold ischemia time (CIT) and markers of inflammation. In conclusion, this study suggest an important role of complement in transplant pathology which seems to be at least in part triggered by CIT. Multiplex mRNA analysis might be a useful method to refine diagnosis and explore new pathways involved in rejection.
CRIS-Team Scopus Importer:2021-08-13

Mutations in the leukemia inhibitory factor receptor (LIFR) gene and Lifr deficiency cause urinary tract malformations - Kosfeld, Anne; Brand, Frank; Weiss, Anna-Carina; Kreuzer, Martin; Goerk, Michaela; Martens, Helge; Schubert, Stephanie; Schaefer, Anne-Kathrin; Riehmer, Vera; Hennies, Imke; Braesen, Jan Hinrich; Pape, Lars; et al. (Human Molecular Genetics, 2017)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are the most common cause of chronic kidney disease in children. As CAKUT is a genetically heterogeneous disorder and most cases are genetically unexplained, we aimed to identify new CAKUT causing genes. Using whole-exome sequencing and trio-based de novo analysis, we identified a novel heterozygous de novo frameshift variant in the leukemia inhibitory factor receptor (LIFR) gene causing instability of the mRNA in a patient presenting with bilateral CAKUT and requiring kidney transplantation at one year of age. LIFR encodes a transmembrane receptor utilized by IL-6 family cytokines, mainly by the leukemia inhibitory factor (LIF). Mutational analysis of 121 further patients with severe CAKUT yielded two rare heterozygous LIFR missense variants predicted to be pathogenic in three unrelated patients. LIFR mutants showed decreased half-life and cell membrane localization resulting in reduced LIF-stimulated STAT3 phosphorylation. LIFR showed high expression in human fetal kidney and the human ureter, and was also expressed in the developing murine urogenital system. Lifr knockout mice displayed urinary tract malformations including hydronephrosis, hydroureter, ureter ectopia, and, consistently, reduced ureteral lumen and muscular hypertrophy, similar to the phenotypes observed in patients carrying LIFR variants. Additionally, a form of cryptorchidism was detected in all Lifr-/- mice and the patient carrying the LIFR frameshift mutation. Altogether, we demonstrate heterozygous novel or rare LIFR mutations in 3.3% of CAKUT patients, and provide evidence that Lifr deficiency and deactivating LIFR mutations cause highly similar anomalies of the urogenital tract in mice and humans.
EVALuna2:25536

Mutations in WDR19 encoding the intraflagellar transport component IFT144 cause a broad spectrum of ciliopathies - Fehrenbach, Henry; Decker, Christian; Eisenberger, Tobias; Frank, Valeska; Hampel, Tobias; Walden, Ulrike; Amann, Kerstin Ute; Krueger-Stollfuss, Ingrid; Bolz, Hanno J.; Haeffner, Karsten; Pohl, Martin; Bergmann, Carsten (Pediatric Nephrology, 2014)
An emerging number of clinically and genetically heterogeneous diseases now collectively termed ciliopathies have been connected to the dysfunction of primary cilia. We describe an 8-year-old girl with a complex phenotype that did not clearly match any familiar syndrome.Hypotonia, facial dysmorphism and retardation were noted shortly after birth. Other features included short stature, mild skeletal anomalies, strabism, deafness, subdural hygroma, hepatosplenomegaly and end-stage renal failure. Renal biopsy revealed tubular atrophy, interstitial fibrosis and segmental glomerulosclerosis. After exclusion of a chromosomal abnormality by array-comparative genomic hybridization (CGH), we performed next-generation sequencing (NGS) using a customized panel that targeted 131 genes known or hypothesized to cause ciliopathies. We identified the novel homozygous WDR19 mutation c.1483G > C (p.Gly495Arg) that affects an evolutionarily highly conserved residue in the intraflagellar transport protein IFT144, is absent from databases and is predicted to be pathogenic by all bioinformatic sources used.Mutations in WDR19 encoding the intraflagellar transport component IFT144 have recently been described in single families with the clinically overlapping skeletal ciliopathies Jeune and Sensenbrenner syndromes, combined or isolated nephronophthisis (NPHP) and retinitis pigmentosa (RP) (Senior-Loken syndrome). Our patient emphasizes the usefulness and efficiency of a comprehensive NGS panel approach in patients with unclassified ciliopathies. It further suggests that WDR19 mutations can cause a broad spectrum of ciliopathies that extends to Jeune and Sensenbrenner syndromes, RP and renal NPHP-like phenotypes.
EVALuna2:25461

Myocardial infarction with a preserved ejection fraction—the impaired function of the cardio-renal baroreflex - Pickny, Lisa; Hindermann, Martin; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Frontiers in Physiology, 2023)
Introduction: In experimental myocardial infarction with reduced ejection fraction causing overt congestive heart failure, the control of renal sympathetic nerve activity (RSNA) by the cardio-renal baroreflex was impaired. The afferent vagal nerve activity under these experimental conditions had a lower frequency at saturation than that in controls. Hence, by investigating respective first neurons in the nodose ganglion (NG), we wanted to test the hypothesis that after myocardial infarction with still-preserved ejection fraction, the cardiac afferent nerve pathway is also already impaired. Material and methods: A myocardial infarction was induced by coronary artery ligature. After 21 days, nodose ganglion neurons with cardiac afferents from rats with myocardial infarction were cultured. A current clamp was used to characterize neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., <5 APs upon current injection. Cardiac ejection fraction was measured using echocardiography; RSNA was recorded to evaluate the sensitivity of the cardiopulmonary baroreflex. Renal and cardiac histology was studied for inflammation and fibrosis markers. Results: A total of 192 neurons were investigated. In rats, after myocardial infarction, the number of neurons with a tonic response pattern increased compared to that in the controls (infarction vs. control: 78.6% vs. 48.5%; z-test, *p < 0.05), with augmented production of APs (23.7 ± 2.86 vs. 15.5 ± 1.86 APs/600 ms; mean ± SEM, t-test, *p < 0.05). The baseline activity of RSNA was subtly increased, and its control by the cardiopulmonary baroreflex was impaired following myocardial infarction: the fibrosis marker collagen I augmented in the renal interstitium. Discussion: After myocardial infarction with still-preserved ejection fraction, a complex impairment of the afferent limb of the cardio-renal baroreflex caused dysregulation of renal sympathetic nerve activity with signs of renal fibrosis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: cardiac afferent neurons after myocardial infarction cardiac afferent innervation; congestive heart failure; myocardial infarction; neuronal cell culture; preserved ejection fraction; renal innervation

Nebenwirkungen neuer onkologischer Immuntherapien - Braun, G. S.; Kirschner, M.; Ruebben, A.; Wahl, R. U.; Amann, Kerstin Ute; Benesova, K.; Leipe, J. (Nephrologe, 2020)
Systemic treatment with immune checkpoint inhibitors (ICI) has revolutionized the treatment of hematological and oncological diseases in recent years. The mechanism of action hinges on enhancing the natural ability of the immune system to eliminate malignant cells. The most important substances in this arena include inhibitors of PD-1, PD-L1 and CTLA-4. As a consequence, the spectrum of treatment-associated adverse reactions is shifting away from classical cytotoxic effects (e.g. pancytopenia and polyneuropathy) towards novel entities of immune-mediated complex diseases. These so-called immune-related adverse events (irAEs) can involve any organ system and mimic known classical autoimmune conditions. Timely recognition of irAEs is the key for rapid initiation of a suitable treatment and is especially challenging in the clinical routine as it requires an intensive interdisciplinary management. Nephrologists are particularly confronted with this kind of problem due to the highly interdisciplinary nature of their work. This article summarizes the broad spectrum of currently known renal and more frequently occuring non-renal forms of irAEs and aims to prime the reader on diagnostic and therapeutic options.
CRIS-Team WoS Importer:2020-05-15

Nephron-specific knockout of TMEM16A leads to reduced number of glomeruli and albuminuria - Schenk, Laura K.; Buchholz, Björn; Henke, Sebastian F.; Michgehl, Ulf; Daniel, Christoph; Amann, Kerstin Ute; Kunzelmann, Karl; Pavenstaedt, Hermann (American Journal of Physiology-Renal Physiology, 2018)
TMEM16A is a transmembrane protein from a conserved family of calcium activated proteins, which is highly expressed in the kidney. TMEM16A confers calcium-activated chloride channel activity which is of importance for various cellular functions in secretory epithelia and involved in secretion-dependent renal cyst growth. However, its specific function in renal physiology has remained elusive so far. Therefore we generated conditional nephron specific TMEM16A knockout mice and found that these animals suffered from albuminuria. Kidney histology demonstrated an intact corticomedullary differentiation and absence of cysts. Electron microscopy showed a normal slit diaphragm. However, the total number of glomeruli and total nephron count was decreased in TMEM16A knockout animals. At the same time, glomerular diameter was increased, presumably as a result of the hyperfiltration in the remaining glomeruli. TUNEL and PCNA stainings showed increased cell death and increased proliferation. Proximal tubular cilia were intact in young animals but the number of properly ciliated cells was decreased in older, albuminuric animals. Taken together, our data suggests that TMEM16A may be involved in ureteric bud branching and proper nephron endowment. Loss of TMEM16A resulted in reduced nephron number and, subsequently, albuminuria and tubular damage.
EVALuna2:35395
Keywords: albuminuria; Ano1; kidney; nephron number; TMEM16A

Nephropathologie - Amann, Kerstin Ute; Wolf, G. (Nephrologe, 2019)
CRIS-Team Scopus Importer:2019-05-03

Nephropathologie infektiöser Erkrankungen - Büttner-Herold, Maike; Amann, Kerstin Ute; Velden, Joachim (Die Pathologie, 2024)
Infections can affect the kidney via different pathways. Urinary tract infections can directly involve the renal tissue by spreading along pre-existing canalicular structures. Such an ascending infection can manifest as a highly active and purulent or even abscessing interstitial nephritis or as a chronic-fibrosing process in recurrent pyelonephritis. Viral infections can also use the canalicular route as in polyomavirus nephropathy or spread via the blood stream in a hematogenous manner as in the case of cytomegalovirus or hantavirus infections. Likewise, bacterial infections can reach the kidney via the blood in the case of systemic infection. Another large group of nephropathies taking place as a sequel of infections includes infection-related glomerulonephritides (IRGN), which are mediated by a series of immunological mechanisms. These IRGN can be subdivided according to their temporal association with the infectious process, occurring either after the infection has healed (postinfectious) or accompanying the ongoing infectious process (parainfectious). The latter, in particular, is of increasing importance in the daily practice of nephropathologists, especially in older patients. A number of other glomerulonephritis forms, i.e., membranous or membranoproliferative forms, can occur as a consequence of infection. In addition, infections can trigger nephropathies, such as thrombotic microangiopathy. The present article gives an overview of morphologic changes in renal parenchyma that take place as a consequence of infectious processes, with particular focus on IRGN.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Immune complex; Infection-related glomerulonephritis; Path of infection; Pathogen spectrum; Urinary tract infection

Nephropathology Nephropathologie - Wolf, Gunter; Amann, Kerstin Ute (Die Nephrologie, 2022)
CRIS-Team Scopus Importer:2024-12-16

Nephropathy in illicit drug abusers: a postmortem analysis - Büttner, Maike; Toennes, Stefan W.; Buettner, Stefan; Bickel, Markus; Allwinn, Regina; Geiger, Helmut; Bratzke, Hansjuergen; Amann, Kerstin Ute; Jung, Oliver (American Journal of Kidney Diseases, 2014)
Illicit drug abuse is an independent risk factor for chronic kidney disease, but the pathogenic consequences of long-term exposure to illicit drugs and contaminants under unsterile conditions remains unclear.Case series.All deceased persons (n 5 129) who underwent forensic autopsy because of suspected connection with illicit drug abuse between January 1, 2009, and April 30, 2011, in Frankfurt/Main, Germany.Clinical characteristics and patterns of drug abuse.Histopathologic alterations of the kidney.Hematoxylin and eosin, periodic acid-Schiff, Sirius, and Congo Red stainings and immunoglobulin A immunohistochemistry of all cases; additional histochemical stainings or immunohistochemistry and electron microscopy in selected cases.Individuals were mostly white (99.2%), were male (82.2%), and had intravenous drug use (IVDU) (81.4%). Median age at death was 39 years and duration of drug abuse was 17 years. The majority (79.1%) took various drugs in parallel as assessed by toxicologic analysis. Despite a young age, the deceased had a high burden of comorbid conditions, especially cardiovascular disease, liver cirrhosis, and infections. Evaluation of the kidneys demonstrated a broad spectrum of pathologic alterations predominated by arteriosclerotic and ischemic damage, mild interstitial inflammation, calcification of renal parenchyma, and interstitial fibrosis and tubular atrophy, with hypertensive-ischemic nephropathy as the most common cause of nephropathy. Interstitial inflammation (OR, 16.59; 95% CI, 3.91-70.39) and renal calcification (OR, 2.43; 95% CI, 1.03- 5.75) were associated with severe IVDU, whereas hypertensive and ischemic damage were associated with cocaine abuse (OR, 6.00; 95% CI, 1.27-28.44). Neither specific glomerular damage indicative for heroin and hepatitis C virus-related disease nor signs of analgesic nephropathy were found.White population, lack of a comparable control group, incomplete clinical data, and absence of routine immunohistochemistry and electron microscopy.Illicit drug abuse is associated with a broad but unspecific spectrum of pathologic alterations of the kidneys. Cocaine abuse has a deleterious role in this setting by promoting hypertensive and ischemic damage.
EVALuna2:25464

Nephrotic syndrome in antibody deficiency syndrome in CLL - Strutz, Frank; Amann, Kerstin Ute; Wittmann, Gertraud; Beck, Joachim (Die Nephrologie, 2022)
CRIS-Team WoS Importer:2022-12-16

Nephrotisches Syndrom nach COVID-19-Impfung: Drei neue Fälle aus Deutschland - Dormann, Harald; Knüppel-Ruppert, Anja; Amann, Kerstin Ute; Erley, Christiane (Deutsches Ärzteblatt international, 2021)
CRIS-Team Scopus Importer:2021-10-29

Neurogenic substance P-influences on action potential production in afferent neurons of the kidney? - Rodionova, Kristina; Hilgers, Karl Friedrich; Linz, Peter; Schaetzl, Johannes; Raschke, Giulia; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2021)
We recently showed that a substance P (SP)-dependent sympatho-inhibitory mechanism via afferent renal nerves is impaired in mesangioproliferative nephritis. Therefore, we tested the hypothesis that SP released from renal afferents inhibits the action potential (AP) production in their dorsal root ganglion (DRG) neurons. Cultured DRG neurons (Th11-L2) were investigated in current clamp mode to assess AP generation during both TRPV1 stimulation by protons (pH 6) and current injections with and without exposure to SP (0.5 mu mol) or CGRP (0.5 mu mol). Neurons were classified as tonic (sustained AP generation) or phasic (<= 4 APs) upon current injection; voltage clamp experiments were performed for the investigation of TRPV1-mediated inward currents due to proton stimulation. Superfusion of renal neurons with protons and SP increased the number of action potentials in tonic neurons (9.6 +/- 5 APs/10 s vs. 16.9 +/- 6.1 APs/10 s, P < 0.05, mean +/- SD, n = 7), while current injections with SP decreased it (15.2 +/- 6 APs/600 ms vs. 10.2 +/- 8 APs/600 ms, P < 0.05, mean +/- SD, n = 29). Addition of SP significantly reduced acid-induced TRPV1-mediated currents in renal tonic neurons (- 518 +/- 743 pA due to pH 6 superfusion vs. - 82 +/- 50 pA due to pH 6 with SP superfusion). In conclusion, SP increased action potential production via a TRPV1-dependent mechanism in acid-sensitive renal neurons. On the other hand, current injection in the presence of SP led to decreased action potential production. Thus, the peptide SP modulates signaling pathways in renal neurons in an unexpected manner leading to both stimulation and inhibition of renal neuronal activity in different (e.g., acidic) environmental contexts.
CRIS-Team WoS Importer:2021-04-16

Neurogenic tachykinin mechanisms in experimental nephritis of rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Paulus, Eva-Maria; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2020)
We demonstrated earlier that renal afferent pathways combine very likely "classical" neural signal transduction to the central nervous system and a substance P (SP)-dependent mechanism to control sympathetic activity. SP content of afferent sensory neurons is known to mediate neurogenic inflammation upon release. We tested the hypothesis that alterations in SP-dependent mechanisms of renal innervation contribute to experimental nephritis. Nephritis was induced by OX-7 antibodies in rats, 6 days later instrumented for recording of blood pressure (BP), heart rate (HR), drug administration, and intrarenal administration (IRA) of the TRPV1 agonist capsaicin to stimulate afferent renal nerve pathways containing SP and electrodes for renal sympathetic nerve activity (RSNA). The presence of the SP receptor NK-1 on renal immune cells was assessed by FACS. IRA capsaicin decreased RSNA from 62.4 +/- 5.1 to 21.6 +/- 1.5 mV s (*p < 0.05) in controls, a response impaired in nephritis. Suppressed RSNA transiently but completely recovered after systemic administration of a neurokinin 1 (NK1-R) blocker. NK-1 receptors occurred mainly on CD11(+)dendritic cells (DCs). An enhanced frequency of CD11c(+)NK1R(+)cell, NK-1 receptor(+)macrophages, and DCs was assessed in nephritis. Administration of the NK-1R antagonist aprepitant during nephritis reduced CD11c(+)NK1R(+)cells, macrophage infiltration, renal expression of chemokines, and markers of sclerosis. Hence, SP promoted renal inflammation by weakening sympathoinhibitory mechanisms, while at the same time, substance SP released intrarenally from afferent nerve fibers aggravated immunological processes i.e. by the recruitment of DCs.
CRIS-Team WoS Importer:2020-11-06

Next generation sequencing and functional analysis of patient urine renal progenitor-derived podocytes to unravel the diagnosis underlying refractory lupus nephritis - Romagnani, Paola; Giglio, Sabrina; Angelotti, Maria Lucia; Provenzano, Aldesia; Becherucci, Francesca; Mazzinghi, Benedetta; Mueller, Susanna; Amann, Kerstin Ute; Weidenbusch, Marc; Romoli, Simone; Lazzeri, Elena; Anders, Hans-Joachim (Nephrology Dialysis Transplantation, 2016)
Often the cause of refractory lupus nephritis (RLN) remains unclear. We performed next-generation sequencing for podocyte genes in an RLN patient and identified compound heterozygosity for APOL1 risk alleles G1 and G2 and a novel homozygous c.[1049C>T]+[1049C>T] NPHS1 gene variant of unknown significance. To test for causality renal progenitor cells isolated from urine of this patient were differentiated into podocytes in vitro. Podocytes revealed aberrant nephrin trafficking, cytoskeletal structure and lysosomal leakage, and increased detachment as compared with podocytes isolated from controls. Thus, lupus podocytopathy can be confirmed as a cause of RLN by functional genetics on patient-derived podocytes.
EVALuna2:25516

Nierenbeteiligung bei Kollagenosen - Teil 1: Lupus-Nephritis - Oelzner, Peter; Amann, Kerstin Ute; Wolf, Gunter (Aktuelle Rheumatologie, 2020)
Lupus nephritis (LN) occurs dependent on ethnicity and gender in up to 50% of patients with systemic lupus erythematosus (SLE) and represents the prognostic most important organ manifestation in SLE. Pathogenetic important aspects of SLE are a multifactorial caused disturbance of the clearance of autoantigen released in the context of apoptosis and NETosis resulting in the development of autoimmune reaction, an amplification of the pathologic immune reaction by hyperactivation of type I-interferon signaling and cytokine imbalance. The pathogenetic process in the kidney results in immune complex glomerulonephritis. Early diagnosis and initiation of therapy are of critical importance for the prognosis of LN. The selection of therapy is based principally on the findings in renal biopsy. In the case of proliferative LN (class III or IV, also in combination with membranous LN) a remission induction with low-dose cyclophosphamide (CYC)-pulse therapy (6 x 500 mg) or with mycophenolatofetil (MMF) in combination with initial high dose glucocorticoids (GC) is followed by a maintenance therapy with azathioprine or MMF. In refractory situations a switch from CYC to MMF or conversely is indicated. Alternatively rituximab or calcineurin inhibitors can also be used. In other forms of LN the therapeutic procedure is essentially determinated by the course of renal function and the extent of proteinuria. In addition supportive procedures such as the general use of hydroxychloroquine, ACE inhibitors or angiotensin rezeptor blockers in dependence of the extent of proteinuria and of blood pressure and prophylactic measures to prevent thromboembolism, osteoporosis and infections come into use. Aims of therapy are a preferably complete renal remission, prevention of chronic damage and an effective reduction of GC dose. A complete remission which is defined by the preservation of normal renal function and a substantial reduction of proteinuria is achieved in approximately 50-60%. This underlines the effectiveness of the curent therapy on one hand but illuminates the need of new therapeutic strategies on the other, especially in view of the high rate of damage. New therapeutic approaches such multitarget therapy, new protocolls of B cell depletion and B cell neutralization and GC free treatment principles aim at a more effective and side effect poor therapy of LN.
CRIS-Team Scopus Importer:2020-04-21
Keywords: Lupus nephritis; pathogenesis; therapy

Nierenbeteiligung bei Kollagenosen – Teil 2: Antiphospholipid-Syndrom, primäres Sjögren-Syndrom, systemische Sklerose - Oelzner, Peter; Amann, Kerstin Ute; Wolf, Gunter (Aktuelle Rheumatologie, 2020)
Renal manifestations in antiphospholipid syndrome (APS), primary Sjögren?s syndrome (pSS) and systemic sclerosis (SSc) differ from each other substantially with respect to pathogenesis, histology, clinical picture, prognosis and therapeutic consequences. The frequency of APS-associated renal affections ranges from 10 to 40%. APS can affect the kidney in the form of renal hypertension, thrombosis or stenosis of the renal artery, renal infarction, thrombosis of the renal vein and intrarenal vasculopathy (APS nephropathy). Especially in the case of secondary APS, the differential diagnosis of lupus nephritis by renal biopsy is important because APS requires anticoagulation, but generally no immunosuppression. In pSS, too, renal affections are relatively common (20-40%). The characteristic and most frequent manifestation is interstitial nephritis with distal tubular acidosis type 1. Distal tubular acidosis is often asymptomatic, but can result in hypokalaemia and osteomalacia. Whereas interstitial nephritis and the less frequent glomerulonephritis generally respond well to immunosuppression, the response of distal tubular acidosis to immunosuppression is insufficient. Decrease of renal function and proteinuria as a sign of renal affection are observed in up to 36% of patients with SSc. This type of nephropathy, often multifactorial in origin, is characterised by sclerosed glomeruli, tubular atrophy and interstitial fibrosis, and has a good prognosis with respect to renal function. Scleroderma renal crisis, which is characterised by obstructive vasculopathy, accelerated arterial hypertension and progressive renal failure, is substantially less frequent (4-11%). Risk factors for renal crisis in SSc involve the presence of diffuse cutaneous SSc, older age, male gender, glucocorticoid use, pericardial effusion and the presence of anti-RNA polymerase III antibodies. Therapy of hypertensive renal crisis aims to reduce the systolic blood pressure by 10% per day to the normal range, preferably with ACE inhibitors, while avoiding prolonged periods of hypotension. In the case of insufficient reduction of blood pressure despite ACE inhibitor therapy, alpha-blockers, calcium channel blockers and/or minoxidil are used in addition. Intravenous administration of prostacycline to improve renal perfusion and the use of the endothelin receptor antagonist bosentan are also useful. The availability of ACE inhibitors has resulted in a significant reduction of mortality due to renal crisis; however, a progression to end-stage renal disease is to be expected in 40-50%.
CRIS-Team Scopus Importer:2020-04-24
Keywords: connective tissue diseases; pathogenesis; renal involvement; therapy

Nierenerkrankungen bei HIV‑Infektion - Bestandsaufnahme nach fast 40 Jahren Erfahrung mit HIV - Rieke, A.; Amann, Kerstin Ute; Lutz, J. (Nephrologe, 2020)
Human immunodeficiency virus (HIV) infections are nowadays a treatable chronic disease with a nearly normal life expectation. Kidney diseases play an increasingly important role in these patients due to the direct and indirect effects of HIV on the kidneys in the form of HIV-associated nephropathy (HIVAN), secondary glomerulonephritis, chronic inflammation and the increasing age with corresponding comorbidities. In patients with HIVAN and secondary glomerulonephritis an antiretroviral therapy (ART) should be quickly initiated; however, ART requires a continuous surveillance of the renal function as some medications can accumulate with decreasing renal function and can even have nephrotoxic effects themselves.
CRIS-Team Scopus Importer:2020-06-16
Keywords: AIDS-associated nephropathy; Antiretroviral therapy; Fanconi syndrome; Tubular transporters; Tubulopathy

No benefit of HIF prolyl hydroxylase inhibition for hypertensive renal damage in renovascular hypertensive rats - Hartner, Andrea; Dambietz, Thomas; Cordasic, Nada; Willam, Carsten; Burzlaff, Nicolai; Brötsch, Martin; Daniel, Christoph; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Schley, Gunnar; Hilgers, Karl Friedrich (Frontiers in Physiology, 2023)
Introduction: We previously reported that malignant hypertension is associated with impaired capillary density of target organs. Here, we tested the hypothesis that stabilization of hypoxia-inducible factor (HIF) in a modified “preconditioning” approach prevents the development of malignant hypertension. To stabilize HIF, we employed pharmacological inhibition of HIF prolyl hydroxylases (PHD), that profoundly affect HIF metabolism. Methods: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats; controls were sham operated. 2K1C rats received either intermittent injections of the PHD inhibitor ICA (2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetate) or placebo. Thirty-five days after clipping, the frequency of malignant hypertension was assessed (based on weight loss and the occurrence of characteristic vascular lesions). In addition, kidney injury was compared between all ICA treated versus all placebo treated 2K1C, regardless of the occurrence of malignant hypertension. HIF stabilization was evaluated by immunohistochemistry, and HIF target gene expression by RT-PCR. Results: Blood pressure was elevated to the same degree in ICA- and placebo-treated 2K1C compared to control rats. ICA treatment did not affect the frequency of malignant hypertension or the extent of kidney tissue fibrosis, inflammation, or capillary density. There was a trend towards higher mortality and worse kidney function in ICA-treated 2K1C rats. ICA increased the number of HIF-1α-positive renal tubular cell nuclei and induced several HIF-1 target genes. In contrast, expression of HIF-2α protein as well as HIF-2 target genes were markedly enhanced by 2K1C hypertension, irrespective of ICA treatment. Discussion: We conclude that intermittent PHD inhibition did not ameliorate severe renovascular hypertension in rats. We speculate that the unexpected strong renal accumulation of HIF-2α in renovascular hypertension, which could not be further augmented by ICA, may contribute to the lack of a benefit from PHD inhibition.
CRIS-Team Scopus Importer:2023-07-21
Keywords: capillarization; HIF stabilization; malignant hypertension; renovascular; vascular lesions

No evidence of pathogenic involvement of cathelicidins in patient cohorts and mouse models of lupus and arthritis - Kienhofer, D.; Hahn, Jonas; Schubert, I.; Reinwald, Christiane; Ipseiz, N.; Lang, Sabine; Borras, E. Bosch; Amann, Kerstin Ute; Sjowall, C.; Barron, A. E.; Hueber, Axel; Agerberth, B.; et al. (PLoS ONE, 2014)
Apart from their role in the immune defence against pathogens evidence of a role of antimicrobial peptides (AMPs) in autoimmune diseases has accumulated in the past years. The aim of this project was to examine the functional impact of the human cathelicidin LL-37 and the mouse cathelicidin-related AMP (CRAMP) on the pathogenesis of lupus and arthritis. Serum LL-37 and anti-LL-37 levels were measured by ELISA in healthy donors and patients with Systemic Lupus Erythematosus (SLE) and Rheumatoid arthritis (RA). Pristane-induced lupus was induced in female wild type (WT) and cathelicidin-deficient (CRAMP-/-) mice. Serum levels of anti-Sm/RNP, anti-dsDNA, and anti-histone were determined via ELISA, cytokines in sera and peritoneal lavages were measured via Multiplex. Expression of Interferon I stimulated genes (ISG) was determined by real-time PCR. Collagen-induced arthritis (CIA) was induced in male WT and CRAMP-/- mice and arthritis severity was visually scored and analysed histomorphometrically by OsteoMeasure software. Serum levels of anti-LL-37 were higher in SLE-patients compared to healthy donors or patients with RA. However, no correlation to markers of disease activity or organ involvement was observed. No significant differences of autoantibody or cytokine/chemokine levels, or of expression of ISGs were observed between WT and CRAMP-/- mice after pristane-injection. Furthermore, lung and kidney pathology did not differ in the absence of CRAMP. Incidence and severity of CIA and histological parameters (inflammation, cartilage degradation, and bone erosion) were not different in WT and CRAMP-/- mice. Although cathelicidins are upregulated in mouse models of lupus and arthritis, cathelicidin-deficiency did not persistently affect the diseases. Also in patients with SLE, autoantibodies against cathelicidins did not correlate with disease manifestation. Reactivity against cathelicidins in lupus and arthritis could thus be an epiphenomenon caused by extensive overexpression in blood and affected tissues. In addition, other cationic AMPs could functionally compensate for the deficiency of cathelicidins.
EVALuna2:12499

No juvenile arterial hypertension in sheep multiples despite reduced nephron numbers - Muehle, Anja; Mühle, Christiane; Amann, Kerstin Ute; Dötsch, Jörg; Nuesken, Kai-Dietrich; Boltze, Johannes; Schneider, Holm (Pediatric Nephrology, 2010)
Low birth weight is associated with an increased risk of metabolic dysfunction and arterial hypertension in later life. Because of their reduced birth weight twins have been used repeatedly as a natural model to investigate prenatal programming of hypertension. To reveal an early impact of lower nephron endowment on blood pressure, we performed a longitudinal study on lambs from single, twin and triplet pregnancies. The lambs were studied from birth until adulthood, including regular blood analyses, measurements of body weight and blood pressure and post-mortem estimation of glomerular numbers. Relative weight differences between multiples and singletons at birth were -28% for twins and -44% for triplets, respectively. Some lambs showed rapid catch-up growth. Total nephron number of twins and triplets was reduced by 21 and 37% with respect to that of singletons (p∈<∈0.01). However, multiples did not show increased blood pressure within the time frame of this study. No gender-specific effect was observed. Plasma concentrations of creatinine, urea, electrolytes or osmolality also did not differ. Our data indicate that the previously reported postnatal blood pressure differences between sheep multiples and singletons are a time-limited phenomenon. During infancy and adolescence, a reduced nephron number in sheep multiples is neither associated with increased blood pressure nor reflected by plasma parameters. © 2010 IPNA.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Blood pressure; Nephron number; Prenatal programming

Non-Invasive Biomarkers for Diagnosis, Risk Prediction, and Therapy Guidance of Glomerular Kidney Diseases: A Comprehensive Review - Catanese, Lorenzo; Rupprecht, Harald; Huber, Tobias B.; Lindenmeyer, Maja T.; Hengel, Felicitas E.; Amann, Kerstin Ute; Wendt, Ralph; Siwy, Justyna; Mischak, Harald; Beige, Joachim (International Journal of Molecular Sciences, 2024)
Effective management of glomerular kidney disease, one of the main categories of chronic kidney disease (CKD), requires accurate diagnosis, prognosis of progression, assessment of therapeutic efficacy, and, ideally, prediction of drug response. Multiple biomarkers and algorithms for the assessment of specific aspects of glomerular diseases have been reported in the literature. Though, the vast majority of these have not been implemented in clinical practice or are not available on a global scale due to limited access, missing medical infrastructure, or economical as well as political reasons. The aim of this review is to compile all currently available information on the diagnostic, prognostic, and predictive biomarkers currently available for the management of glomerular diseases, and provide guidance on the application of these biomarkers. As a result of the compiled evidence for the different biomarkers available, we present a decision tree for a non-invasive, biomarker-guided diagnostic path. The data currently available demonstrate that for the large majority of patients with glomerular diseases, valid biomarkers are available. However, despite the obvious disadvantages of kidney biopsy, being invasive and not applicable for monitoring, especially in the context of rare CKD etiologies, kidney biopsy still cannot be replaced by non-invasive strategies.
CRIS-Team Scopus Importer:2024-04-05
Keywords: biomarker; CKD; diagnosis; glomerular diseases; kidney disease; prognosis; risk prediction

Obligatory role for GPER in cardiovascular aging and disease - Meyer, Matthias R.; Fredette, Natalie C.; Daniel, Christoph; Sharma, Geetanjali; Amann, Kerstin Ute; Arterburn, Jeffrey B.; Barton, Matthias; Prossnitz, Eric R. (Science Signaling, 2016)
Pharmacological activation of the heptahelical G protein-coupled estrogen receptor (GPER) by selective ligands counteracts multiple aspects of cardiovascular disease. We thus expected that genetic deletion or pharmacological inhibition of GPER would further aggravate such disease states, particularly with age. To the contrary, we found that genetic ablation of Gper in mice prevented cardiovascular pathologies associated with aging by reducing superoxide (?O2(-)) formation by NADPH oxidase (Nox) specifically through reducing the expression of the Nox isoform Nox1 Blocking GPER activity pharmacologically with G36, a synthetic, small-molecule, GPER-selective blocker (GRB), decreased Nox1 abundance and ?O2(-) production to basal amounts in cells exposed to angiotensin II and in mice chronically infused with angiotensin II, reducing arterial hypertension. Thus, this study revealed a role for GPER activity in regulating Nox1 abundance and associated ?O2(-)-mediated structural and functional damage that contributes to disease pathology. Our results indicated that GRBs represent a new class of drugs that can reduce Nox abundance and activity and could be used for the treatment of chronic disease processes involving excessive ?O2(-) formation, including arterial hypertension and heart failure.
EVALuna2:25526

Only IF/TA in the Histological Evaluation of Post-Reperfusion Baseline Biopsies Correlates With Kidney Transplant Outcome. - Bachmann, Quirin; Torrez, Carlos; Büttner-Herold, Maike; Haller, Bernhard; Haberfellner, Flora; Hausinger, Renate; Assfalg, Volker; Renders, Lutz; Amann, Kerstin Ute; Heemann, Uwe; Schmaderer, Christoph; Kemmner, Stephan (Transplant International, 2025)
Here, we retrospectively evaluated the informational yield of 338 post-reperfusion kidney transplant biopsies (including 95 living donations) assessed according to BANFF for the histological characteristics interstitial fibrosis and tubular atrophy (IF/TA), glomerulosclerosis, arteriosclerosis, and acute tubular injury (ATI). Associations with delayed graft function (DGF) and death-censored graft survival were explored through Cox-regression analyses. The maximum follow-up time was 11.4 years, with DGF observed in 108 (32%) cases. After deceased donation there was no association between DGF and histologic parameters. Univariable Cox-regression unveiled an association of IF/TA and glomerulosclerosis with long-term death-censored graft survival (HR per 10% increase: IF/TA 1.63; 95% CI 1.17-2.28; p = 0.003; glomerulosclerosis 1.19; 95% CI 1.01-1.39; p = 0.031). In multivariable Cox regression analyses, adjusted for recognized clinical risk variables like expanded criteria donor-status, donor age, history of diabetes, and HLA-mismatches, only IF/TA maintained association over the total observation period in deceased donations and in the total cohort. Arteriosclerosis and ATI were not associated with clinical outcome after deceased donation. Especially ATI did not affect delayed graft function if only deceased donations were considered. Our data underlines the role of organ quality for transplant outcome prior to acute lesions such as ATI during the transplantation process.
EVALuna2:583979

Organ manifestations of COVID-19: what have we learned so far (not only) from autopsies? - Jonigk, Danny; Werlein, Christopher; Acker, Till; Aepfelbacher, Martin; Amann, Kerstin Ute; Baretton, Gustavo; Barth, Peter; Bohle, Rainer M.; Buettner, Andreas; Buettner, Reinhard; Dettmeyer, Reinhard; Eichhorn, Philip; et al. (Virchows Archiv, 2022)
The use of autopsies in medicine has been declining. The COVID-19 pandemic has documented and rejuvenated the importance of autopsies as a tool of modern medicine. In this review, we discuss the various autopsy techniques, the applicability of modern analytical methods to understand the pathophysiology of COVID-19, the major pathological organ findings, limitations or current studies, and open questions. This article summarizes published literature and the consented experience of the nationwide network of clinical, neuro-, and forensic pathologists from 27 German autopsy centers with more than 1200 COVID-19 autopsies. The autopsy tissues revealed that SARS-CoV-2 can be found in virtually all human organs and tissues, and the majority of cells. Autopsies have revealed the organ and tissue tropism of SARS-CoV-2, and the morphological features of COVID-19. This is characterized by diffuse alveolar damage, combined with angiocentric disease, which in turn is characterized by endothelial dysfunction, vascular inflammation, (micro-) thrombosis, vasoconstriction, and intussusceptive angiogenesis. These findings explained the increased pulmonary resistance in COVID-19 and supported the recommendations for antithrombotic treatment in COVID-19. In contrast, in extra-respiratory organs, pathological changes are often nonspecific and unclear to which extent these changes are due to direct infection vs. indirect/secondary mechanisms of organ injury, or a combination thereof. Ongoing research using autopsies aims at answering questions on disease mechanisms, e.g., focusing on variants of concern, and future challenges, such as post-COVID conditions. Autopsies are an invaluable tool in medicine and national and international interdisciplinary collaborative autopsy-based research initiatives are essential.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Acute kidney damage; Diffuse alveolar damage; Immune response; SARS-CoV-2

Osteoclastic expression of higher-level regulators NFATc1 and BCL6 in medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy: a comparison with osteoradionecrosis and osteomyelitis - Wehrhan, Falk; Gross, Christian; Creutzburg, Kay; Amann, Kerstin Ute; Ries, Jutta; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Weber, Manuel (Journal of Translational Medicine, 2019)
BackgroundWith an increasing indication spectrum of antiresorptive drugs, the medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy [MRONJ (BP)] is continuously gaining clinical relevance. Impaired osteoclast function, accompanied by altered cell morphology and expression of osteoclastic effector proteins, contributes to the pathogenesis of MRONJ (BP). However, the underlying regulatory mechanisms at a transcriptional level are unaddressed so far. These mechanisms are crucial to the development of disease-characteristic osteoclastic anomalies, that contribute to the pathogenesis of MRONJ (BP). NFATc1 is considered a master upstream osteoclastic activator, whereas BCL6 acts as osteoclastic suppressor. The present study aimed to elucidate the NFATc1 and BCL6 mediated osteoclastic regulation and activity in MRONJ (BP) compared to osteoradionecrosis (ORN) and osteomyelitis (OM) and normal jaw bone.MethodsFormalin-fixed jaw bone specimens from 70 patients [MRONJ (BP) n=30; OM: n=15, ORN: n=15, control: n=10] were analyzed retrospectively for osteoclast expression of NFATc1 and BCL6. The specimens were processed for H&E staining and immunohistochemistry. The histological sections were digitalized and analyzed by virtual microscopy.ResultsOsteoclastic expression of NFATc1 and BCL6 was significantly higher in MRONJ (BP) specimens compared to OM and control specimens. NFATc1 and BCL6 labeling indices revealed no significant differences between MRONJ (BP) and ORN. The ratio of nuclear BCL6+ osteoclasts to cytoplasmic BCL6+ osteoclasts revealed significantly higher values for MRONJ (BP) specimens compared to OM and controls.ConclusionThis study displays that osteoclasts in MRONJ (BP) tissues feature increased expression of the higher-level regulators, paradoxically of both NFATc1 and BCL6. These observations can help to explain the genesis of morphologically altered and resorptive inactive osteoclasts in MRONJ (BP) tissues by outlining the transcriptional regulation of the pathomechanically relevant osteoclastic effector proteins. Furthermore, they strengthen the etiological delineation of MRONJ (BP) from OM and extend the osteoclast profiles of MRONJ (BP), OM and ORN and thus could lead to a better histopathological differentiation that can improve treatment decision and motivate new therapeutic concepts.
CRIS-Team WoS Importer:2019-03-20

Osteoclast profile of medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy: a comparison with osteoradionecrosis and osteomyelitis - Gross, Christian; Weber, Manuel; Creutzburg, Kay; Moebius, Patrick; Preidl, Raimund; Amann, Kerstin Ute; Wehrhan, Falk (Journal of Translational Medicine, 2017)
The medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy [MRONJ (BP)] is characterized by non-healing exposed bone in the maxillofacial region. The pathogenesis of MRONJ (BP) is not fully understood. Giant, hypernucleated, inactive osteoclasts were found in MRONJ (BP) tissues, which indicated that accelerated cell-cell fusion might play a role. Dendritic cell-specific transmembrane protein (DC-STAMP) is associated with the cell-cell fusion of osteoclasts and precursor cells. Tartrate-resistant acid phosphatase (TRAP) is essential for osteoclastic bone resorption. The cell-cell fusion, as part of the osteoclastogenesis, and the resorptive activity can determine the morphology of osteoclasts. This study analyzed jaw bone from patients with MRONJ (BP), osteomyelitis (OM) and osteoradionecrosis (ORN) because a comparison with the osteoclast profiles of OM and ORN is essential for characterizing the osteoclast profile of MRONJ (BP).Formalin-fixed routine jaw bone specimens from 70 patients [MRONJ (BP) n = 30; OM: n = 15, ORN: n = 15, control: n = 10] were analyzed retrospectively for osteoclast quantity, morphology and the expression of TRAP and DC-STAMP. The specimens were processed for hematoxylin and eosin staining (H&E), histochemistry (TRAP) and immunohistochemistry (anti-DC-STAMP) and were analyzed via virtual microscopy.The quantity, diameter and nuclearity of osteoclasts were significantly higher in MRONJ (BP) specimens than in OM, ORN and control specimens. Giant, hypernucleated osteoclasts were detected in MRONJ (BP) specimens only. Osteoclastic TRAP expression was lower in MRONJ (BP) and ORN specimens than in OM and control specimens. The DC-STAMP expression of osteoclasts and mononuclear cells was significantly higher in MRONJ (BP) and ORN specimens than in OM and control specimens.This study indicates that the osteoclast profile of MRONJ (BP) is characterized by osteoclast inactivation and a high cell-cell fusion rate; however, the presence of giant, hypernucleated osteoclasts cannot be attributed to increased DC-STAMP-triggered cell-cell fusion alone. The incidental characterization of the osteoclast profiles of OM and ORN revealed differences that might facilitate the histopathological differentiation of these diseases from MRONJ (BP), which is essential because their therapies are somewhat different.
EVALuna2:24432

Osteo-radio-necrosis (ORN) and bisphosphonate-related osteonecrosis of the jaws (BRONJ): the histopathological differences under the clinical similarities - Mitsimponas, Konstantinos; Moebius, Patrick; Amann, Kerstin Ute; Stockmann, Philipp; Schlegel, Karl-Andreas; Neukam, Friedrich Wilhelm; Wehrhan, Falk (International Journal of Clinical and Experimental Pathology, 2014)
Both Osteoradionecrosis (ORN) and Bisphosphonate associated osteonecrosis of the jaws (BRONJ) present clinically as regions of exposed necrotic bone. The study aimed to demonstrate the histopathological differences behind the observed clinical similarities.Ten ORN specimens and ten BRONJ specimens were used, as well as ten samples of normal mandibular bone as control. Two bone-specific stainings were used, i.e. Sirius Red for the study of the relative presence of collagen types I and III and toluidine blue for the study the osteon density.The Red Green Blue (RGB)-analysis of the specimens stained with Sirius Red identified significant differences between the chromatic patterns observed in bone preparations of patients suffering from ORN when compared to both BRONJ and control samples. Moreover, the osteon density of the BRONJ samples was significantly lower when compared to ORN and normal bone samples.The demonstrated differences in the bone architecture and in the bone collagen content between the two pathological conditions most likely reflect underlying pathophysiological differences.
EVALuna2:24379

Oxalate-induced chronic kidney disease with its uremic and cardiovascular complications in C57BL/6 mice - Mulay, Shrikant R.; Eberhard, Jonathan N.; Pfann, Victoria; Marschner, Julian A.; Darisipudi, Murthy N.; Daniel, Christoph; Romoli, Simone; Desai, Jyaysi; Grigorescu, Melissa; Kumar, Santhosh V.; Rathkolb, Birgit; Wolf, Eckhard; et al. (American Journal of Physiology-Renal Physiology, 2016)
Chronic kidney disease (CKD) research is limited by the lack of convenient inducible models mimicking human CKD and its complications in experimental animals. We demonstrate that a soluble oxalate-rich diet induces stable stages of CKD in male and female C57BL/6 mice. Renal histology is characterized by tubular damage, remnant atubular glomeruli, interstitial inflammation, and fibrosis, with the extent of tissue involvement depending on the duration of oxalate feeding. Expression profiling of markers and magnetic resonance imaging findings established to reflect inflammation and fibrosis parallel the histological changes. Within 3 wk, the mice reproducibly develop normochromic anemia, metabolic acidosis, hyperkalemia, FGF23 activation, hyperphosphatemia, and hyperparathyroidism. In addition, the model is characterized by profound arterial hypertension as well as cardiac fibrosis that persist following the switch to a control diet. Together, this new model of inducible CKD overcomes a number of previous experimental limitations and should serve useful in research related to CKD and its complications.
EVALuna2:3844

Oxidative DNA Damage in Kidneys and Heart of Hypertensive Mice Is Prevented by Blocking Angiotensin II and Aldosterone Receptors - Brand, Susanne; Amann, Kerstin Ute; Mandel, Philipp; Zimnol, Anna; Schupp, Nicole (PLoS ONE, 2014)
Recently, we could show that angiotensin II, the reactive peptide of the blood pressure-regulating renin-angiotensin-aldosterone-system, causes the formation of reactive oxygen species and DNA damage in kidneys and hearts of hypertensive mice. To further investigate on the one hand the mechanism of DNA damage caused by angiotensin II, and on the other hand possible intervention strategies against end-organ damage, the effects of substances interfering with the renin-angiotensin-aldosterone-system on angiotensin II-induced genomic damage were studied.In C57BL/6-mice, hypertension was induced by infusion of 600 ng/kg o min angiotensin II. The animals were additionally treated with the angiotensin II type 1 receptor blocker candesartan, the mineralocorticoid receptor blocker eplerenone and the antioxidant tempol. DNA damage and the activation of transcription factors were studied by immunohistochemistry and protein expression analysis.Administration of angiotensin II led to a significant increase of blood pressure, decreased only by candesartan. In kidneys and hearts of angiotensin II-treated animals, significant oxidative stress could be detected (1.5-fold over control). The redox-sensitive transcription factors Nrf2 and NF-?B were activated in the kidney by angiotensin II-treatment (4- and 3-fold over control, respectively) and reduced by all interventions. In kidneys and hearts an increase of DNA damage (3- and 2-fold over control, respectively) and of DNA repair (3-fold over control) was found. These effects were ameliorated by all interventions in both organs. Consistently, candesartan and tempol were more effective than eplerenone.Angiotensin II-induced DNA damage is caused by angiotensin II type 1 receptor-mediated formation of oxidative stress in vivo. The angiotensin II-mediated physiological increase of aldosterone adds to the DNA-damaging effects. Blocking angiotensin II and mineralocorticoid receptors therefore has beneficial effects on end-organ damage independent of blood pressure normalization.
EVALuna2:25417

P2Y1 gene deficiency protects from renal disease progression and capillary rarefaction during passive crescentic glomerulonephritis - Hohenstein, Bernd; Renk, Sindy; Lang, Kathrin; Daniel, Christoph; Freund, Monique; Léon, Catherine; Amann, Kerstin Ute; Gachet, Christian; Hugo, Christian (Journal of the American Society of Nephrology, 2007)
The metabotropic receptor P2Y1 is necessary for full ADP-induced platelet activation and is localized on various intrinsic renal cells, including mesangial cells, podocytes, and endothelial cells. To date, nothing is known about the role of the P2Y1 receptor during inflammatory renal disease. The role of the P2Y1 receptor was investigated using 22 P2Y1 gene-deficient (-/-) and 27 wild-type (wt) mice during the time course of passive crescentic nephrotoxic glomerulonephritis. Six P2Y1 -/- and six wt mice served as undiseased controls. Renal tissues were harvested on days 1, 10, and 28 after disease induction. No renal phenotype was found in P2Y1 -/- versus wt mice. In contrast, during crescentic glomerulonephritis, approximately 50% of all wt mice died, whereas all P2Y1 -/- mice survived. Renal function as assessed by creatinine clearance measurements, glomerulosclerosis, and tubulointerstitial injury indices as well as glomerular and interstitial matrix expansion were improved significantly in P2Y1 -/- compared with wt mice. These changes were preceded by reduced glomerular and peritubular capillary rarefaction indices in P2Y1 -/- compared with wt mice. The alteration of the rates of both peritubular apoptosis and endothelial cell proliferation suggests improved capillary preservation in P2Y1 -/- mice early in disease (day 10) and an additional enhanced repair reaction in P2Y1 -/- mice at the late time point (day 28), whereas injury on day 1 seemed to be equivalent in both groups. It is concluded that loss of P2Y1 receptor function safeguards against capillary loss, fibrosis, and death by renal failure during experimental crescentic glomerulonephritis. Copyright © 2007 by the American Society of Nephrology.
Created from Fastlane, Scopus look-up

Pals1 Haploinsufficiency Results in Proteinuria and Cyst Formation - Weide, Thomas; Vollenbroeker, Beate; Schulze, Ulf; Djuric, Ivona; Edeling, Maria; Bonse, Jakob; Hochapfel, Florian; Panichkina, Olga; Wennmann, Dirk-Oliver; George, Britta; Kim, Seonhee; Daniel, Christoph; et al. (Journal of the American Society of Nephrology, 2017)
The nephron is the basic physiologic subunit of the mammalian kidney and is made up of several apicobasally polarized epithelial cell types. The process of apicobasal polarization in animal cells is controlled by the evolutionarily conserved Crumbs (CRB), Partitioning-defective, and Scribble protein complexes. Here, we investigated the role of protein associated with LIN-7 1 (Pals1, also known as Mpp5), a core component of the apical membrane-determining CRB complex in the nephron. Pals1 interacting proteins, including Crb3 and Wwtr1/Taz, have been linked to renal cyst formation in mice before. Immunohistologic analysis revealed Pals1 expression in renal tubular cells and podocytes of human kidneys. Mice lacking one Pals1 allele (functionally haploid for Pals1) in nephrons developed a fully penetrant phenotype, characterized by cyst formation and severe defects in renal barrier function, which led to death within 6-8 weeks. In Drosophila nephrocytes, deficiency of the Pals1 ortholog caused alterations in slit-diaphragm-like structures. Additional studies in epithelial cell culture models revealed that Pals1 functions as a dose-dependent upstream regulator of the crosstalk between Hippo- and TGF-?-mediated signaling. Furthermore, Pals1 haploinsufficiency in mouse kidneys associated with the upregulation of Hippo pathway target genes and marker genes of TGF-? signaling, including biomarkers of renal diseases. These findings support a link between apical polarity proteins and renal diseases, especially renal cyst diseases. Further investigation of the Pals1-linked networks is required to decipher the mechanisms underlying the pathogenesis of these diseases.
EVALuna2:25537

Pancreas transplantation—clinic, technique, and histological assessment Pankreastransplantation – Klinik, Technik und histologische Beurteilung - Büttner-Herold, Maike; Amann, Kerstin Ute; Pfister, Frederick; Tannapfel, Andrea; Maslova, Marina; Wunsch, Andreas; Pillokeit, Nina; Viebahn, Richard; Schenker, Peter (Pathologe, 2021)
Background: In Germany pancreas transplants are performed in only a few selected and specialized centres, usually combined with a kidney transplant. Knowlegde of the indications for and techniques of transplantation as well as of the histopathological assessment for rejection in pancreas and duodenal biopsies is not very widespread. Aim: To give an overview of the development and status quo in pancreas-kidney-transplantation in Germany summarizing the experience of the largest German pancreas transplant centre and to give a résumé of the results of histological diagnoses of biopsy specimens submitted between 06/2017 and 12/2020. Moreover, a detailed description and illustration of histological findings is included. Material and Methods: A thorough literature search for aspects of the history, technique and indication for pancreas transplantation was performed and discussed in the context of the local experience and technical particularities specific for the transplant centre in Bochum. The occurrence of complications was compared with international reports. Results of pancreas and duodenal biopsies submitted to Erlangen between 06/2017 and 12/2020 for histological evaluation, which were evaluated according to the Banff classification, were summarized. For a better understanding key histological findings of pancreas rejection and differential diagnoses were illustrated and discussed. Results: A total of 93 pancreas transplant specimens and 3 duodenal biopsies were included. 34.4% of pancreas specimens did not contain representative material for a diagnosis. In the remaining 61 biopsies 24.6% showed no rejection, 62.3% were diagnosed with acute T-cell mediated rejection (TCMR) and 8.2% with signs suspicious of antibody-mediated rejection (ABMR). Acute acinary epithelial injury was seen in 59%, pancreatitis in 8.2% and allograft fibrosis was reported in as many as 54.1%. Calcineurin-inhibitor toxicity was discussed in only 4.9%. Conclusion: Pancreas-kidney-transplantation and standardized histological assessment of the transplanted pancreas or rarely duodenum with reporting according to the updated Banff classification of pancreas transplants or previous reports of duodenal rejection are important mainstays in the management of patients with diabetes.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Biopsy; Diabetes mellitus; Duodenum; Histology; Kidney transplantation

Paraproteinemia and renal involvement - Rupprecht, Harald; Amann, Kerstin Ute (Die Nephrologie, 2022)
Renal manifestations in patients with monoclonal paraproteinemia are frequent. Cast nephropathy is a disease that only occurs in manifest multiple myeloma with a high tumor burden. In contrast, monoclonal gammopathy of renal significance (MGRS) is defined as renal involvement due to a nephrotoxic clone that from a hematological standpoint would per se not require treatment. The diagnosis of MGRS can only be made by renal biopsy. Here monotypic immunoglobulin (Ig) deposits can be found in either organized (amyloidosis, fibrillary glomerulonephritis, GN, immunotactoid GN, cryoglobulinemic GN) or nonorganized forms (monoclonal Ig deposition disease, proliferative GN with monoclonal Ig deposits). There are two forms of MGRS that can occur without the deposition of Ig, namely C3 glomerulopathy and thrombotic microangiopathy. For cast nephropathy there is always a fundamental indication for chemotherapy. The data on mechanical elimination of light chains by plasmapheresis or high cut-off dialysis are inconsistent. In patients with MGRS the indications for treatment must be made based on the renal prognosis in a cooperation between nephrologists and hematologists. Only a clone-directed treatment can lead to an improvement of renal function.
CRIS-Team WoS Importer:2022-12-16

PEG matrix enables cell-mediated local BMP-2 gene delivery and increased bone formation in a porcine critical size defect model of craniofacial bone regeneration - Wehrhan, Falk; Amann, Kerstin Ute; Molenberg, Aart; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2012)
Purpose: This study addressed the suitability of a polyethylene glycol (PEG) matrix as scaffold for cell-mediated local BMP-2 gene transfer in a calvarial critical size defect (CSD) model. Materials and methods: PEG matrix (degradation time 10 days) and PEG membrane (degradation time 120 days) were used in the pig calvarial model. Cylindrical (1 × 1 cm) CSD (9 per animal; 20 animals) were filled with: (i) HA/TCP, covered by PEG membrane (group 1); (ii) HA/TCP, mixed with PEG matrix (group 2); and (iii) HA/TCP mixed with BMP-2 transfected osteoblasts and PEG matrix (group 3). BMP-2/4 gene transfer: liposomal in vitro transfection of BMP-2/V5-tag fusion-protein. Quantitative histomorphometry (toluidine blue staining) after 2, 4 and 12 weeks assessed bone formation. Semiquantitative immunohistochemistry estimated the expression of BMP-2 and V5-tag. Results: Group 3 showed significantly higher new bone formation than groups 1, 2 at 4 (P < 0.05) and 12 (P < 0.02) weeks. BMP-2-V5-tag was detected for 4 weeks. BMP-2 expression in group 3 was higher compared to all other groups after 2 and 4 (P < 0.02) weeks. Conclusions: The PEG matrix serves as scaffold for cell-mediated BMP-2 gene delivery in guided bone regeneration facilitating cell survival and protein synthesis for at least 4 weeks. Local BMP-2 gene delivery by PEG matrix-embedded cells leads to increased bone formation during critical size defect regeneration. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: BMP-2; Bone regeneration; Critical size defect; Gene transfer; PEG

PGAM5-mediated programmed necrosis of hepatocytes drives acute liver injury - He, Gui-Wei; Günther, Claudia; Kremer, Andreas; Thonn, Veronika; Amann, Kerstin Ute; Poremba, Christopher; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Gut, 2016)
Autoimmune hepatitis (AIH) is a severe necroinflammatory liver disease associated with significant mortality. Although loss of hepatocytes is generally recognised as a key trigger of liver inflammation and liver failure, the regulation of hepatic cell death causing AIH remains poorly understood. The aim of this study was to identify molecular mechanisms that drive hepatocyte cell death in the pathogenesis of acute liver injury.Acute liver injury was modelled in mice by intravenous administration of concanavalin A (ConA). Liver injury was demonstrated by serum transaminases and histological assessment of liver sections. PGAM5-deficient mice (PGAM5-/-) were used to determine its role in experimental hepatitis. Mdivi-1 was used as an inhibitor of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Mitochondrial fission and the expression of PGAM5 were compared between liver biopsies derived from patients with AIH and control patients.PGAM5 was highly expressed in hepatocytes of patients with AIH and in mice with ConA-induced experimental hepatitis. Deficiency of PGAM5 protected mice from ConA-induced hepatocellular death and liver injury. PGAM5 regulated ConA-induced mitochondrial fission in hepatocytes. Administration of the Drp1-inhibitor Mdivi-1 blocked mitochondrial fission, diminished hepatocyte cell death and attenuated liver tissue damage induced by ConA.Our data demonstrate for the first time that PGAM5 plays an indispensable role in the pathogenesis of ConA-induced liver injury. Downstream of PGAM5, Drp1-mediated mitochondrial fission is an obligatory step that drives the execution of hepatic necrosis and tissue damage. Our data highlight the PGAM5-Drp1 axis as a potential therapeutic target for acute immune-mediated liver injury.
EVALuna2:2219

[Philipp A. Schnabel : 24 May 1953-13 May 2021]. - Amann, Kerstin Ute (Pathologe, 2021)
EVALuna2:475671

PLA2R-positive (primary) membranous nephropathy in a child with IPEX syndrome - Chuva, Teresa; Pfister, Frederick; Beringer, Ortraud; Felgentreff, Kerstin; Buettner-Herold, Maike; Amann, Kerstin Ute (Pediatric Nephrology, 2017)
Immunodysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare primary immunodeficiency syndrome characterized by the development of multiple autoimmune disorders in affected individuals. Different forms of renal injury have been reported in IPEX syndrome, and membranous nephropathy (MN) is among the most common glomerulopathies found. However, the exact pathogenesis of MN in this setting has not been elucidated, and it is not clear whether it is part of the clinical spectrum of the disease or secondary to medications, infections or other concomitant insults.We describe a child diagnosed with IPEX syndrome shortly after birth who presented with nephrotic syndrome at the age of 11 weeks. Renal biopsy revealed a MN with enhanced immunohistochemical staining for phospholipase A2 receptor (PLA2R).This is the first report of a PLA2R-positive MN in a patient with IPEX syndrome. We suggest that, in this context, MN results from an autoimmune process against podocytic antigens, namely PLA2R.
EVALuna2:25544

Plasminogen deficiency does not prevent sodium retention in a genetic mouse model of experimental nephrotic syndrome - Xiao, Mengyun; Bohnert, Bernhard N.; Aypek, Hande; Kretz, Oliver; Grahammer, Florian; Aukschun, Ute; Woern, Matthias; Janessa, Andrea; Essigke, Daniel; Daniel, Christoph; Amann, Kerstin Ute; Huber, Tobias B.; et al. (Acta Physiologica, 2020)
Aim: Sodium retention is the hallmark of nephrotic syndrome (NS) and mediated by the proteolytic activation of the epithelial sodium channel (ENaC) by aberrantly filtered serine proteases. Plasmin is highly abundant in nephrotic urine and has been proposed to be the principal serine protease responsible for ENaC activation in NS. However, a proof of the essential role of plasmin in experimental NS is lacking. Methods: We used a genetic mouse model of NS based on an inducible podocin knockout (Bl6-Nphs2tm3.1Antc*Tg(Nphs1-rtTA*3G)8Jhm*Tg(tetO-cre)1Jaw or nphs2Δipod). These mice were crossed with plasminogen deficient mice (Bl6-Plgtm1Jld or plg−/−) to generate double knockout mice (nphs2Δipod*plg−/−). NS was induced after oral doxycycline treatment for 14 days and mice were followed for subsequent 14 days. Results: Uninduced nphs2Δipod*plg−/− mice had normal kidney function and sodium handling. After induction, proteinuria increased similarly in both nphs2Δipod*plg+/+ and nphs2Δipod*plg−/− mice. Western blot revealed the urinary excretion of plasminogen and plasmin in nphs2Δipod*plg+/+ mice which were absent in nphs2Δipod*plg−/− mice. After the onset of proteinuria, amiloride-sensitive natriuresis was increased compared to the uninduced state in both genotypes. Subsequently, urinary sodium excretion dropped in both genotypes leading to an increase in body weight and development of ascites. Treatment with the serine protease inhibitor aprotinin prevented sodium retention in both genotypes. Conclusions: This study shows that mice lacking urinary plasminogen are not protected from ENaC-mediated sodium retention in experimental NS. This points to an essential role of other urinary serine proteases in the absence of plasminogen.
CRIS-Team Scopus Importer:2020-08-07
Keywords: epithelial sodium channel; nephrotic syndrome; plasminogen; proteasuria; sodium retention

PODOCYTE AND GLOMERULAR ENDOTHELIAL CELL DERIVED MICRORNAS REGULATE PODOCYTE NEPHRONECTIN IN MEMBRANOUS GLOMERULONEPHRITIS - Müller-Deile, Janina; Sopel, Nina; Ohs, Alexandra; Kotb, Ahmed; Gröner, Marwin; Daniel, Christoph; Amann, Kerstin Ute; Schiffer, Mario (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03

Possible links between groundwater geochemistry and chronic kidney disease of unknown etiology (CKDu): an investigation from the Ginnoruwa region in Sri Lanka - Balasooriya, Shyamalie; Munasinghe, Harshaka; Herath, A. T.; Diyabalanage, Saranga; Ileperuma, O. A.; Manthrithilake, Herath; Daniel, Christoph; Amann, Kerstin Ute; Zwiener, Christian; Barth, Johannes; Chandrajith, Rohana (Exposure and Health, 2019)
Since at least two decades, Chronic Kidney Disease of Uncertain Etiology (CKDu) has become an increasingly discussed health issue in Sri Lanka and as well as in other tropical regions. Areas that are particularly affected with the disease are mostly located in the dry zone of Sri Lanka. The disease is more prominent among communities that consume groundwater as their main source of drinking water. Hydrogeochemical investigations were carried out in the Ginnoruwa area, a known hotspot of CKDu. It revealed possible links between drinking water chemistry and the spreading of the disease. This work compares hydrogeochemical data of drinking water sources of wells whose consumers are affected by CKDu and other nearby wells whose consumers were not affected by the disease. A total of 63 groundwater samples were collected from selected wells. About one-third of these samples (i.e., 19) were collected from wells used by CKDu patients. Significantly higher values of pH, total hardness, electrical conductivity, Ca2+, Mg2+, F−, Cl−, PO4 3−, and SO4 2− were found in wells that were used by CKDu patients. Mean contents of Na+, Ca2+, and Mg2+ in CKDu affected wells were 33.8 mg/L, 30.1 mg/L, and 14.9 mg/L, respectively, compared to 23.1 mg/L, 26.7 mg/L, and 9.65 mg/L in non-CKDu wells. Differences in major ion geochemistry in groundwaters are possibly governed by variable time periods of water storage in fractured hard rock aquifers in this region. Hydrogeochemical parameters were statistically compared by a Mann–Whitney U test and indicated significant differences in total dissolved solids (TDS) (p = 0.016), SO4 2− (p = 0.005), PO4 3− (p = 0.030), F− (p = 0.048), Na+ (p = 0.008), and Mg2+(p = 0.008) between non-CKDu and CKDu wells at p = 0.050 level. Other suspected solutes such as nephrotoxic trace elements including As, Cd, and Pb were similar in both types of wells. They were also lower than the accepted guideline limits of the World Health Organization (WHO). Results of this study suggest that fluoride in drinking water in combination with water hardness may be one of the responsible factors for kidney damage and progression of the disease. This may be particularly the case when elevated amounts of Mg2+ are present in hard groundwater.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Fluoride; Girandurukotte; Kidney damage; Magnesium; Mann–Whitney U test; Water hardness

Potential and Uncertainties of RejectClass in Acute Kidney Graft Dysfunction: An Independent Validation Study. - Von Samson-Himmelstjerna, Friedrich A.; Kakavand, Nassim; Gleske, Charlotte; Schraml, Florian; Basta, Agathe A.; Braunisch, Matthias C.; Bräsen, Jan H.; Schmitz, Jessica; Kraus, Daniel; Weinmann-Menke, Julia; Zacharias, Helena U.; Vaulet, Thibaut; et al. (Transplantation, 2024)
BACKGROUND: Kidney graft rejections are classified based on the Banff classification. The RejectClass algorithm, initially derived from a cohort comprising mostly protocol biopsies, identifies data-driven phenotypes of acute rejection and chronic pathology using Banff lesion scores. It also provides composite scores for inflammation activity and chronicity. This study independently evaluates the performance of RejectClass in a cohort consisting entirely of indication biopsies. METHODS: We retrospectively applied RejectClass to 441 patients from the German TRABIO (TRAnsplant BIOpsies) cohort who had received indication biopsies. The primary endpoint was death-censored graft failure during 2 y of follow-up. RESULTS: The application of RejectClass to our cohort demonstrated moderately comparable phenotypic features with the derivation cohort, and most clusters indicated an elevated risk of graft loss. However, the reproduction of all phenotypes and the associated risks of graft failure, as depicted in the original studies, was not fully accomplished. In contrast, adjusted Cox proportional hazards analyses substantiated that both the inflammation score and the chronicity score are independently associated with graft loss, exhibiting hazard ratios of 1.7 (95% confidence interval, 1.2-2.3; P = 0.002) and 2.2 (95% confidence interval, 1.8-2.6; P < 0.001), respectively, per 0.25-point increment (scale: 0.0-1.0). CONCLUSIONS: The composite inflammation and chronicity scores may already have direct utility in quantitatively assessing the disease stage. Further refinement and validation of RejectClass clusters are necessary to achieve more reliable and accurate phenotyping of rejection.
EVALuna2:549467

Primary glomerulonephritides - Floege, Juergen; Amann, Kerstin Ute (Lancet, 2016)
Most glomerulonephritides, even the more common types, are rare diseases. They are nevertheless important since they frequently affect young people, often cannot be cured, and can lead to chronic kidney disease, including end-stage renal failure, with associated morbidity and cost. For example, in young adults, IgA nephropathy is the most common cause of end-stage renal disease. In this Seminar, we summarise existing knowledge of clinical signs, pathogenesis, prognosis, and treatment of glomerulonephritides, with a particular focus on data published between 2008 and 2015, and the most common European glomerulonephritis types, namely IgA nephropathy, membranous glomerulonephritis, minimal change disease, focal segmental glomerulosclerosis, membranoproliferative glomerulonephritis, and the rare complement-associated glomerulonephritides such as dense deposit disease and C3 glomerulonephritis.
EVALuna2:25514

Prognostic significance of macrophage polarization in early stage oral squamous cell carcinomas - Weber, Manuel; Iliopoulos, Christos; Moebius, Patrick; Buettner-Herold, Maike; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Oral Oncology, 2016)
Polarization of tumor infiltrating macrophages is associated with the prognosis of solid malignancies and correlates with the occurrence of lymph node metastases in oral squamous cell carcinomas (oscc). Early stage (T1/T2, N0) oscc are characterized by a good prognosis and can be cured by surgery. The postoperative regime usually contains no adjuvant radio-/chemotherapy. The current pilot study was conducted to elucidate whether macrophage polarization in tumor resection specimens and diagnostic biopsies of early stage oscc is associated with tumor outcome.Patients with T1/T2, N0, and R0>5mm oscc without adjuvant therapy and 3-year follow-up after tumor resection were retrospectively selected. Tissue microarrays (TMA) containing diagnostic biopsies (n=17) and tumor resection specimens (n=17) were processed for immunohistochemistry in this pilot study to detect CD68-, CD11c-, CD163- and MRC1-positive macrophages. Samples were digitized, and the expression of macrophage markers was quantitatively analyzed.High infiltration of M2 polarized macrophages correlated with poor tumor outcome in early stage (T1/T2, N0) oscc. This correlation was observed in tumor resection specimens, but was also observed in diagnostic biopsies. M2 macrophage polarization in biopsies - but not in tumor resection samples - correlated with high scores in tumor grading.Macrophage polarization in early stage oscc is a potential prognostic marker for tumor outcome. The correlation of M2 polarized macrophages with tumor outcome can already be detected in the initial biopsies. Furthermore, M2 polarization of macrophages in biopsies is associated with an increased dedifferentiation.
EVALuna2:24408

Prolonged podocyte depletion in larval zebrafish resembles mammalian focal and segmental glomerulosclerosis - Hansen, Kerrin Ursula Ingeborg; Siegerist, Florian; Daniel, Sophie; Schindler, Maximilian; Iervolino, Anna; Blumenthal, Antje; Daniel, Christoph; Amann, Kerstin Ute; Zhou, Weibin; Endlich, Karlhans; Endlich, Nicole (The FASEB Journal, 2020)
Focal and segmental glomerulosclerosis (FSGS) is a histological pattern frequently found in patients with nephrotic syndrome that often progress to end-stage kidney disease. The initial step in development of this histologically defined entity is injury and ultimately depletion of podocytes, highly arborized interdigitating cells on the glomerular capillaries with important function for the glomerular filtration barrier. Since there are still no causal therapeutic options, animal models are needed to develop new treatment strategies. Here, we present an FSGS-like model in zebrafish larvae, an eligible vertebrate model for kidney research. In a transgenic zebrafish strain, podocytes were depleted, and the glomerular response was investigated by histological and morphometrical analysis combined with immunofluorescence staining and ultrastructural analysis by transmission electron microscopy. By intravenous injection of fluorescent high-molecular weight dextran, we confirmed leakage of the size selective filtration barrier. Additionally, we observed severe podocyte foot process effacement of remaining podocytes, activation of proximal tubule-like parietal epithelial cells identified by ultrastructural cytomorphology, and expression of proximal tubule markers. These activated cells deposited extracellular matrix on the glomerular tuft which are all hallmarks of FSGS. Our findings indicate that glomerular response to podocyte depletion in larval zebrafish resembles human FSGS in several important characteristics. Therefore, this model will help to investigate the disease development and the effects of potential drugs in a living organism.
CRIS-Team Scopus Importer:2020-10-23
Keywords: FSGS; glomerulus; podocyte injury; zebrafish model organism

Protease-activated receptor 2 deficient mice develop less angiotensin II induced left ventricular hypertrophy but more cardiac fibrosis. - Meyer zu Schwabedissen, Albrecht; Vergarajauregui, Silvia; Bertog, Marko; Amann, Kerstin Ute; Engel, Felix; Daniel, Christoph (PLoS ONE, 2024)
AIMS: Activation of Protease Activated Receptor 2 (PAR2) has been shown to be involved in regulation of injury-related processes including inflammation, fibrosis and hypertrophy. In this study we will investigate the role of PAR2 in cardiac injury in a mouse model of hypertension using continuous infusion with angiotensin II. METHODS: Hypertension was induced in 12 weeks old wildtype (wt, n = 8) and PAR2 deficient mice (n = 9) by continuous infusion with angiotensin II for 4 weeks using osmotic minipumps. At the end, hearts were collected for analysis of left ventricular hypertrophy (LVH), myocardial capillary supply, fibrosis and localization of PAR2 expression using histological, immunohistological and mRNA expression analysis techniques. In addition, rat cardiac fibroblasts were treated with angiotensin II and PAR2 was inhibited by a blocking antibody and the PAR2 inhibitor AZ3451. RESULTS: Cardiac PAR2 mRNA expression was downregulated by 40±20% in wt mice treated with AngII compared to untreated controls. Four weeks after AngII treatment, LVH was significantly increased in AngII-treated wt mice compared to similarly treated PAR2-deficient animals as determined by relative heart weight, left ventricular cross-sectional area, and analysis of ventricular lumen area determined on sections. Treatment of wt mice resulted in an approximately 3-fold increase in cardiac expression of FGF23, which was 50% lower in PAR2-deficient animals compared to wt animals and therefore no longer significantly different from expression levels in untreated control mice. In contrast, cardiac interstitial fibrosis was significantly higher in PAR2-deficient mice compared to similar treated wt controls, as assessed by Sirius Red staining (>3-fold) and collagen IV staining (>2-fold). Additional experiments with isolated cardiac fibroblasts showed induction of pro-fibrotic genes when treated with PAR2 inhibitors. CONCLUSION: In angiotensin II-induced cardiac injury, PAR2 deficiency has an ambivalent effect, enhancing fibrosis on the one hand, but reducing LVH on the other.
EVALuna2:577005

Quantitative assessment of microperfusion by indocyanine green angiography in kidney transplantation resembles chronic morphological changes in kidney specimens - Rother, Ulrich; Amann, Kerstin Ute; Adler, Werner; Nawroth, Nina; Karampinis, Ioannis; Keese, Michael; Manap, Serhat; Regus, Susanne; Meyer, Alexander; Porubsky, Stefan; Hilgers, Karl Friedrich; Krämer, Bernhard K.; et al. (Microcirculation, 2019)
OBJECTIVE: Indocyanine green fluorescence angiography enables a quantitative real-time perfusion assessment in kidney transplantation. The results of intraoperative microperfusion of the kidney allograft were compared to the renal chronicity score in pre-transplantation kidney biopsy specimens. The intrarenal resistance index was calculated by duplex sonography as a method of reference. METHODS: Seventy-seven patients with end stage renal disease undergoing kidney transplantation were prospectively included in two centers. Correlation analysis of chronic changes in kidney biopsy specimens and the ingress of ICG fluorescence signal were investigated. RESULTS: The results yielded a significantly negative correlation for the renal chronicity (r= -0.294, p=0.017) as well as the intestinal fibrosis and tubular atrophy score (r=-0.328, p=0.007). There was a significant inverse relationship between the ingress and the mean RI values of the upper pole of the kidney allograft. CONCLUSION: In summary, fluorescence angiography reflects preexisting morphological changes of the renal cortex. ICG angiography may serve as an alternative method for the assessment of microperfusion of the kidney allograft. This article is protected by copyright. All rights reserved.
EVALuna2:35427

Recombinant Adenosine Deaminase Ameliorates Inflammation, Vascular Disease, and Fibrosis in Preclinical Models of Systemic Sclerosis - Zhang, Yun; Zhu, Honglin; Layritz, Florian; Luo, Hui; Wohlfahrt, Thomas; Chen, Chih-Wei; Soare, Alina; Bergmann, Christina; Ramming, Andreas; Groeber, Florian; Reuter, Christian; Fornasini, Gianfranco; et al. (Arthritis and Rheumatology, 2020)
Objective: Systemic sclerosis (SSc) is characterized by fibrosis, vascular disease, and inflammation. Adenosine signaling plays a central role in fibroblast activation. We undertook this study to evaluate the therapeutic effects of adenosine depletion with PEGylated adenosine deaminase (PEG-ADA) in preclinical models of SSc. Methods: The effects of PEG-ADA on inflammation, vascular remodeling, and tissue fibrosis were analyzed in Fra-2 mice and in a B10.D2→BALB/c (H-2d) model of sclerodermatous chronic graft-versus-host disease (GVHD). The effects of PEG-ADA were confirmed in vitro in a human full-thickness skin model. Results: PEG-ADA effectively inhibited myofibroblast differentiation and reduced pulmonary fibrosis by 34.3% (with decreased collagen expression) (P = 0.0079; n = 6), dermal fibrosis by 51.8% (P = 0.0006; n = 6), and intestinal fibrosis by 17.7% (P = 0.0228; n = 6) in Fra-2 mice. Antifibrotic effects of PEG-ADA were also demonstrated in sclerodermatous chronic GVHD (reduced by 38.4%) (P = 0.0063; n = 8), and in a human full-thickness skin model. PEG-ADA treatment decreased inflammation and corrected the M2/Th2/group 2 innate lymphoid cell 2 bias. Moreover, PEG-ADA inhibited proliferation of pulmonary vascular smooth muscle cells (reduced by 40.5%) (P < 0.0001; n = 6), and prevented thickening of the vessel walls (reduced by 39.6%) (P = 0.0028; n = 6) and occlusions of pulmonary arteries (reduced by 63.9%) (P = 0.0147; n = 6). Treatment with PEG-ADA inhibited apoptosis of microvascular endothelial cells (reduced by 65.4%) (P = 0.0001; n = 6) and blunted the capillary rarefication (reduced by 32.5%) (P = 0.0199; n = 6). RNA sequencing demonstrated that treatment with PEG-ADA normalized multiple pathways related to fibrosis, vasculopathy, and inflammation in Fra-2 mice. Conclusion: Treatment with PEG-ADA ameliorates the 3 cardinal features of SSc in pharmacologically relevant and well-tolerated doses. These findings may have direct translational implications, as PEG-ADA has already been approved by the Food and Drug Administration for the treatment of patients with ADA-deficient severe combined immunodeficiency disease.
CRIS-Team Scopus Importer:2020-07-10

Recommendations for mRNA analysis of micro-dissected glomerular tufts from paraffin-embedded human kidney biopsy samples - Bockmeyer, Clemens L.; Wittig, Juliane; Saeuberlich, Karen; Selhausen, Philipp; Esser, Marc; Zeuschner, Philip; Modde, Friedrich; Amann, Kerstin Ute; Daniel, Christoph (Bmc Molecular Biology, 2018)
BACKGROUND: Glomeruli are excellent pre-determined natural structures for laser micro-dissection. Compartment-specific glomerular gene expression analysis of formalin-fixed paraffin-embedded renal biopsies could improve research applications. The major challenge for such studies is to obtain good-quality RNA from small amounts of starting material, as applicable for the analysis of glomerular compartments. In this work, we provide data and recommendations for an optimized workflow of glomerular mRNA analysis. RESULTS: With a proper resolution of the camera and screen provided by the next generation of micro-dissection systems, we are able to separate parietal epithelial cells from glomerular tufts. Selected compartment-specific transcripts (WT1 and GLEPP1 for glomerular tuft as well as PAX2 for parietal epithelial cells) seem to be reliable discriminators for these micro-dissected glomerular substructures. Using the phenol-chloroform extraction and hemalaun-stained sections (2 µm), high amounts of Bowman's capsule transections (> 300) reveal sufficient RNA concentrations (> 300 ng mRNA) for further analysis. For comparison, in unstained sections from a number of 60 glomerular transections upwards, a minimum amount of 157 ng mRNA with a reasonable mRNA purity [A260/A280 ratio of 1.5 (1.4/1.7) median (25th/75th percentiles)] was reversely transcribed into cDNA. Comparing the effect of input RNA (20, 60, 150 and 300 micro-dissected glomerular transections), transcript expression of POLR2A significantly correlated when 60 and 150 laser micro-dissected glomerular transections were used for analysis. There was a lower inter-assay coefficient of variability for ADAMTS13, when at least 60 glomerular transections were used. According to the algorithms of geNormPlus and NormFinder, PGK1 and PPIA are more stable glomerular reference transcripts compared to GUSB, GAPDH, POLR2A, RPLPO, TBP, B2M, ACTB, 18SrRNA and HMBS. CONCLUSIONS: Our approach implements compartment-specific glomerular mRNA expression analysis into research applications, even regarding glomerular substructures like parietal epithelial cells. We recommend using of at least 60 micro-dissected unstained glomerular or 300 hemalaun-stained Bowman's capsule transections to obtain sufficient input mRNA for reproducible results. Hereby, the range of RNA concentrations in 60 micro-dissected glomeruli is low and appropriate normalization of Cq values using our suggested reference transcripts (PGK1 and PPIA) allows compensation with respect to different amounts of RNA purity and quantity.
EVALuna2:34425

Reconstitution of EBV-directed T cell immunity by adoptive transfer of peptide-stimulated T cells in a patient after allogeneic stem cell transplantation for AITL - Cobo, María Fernanda Lammoglia; Ritter, Julia; Gary, Regina; Seitz, Volkhard; Mautner, Josef; Aigner, Michael; Völkl, Simon; Schaffer, Stefanie; Moi, Stephanie; Seegebarth, Anke; Bruns, Heiko; Rösler, Wolf; et al. (PLoS Pathogens, 2022)
Reconstitution of the T cell repertoire after allogeneic stem cell transplantation is a long and often incomplete process. As a result, reactivation of Epstein-Barr virus (EBV) is a frequent complication that may be treated by adoptive transfer of donor-derived EBV-specific T cells. We generated donor-derived EBV-specific T cells by stimulation with peptides representing defined epitopes covering multiple HLA restrictions. T cells were adoptively transferred to a patient who had developed persisting high titers of EBV after allogeneic stem cell transplantation for angioimmunoblastic T-cell lymphoma (AITL). T cell receptor beta (TCRβ) deep sequencing showed that the T cell repertoire of the patient early after transplantation (day 60) was strongly reduced and only very low numbers of EBV-specific T cells were detectable. Manufacturing and in vitro expansion of donor-derived EBV-specific T cells resulted in enrichment of EBV epitope-specific, HLA-restricted T cells. Monitoring of T cell clonotypes at a molecular level after adoptive transfer revealed that the dominant TCR sequences from peptide-stimulated T cells persisted long-term and established an EBV-specific TCR clonotype repertoire in the host, with many of the EBV-specific TCRs present in the donor. This reconstituted repertoire was associated with immunological control of EBV and with lack of further AITL relapse.
CRIS-Team Scopus Importer:2022-05-20

Reduction in Renal Heme Oxygenase-1 Is Associated with an Aggravation of Kidney Injury in Shiga Toxin-Induced Murine Hemolytic-Uremic Syndrome. - Mestekemper, Antonio N.; Pirschel, Wiebke; Krieg, Nadine; Paulmann, Maria K.; Daniel, Christoph; Amann, Kerstin Ute; Coldewey, Sina M. (Toxins, 2024)
Hemolytic-uremic syndrome (HUS) is a systemic complication of an infection with Shiga toxin (Stx)-producing enterohemorrhagic Escherichia coli, primarily leading to acute kidney injury (AKI) and microangiopathic hemolytic anemia. Although free heme has been found to aggravate renal damage in hemolytic diseases, the relevance of the heme-degrading enzyme heme oxygenase-1 (HO-1, encoded by Hmox1) in HUS has not yet been investigated. We hypothesized that HO-1, also important in acute phase responses in damage and inflammation, contributes to renal pathogenesis in HUS. The effect of tamoxifen-induced Hmox1 gene deletion on renal HO-1 expression, disease progression and AKI was investigated in mice 7 days after HUS induction. Renal HO-1 levels were increased in Stx-challenged mice with tamoxifen-induced Hmox1 gene deletion (Hmox1R26Δ/Δ) and control mice (Hmox1lox/lox). This HO-1 induction was significantly lower (-43%) in Hmox1R26Δ/Δ mice compared to Hmox1lox/lox mice with HUS. Notably, the reduced renal HO-1 expression was associated with an exacerbation of kidney injury in mice with HUS as indicated by a 1.7-fold increase (p = 0.02) in plasma neutrophil gelatinase-associated lipocalin (NGAL) and a 1.3-fold increase (p = 0.06) in plasma urea, while other surrogate parameters for AKI (e.g., periodic acid Schiff staining, kidney injury molecule-1, fibrin deposition) and general disease progression (HUS score, weight loss) remained unchanged. These results indicate a potentially protective role of HO-1 in the pathogenesis of Stx-mediated AKI in HUS.
EVALuna2:578194

Re-expression of pro-fibrotic, embryonic preserved mediators in irradiated arterial vessels of the head and neck region - Möbius, Patrick; Preidl, Raimund; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Strahlentherapie und Onkologie, 2017)
Surgical treatment of head and neck malignancies frequently includes microvascular free tissue transfer. Preoperative radiotherapy increases postoperative fibrosis-related complications up to transplant loss. Fibrogenesis is associated with re-expression of embryonic preserved tissue developmental mediators: osteopontin (OPN), regulated by sex-determining region Y-box 9 (Sox9), and homeobox A9 (HoxA9) play important roles in pathologic tissue remodeling and are upregulated in atherosclerotic vascular lesions; dickkopf-1 (DKK1) inhibits pro-fibrotic and atherogenic Wnt signaling. We evaluated the influence of irradiation on expression of these mediators in arteries of the head and neck region.DKK1, HoxA9, OPN, and Sox9 expression was examined immunohistochemically in 24 irradiated and 24 nonirradiated arteries of the lower head and neck region. The ratio of positive cells to total cell number (labeling index) in the investigated vessel walls was assessed semiquantitatively.DKK1 expression was significantly decreased, whereas HoxA9, OPN, and Sox9 expression were significantly increased in irradiated compared to nonirradiated arterial vessels.Preoperative radiotherapy induces re-expression of embryonic preserved mediators in arterial vessels and may thus contribute to enhanced activation of pro-fibrotic downstream signaling leading to media hypertrophy and intima degeneration comparable to fibrotic development steps in atherosclerosis. These histopathological changes may be promoted by HoxA9-, OPN-, and Sox9-related inflammation and vascular remodeling, supported by downregulation of anti-fibrotic DKK1. Future pharmaceutical strategies targeting these vessel alterations, e. g., bisphosphonates, might reduce postoperative complications in free tissue transfer.
EVALuna2:24435

Relevance of glomerular c4d deposition in pediatric patients with henoch-schönlein purpura compared to IgA nephritis - Benz, Kerstin; Ferrazzi, Fulvia; Galiano, Matthias; Sauerstein, Katja; Vonbrunn, Eva; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute (Journal of Nephropathology, 2021)
Introduction: IgA nephropathy (IgAN) is the most common primary glomerulonephritis (GN) in western countries and Henoch-Schönlein purpura nephritis (HSPN) is the most common form of vasculitis in childhood. Renal biopsy findings in both nephropathies are often similar and are characterized by mesangioproliferative GN with mesangial or mesangiocapillary IgA and C3c deposits. Objectives: The aim of this study was to investigate the significance of glomerular C4d-deposition as a discriminating factor between pediatric HSPN and IgAN. Patients and Methods: We retrospectively analyzed patient records and renal biopsies from 53 pediatric patients from one single center with a median age of 10.5 years (range 2.3-18 years). Twenty-two patients suffered from IgAN and 31 from HSPN. Work-up of all renal biopsies was performed using standard protocols including immunohistochemistry for C4d. Results: Pediatric IgAN patients presented significantly more often with gross hematuria, higher serum creatinine, lower glomerular filtration rate, lower serum C3 and proteinuria and on histology less endocapillary hypercellularity compared to HSPN patients. However, the rate of glomerular C4d-positivity was not different between IgAN (36%) and HSPN (42%). Comparing all cases with positive versus negative glomerular C4d-staining, pediatric patients with glomerular C4d-positivity showed significantly lesser gross hematuria and received significantly more often cyclophosphamide. This was in line with a tendency towards more proteinuria, hypertension and renal insufficiency at last follow-up in C4d-positive compared to C4d-negative patients. Conclusion: In conclusion, in our monocentric study glomerular C4d does not differ between pediatric HSPN and IgAN, but was associated with a tendency to a more severe course of the disease that needs to be confirmed in larger multicentric studies.
CRIS-Team Scopus Importer:2021-01-22
Keywords: C4d staining; Glomerulonephritis; Henoch-Schönlein purpura; IgA nephritis; IgA vasculitis; Pediatric nephrology

Renal effects of the serine protease inhibitor aprotinin in healthy conscious mice - Woerner, Stefan; Bohnert, Bernhard N.; Woern, Matthias; Xiao, Mengyun; Janessa, Andrea; Birkenfeld, Andreas L.; Amann, Kerstin Ute; Daniel, Christoph; Artunc, Ferruh (Acta Pharmacologica Sinica, 2021)
Treatment with aprotinin, a broad-spectrum serine protease inhibitor with a molecular weight of 6512 Da, was associated with acute kidney injury, which was one of the reasons for withdrawal from the market in 2007. Inhibition of renal serine proteases regulating the epithelial sodium channel ENaC could be a possible mechanism. Herein, we studied the effect of aprotinin in wild-type 129S1/SvImJ mice on sodium handling, tubular function, and integrity under a control and low-salt diet. Mice were studied in metabolic cages, and aprotinin was delivered by subcutaneously implanted sustained release pellets (2 mg/day over 10 days). Mean urinary aprotinin concentration ranged between 642 ± 135 (day 2) and 127 ± 16 (day 8) µg/mL. Aprotinin caused impaired sodium preservation under a low-salt diet while stimulating excessive hyperaldosteronism and unexpectedly, proteolytic activation of ENaC. Aprotinin inhibited proximal tubular function leading to glucosuria and proteinuria. Plasma urea and cystatin C concentration increased significantly under aprotinin treatment. Kidney tissues from aprotinin-treated mice showed accumulation of intracellular aprotinin and expression of the kidney injury molecule 1 (KIM-1). In electron microscopy, electron-dense deposits were observed. There was no evidence for kidney injury in mice treated with a lower aprotinin dose (0.5 mg/day). In conclusion, high doses of aprotinin exert nephrotoxic effects by accumulation in the tubular system of healthy mice, leading to inhibition of proximal tubular function and counterregulatory stimulation of ENaC-mediated sodium transport.
CRIS-Team Scopus Importer:2021-04-09
Keywords: aprotinin; epithelial sodium channel; renal dysfunction; serine proteases; sodium

Renal fibrosis is the common feature of autosomal dominant tubulointerstitial kidney diseases caused by mutations in mucin 1 or uromodulin - Ekici, Arif Bülent; Hackenbeck, Thomas; Moriniere, Vincent; Panness, Andrea; Büttner, Maike; Uebe, Steffen; Janka, Rolf Matthias; Wiesener, Antje; Hermann, Ingo; Grupp, Sina; Hornberger, Martin; Huber, Tobias B.; et al. (Kidney International, 2014)
For decades, ill-defined autosomal dominant renal diseases have been reported, which originate from tubular cells and lead to tubular atrophy and interstitial fibrosis. These diseases are clinically indistinguishable, but caused by mutations in at least four different genes: UMOD, HNF1B, REN, and, as recently described, MUC1. Affected family members show renal fibrosis in the biopsy and gradually declining renal function, with renal failure usually occurring between the third and sixth decade of life. Here we describe 10 families and define eligibility criteria to consider this type of inherited disease, as well as propose a practicable approach for diagnosis. In contrast to what the frequently used term 'Medullary Cystic Kidney Disease' implies, development of (medullary) cysts is neither an early nor a typical feature, as determined by MRI. In addition to Sanger and gene panel sequencing of the four genes, we established SNaPshot minisequencing for the predescribed cytosine duplication within a distinct repeat region of MUC1 causing a frameshift. A mutation was found in 7 of 9 families (3 in UMOD and 4 in MUC1), with one indeterminate (UMOD p.T62P). On the basis of clinical and pathological characteristics we propose the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' as an improved terminology. This should enhance recognition and correct diagnosis of affected individuals, facilitate genetic counseling, and stimulate research into the underlying pathophysiology.
EVALuna2:3695

Renal Function, Blood Pressure, and Histologic Changes in Living Kidney Transplant Recipients from Hypertensive Donors - Dienemann, T.; Schellenberg, J.; Amann, Kerstin Ute; Heller, K.; Weidemann, Alexander (2018)
EVALuna2:34437

Renal involvement in sarcoidosis: Histologic findings and clinical course - Naderi, Shirin; Amann, Kerstin Ute; Janssen, Ulf (Nephrology @ Point of Care, 2019)
Background: Renal failure in sarcoidosis is rare and data on its long-term outcome are scarce. Aim: To investigate the pattern of renal involvement in sarcoidosis, its clinical course and response to treatment in the long-term. Methods: A single-center retrospective study with review of renal biopsies and medical charts was performed. Results: Between January 2005 and December 2016, seven patients with sarcoidosis underwent a kidney biopsy. This is equivalent to a frequency of 1.6% in a total of 434 biopsies from native kidney performed in our institution. All patients presented with renal failure. Five patients had granulomatous interstitial nephritis (GIN) and one patient each interstitial nephritis without granuloma and nephrocalcinosis. Three patients had concomitant glomerular disease: IgA nephropathy (n = 2), membranous and focal proliferative glomerulonephritis (n = 1). Most patients (n = 5) presented with hypercalcemia. All patients initially received oral prednisolone 1 mg/kg/day (n = 3) or 0.5 mg/kg/day (n = 4), respectively, with subsequent tapering or suspension. One patient was started on azathioprine after 18 months to spare steroids. After a mean follow-up of 59 months mean estimated glomerular filtration rate (eGFR) had improved from 19 +/- 7 at presentation to 49 +/- 16 mL/min. No patient required dialysis. All patients started on prednisolone 1 mg/kg/day developed transient diabetes mellitus while patients on 0.5 mg/kg/day did not. Renal function improvement did not differ between both treatment groups. Conclusion: GIN was the most common diagnosis in sarcoidosis patients with renal failure. Initial hypercalcemia was observed in the majority. Early steroid treatment lead to sustained renal function improvement.
CRIS-Team WoS Importer:2019-04-16

Renal leishmaniasis as unusual cause of nephrotic syndrome in an HIV patient - Amann, Kerstin Ute; Bogdan, Christian; Harrer, Thomas; Rech, Jürgen (Journal of the American Society of Nephrology, 2012)
Renal involvement is a rare complication in HIV-1-infected patients leading to various pathologies and clinical symptoms. In addition to the classic HIV-1-associated nephropathy with collapsing-type focal segmental glomerulosclerosis and characteristic tubulocystic changes, which is more common in Afro-American than in Caucasian HIV-1 patients, immune complex GNs such as membranous GN and membranoproliferative GN are particularly common renal manifestations. Besides HIV-1 itself, a number of opportunistic infections may cause renal disease in HIV-1-infected patients. In this study, we report an unusual case of HIV-1 infection with a severe renal manifestation of systemic leishmaniasis that developed years after repeated visits to Mediterranean countries. The case presents several remarkable clinical, pathologic, and therapeutic aspects that may be important for daily clinical practice. Copyright © 2012 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2021-02-03

Renal pathology Nierenpathologie - Amann, Kerstin Ute (Die Pathologie, 2024)
CRIS-Team Scopus Importer:2024-07-05

Renal replacement therapy-requiring acute kidney injury due to tubulointerstitial nephritis and uveitis syndrome: case report - Marahrens, B.; Amann, Kerstin Ute; Asmus, K.; Erfurt, S.; Patschan, D. (Journal of Medical Case Reports, 2021)
Background: Acute kidney injury is a major challenge for today’s healthcare systems around the globe. Renal replacement therapy has been shown to be beneficial in acute kidney injury, but treatment highly depends on the cause of the acute kidney injury. One less common cause is tubulointerstitial nephritis, which comes in different entities. A very rare type of tubulointerstitial nephritis is tubulointerstitial nephritis and uveitis syndrome, in which the patient presents with additional uveitis. Case presentation: A 19-year-old caucasian male presented with mild dyspnea, lack of appetite, weight loss, and moderate itchiness. Lab results showed an acute kidney injury with marked increase of serum creatinine. The patient was started on prednisolone immediately after admission. As the patient in this case showed symptoms of uremia on admission, we decided to establish renal replacement therapy, which is unusual in tubulointerstitial nephritis and uveitis syndrome. During his course of dialysis, the patient developed symptoms of sepsis probably due to a catheter-related infection requiring intensive care and antibiotic treatment, which had to be terminated early as the patient developed a rash. Intensified immunosuppression, combined with antibiotics, significantly resolved excretory kidney dysfunction. Conclusions: Since both the primary inflammatory process and the secondary infectious complication significantly impaired excretory kidney function, kidney function of younger individuals with new-onset anterior uveitis should be monitored over time and during follow-up.
CRIS-Team Scopus Importer:2021-12-31
Keywords: AKI; Case report; Interstitial nephritis; RRT; TINU syndrome

Renal tubular HIF-2α expression requires VHL inactivation and causes fibrosis and cysts - Schietke, Ruth E.; Hackenbeck, Thomas; Tran, Maxine; Guenther, Regina; Klanke, Bernd; Warnecke, Christina; Knaup, Karl X.; Shukla, Deepa; Rosenberger, Christian; Koesters, Robert; Bachmann, Sebastian; Betz, Peter; et al. (PLoS ONE, 2012)
The Hypoxia-inducible transcription Factor (HIF) represents an important adaptive mechanism under hypoxia, whereas sustained activation may also have deleterious effects. HIF activity is determined by the oxygen regulated α-subunits HIF-1α or HIF-2α. Both are regulated by oxygen dependent degradation, which is controlled by the tumor suppressor "von Hippel-Lindau" (VHL), the gatekeeper of renal tubular growth control. HIF appears to play a particular role for the kidney, where renal EPO production, organ preservation from ischemia-reperfusion injury and renal tumorigenesis are prominent examples. Whereas HIF-1α is inducible in physiological renal mouse, rat and human tubular epithelia, HIF-2α is never detected in these cells, in any species. In contrast, distinct early lesions of biallelic VHL inactivation in kidneys of the hereditary VHL syndrome show strong HIF-2α expression. Furthermore, knockout of VHL in the mouse tubular apparatus enables HIF-2α expression. Continuous transgenic expression of HIF-2α by the Ksp-Cadherin promotor leads to renal fibrosis and insufficiency, next to multiple renal cysts. In conclusion, VHL appears to specifically repress HIF-2α in renal epithelia. Unphysiological expression of HIF-2α in tubular epithelia has deleterious effects. Our data are compatible with dedifferentiation of renal epithelial cells by sustained HIF-2α expression. However, HIF-2α overexpression alone is insufficient to induce tumors. Thus, our data bear implications for renal tumorigenesis, epithelial differentiation and renal repair mechanisms. © 2012 Schietke et al.

Renal uptake of the antiapoptotic protein survivin is mediated by megalin at the apical membrane of the proximal tubule - Jobst-Schwan, Tilman; Knaup, Karl; Nielsen, Rikke; Hackenbeck, Thomas; Büttner-Herold, Maike; Lechler, Philipp; Kroening, Sven; Goppelt-Strübe, Margarete; Schlötzer-Schrehardt, Ursula; Fuernrohr, Barbara G.; Voll, Reinhard E.; Amann, Kerstin Ute; et al. (American Journal of Physiology-Renal Physiology, 2013)
The inhibitor of apoptosis protein survivin is a bifunctional molecule that regulates cellular division and survival. We have previously shown that survivin protein can be found at high concentrations in the adult kidney, particularly in the proximal tubules. Here, survivin is localized primarily at the apical membrane, a pattern that may indicate absorption of the protein. Several proteins in primary urine are internalized by megalin, an endocytosis receptor, which is in principle found in the same localization as survivin. Immunolabeling for survivin in different species confirmed survivin signal localizing to the apical membrane of the proximal tubule. Immunoelectron microscopy also showed apical localization of survivin in human kidneys. Furthermore, in polarized human primary tubular cells endogenous as well as external recombinant survivin is stored in the apical region of the cells. Costaining of survivin and megalin by immunohistochemistry and immunoelectron microscopy confirmed colocalization. Finally, by surface plasmon resonance we were able to demonstrate that survivin binds megalin and cubilin and that megalin knockout mice lose survivin through the urine. Survivin accumulates at the apical membrane of the renal tubule by reuptake, which is achieved by the endocytic receptor megalin, collaborating with cubilin. For this to occur, survivin will have to circulate in the blood and be filtered into the primary urine. It is not known at this stage what the functional role of tubular survivin is. However, a small number of experimental and clinical reports implicate that renal survivin is important for functional integrity of the kidney. © 2013 by the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: Acute kidney injury; Apoptosis; Glomerular filtration; Lysosomes; Proteinuria

Responsiveness of afferent renal nerve units in renovascular hypertension in rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Rafii-Tabrizi, Salman; Doellner, Johannes; Cordasic, Nada; Linz, Peter; Karl, Annalena; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; et al. (Pflügers Archiv: European Journal of Physiology, 2021)
Previous data suggest that renal afferent nerve activity is increased in hypertension exerting sympathoexcitatory effects. Hence, we wanted to test the hypothesis that in renovascular hypertension, the activity of dorsal root ganglion (DRG) neurons with afferent projections from the kidneys is augmented depending on the degree of intrarenal inflammation. For comparison, a nonhypertensive model of mesangioproliferative nephritis was investigated. Renovascular hypertension (2-kidney, 1-clip [2K1C]) was induced by unilateral clipping of the left renal artery and mesangioproliferative glomerulonephritis (anti-Thy1.1) by IV injection of a 1.75-mg/kg BW OX-7 antibody. Neuronal labeling (dicarbocyanine dye [DiI]) in all rats allowed identification of renal afferent dorsal root ganglion (DRG) neurons. A current clamp was used to characterize neurons as tonic (sustained action potential [AP] firing) or phasic (1-4 AP) upon stimulation by current injection. All kidneys were investigated using standard morphological techniques. DRG neurons exhibited less often tonic response if in vivo axonal input from clipped kidneys was received (30.4% vs. 61.2% control, p < 0.05). However, if the nerves to the left clipped kidneys were cut 7 days prior to investigation, the number of tonic renal neurons completely recovered to well above control levels. Interestingly, electrophysiological properties of neurons that had in vivo axons from the right non-clipped kidneys were not distinguishable from controls. Renal DRG neurons from nephritic rats also showed less often tonic activity upon current injection (43.4% vs. 64.8% control, p < 0.05). Putative sympathoexcitatory and impaired sympathoinhibitory renal afferent nerve fibers probably contribute to increased sympathetic activity in 2K1C hypertension.
CRIS-Team WoS Importer:2021-07-23

Restricted expression of mGCMa in kidney ind thymus - Hashemolhosseini, Said; Hadjihannas, Michel; Haase, Christian; Amann, Kerstin Ute; Wegner, Michael (Mechanisms of Development, 2002)
UnivIS-Import:2015-04-14:Pub.2002.forsch.sonder.sfb423.restri

RNA sequencing reveals induction of specific renal inflammatory pathways in a rat model of malignant hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Fahlbusch, Fabian; Ekici, Arif Bülent; Kirchner, Philipp; Daniel, Christoph; Amann, Kerstin Ute; Velkeen, Roland; Wölfle, Joachim; Schiffer, Mario; Hartner, Andrea; Hilgers, Karl Friedrich (Journal of Molecular Medicine, 2021)
Abstract: In malignant hypertension, far more severe kidney injury occurs than in the “benign” form of the disease. The role of high blood pressure and the renin–angiotensin–aldosterone system is well recognized, but the pathogenesis of the renal injury of malignant hypertension (MH) remains incompletely understood. Using the rat model of two-kidney, one-clip renovascular hypertension in which some but not all animals develop MH, we performed a transcriptomic analysis of gene expression by RNA sequencing to identify transcriptional changes in the kidney cortex specific for MH. Differential gene expression was assessed in three groups: MH, non-malignant hypertension (NMH), and normotensive, sham-operated controls. To distinguish MH from NMH, we considered two factors: weight loss and typical renovascular lesions. Mean blood pressure measured intraarterially was elevated in MH (220 ± 6.5 mmHg) as well as in NMH (192 ± 6.4 mmHg), compared to controls (119 ± 1.7 mmHg, p < 0.05). Eight hundred eighty-six genes were exclusively regulated in MH only. Principal component analysis revealed a separated clustering of the three groups. The data pointed to an upregulation of many inflammatory mechanisms in MH including pathways which previously attracted relatively little attention in the setting of hypertensive kidney injury: Transcripts from all three complement activation pathways were upregulated in MH compared to NMH but not in NMH compared with controls; immunohistochemistry confirmed complement deposition in MH exclusively. The expression of chemokines attracting neutrophil granulocytes (CXCL6) and infiltration of myeloperoxidase-positive cells were increased only in MH rats. The data suggest that these pathways, especially complement deposition, may contribute to kidney injury under MH. Key messages: The most severe hypertension-induced kidney injury occurs in malignant hypertension.In a rat model of malignant hypertension, we assessed transcriptional responses in the kidney exposed to high blood pressure. A broad stimulation of inflammatory mechanisms was observed, but a few specific pathways were activated only in the malignant form of the disease, notably activation of the complement cascades.Complement inhibitors may alleviate the thrombotic microangiopathy of malignant hypertension even in the absence of primary complement abnormalities.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Complement activation; Inflammation; Kidney injury; Malignant hypertension; RNA-Seq; Two-kidney one-clip renovascular hypertension (2K1C)

Role of guanylate binding protein-1 in vascular defects associated with chronic inflammatory diseases - Hammon, Matthias; Herrmann, Martin; Bleiziffer, Oliver; Pryymachuk, Galyna; Andreoli, Laura; Munoz, Luis Enrique; Amann, Kerstin Ute; Mondini, Michele; Gariglio, Marisa; Airo, Paolo; Schellerer, Vera; Hatzopoulos, Antonis K.; et al. (Journal of Cellular and Molecular Medicine, 2011)
Rheumatic autoimmune disorders are characterized by a sustained pro-inflammatory microenvironment associated with impaired function of endothelial progenitor cells (EPC) and concomitant vascular defects. Guanylate binding protein-1 (GBP-1) is a marker and intracellular regulator of the inhibition of proliferation, migration and invasion of endothelial cells induced by several pro-inflammatory cytokines. In addition, GBP-1 is actively secreted by endothelial cells. In this study, significantly increased levels of GBP-1 were detected in the sera of patients with chronic inflammatory disorders. Accordingly we investigated the function of GBP-1 in EPC. Interestingly, stable expression of GBP-1 in T17b EPC induced premature differentiation of these cells, as indicated by a robust up-regulation of both Flk-1 and von Willebrand factor expression. In addition, GBP-1 inhibited the proliferation and migration of EPC in vitro. We confirmed that GBP-1 inhibited vessel-directed migration of EPC at the tissue level using the rat arterio-venous loop model as a novel quantitative in vivo migration assay. Overall, our findings indicate that GBP-1 contributes to vascular dysfunction in chronic inflammatory diseases by inhibiting EPC angiogenic activity via the induction of premature EPC differentiation. © 2011 The Authors Journal of Cellular and Molecular Medicine © 2011 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Endothelial progenitor cells; Guanylate binding protein-1; Inflammation; Rheumatic autoimmune disorders; Rheumatoid arthritis; Systemic lupus erythematosus; Systemic sclerosis

Round-Robin test for the histological diagnosis of acute colonic Graft-versus-Host disease validating established histological criteria and grading systems - Hippe, Katrin; Kreft, Andreas; Reu-Hofer, Simone; Rosenwald, Andreas; Ferrazzi, Fulvia; Daniel, Christoph; Amann, Kerstin Ute; Kraus, Sabrina; Holler, Ernst; Kandulski, Arne; Hirsch, Daniela; Buttner, Anke; et al. (Virchows Archiv, 2023)
Histomorpholgy is one of the mainstays of acute Graft-versus-host disease (GvHD) diagnosis. However, concerns about reproducibility and the most appropriate grading system question its usefulness. Our aim was to assess histomorphological parameters and previously reported grading systems for GvHD regarding reproducibility and validity. Moreover, we propose that sum scores, derived by combining separately scored morphological parameters into a total score, might provide a simplified but equally effective means to grade GvHD. A total of 123 colon biopsies were assessed across four pathologists for intestinal GvHD using a Round-Robin test and results were correlated with clinical findings. Interobserver reproducibility was high for histological parameters that were evaluated as indicators of acute GvHD. Published grading systems were moderately reproducible (ICC 0.679–0.769) while simplified sum scores, in comparison, showed better interrater reliability (ICC 0.818–0.896). All grading systems and sum scores were associated with clinical signs of GvHD and in part with therapy response and survival. However, they were not able to stratify patients according to the clinical severity of GvHD. In a hot-spot analysis 1 crypt apoptotic body (CAB) in 10 crypts was a reasonable cut-off value for minimal diagnostic criteria of GvHD. In conclusion, histology can contribute to the diagnosis of GvHD and is reproducible. Published grading systems are able to reflect clinical findings as are simplified sum scores, which showed improved reproducibility and might be easier to handle as they are based on adding up histological parameters rather than transferring histological findings into a separate grading system. Sum scores will have to be further tested in a prospective setting.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Acute Graft-versus-host disease; Colon biopsy; Grading; Interobserver agreement; Round-Robin test

Screening of Micro-organic Compounds in Groundwater from Areas with Chronic Kidney Disease of Unclear Aetiology (CKDu) in the Dry Zone of Sri Lanka - Chandrajith, Rohana; Zwiener, Christian; Daniel, Christoph; Amann, Kerstin Ute; Nanayakkara, Nishantha; Barth, Johannes (Exposure and Health, 2024)
Chronic kidney disease of unknown aetiology (CKDu) occurs in tropical countries, including Latin America, Mexico, Sri Lanka, and India. The disease occurs mainly in men who work in the agricultural sector. Although many studies have been conducted in CKDu areas, hardly any have examined emerging organic contaminants (EOCs) in drinking water. Therefore, this study examined EOCs, including pesticide residues, pharmaceuticals, and personal care products, in 29 shallow groundwater samples collected from wells commonly used by CKDu patients. These patients were identified through renal biopsy examinations from the Girandurukotte and Wilgamuwa regions in the dry zone of Sri Lanka. Of 110 EOCs measured, 40 were found in at least one or more samples. Among the detected EOCs, all groundwater samples examined showed the highest concentrations of caffeine (max: 950 ng/L) and DEET (max: 647 ng/L). In particular, the insect repellents commonly used in the region, such as coils, mats, vaporizers, spray and creams, would be the source of DEET in the environment. Pharmaceuticals and personal care products were the most common EOCs in all groundwater samples, with concentrations ranging from 129 (propylparaben) to 1.26 ng/L (carbamazepine) and 1.25 ng/L (hydrochlorothiazide), respectively, followed by herbicides and fungicides. Sources of such compounds would be insect repellents, antifungal and bactericidal preservatives, and agricultural pesticides. Notably, none of the identified EOCs reached critical values and were often below the values in European drinking water standards. Although primary evidence of EOCs as a cause of the disease does not emerge from the results of this study, regular monitoring of EOCs in groundwater, particularly in the dry zone of Sri Lanka, is essential as the presence of these compounds highlights their vulnerability in shallow groundwater wells.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Emerging contaminants; Personal-care product; Pesticides; Pharmaceuticals; Solid-phase extraction

Selective stabilization of HIF-1α in renal tubular cells by 2-oxoglutarate analogues - Schley, Gunnar; Klanke, Bernd; Schödel, Johannes; Kroening, Sven; Türkoglu, Gazi; Beyer, Andreas; Hagos, Yohannes; Amann, Kerstin Ute; Burckhardt, Birgitta C.; Burzlaff, Nicolai; Eckardt, Kai-Uwe; Willam, Carsten (American Journal of Pathology, 2012)
The role of proximal versus distal tubular injury in the pathogenesis of acute kidney injury (AKI) is debatable. Inhibition of prolyl hydroxylases that regulate the degradation of hypoxia-inducible transcription factors (HIFs) is a promising therapeutic approach to optimize energy preservation under hypoxia and has successfully been applied to protect kidney structure and function in AKI models. Presently used prolyl hydroxylase inhibitors are lipophilic 2-oxoglutarate analogues (2OGAs) that are widely taken up in cells of most organs. Given the selective expression of organic anion transporters (OATs) in renal proximal tubular cells, we hypothesized that hydrophilic 2OGAs can specifically target proximal tubular cells. We found that cellular hydrophilic 2OGAs uptake depended on OATs and largely confined to the kidney, where it resulted in activation of HIF target genes only in proximal tubular cells. When applied in ischemia-reperfusion experiments, systemically active 2OGA preserved kidney structure and function, but OAT1-transported 2OGA was not protective, suggesting that HIF stabilization in distal tubular rather than proximal tubular cells and/or nontubular cells mediates protective effects. This study provides proof of concept for selective drug targeting of proximal tubular cells on the basis of specific transporters, gives insights into the role of different nephron segments in AKI pathophysiology, and may offer options for long-term HIF stabilization in proximal tubules without confounding effects of erythropoietin induction in peritubular cells and unwarranted extrarenal effects. © 2012 American Society for Investigative Pathology.

Serum Uromodulin as early marker for ischemic acute kidney injury and nephron loss: association with kidney tissue distribution pattern - Vonbrunn, Eva; Ebert, Nadja; Cordasic, Nada; Amann, Kerstin Ute; Büttner, Anke; Büttner-Herold, Maike; Scherberich, Jürgen E.; Daniel, Christoph (Journal of Translational Medicine, 2025)
Background: Uromodulin (UMOD) is expressed in kidneys and is mainly excreted in the urine, although a smaller amount is also released into the serum. Here, we investigated UMOD in acute kidney injury (AKI), with particular focus on the utility of serum UMOD as marker for nephron loss. Methods: Blood and kidney samples were collected 6 h, 24 h, 3 days and 8 weeks after ischemia/reperfusion (I/R) in a rat model. To investigate the impact of nephron number on UMOD levels, sera and tissue from healthy, uninephrectomized (Unx) and 5/6-nephrectomized (Snx) rats were analyzed. Histological changes, kidney function and cell damage were evaluated and serum UMOD, Umod mRNA expression and distribution of UMOD protein in the kidney were examined. Results: In AKI, kidney function was markedly impaired 24 h after I/R, while kidney injury and serum UMOD was increased transiently. Simultaneously, the amount of UMOD-positive kidney cells rapidly decreased 24 h after I/R compared to healthy kidneys, and mRNA expression of Umod was lowest on days 1–3 after I/R. Serum UMOD correlated with nephron number showing the highest levels in healthy rats, which were reduced after Unx and further reduced after Snx. Conclusion: In an AKI model with severe tubular damage, a transient increase in UMOD serum levels in parallel with loss of UMOD-positive cells suggests temporary release of UMOD from destroyed tubular cells into the blood. Serum UMOD appears to be not only a marker of chronic renal failure but also of acute loss of functional and cellular integrity of kidney epithelia in AKI.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Acute kidney injury; Ischemia/reperfusion; Nephron loss; Tamm-Horsfall protein; Uromodulin

SGK1 induces vascular smooth muscle cell calcification through NF-κB signaling - Voelkl, Jakob; Luong, Trang T. D.; Tuffaha, Rashad; Musculus, Katharina; Auer, Tilman; Lian, Xiaoming; Daniel, Christoph; Zickler, Daniel; Boehme, Beate; Sacherer, Michael; Metzler, Bernhard; Kuhl, Dietmar; et al. (Journal of Clinical Investigation, 2018)
Medial vascular calcification, associated with enhanced mortality in chronic kidney disease (CKD), is fostered by osteo-/chondrogenic transdifferentiation of vascular smooth muscle cells (VSMCs). Here, we describe that serum- and glucocorticoid-inducible kinase 1 (SGK1) was upregulated in VSMCs under calcifying conditions. In primary human aortic VSMCs, overexpression of constitutively active SGK1S422D, but not inactive SGK1K127N, upregulated osteo-/chondrogenic marker expression and activity, effects pointing to increased osteo-/chondrogenic transdifferentiation. SGK1S422D induced nuclear translocation and increased transcriptional activity of NF-κB. Silencing or pharmacological inhibition of IKK abrogated the osteoinductive effects of SGK1S422D. Genetic deficiency, silencing, and pharmacological inhibition of SGK1 dissipated phosphate-induced calcification and osteo-/chondrogenic transdifferentiation of VSMCs. Aortic calcification, stiffness, and osteo-/chondrogenic transdifferentiation in mice following cholecalciferol overload were strongly reduced by genetic knockout or pharmacological inhibition of Sgk1 by EMD638683. Similarly, Sgk1 deficiency blunted vascular calcification in apolipoprotein E-deficient mice after subtotal nephrectomy. Treatment of human aortic smooth muscle cells with serum from uremic patients induced osteo-/chondrogenic transdifferentiation, effects ameliorated by EMD638683. These observations identified SGK1 as a key regulator of vascular calcification. SGK1 promoted vascular calcification, at least partly, via NF-κB activation. Inhibition of SGK1 may, thus, reduce the burden of vascular calcification in CKD.
EVALuna2:34426

Siglec-G deficiency leads to more severe collagen-induced arthritis and earlier onset of lupus-like symptoms in MRL/lpr mice - Boekers, Susanne; Urbat, Anne; Daniel, Christoph; Amann, Kerstin Ute; Smith, Kenneth G. C.; Espeli, Marion; Nitschke, Lars (Journal of Immunology, 2014)
Siglec-G is a member of the sialic acid-binding Ig-like lectin (Siglec) family expressed on all B cells. Siglec-G-deficient mice show a large expansion of the B1 cell compartment, demonstrating the crucial role of Siglec-G as an inhibitory receptor on this cellular subset. Although Siglec-G-deficient mice did not develop spontaneous autoimmunity, mice double-deficient for Siglec-G and the related Siglec protein CD22 did show autoimmunity at an older age. In this study, we addressed the question of whether loss of Siglec G on its own affects disease severity in animal models of rheumatoid arthritis and systemic lupus erythematosus. Siglec-G-deficient mice showed moderately increased clinical severity and higher inflammation of the knee joints following collagen-induced arthritis, when compared with control mice. The Siglec-G-deficient mouse was also backcrossed to the autoimmune prone MLR/lpr background. Although both Siglec-G-deficient and control MRL/lpr mice developed a lupus-like disease, Siglec-G-deficient MRL/lpr mice showed an earlier occurrence of autoantibodies; a higher lymphoproliferation of B and T cells; and an earlier onset of disease, as shown by proteinuria and glomerular damage in the kidney. Moreover, Siglec-G-deficient female mice showed a significantly reduced survival compared with female control MRL/lpr mice. Thus, the loss of the inhibitory receptor Siglec-G led to a moderate exacerbation of disease severity and early onset in both collagen-induced arthritis and spontaneous lupus nephritis in MRL/lpr mice.
EVALuna2:25460

Signaling pathways involved in vascular smooth muscle cell calcification during hyperphosphatemia - Voelkl, Jakob; Lang, Florian; Eckardt, Kai Uwe; Amann, Kerstin Ute; Kuro-o, Makoto; Pasch, Andreas; Pieske, Burkert; Alesutan, Ioana (Cellular and Molecular Life Sciences, 2019)
Medial vascular calcification has emerged as a putative key factor contributing to the excessive cardiovascular mortality of patients with chronic kidney disease (CKD). Hyperphosphatemia is considered a decisive determinant of vascular calcification in CKD. A critical role in initiation and progression of vascular calcification during elevated phosphate conditions is attributed to vascular smooth muscle cells (VSMCs), which are able to change their phenotype into osteo-/chondroblasts-like cells. These transdifferentiated VSMCs actively promote calcification in the medial layer of the arteries by producing a local pro-calcifying environment as well as nidus sites for precipitation of calcium and phosphate and growth of calcium phosphate crystals. Elevated extracellular phosphate induces osteo-/chondrogenic transdifferentiation of VSMCs through complex intracellular signaling pathways, which are still incompletely understood. The present review addresses critical intracellular pathways controlling osteo-/chondrogenic transdifferentiation of VSMCs and, thus, vascular calcification during hyperphosphatemia. Elucidating these pathways holds a significant promise to open novel therapeutic opportunities counteracting the progression of vascular calcification in CKD.
CRIS-Team Scopus Importer:2019-05-02
Keywords: CKD; Osteogenic signaling; Phosphate; Vascular calcification; Vascular smooth muscle cells

Significance of Glomerular Immune Reactivity in Time Zero Biopsies for Allograft Survival Beyond IgA - Vonbrunn, Eva; Serikova, Sofya; Daniel, Christoph; Amann, Kerstin Ute; Schödel, Johannes; Buchholz, Björn; Ferrazzi, Fulvia; Heller, Katharina M.; Apel, Hendrik; Büttner-Herold, Maike (Frontiers in Medicine, 2021)
The quality of a renal transplant can influence the clinical course after transplantation. Glomerular immune reactivity in renal transplants has previously been described, focusing particularly on IgA, and has been shown to disappear in most cases without affecting the outcome. Here, we describe a cohort of time zero biopsies with regard to glomerular immune reactivity and implications for histomorphology and follow-up. 204 Time zero biopsies were analyzed by immunohistochemistry for glomerular immune reactivity. Time zero and 1-year biopsies were evaluated for histomorphological changes, which, together with clinical and follow-up data, were assessed for associations with glomerular immune profiles. Nearly half of the analyzed time zero biopsies showed glomerular immune reactivity with mesangial C3 being the most common (32.9%), followed by IgA (13.7%) and fullhouse patterns (6.9%). Strong C3 deposits (C3high) were only observed in deceased transplants. In the majority of cases immune reactivity was undetectable in follow-up biopsies and had no adverse effect on transplant function in follow-up of 5 years. In kidney pairs transplanted to different recipients a strong concordance of immune profiles in both kidneys was observed. Moreover, an association of male donor sex and deceased donor transplantation with the presence of immune reactivity was observed. In conclusion, glomerular immune reactivity is a very frequent finding in time zero biopsies, which seems to be determined by donor parameters including male sex and deceased donor transplants. It had no adverse impact on transplant function in 5-year follow-up. Glomerular immune reactivity in time zero biopsies, therefore, does not appear to indicate an inferior quality of the transplant.
CRIS-Team WoS Importer:2021-04-30
Keywords: complement; renal tranplantation; time zero biopsy; transplant quality; immune reactivity

Small oral squamous cell carcinomas with nodal lymphogenic metastasis show increased infiltration of M2 polarized macrophages - An immunohistochemical analysis - Weber, Manuel; Büttner, Maike; Hyckel, Peter; Moebius, Patrick; Distel, Luitpold; Ries, Jutta; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Journal of Cranio-Maxillofacial Surgery, 2014)
In solid malignancies the influence of immunological parameters - especially of macrophages - on invasiveness, metastatic potential and prognosis has been shown. There are no studies quantitatively analysing the macrophage polarization in oral squamous cell carcinoma (oscc). The aim of this study was to correlate macrophage polarization in the epithelial and stromal compartment of oscc with histopathologic parameters.T1 and T2 oscc samples (n = 34) were used. Automated immunohistochemical staining detected CD68, CD11c, CD163 and MRC1 positive cells. All samples were completely digitalized using whole slide imaging and the number of stained cells per area was assessed quantitatively.Primary tumours with lymphogenic metastasis (N+) showed a significantly (p < 0.05) increased count of CD68, CD11c, CD163 and MRC1 positive cells in the epithelial fraction compared to N0 tumours. The ratio of CD163 positive cells (M2 macrophages) to CD68 positive cells (M1 and M2 macrophages) was significantly (p < 0.05) increased in N+ tumours.An increased macrophage infiltration and an increased M2 polarization in primary oral squamous cell carcinomas with lymphogenic metastasis was shown. Macrophages that migrated into the epithelial tumour fraction seem to be of special biological importance. The results indicate a central role of macrophages in the progression of oscc.
EVALuna2:18151

Smartwatch, hemorrhagic pericardial effusion and acute kidney injury—all united in one diagnosis Smartwatch, hämorrhagischer Perikarderguss und akute Nierenschädigung – alle vereint eine Diagnose - Neumann, L. M.; Baumgärtel, M. W.; Amann, Kerstin Ute; Friesicke, H. (Die Nephrologie, 2024)
CRIS-Team Scopus Importer:2024-11-22

Soluble DPP4 originates in part from bone marrow cells and not from the kidney - Wang, Zhendi; Grigo, Christina; Steinbeck, Julia; von Hörsten, Stephan; Amann, Kerstin Ute; Daniel, Christoph (Peptides, 2014)
Dipeptidyl peptidase 4 (DPP4) is known to inactivate incretins as well as important chemokines and neuropeptides. DPP4 is expressed as a transmembrane protein but also occurs as a soluble enzyme circulating in the blood. However, the origin of the soluble DPP4 (sDPP4) is still unknown. In this study, DPP4 activity was quantified in plasma and extracted from different rat organs. Then, in order to see if the kidney or the bone marrow was the source of sDPP4, kidney or bone marrow transplantation was performed between wildtype (wt) Dark Agouti (DA) and DPP4 deficient congenic rats (n=6-9). Kidney was verified to have the highest DPP4 activity, followed by spleen and lung. In the following three weeks after successful kidney transplantation only transient trace plasma DPP4 activity was detected in DPP4 deficient rats receiving wt kidneys. In addition, DPP4 activity was not diminished in DA wt rats receiving DPP4 deficient kidneys. Both findings indicated that sDPP4 did not originate from the kidney. In contrast, 43±14% (compared to wt) sDPP4 activity was detected in the plasma of DPP4 deficient DA rats that were reconstituted with wt bone marrow cells. Not only leukocyte but also macrophage subpopulations express DPP4 in bone marrow as well as in blood as assessed by flow cytometry. Thus, bone marrow derived cells but not the kidney represent at least one source of sDPP4. And leukocyte or macrophage subpopulations could be potential candidates.
EVALuna2:3742

Soluble guanylate cyclase stimulator BAY 41-8543 and female sex ameliorate uremic aortic remodeling in a rat model of mild uremia - Stancu, Bianca; Kraemer, Stephanie; Loof, Tanja; Mika, Alice; Amann, Kerstin Ute; Neumayer, Hans-H.; Peters, Harm (Journal of Hypertension, 2015)
Cardiovascular disease is the leading comorbidity in renal patients and has been related to impaired nitric oxide signaling. Estrogens exert protective effects on the vascular system. This study investigates the effects of biological sex and nitric oxide-independent soluble guanylate cyclase (sGC) stimulator BAY 41-8543 on aortic remodeling in experimental mild uremia.Age-matched male and female Wistar rats were assigned for 18 weeks into sham-operated, subtotally nephrectomized (SNX), SNX + BAY 41-8543 and SNX + hydralazine. Analysis involved functional, histological, and molecular kidney and thoracic aorta parameters.SNX significantly increased SBP, which was comparably reduced to control levels by BAY 41-8543 and hydralazine. In SNX males, uremic aortic remodeling was characterized by marked media thickening and increased media-to-lumen ratio (P < 0.01), vascular smooth muscle cell (VSMC) proliferation, macrophage infiltration, extracellular matrix turnover, decreased aortic elastin-to-collagen ratio (P < 0.01) and endothelial nitric oxide-synthase (eNOS) mRNA expression (P < 0.05). No significant alterations of aortic media-to-lumen ratio, VSMC proliferation, macrophage infiltration, matrix metalloproteinase-2, and eNOS mRNA expressions were seen in female uremic animals. BAY 41-8543 significantly ameliorated uremic aortic remodeling and stiffening involving reduced VSMC proliferation, collagen I-deposition, extracellular matrix turnover, and increased elastin content and eNOS mRNA expression. Hydralazine treatment did not substantially alter aortic remodeling.Experimental mild uremia leads to pronounced aortic hypertrophic remodeling and stiffening with sex-dependent alternations, and these are more severe in male rats. BAY 41-8543 ameliorates uremic aortic remodeling in a blood pressure-independent manner. The results suggest that sGC-stimulators may offer a novel treatment mode for pathological arterial wall remodeling in patients with impaired renal function.
EVALuna2:25503

Stain-Independent Deep Learning-Based Analysis of Digital Kidney Histopathology. - Bouteldja, Nassim; Hölscher, David Laurin; Klinkhammer, Barbara Mara; Buelow, Roman David; Lotz, Johannes; Weiss, Nick; Daniel, Christoph; Amann, Kerstin Ute; Boor, Peter (American Journal of Pathology, 2023)
Convolutional neural network (CNN)-based image analysis applications in digital pathology (eg, tissue segmentation) require a large amount of annotated data and are mostly trained and applicable on a single stain. Here, a novel concept based on stain augmentation is proposed to develop stain-independent CNNs requiring only one annotated stain. In this benchmark study on stain independence in digital pathology, this approach is comprehensively compared with state-of-the-art techniques including image registration and stain translation, and several modifications thereof. A previously developed CNN for segmentation of periodic acid-Schiff-stained kidney histology was used and applied to various immunohistochemical stainings. Stain augmentation showed very high performance in all evaluated stains and outperformed all other techniques in all structures and stains. Without the need for additional annotations, it enabled segmentation on immunohistochemical stainings with performance nearly comparable to that of the annotated periodic acid-Schiff stain and could further uphold performance on several held-out stains not seen during training. Herein, examples of how this framework can be applied for compartment-specific quantification of immunohistochemical stains for inflammation and fibrosis in animal models and patient biopsy specimens are presented. The results show that stain augmentation is a highly effective approach to enable stain-independent applications of deep-learning segmentation algorithms. This opens new possibilities for broad implementation in digital pathology.
EVALuna2:508561

Standardisierte histomorphologische Aufarbeitung von Peritonealbiopsien im Rahmen des Deutschen Peritonealbiopsieregisters (GRIP, German Registry In PD) - Pfister, Frederick; Büttner-Herold, Maike; Kitsche, Benno; Bulian, Dirk R.; Kielstein, Jan; Wanninger, Reinhard; Eden, Gabriele; Alscher, Dominik; Nebel, Michael; Schwenger, Vedat; Amann, Kerstin Ute (Pathologe, 2020)
The peritoneal lining of the abdominal cavity consists of a parietal and visceral sheet. The serosa is an interesting organ, which in medical practice is particularly important in the context of chronic peritoneal dialysis (PD). This method of renal replacement therapy utilizes the semipermeability of the peritoneal surface by applying PD solutions of differing osmolarity to eliminate toxic substances and regulate fluid and electrolyte equilibrium. This method is an ideal approach especially for younger patients and is very effective at least for some time. Pre-existing injury to the peritoneum, for example as a consequence of chronic renal insufficiency or associated comorbidities and inflammatory changes that develop during PD, results in a structural remodelling of the serosa. As a consequence, the filtering function of the serosa is lost and PD has to be replaced by another renal replacement therapy. Thorough knowledge of the morphology of peritoneal changes as well as of the risk factors is of paramount importance for therapeutic management and prognosis of PD patients. In order to take this into account, the German Registry In Peritoneal Dialysis (Deutsches Peritonealbiopsieregister, GRIP) was founded a few years ago, which now includes roughly 1700 biopsies, of which detailed clinical and histomorphological information was systematically acquired and collected.
CRIS-Team Scopus Importer:2020-09-18
Keywords: EPS; Fibrosis; Morphology; Peritoneal dialysis; Peritoneum

Stressed erythrocytes bind intravascular von Willebrand factor and promote microangiopathy - Nicolay, J. P.; Thorn, V.; Daniel, Christoph; Amann, Kerstin Ute; Siraskar, B.; Lang, F.; Hillgruber, C.; Goerge, T.; Gorzelanny, C.; Huck, V.; Obser, T.; Schneppenheim, R.; et al. (2018)
EVALuna2:34440

Structured illumination microscopy and automatized image processing as a rapid diagnostic tool for podocyte effacement - Siegerist, Florian; Ribback, Silvia; Dombrowski, Frank; Amann, Kerstin Ute; Zimmermann, Uwe; Endlich, Karlhans; Endlich, Nicole (Scientific Reports, 2017)
The morphology of podocyte foot processes is obligatory for renal function. Here we describe a method for the superresolution-visualization of podocyte foot processes using structured illumination microscopy of the slit diaphragm, which before has only been achieved by electron microscopy. As a proof of principle, we measured a mean foot process width of 0.249 ± 0.068 µm in healthy kidneys and a significant higher mean foot process width of 0.675 ± 0.256 µm in minimal change disease patients indicating effacement of foot processes. We then hypothesized that the slit length per glomerular capillary surface area (slit diaphragm density) could be used as an equivalent for the diagnosis of effacement. Using custom-made software we measured a mean value of 3.10 ± 0.27 µm(-1) in healthy subjects and 1.83 ± 0.49 µm(-1) in the minimal change disease patients. As foot process width was highly correlated with slit diaphragm density (R(2) = 0.91), we concluded that our approach is a valid method for the diagnosis of foot process effacement. In summary, we present a new technique to quantify podocyte damage, which combines superresolution microscopy with automatized image processing. Due to its diverse advantages, we propose this technique to be included into routine diagnostics of glomerular histopathology.
EVALuna2:25548

Studies on the Role of the Transcription Factor Tcf21 in the Transdifferentiation of Parietal Epithelial Cells into Podocyte-Like Cells. - Kliewe, Felix; Kuss, Andreas W.; Siegerist, Florian; Schröder, Sindy; Schordan, Sandra; Artelt, Nadine; Kindt, Frances; Amann, Kerstin Ute; Lindenmeyer, Maja T.; Endlich, Karlhans; Endlich, Nicole (Cellular Physiology and Biochemistry, 2021)
BACKGROUND/AIMS: Podocyte differentiation is essential for proper blood filtration in the kidney. It is well known that transcription factors play an essential role to maintain the differentiation of podocytes. The present study is focused on the basic helix-loop-helix (bHLH) transcription factor Tcf21 (Pod1) which is essential for the development of podocytes in vivo. Since parietal epithelial cells (PECs) are still under debate to be progenitor cells which can differentiate into podocytes, we wanted to find out whether the expression of Tcf21 induces a transition of PECs into podocytes. METHODS: We transfected PECs with Tcf21-GFP and analyzed the expression of PEC- and podocyte-specific markers. Furthermore, we performed ChIP-Seq analysis to identify new putative interaction partners and target genes of Tcf21. RESULTS: By gene arrays analysis, we found that podocytes express high levels of Tcf21 in vivo in contrast to cultured podocytes and parietal epithelial cells (PECs) in vitro. After the expression of Tcf21 in PECs, we observed a downregulation of specific PEC markers like caveolin‑1, β-catenin and Pax2. Additionally, we found that the upregulation of Tcf21 induced multi-lobulation of cell nuclei, budding and a formation of micronuclei (MBM). Furthermore, a high number of PECs showed a tetraploid set of chromosomes. By qRT-PCR and Western blot analysis, we revealed that the transcription factor YY1 is downregulated by Tcf21. Interestingly, co-expression of YY1 and Tcf21 rescues MBM and reduced tetraploidy. By ChIP-Seq analysis, we identified a genome-wide Tcf21-binding site (CAGCTG), which matched the CANNTG sequence, a common E-box binding motif used by bHLH transcription factors. Using this technique, we identified additional Tcf21 targets genes that are involved in the regulation of the cell cycle (e.g. Mdm2, Cdc45, Cyclin D1, Cyclin D2), on the stability of microtubules (e.g. Mapt) as well as chromosome segregation. CONCLUSION: Taken together, we demonstrate that Tcf21 inhibits the expression of PEC-specific markers and of the transcription factor YY1, induces MBM as well as regulates the cell cycle suggesting that Tcf21 might be important for PEC differentiation into podocyte-like cells.
EVALuna2:466165

Studying the role of fascin-1 in mechanically stressed podocytes - Kliewe, Felix; Scharf, Christian; Rogge, Henrik; Darm, Katrin; Lindenmeyer, Maja T.; Amann, Kerstin Ute; Cohen, Clemens D.; Endlich, Karlhans; Endlich, Nicole (Scientific Reports, 2017)
Glomerular hypertension causes glomerulosclerosis via the loss of podocytes, which are challenged by increased mechanical load. We have demonstrated that podocytes are mechanosensitive. However, the response of podocytes to mechanical stretching remains incompletely understood. Here we demonstrate that the actin-bundling protein fascin-1 plays an important role in podocytes that are exposed to mechanical stress. Immunofluorescence staining revealed colocalization of fascin-1 and nephrin in mouse kidney sections. In cultured mouse podocytes fascin-1 was localized along actin fibers and filopodia in stretched and unstretched podocytes. The mRNA and protein levels of fascin-1 were not affected by mechanical stress. By Western blot and 2D-gelelectrophoresis we observed that phospho-fascin-1 was significantly downregulated after mechanical stretching. It is known that phosphorylation at serine 39 (S39) regulates the bundling activity of fascin-1, e.g. required for filopodia formation. Podocytes expressing wild type GFP-fascin-1 and non-phosphorylatable GFP-fascin-1-S39A showed marked filopodia formation, being absent in podocytes expressing phosphomimetic GFP-fascin-1-S39D. Finally, the immunofluorescence signal of phosphorylated fascin-1 was strongly reduced in glomeruli of patients with diabetic nephropathy compared to healthy controls. In summary, mechanical stress dephosphorylates fascin-1 in podocytes in vitro and in vivo thereby fascin-1 may play an important role in the adaptation of podocytes to mechanical forces.
EVALuna2:25547

Study protocol: the TRAnsplant BIOpsies (TRABIO) study - a prospective, observational, multicentre cohort study to assess the treatment of kidney graft rejections - von Samson-Himmelstjerna, Friedrich Alexander; Esser, Grit; Schulte, Kevin; Kolbrink, Benedikt; Krautter, Markus; Schwenger, Vedat; Weinmann-Menke, Julia; Matschkal, Julia; Schraml, Florian; Pahl, Anne; Braunisch, Matthias; Amann, Kerstin Ute; et al. (BMJ Open, 2022)
INTRODUCTION: Despite continued efforts, long-term outcomes of kidney transplantation remain unsatisfactory. Kidney graft rejections are independent risk factors for graft failure. At the participating centres of the TRAnsplant BIOpsies study group, a common therapeutic standard has previously been defined for the treatment of graft rejections. The outcomes of this strategy will be assessed in a prospective, observational cohort study. METHODS AND ANALYSIS: A total of 800 kidney transplantation patients will be enrolled who undergo a graft biopsy because of deteriorating kidney function. Patients will be stratified according to the Banff classification, and the influence of the treatment strategy on end points will be assessed using regression analysis. Primary end points will be all-cause mortality and graft survival. Secondary end points will be worsening of kidney function (≥30% decline of estimated Glomerular Filtration Rate [eGFR] or new-onset large proteinuria), recurrence of graft rejection and treatment response. Baseline data and detailed histopathology data will be entered into an electronic database on enrolment. During a first follow-up period (within 14 days) and subsequent yearly follow-ups (for 5 years), treatment strategies and clinical course will be recorded. Recruitment at the four participating centres started in September 2016. As of August 2020, 495 patients have been included. ETHICS AND DISSEMINATION: Ethical approval for the study has been obtained from the ethics committee of Kiel (AZ B 278/16) and was confirmed by the committees of Munich, Mainz and Stuttgart. The results will be reported in a peer-reviewed journal, according to the Strengthening the Reporting of Observational Studies in Epidemiology criteria. TRIAL REGISTRATION NUMBER: ISRCTN78772632; Pre-results.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Nephrology; Renal transplantation; TRANSPLANT MEDICINE; Transplant pathology

Successful Desensitization with Imlifidase and Daratumumab in a Highly Immunized, Crossmatch Positive, Blood Group-Incompatible Living-Donor Re-Transplant Recipient with Systemic Lupus Erythematosus and Antiphospholipid Syndrome - Schrezenmeier, Eva; Choi, Mira; Globke, Brigitta; Dörner, Thomas; Leimbach, Alexandra; Osmanodja, Bilgin; Schramm, Alexander; Amann, Kerstin Ute; Eckardt, Kai Uwe; Budde, Klemens; Öllinger, Robert; Lachmann, Nils; et al. (Transfusion Medicine and Hemotherapy, 2024)
Introduction: The transplantation of highly sensitized patients remains a major obstacle. Immunized patients wait longer for a transplant if not prioritized, and if transplanted, their transplant outcome is worse. Case Presentation: We report a successful AB0- and HLA-incompatible living donor kidney transplantation in a 35-year-old female patient with systemic lupus erythematosus (SLE) and antiphospholipid syndrome. The patient had a positive T- and B-cell complement-dependent cytotoxicity (CDC) crossmatch and previous graft loss due to renal vein thrombosis. We treated the patient with intravenous immunoglobulins, rituximab, horse anti-thymocyte globulin, daratumumab, and imlifidase, besides standard immunosuppression. All IgG antibodies were sensitive to imlifidase treatment. Besides donor-specific HLA antibodies, anti-dsDNA antibodies and antiphospholipid antibodies were cleaved. The patient initially had delayed graft function. Two kidney biopsies (day 7 and day 14) revealed acute tubular necrosis without signs of HLA antibody-mediated rejection. On posttransplant day 30, hemodialysis was stopped, and creatinine levels declined over the next weeks to a baseline creatinine of about 1.7 mg/ dL after 12 months. Conclusion: In this case, a novel multimodal treatment strategy including daratumumab and imlifidase enabled successful kidney transplantation for a highly immunized patient with antiphospholipid antibodies.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Daratumumab; Imlifidase; Kidney transplant

Successful long-term management of recurrent focal segmental glomerulosclerosis after kidney transplantation with costimulation blockade - Muehlbacher, Thomas; Amann, Kerstin Ute; Mahling, Moritz; Nadalin, Silvio; Heyne, Nils; Guthoff, Martina (Clinical Kidney Journal, 2021)
Recurrence of primary focal segmental glomerulosclerosis (FSGS) occurs in up to 50% of patients after kidney transplantation and is associated with poor allograft outcome. Novel therapeutic concepts directly target podocyte function via B7-1 with inconsistent response. We present the case of a 19-year-old patient with recurrent primary FSGS early after living donor kidney transplantation. Plasmapheresis and rituximab did not induce remission. Repetitive abatacept administration was able to achieve partial remission. Maintenance immunosuppression was subsequently switched to a belatacept-based calcineurin inhibitor-free immunosuppression, resulting in sustained complete remission with excellent allograft function throughout a follow-up of >56months.
CRIS-Team WoS Importer:2021-10-01

Super-resolved local recruitment of CLDN5 to filtration slits implicates a direct relationship with podocyte foot process effacement - Tesch, Florian; Siegerist, Florian; Hay, Eleonora; Artelt, Nadine; Daniel, Christoph; Amann, Kerstin Ute; Zimmermann, Uwe; Kavvadas, Panagiotis; Grisk, Olaf; Chadjichristos, Christos; Endlich, Karlhans; Chatziantoniou, Christos; et al. (Journal of Cellular and Molecular Medicine, 2021)
Under healthy conditions, foot processes of neighbouring podocytes are interdigitating and connected by an electron-dense slit diaphragm. Besides slit diaphragm proteins, typical adherens junction proteins are also found to be expressed at this cell-cell junction. It is therefore considered as a highly specialized type of adherens junction. During podocyte injury, podocyte foot processes lose their characteristic 3D structure and the filtration slits typical meandering structure gets linearized. It is still under debate how this change of structure leads to the phenomenon of proteinuria. Using super-resolution 3D-structured illumination microscopy, we observed a spatially restricted up-regulation of the tight junction protein claudin-5 (CLDN5) in areas where podocyte processes of patients suffering from minimal change disease (MCD), focal and segmental glomerulosclerosis (FSGS) as well as in murine nephrotoxic serum (NTS) nephritis and uninephrectomy DOCA-salt hypertension models, were locally injured. CLDN5/nephrin ratios in human glomerulopathies and NTS-treated mice were significantly higher compared to controls. In patients, the CLDN5/nephrin ratio is significantly correlated with the filtration slit density as a foot process effacement marker, confirming a direct association of local CLDN5 up-regulation in injured foot processes. Moreover, CLDN5 up-regulation was observed in some areas of high filtration slit density, suggesting that CLND5 up-regulation preceded the changes of foot processes. Therefore, CLDN5 could serve as a biomarker predicting early foot process effacement.
CRIS-Team Scopus Importer:2021-07-02
Keywords: 3D-structured illumination microscopy; Claudin-5; foot process effacement; glomerulosclerosis; podocyte; tight junction proteins

Targeting the innate repair receptor axis via erythropoietin or pyroglutamate helix B surface peptide attenuates hemolytic-uremic syndrome in mice - Dennhardt, Sophie; Pirschel, Wiebke; Wissuwa, Bianka; Imhof, Diana; Daniel, Christoph; Kielstein, Jan T.; Hennig-Pauka, Isabel; Amann, Kerstin Ute; Gunzer, Florian; Coldewey, Sina M. (Frontiers in Immunology, 2022)
Hemolytic-uremic syndrome (HUS) can occur as a systemic complication of infections with Shiga toxin (Stx)-producing Escherichia coli and is characterized by microangiopathic hemolytic anemia and acute kidney injury. Hitherto, therapy has been limited to organ-supportive strategies. Erythropoietin (EPO) stimulates erythropoiesis and is approved for the treatment of certain forms of anemia, but not for HUS-associated hemolytic anemia. EPO and its non-hematopoietic analog pyroglutamate helix B surface peptide (pHBSP) have been shown to mediate tissue protection via an innate repair receptor (IRR) that is pharmacologically distinct from the erythropoiesis-mediating receptor (EPO-R). Here, we investigated the changes in endogenous EPO levels in patients with HUS and in piglets and mice subjected to preclinical HUS models. We found that endogenous EPO was elevated in plasma of humans, piglets, and mice with HUS, regardless of species and degree of anemia, suggesting that EPO signaling plays a role in HUS pathology. Therefore, we aimed to examine the therapeutic potential of EPO and pHBSP in mice with Stx-induced HUS. Administration of EPO or pHBSP improved 7-day survival and attenuated renal oxidative stress but did not significantly reduce renal dysfunction and injury in the employed model. pHBSP, but not EPO, attenuated renal nitrosative stress and reduced tubular dedifferentiation. In conclusion, targeting the EPO-R/IRR axis reduced mortality and renal oxidative stress in murine HUS without occurrence of thromboembolic complications or other adverse side effects. We therefore suggest that repurposing EPO for the treatment of patients with hemolytic anemia in HUS should be systematically investigated in future clinical trials.
CRIS-Team Scopus Importer:2022-10-21
Keywords: erythropoietin; hemolytic-uremic syndrome; mice; microangiopathic hemolytic anemia; pyroglutamate helix B surface peptide; shiga toxin; thrombotic microangiopathy

The Babylonian confusion in describing chronic changes in renal allografts - Kemmner, Stephan; Büttner-Herold, Maike; Heemann, Uwe; Amann, Kerstin Ute; Schmaderer, Christoph (Minerva Urologica e Nefrologica, 2017)
EVALuna2:25543

The Case | A 74-year-old liver transplant recipient with nephrotic-range proteinuria - Bohnert, Bernhard N.; Büttner-Herold, Maike; Amann, Kerstin Ute; Schork, Anja; Birkenfeld, Andreas L.; Guthoff, Martina; Heyne, Nils; Nadalin, Silvio; Artunc, Ferruh (Kidney International, 2021)
CRIS-Team Scopus Importer:2021-03-26

The complement system-a "hot topic" not only for kidney diseases - Amann, Kerstin Ute; Daniel, Christoph; Büttner-Herold, Maike (Pathologe, 2020)
Increasing interest in the role of the complement system in systemic and renal disease is based on new pathophysiological and therapeutic insights of the recent past and particularly in genetic analyses in children with atypical hemolytic uremic syndrome (aHUS). aHUS is the prototypical systemic disease associated with excessive activation of the alternative complement pathway and manifests in the kidney, but also in other organs as thrombotic microangiopathy (TMA). Pathomechanisms discovered to induce the overactivation of the alternative complement pathway in aHUS led to the first successful therapeutic application of a C5b9 inhibitor. This suppression of the terminal complement cascade succeeded in inhibiting local tissue damage. Thereafter, thanks to advanced modern technologies, further systemic and renal diseases associated with mutations or auto-antibodies targeting the complement pathway were identified. Hereby, disease onset is frequently associated with an additional trigger, e.g. infection or hormonal alterations/imbalances, against the background of a pre-existing predisposition of the patient. Due to the growing understanding of the regulation, and thus the possibility of therapeutic modulation of the different complement pathways, and due to the increasing availability of a variety of drugs inhibiting the complement system, interest in complement-mediated systemic and renal disease has been steadily increasing, making it a "hot-topic" in medicine in recent years.
CRIS-Team WoS Importer:2020-04-10

The dipeptidyl peptidase 4 inhibitor linagliptin ameliorates renal injury and accelerated resolution in a rat model of crescentic nephritis - Mayer, Anna-Lena; Scheitacker, Iris; Ebert, Nadja; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (British Journal of Pharmacology, 2021)
Background and Purpose: Dipeptidyl peptidase 4 (DPP-4) inhibitors are a class of oral glucose-lowering drugs used in the treatment of type 2 diabetes. In a pilot study using human kidney biopsies, we observed high DPP-4 expression in early crescent formation. This glomerular lesion occurs in different kidney diseases and is a hallmark in the pathogenesis of renal dysfunction. Therefore, we investigated the potential involvement of DPP-4 in the pathogenesis of nephritis induced by anti-glomerular basement membrane (GBM) antibody in rats. Experimental Approach: Linagliptin and vehicle were used to treat anti-GBM nephritis in a 2- and 8-week regimen, that is either preventive or therapeutic (treatment started 7 days or 4 weeks after disease induction). Kidney function, morphologic changes, inflammation and fibrosis were monitored. Key Results: In the long-term experiment, linagliptin preventive treatment in anti-GBM nephritic rats significantly reduced the number of crescents, glomerulosclerosis, tubular injury and renal fibrosis, compared with those in untreated nephritic rats. Both linagliptin regimes significantly lowered the number of Pax8+ cells on the glomerular tuft in anti-GBM nephritis, indicating accelerated resolution of the cellular crescents. The linagliptin treatment did not change the podocyte stress in both therapeutic groups. Therapeutic intervention with linagliptin resulted in weaker amelioration of renal disease on Week 8 than did preventive intervention. Conclusion and Implications: DPP-4 inhibition with linagliptin ameliorates renal injury in a rat model of anti-GBM, indicating that linagliptin not only is a secure therapy in diabetes but also can improve resolution of glomerular injury and healing in non-diabetic renal disease.
CRIS-Team Scopus Importer:2021-02-12
Keywords: crescent formation; DPP-4 inhibitor; fibrosis; non-diabetic renal disease

The extracellular matrix protein fibronectin promotes metanephric kidney development - Skoczynski, Kathrin; Kraus, Andre; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute; Schiffer, Mario; Hermann, Kristina; Herrnberger-Eimer, Leonie; Tamm, Ernst R.; Buchholz, Björn (Pflügers Archiv: European Journal of Physiology, 2024)
Complex interactions of the branching ureteric bud (UB) and surrounding mesenchymal cells during metanephric kidney development determine the final number of nephrons. Impaired nephron endowment predisposes to arterial hypertension and chronic kidney disease. In the kidney, extracellular matrix (ECM) proteins are usually regarded as acellular scaffolds or as the common histological end-point of chronic kidney diseases. Since only little is known about their physiological role in kidney development, we aimed for analyzing the expression and role of fibronectin. In mouse, fibronectin was expressed during all stages of kidney development with significant changes over time. At embryonic day (E) 12.5 and E13.5, fibronectin lined the UB epithelium, which became less pronounced at E16.5 and then switched to a glomerular expression in the postnatal and adult kidneys. Similar results were obtained in human kidneys. Deletion of fibronectin at E13.5 in cultured metanephric mouse kidneys resulted in reduced kidney sizes and impaired glomerulogenesis following reduced cell proliferation and branching of the UB epithelium. Fibronectin colocalized with alpha 8 integrin and fibronectin loss caused a reduction in alpha 8 integrin expression, release of glial-derived neurotrophic factor and expression of Wnt11, both of which are promoters of UB branching. In conclusion, the ECM protein fibronectin acts as a regulator of kidney development and is a determinant of the final nephron number.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Alpha 8 integrin; Branching; Fibronectin; Kidney development; Nephron number

The heart and vascular system in dialysis - Wanner, Christoph; Amann, Kerstin Ute; Shoji, Tetsuo (Lancet, 2016)
The heart and the vascular tree undergo major structural and functional changes when kidney function declines and renal replacement therapy is required. The many cardiovascular risk factors and adaptive changes the heart undergoes include left ventricular hypertrophy and dilatation with concomitant systolic and diastolic dysfunction. Myocardial fibrosis is the consequence of impaired angio-adaptation, reduced capillary angiogenesis, myocyte-capillary mismatch, and myocardial micro-arteriopathy. The vascular tree can be affected by both atherosclerosis and arteriosclerosis with both lipid rich plaques and abundant media calcification. Development of cardiac and vascular disease is rapid, especially in young patients, and the phenotype resembles all aspects of an accelerated ageing process and latent cardiac failure. The major cause of left ventricular hypertrophy and failure and the most common problem directly affecting myocardial function is fluid overload and, usually, hypertension. In situations of stress, such as intradialytic hypotension and hypoxaemia, the hearts of these patients are more vulnerable to developing cardiac arrest, especially when such episodes occur frequently. As a result, cardiac and vascular mortality are several times higher in dialysis patients than in the general population. Trials investigating one pharmacological intervention (eg, statins) have shown limitations. Pragmatic designs for large trials on cardio-active interventions are mandatory for adequate cardioprotective renal replacement therapy.
EVALuna2:25515

The Kidney Donor Profile Index (KDPI) Correlates With Histopathologic Findings in Post-reperfusion Baseline Biopsies and Predicts Kidney Transplant Outcome - Bachmann, Quirin; Haberfellner, Flora; Büttner-Herold, Maike; Torrez, Carlos; Haller, Bernhard; Assfalg, Volker; Renders, Lutz; Amann, Kerstin Ute; Heemann, Uwe; Schmaderer, Christoph; Kemmner, Stephan (Frontiers in Medicine, 2022)
BackgroundThe increasing organ shortage in kidney transplantation leads to the necessity to use kidneys previously considered unsuitable for transplantation. Numerous studies illustrate the need for a better decision guidance rather than only the classification into kidneys from standard or expanded criteria donors referred to as SCD/ECD-classification. The kidney donor profile index (KDPI) exhibits a score utilizing a much higher number of donor characteristics. Moreover, graft biopsies provide an opportunity to assess organ quality. MethodsIn a single center analysis 383 kidney transplantations (277 after deceased and 106 after living donation) performed between January 1st, 2006, and December 31st, 2016, retrospectively underwent SCD/ECD and KDPI scoring. Thereby, the quality of deceased donor kidneys was assessed by using the KDPI and the living donor kidneys by using the living KDPI, in the further analysis merged as (L)KDPI. Baseline biopsies taken 10 min after the onset of reperfusion were reviewed for chronic and acute lesions. Survival analyses were performed using Kaplan-Meier analysis and Cox proportional hazards analysis within a 5-year follow-up. ResultsThe (L)KDPI correlated with glomerulosclerosis (r = 0.30, p < 0.001), arteriosclerosis (r = 0.33, p < 0.001), interstitial fibrosis, and tubular atrophy (r = 0.28, p < 0.001) as well as the extent of acute tubular injury (r = 0.20, p < 0.001). The C-statistic of the (L)KDPI concerning 5-year death censored graft survival was 0.692. Around 48% of ECD-kidneys were classified as (L)KDPI<85%. In a multivariate Cox proportional hazard analysis including (preformed) panel reactive antibodies, cold ischemia time, (L)KDPI, and SCD/ECD-classification, the (L)KDPI was significantly associated with risk of graft loss (hazard ratio per 10% increase in (L)KDPI: 1.185, 95% confidence interval: 1.033-1.360, p = 0.025). Survival analysis revealed decreased death censored (p < 0.001) and non-death censored (p < 0.001) graft survival in kidneys with an increasing (L)KDPI divided into groups of <35, 35-85, and >85%, respectively. ConclusionWith a higher granularity compared to the SCD/ECD-classification the (L)KDPI is a promising tool to judge graft quality. The correlation with chronic and acute histological lesions in post-reperfusion kidney biopsies underlines the descriptive value of the (L)KDPI. However, its prognostic value is limited and underlines the urgent need for a more precise prognostic tool adopted to European kidney transplant conditions.
CRIS-Team WoS Importer:2022-05-27

The lysyl oxidases LOX and LOXL2 are necessary and sufficient to repress E-cadherin in Hypoxia: Insights into cellular transformation processes mediated by HIF-1 - Schietke, Ruth; Warnecke, Christina; Wacker, Ingrid; Schödel, Johannes; Mole, David R.; Campean, Valentina; Amann, Kerstin Ute; Goppelt-Strübe, Margarete; Behrens, Jürgen; Eckardt, Kai-Uwe; Wiesener, Michael Sean (Journal of Biological Chemistry, 2010)
Hypoxia has been shown to promote tumor metastasis and lead to therapy resistance. Recent work has demonstrated that hypoxia represses E-cadherin expression, a hallmark of epithelial to mesenchymal transition, which is believed to amplify tumor aggressiveness. The molecular mechanism of E-cadherin repression is unknown, yet lysyl oxidases have been implicated to be involved. Gene expression of lysyl oxidase (LOX) and the related LOX-like 2 (LOXL2) is strongly induced by hypoxia. In addition to the previously demonstrated LOX, we characterize LOXL2 as a direct transcriptional target of HIF-1. We demonstrate that activation of lysyl oxidases is required and sufficient for hypoxic repression of E-cadherin, which mediates cellular transformation and takes effect in cellular invasion assays. Our data support a molecular pathway from hypoxia to cellular transformation. It includes up-regulation of HIF and subsequent transcriptional induction of LOX and LOXL2, which repress E-cadherin and induce epithelial to mesenchymal transition. Lysyl oxidases could be an attractive molecular target for cancers of epithelial origin, in particular because they are partly extracellular. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2024-05-13

The marine triterpene glycoside frondoside A exhibits activity in vitro and in vivo in prostate cancer - Dyshlovoy, Sergey A.; Menchinskaya, Ekaterina S.; Venz, Simone; Rast, Stefanie; Amann, Kerstin Ute; Hauschild, Jessica; Otte, Katharina; Kalinin, Vladimir I.; Silchenko, Alexandra S.; Avilov, Sergey A.; Alsdorf, Winfried; Madanchi, Ramin; et al. (International Journal of Cancer, 2016)
Despite recent advances in the treatment of metastatic castration-resistant prostate cancer (CRPC), outcome of patients remains poor due to the development of drug resistance. Thus, new drugs are urgently needed. We investigated efficacy, toxicity and mechanism of action of marine triterpene glycoside frondoside A (FrA) using CRPC cell lines in vitro and in vivo. FrA revealed high efficacy in human prostate cancer cells, while non-malignant cells were less sensitive. Remarkably, proliferation and colony formation of cells resistant to enzalutamide and abiraterone (due to the androgen receptor splice variant AR-V7) were also significantly inhibited by FrA. The marine compound caused cell type specific cell cycle arrest and induction of caspase-dependent or -independent apoptosis. Up-regulation or induction of several pro-apoptotic proteins (Bax, Bad, PTEN), cleavage of PARP and caspase-3 and down-regulation of anti-apoptotic proteins (survivin and Bcl-2) were detected in treated cells. Global proteome analysis revealed regulation of proteins involved in formation of metastases, tumor cell invasion, and apoptosis, like keratin 81, CrkII, IL-1? and cathepsin B. Inhibition of pro-survival autophagy was observed following FrA exposure. In vivo, FrA inhibited tumor growth of PC-3 and DU145 cells with a notable reduction of lung metastasis, as well as circulating tumor cells in the peripheral blood. Increased lymphocyte counts of treated animals might indicate an immune modulating effect of FrA. In conclusion, our results suggest that FrA is a promising new drug for the treatment of mCRPC. Induction of apoptosis, inhibition of pro-survival autophagy, and immune modulatory effects are suspected modes of actions.
EVALuna2:25513

The Myocardium in Renal Failure - Amann, Kerstin Ute (Springer International Publishing, 2020)
Patients with chronic kidney disease (CKD) suffer disproportionately from cardiovascular (cv) complications and specifically death from cardiac causes. Although the pathogenesis of this exceedingly high cv morbidity and mortality is not well understood, specific structural and functional alterations of the myocardium have been described which can contribute to the increased burden of cv disease in these patients. In the following some of these specific aspects will be discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Angioadaptation; Capillary supply; CKD; Coronary arteries; Fibrosis; Heart; Hypertrophy; Myocardium

The Phenotypic Spectrum of Nephropathies Associated with Mutations in Diacylglycerol Kinase? - Azukaitis, Karolis; Simkova, Eva; Majid, Mohammad Abdul; Galiano, Matthias; Benz, Kerstin; Amann, Kerstin Ute; Bockmeyer, Clemens; Gajjar, Radha; Meyers, Kevin E.; Cheong, Hae Ii; Lange-Sperandio, Baerbel; Jungraithnnayr, Therese; et al. (Journal of the American Society of Nephrology, 2017)
The recent discovery of mutations in the gene encoding diacylglycerol kinase ? (DGKE) identified a novel pathophysiologic mechanism leading to HUS and/or MPGN. We report ten new patients from eight unrelated kindreds with DGKE nephropathy. We combined these cases with all previously published cases to characterize the phenotypic spectrum and outcomes of this new disease entity. Most patients presented with HUS accompanied by proteinuria, whereas a subset of patients exhibited clinical and histologic patterns of MPGN without TMA. We also report the first two patients with clinical and histologic HUS/MPGN overlap. DGKE-HUS typically manifested in the first year of life but was not exclusively limited to infancy, and viral triggers frequently preceded HUS episodes. We observed signs of complement activation in some patients with DGKE-HUS, but the role of complement activation remains unclear. Most patients developed a slowly progressive proteinuric nephropathy: 80% of patients did not have ESRD within 10 years of diagnosis. Many patients experienced HUS remission without specific treatment, and a few patients experienced HUS recurrence despite complete suppression of the complement pathway. Five patients received renal allografts, with no post-transplant recurrence reported. In conclusion, we did not observe a clear genotype-phenotype correlation in patients with DGKE nephropathy, suggesting additional factors mediating phenotypic heterogeneity. Furthermore, the benefits of anti-complement therapy are questionable but renal transplant may be a feasible option in the treatment of patients with this condition.
EVALuna2:25541

The proteasome inhibitor bortezomib depletes plasma cells and protects mice with lupus-like disease from nephritis - Neubert, Kirsten; Meister, Silke; Moser, Katrin; Weisel, Florian; Maseda, Damian; Amann, Kerstin Ute; Wiethe, Carsten; Winkler, Thomas; Kalden, Joachim; Manz, Rudolf A.; Voll, Reinhard E. (Nature Medicine, 2008)
Autoantibody-mediated diseases like myasthenia gravis, autoimmune hemolytic anemia and systemic lupus erythematosus represent a therapeutic challenge. In particular, long-lived plasma cells producing autoantibodies resist current therapeutic and experimental approaches. Recently, we showed that the sensitivity of myeloma cells toward proteasome inhibitors directly correlates with their immunoglobulin synthesis rates. Therefore, we hypothesized that normal plasma cells are also hypersensitive to proteasome inhibition owing to their extremely high amount of protein biosynthesis. Here we show that the proteasome inhibitor bortezomib, which is approved for the treatment of multiple myeloma, eliminates both short- and long-lived plasma cells by activation of the terminal unfolded protein response. Treatment with bortezomib depleted plasma cells producing antibodies to double-stranded DNA, eliminated autoantibody production, ameliorated glomerulonephritis and prolonged survival of two mouse strains with lupus-like disease, NZB/W F1 and MRL/lpr mice. Hence, the elimination of autoreactive plasma cells by proteasome inhibitors might represent a new treatment strategy for antibody-mediated diseases. © 2008 Nature Publishing Grou

The protective effect of prolyl-hydroxylase inhibition against renal ischaemia requires application prior to ischaemia but is superior to EPO treatment - Wang, Zhendi; Schley, Gunnar; Türkoglu, Gazi; Burzlaff, Nicolai; Amann, Kerstin Ute; Willam, Carsten; Eckardt, Kai-Uwe; Bernhardt, Wanja M. (Nephrology Dialysis Transplantation, 2012)
Background. Inhibition of the HIF regulating prolyl hydroxylation domain (PHDs) proteins prior to renal injury (preconditioning) has been shown to protect the kidney via activation of hypoxia-inducible transcription factors (HIF). Application of erythropoietin (EPO), one of the HIF target genes, has also been shown to be nephroprotective, and it remains unclear to what extent the effect of HIF induction is mediated by EPO. It is also unknown whether HIF activation after the onset of ischaemia (postconditioning) is still able to protect the kidney. Methods. Using a rat model of renal ischaemia-reperfusion injury, animals were treated with the PHD inhibitor (PHD-I) 2-(1-chloro-4- hydroxyisoquinoline-3-carboxamido) acetate (ICA), vehicle (Veh) or recombinant human EPO (300 IU/ kg) 6 h (ICA or Veh) or 30 min (EPO) prior to ischaemia (preconditioning) or with ICA prior to reperfusion (postconditioning). Renal function was assessed at baseline, 24 h and 72 h. After 72 h, kidneys were processed for histology and morphometric analysis. HIF immunohistochemistry and real-time polymerase chain reaction for HIF target genes, including EPO, were performed to evaluate ICA effects. Results. ICA treatment resulted in stabilization of HIF-1α and -2α and up-regulation of HIF target genes in a dosedependent manner. Preconditional activation of HIF by ICA significantly improved serum creatinine levels and renal morphology in comparison to Veh (P < 0.05), while postconditional ICA treatment was ineffective. EPO therapy improved tissue morphology but had no impact on the course of serum creatinine. Conclusion. These findings are in line with the concept that PHD-Is exert their protective effects through accumulation of HIF target gene products, with time requirements for increased transcription and translation of HIF-dependent genes, and suggest that their renoprotective effect is not predominately mediated by EPO. © 2011 The Author.

The pseudokinase MLKL mediates programmed hepatocellular necrosis independently of RIPK3 during hepatitis - Lopez Posadas, Rocío; Becker, Christoph; Günther, Claudia; Tenzer, Stefan; Amann, Kerstin Ute; Billmeier, Ulrike; Atreya, Raja; Fiorino, Gionata; Vetrano, Stefania; Danese, Silvio; Ekici, Arif Bülent; Wirtz, Stefan; et al. (Journal of Clinical Investigation, 2016)
Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptor-interacting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis. Using genetic and pharmacologic approaches, we determined that hepatocellular necrosis in experimental hepatitis is driven by an MLKL-dependent pathway that occurs independently of RIPK3. Moreover, we have provided evidence that the cytotoxic activity of the proinflammatory cytokine IFN-? in hepatic inflammation is strongly connected to induction of MLKL expression via activation of the transcription factor STAT1. In summary, our results reveal a pathway for MLKL-dependent programmed necrosis that is executed in the absence of RIPK3 and potentially drives the pathogenesis of severe liver diseases.
EVALuna2:2178

The role of filamins in mechanically stressed podocytes - Greiten, Jonas K.; Kliewe, Felix; Schnarre, Annabel; Artelt, Nadine; Schröder, Sindy; Rogge, Henrik; Amann, Kerstin Ute; Daniel, Christoph; Lindenmeyer, Maja T.; Cohen, Clemens D.; Endlich, Karlhans; Endlich, Nicole (The FASEB Journal, 2021)
Glomerular hypertension induces mechanical load to podocytes, often resulting in podocyte detachment and the development of glomerulosclerosis. Although it is well known that podocytes are mechanosensitive, the mechanosensors and mechanotransducers are still unknown. Since filamin A, an actin-binding protein, is already described to be a mechanosensor and mechanotransducer, we hypothesized that filamins could be important for the outside-in signaling as well as the actin cytoskeleton of podocytes under mechanical stress. In this study, we demonstrate that filamin A is the main isoform of the filamin family that is expressed in cultured podocytes. Together with filamin B, filamin A was significantly up-regulated during mechanical stretch (3 days, 0.5 Hz, and 5% extension). To study the role of filamin A in cultured podocytes under mechanical stress, filamin A was knocked down (Flna KD) by specific siRNA. Additionally, we established a filamin A knockout podocyte cell line (Flna KO) by CRISPR/Cas9. Knockdown and knockout of filamin A influenced the expression of synaptopodin, a podocyte-specific protein, focal adhesions as well as the morphology of the actin cytoskeleton. Moreover, the cell motility of Flna KO podocytes was significantly increased. Since the knockout of filamin A has had no effect on cell adhesion of podocytes during mechanical stress, we simultaneously knocked down the expression of filamin A and B. Thereby, we observed a significant loss of podocytes during mechanical stress indicating a compensatory mechanism. Analyzing hypertensive mice kidneys as well as biopsies of patients suffering from diabetic nephropathy, we found an up-regulation of filamin A in podocytes in contrast to the control. In summary, filamin A and B mediate matrix-actin cytoskeleton interactions which are essential for the adaptation of cultured podocyte to mechanical stress.
CRIS-Team Scopus Importer:2021-04-30
Keywords: diabetic nephropathy; Flna; mechanical load; mechanosensor; mechanotransducer

The Role of Palladin in Podocytes - Artelt, Nadine; Ludwig, Tim A.; Rogge, Henrik; Kavvadas, Panagiotis; Siegerist, Florian; Blumenthal, Antje; Van Den Brandt, Jens; Otey, Carol A.; Bang, Marie-Louise; Amann, Kerstin Ute; Chadjichristos, Christos E.; Chatziantoniou, Christos; et al. (Journal of the American Society of Nephrology, 2018)
Background Podocyte loss and effacement of interdigitating podocyte foot processes are the major cause of a leaky filtration barrier and ESRD. Because the complex three-dimensional morphology of podocytes depends on the actin cytoskeleton, we studied the role in podocytes of the actin bundling protein palladin, which is highly expressed therein.Methods We knocked down palladin in cultured podocytes by siRNA transfection or in zebrafish embryos by morpholino injection and studied the effects by immunofluorescence and live imaging. We also investigated kidneys of mice with podocyte-specific knockout of palladin (PodoPalld-/- mice) by immunofluorescence and ultrastructural analysis and kidney biopsy specimens from patients by immunostaining for palladin.Results Compared with control-treated podocytes, palladin-knockdown podocytes had reduced actin filament staining, smaller focal adhesions, and downregulation of the podocyte-specific proteins synaptopodin and α-actinin-4. Furthermore, palladin-knockdown podocytes were more susceptible to disruption of the actin cytoskeleton with cytochalasin D, latrunculin A, or jasplakinolide and showed altered migration dynamics. In zebrafish embryos, palladin knockdown compromised the morphology and dynamics of epithelial cells at an early developmental stage. Compared with PodoPalld+/+ controls, PodoPalld-/- mice developed glomeruli with a disturbed morphology, an enlarged subpodocyte space, mild effacement, and significantly reduced expression of nephrin and vinculin. Furthermore, nephrotoxic serum injection led to significantly higher levels of proteinuria in PodoPalld-/- mice than in controls. Kidney biopsy specimens from patients with diabetic nephropathy and FSGS showed downregulation of palladin in podocytes as well.Conclusions Palladin has an important role in podocyte function in vitro and in vivo.
EVALuna2:34432

The transcription factor Dach1 is essential for podocyte function - Endlich, Nicole; Kliewe, Felix; Kindt, Frances; Schmidt, Katharina; Kotb, Ahmedm.; Artelt, Nadine; Lindenmeyer, Maja T.; Cohen, Clemens D.; Doering, Franziska; Kuss, Andreas W.; Amann, Kerstin Ute; Moeller, Marcus J.; et al. (Journal of Cellular and Molecular Medicine, 2018)
Dedifferentiation and loss of podocytes are the major cause of chronic kidney disease. Dach1, a transcription factor that is essential for cell fate, was found in genome-wide association studies to be associated with the glomerular filtration rate. We found that podocytes express high levels of Dach1 in vivo and to a much lower extent in vitro. Parietal epithelial cells (PECs) that are still under debate to be a type of progenitor cell for podocytes expressed Dach1 only at low levels. The transfection of PECs with a plasmid encoding for Dach1 induced the expression of synaptopodin, a podocyte-specific protein, demonstrated by immunocytochemistry and Western blot. Furthermore, synaptopodin was located along actin fibres in a punctate pattern in Dach1-expressing PECs comparable with differentiated podocytes. Moreover, dedifferentiating podocytes of isolated glomeruli showed a significant reduction in the expression of Dach1 together with synaptopodin after 9 days in cell culture. To study the role of Dach1 in vivo, we used the zebrafish larva as an animal model. Knockdown of the zebrafish ortholog Dachd by morpholino injection into fertilized eggs resulted in a severe renal phenotype. The glomeruli of the zebrafish larvae showed morphological changes of the glomerulus accompanied by down-regulation of nephrin and leakage of the filtration barrier. Interestingly, glomeruli of biopsies from patients suffering from diabetic nephropathy showed also a significant reduction of Dach1 and synaptopodin in contrast to control biopsies. Taken together, Dach1 is a transcription factor that is important for podocyte differentiation and proper kidney function.
EVALuna2:34433

Thrombospondin-1 is an endogenous activator of TGF-β in experimental diabetic nephropathy in vivo - Daniel, Christoph; Schaub, Kathrin; Amann, Kerstin Ute; Lawler, Jack; Hugo, Christian (Diabetes, 2007)
OBJECTIVE - Transforming growth factor-β (TGF-β), the central cytokine responsible for the development of diabetic nephropathy, is usually secreted as a latent procytokine complex that has to be activated before it can bind to its receptors. Recent studies by our group demonstrated that thrombospondin-1 (TSP-1) is the major activator of latent TGF-β in experimental glomerulonephritis in the rat, but its role in diabetic nephropathy in vivo is unknown. RESEARCH DESIGN AND METHODS - Type 1 diabetes was induced in wild-type (n = 27) and TSP-1-deficient mice (n = 36) via streptozotocin injection, and diabetic nephropathy was investigated after 7, 9.5, and 20 weeks. Renal histology, TGF-β activation, matrix accumulation, and inflammation were assessed by immunohistology. Expression of fibronectin and TGF-β was evaluated using real-time PCR. Furthermore, functional parameters were examined. RESULTS - In TSP-1-deficient compared with wild-type mice, the amount of active TGF-β within glomeruli was significantly lower, as indicated by staining with specific antibodies against active TGF-β or the TGF-β signaling molecule phospho-smad2/3 or the typical TGF-β target gene product plasminogen activator inhibitor-1. In contrast, the amount of glomerular total TGF-β remained unchanged. The development of diabetic nephropathy was attenuated in TSP-1-deficient mice as demonstrated by a significant reduction of glomerulosclerosis, glomerular matrix accumulation, podocyte injury, renal infiltration with inflammatory cells, and renal functional parameters. CONCLUSIONS - We conclude that TSP-1 is an important activator of TGF-β in diabetic nephropathy in vivo. TSP-1-blocking therapies may be considered a promising future treatment option for diabetic nephropathy. © 2007 by the American Diabetes Association.
Created from Fastlane, Scopus look-up

Thrombospondin 2 functions as an endogenous regulator of angiogenesis and inflammation in experimental glomerulonephritis in mice - Daniel, Christoph; Amann, Kerstin Ute; Hohenstein, Bernd; Bornstein, Paul; Hugo, Christian (Journal of the American Society of Nephrology, 2007)
The role of thrombospondin 2 (TSP2) was investigated in an anti-glomerular basement membrane (GBM) nephritis model that compared TSP2-null mice with wild-type (WT) controls. TSP2-null mice were analyzed for kidney function, renal cortical matrix expansion, influx of inflammatory cells, proliferation, and apoptosis, as well as for capillary rarefaction after induction of anti-GBM disease. Whereas the renal cortex of normal control WT mice did not show any detectable TSP2 staining above background, TSP2 protein expression was clearly upregulated in anti-GBM disease. TSP2 deficiency led to an accelerated and enhanced inflammatory response, as indicated by the influx of CD4+ and CD8a+ cells and monocytes/macrophages. Glomerular fibrin deposition and a matrix-remodeling response were also observed, as indicated by collagens I and IV staining and a proliferative response within the renal interstitium. These changes were accompanied by increased matrix metalloproteinase 2 activity and enhanced α-smooth muscle actin staining in the TSP2-null mice. Neither a compensatory increase in TSP1 nor increased phosphorylation of Smad 2/3, an indicator for TGF-β activity, was observed. The proliferative response of the peritubular endothelium was accelerated and enhanced, leading to a reversal of capillary rarefaction in TSP2-null mice, whereas interstitial cell death was equivalent to that in WT mice. In conclusion, the lack of the matricellular protein TSP2 in mice accelerates and enhances several responses to renal injury and reveals an important role for TSP2 as a major endogenous antiangiogenic and matrix metalloproteinase 2-regulating factor in renal disease. Copyright © 2007 by the American Society of Nephrology.
Created from Fastlane, Scopus look-up

TIMP-2 and IGFBP7 in human kidney biopsies in renal disease - Schanz, Moritz; Kimmel, Martin; Alscher, Mark Dominik; Amann, Kerstin Ute; Daniel, Christoph (Clinical Kidney Journal, 2023)
Background Tissue inhibitor of matrix metalloproteinase-2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP7) are markers of tubular stress and urinary [TIMP-2]*[IGFBP7] is an established biomarker for risk assessment of acute kidney injury. There are no studies of expression profiles or localization of these markers in human renal tissue with confirmed renal disease. Methods We analysed 37 kidney biopsies of patients with renal disease and 10 non-diseased control biopsies for TIMP-2 and IGFBP7 expression using immunohistochemistry. Changes in glomerular morphology were evaluated by a semi-quantitative glomerulosclerosis score (GSI) and tubular interstitial changes were graded by the tubular injury score (TSI) using periodic acid-Schiff-stained paraffin sections. Interstitial fibrosis and tubular atrophy (IF/TA) were graded according to the Banff classification. Urinary [TIMP-2]*[IGFBP7] was collected at the time of biopsy. Results TIMP-2 and IGFBP7 had significantly greater expression in kidney biopsies from patients with renal disease compared with control tissue, especially in the tubular compartment. Here, IGFBP7 was detected in proximal and distal tubules while TIMP-2 was predominantly localized in the collecting ducts. Renal injury significantly correlated with staining intensity for TIMP-2 and IGFBP7: GSI weakly correlated with glomerular TIMP-2 (r = 0.36) and IGFBP7 (r = 0.35) and TSI correlated with tubular TIMP-2 (r = 0.41) and IGFBP7 (r = 0.43). Urinary [TIMP-2]*[IGFBP7] correlated weakly with the histopathological damage score but not with glomerular and tubular expression. Conclusion Our findings underline the role of TIMP-2/IGFBP7 as an unspecific marker of renal injury that is already in use for early detection of acute kidney injury.
CRIS-Team WoS Importer:2023-03-31

Tracking cell turnover in human brain using 15N-thymidine imaging mass spectrometry - Röder, Sebastian; Bonnin, Elisa A.; Wu, Ting Di; Guerquin-Kern, Jean Luc; Jabari, Samir; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Gollwitzer, Stephanie; Hamer, Hajo; Gerner, Stefan; Döppner, Thorsten R.; Rummel, Christoph; et al. (Frontiers in Neuroscience, 2023)
Microcephaly is often caused by an impairment of the generation of neurons in the brain, a process referred to as neurogenesis. While most neurogenesis in mammals occurs during brain development, it thought to continue to take place through adulthood in selected regions of the mammalian brain, notably the hippocampus. However, the generality of neurogenesis in the adult brain has been controversial. While studies in mice and rats have provided compelling evidence for neurogenesis occurring in the adult rodent hippocampus, the lack of applicability in humans of key methods to demonstrate neurogenesis has led to an intense debate about the existence and, in particular, the magnitude of neurogenesis in the adult human brain. Here, we demonstrate the applicability of a powerful method to address this debate, that is, the in vivo labeling of adult human patients with 15N-thymidine, a non-hazardous form of thymidine, an approach without any clinical harm or ethical concerns. 15N-thymidine incorporation into newly synthesized DNA of specific cells was quantified at the single-cell level with subcellular resolution by Multiple-isotype imaging mass spectrometry (MIMS) of brain tissue resected for medical reasons. Two adult human patients, a glioblastoma patient and a patient with drug-refractory right temporal lobe epilepsy, were infused for 24 h with 15N-thymidine. Detection of 15N-positive leukocyte nuclei in blood samples from these patients confirmed previous findings by others and demonstrated the appropriateness of this approach to search for the generation of new cells in the adult human brain. 15N-positive neural cells were easily identified in the glioblastoma tissue sample, and the range of the 15N signal suggested that cells that underwent S-phase fully or partially during the 24 h in vivo labeling period, as well as cells generated therefrom, were detected. In contrast, within the hippocampus tissue resected from the epilepsy patient, none of the 2,000 dentate gyrus neurons analyzed was positive for 15N-thymidine uptake, consistent with the notion that the rate of neurogenesis in the adult human hippocampus is rather low. Of note, the likelihood of detecting neurogenesis was reduced because of (i) the low number of cells analyzed, (ii) the fact that hippocampal tissue was explored that may have had reduced neurogenesis due to epilepsy, and (iii) the labeling period of 24 h which may have been too short to capture quiescent neural stem cells. Yet, overall, our approach to enrich NeuN-labeled neuronal nuclei by FACS prior to MIMS analysis provides a promising strategy to quantify even low rates of neurogenesis in the adult human hippocampus after in vivo15N-thymidine infusion. From a general point of view and regarding future perspectives, the in vivo labeling of humans with 15N-thymidine followed by MIMS analysis of brain tissue constitutes a novel approach to study mitotically active cells and their progeny in the brain, and thus allows a broad spectrum of studies of brain physiology and pathology, including microcephaly.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adult; cell turnover; DNA-labeling; glioblastoma; hippocampus; Nano-SIMS; neurogenesis

Transvascular kidney biopsy in adolescent patients-safe alternative to open procedures - Utsch, Boris; Hoppe, Hanno; Dittrich, Katalin; Amann, Kerstin Ute; Gugger, Mathias; Tschumi, Sibylle; Galiano, Matthias; Plank, Christian Georg; Rascher, Wolfgang; Schmid, Axel; Uder, Michael; Dötsch, Jörg (Clinical Kidney Journal, 2021)
CRIS-Team WoS Importer:2021-05-21

Transvenous renal transplant biopsy via a transfemoral approach - Schmid, Axel; Jacobi, Johannes; Kuefner, M. A.; Lell, Michael; Wüst, Wolfgang; Mayer-Kadner, I.; Benz, Kerstin; Schmid, Matthias; Amann, Kerstin Ute; Uder, Michael (American Journal of Transplantation, 2013)
Percutaneous renal biopsy (PRB) of kidney transplants might be prevented by an elevated risk of bleeding or limited access to the allograft. In the following, we describe our initial experience with 71 transvenous renal transplant biopsies in 53 consecutive patients with unexplained reduced graft function who were considered unsuitable candidates for PRB (4.2% of all renal transplant biopsies at our institution). Biopsies were performed via the ipsilateral femoral vein with a renal biopsy set designed for transjugular renal biopsy (TJRB) of native kidneys. Positioning of the biopsy system within the transplant vein was achievable in 58 of 71 (81.7%) procedures. The specimen contained a median of 10 glomeruli (range 0-38). Tissue was considered as adequate for diagnosis in 56 of 57 (98.2%) biopsies. With respect to BANFF 50.9% of the specimen were adequate (>10 glomeruli), 47.4% marginally adequate (1-9 glomeruli) and 1.8% inadequate (no glomeruli). After implementation of real-time assessment all specimen contained glomeruli. One of the fifty-eight (1.8%) procedure-related major complications occurred (hydronephrosis requiring nephrostomy due to gross hematuria). Transfemoral renal transplant biopsy (TFRTB) is feasible and appears to be safe compared to PRB. It offers a useful new alternative for histological evaluation of graft dysfunction in selected patients with contraindications to PRB. The authors report on an experience using transvenous renal transplant biopsy to enable histological evaluation in patients unsuitable for percutaneous transplant biopsy. © 2013 The American Society of Transplantation and the American Society of Transplant Surgeons.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Kidney transplant; percutaneous renal transplant biopsy; renal allograft; renal transplant biopsy; transjugular renal biopsy; transvenous biopsy

Treatment of Membranous Nephropathy in Patients With THSD7A Antibodies Using Immunoadsorption - Weinmann-Menke, Julia; Holtz, Stefan; Sollinger, Daniel; Dörken, Mara; Boedecker, Simone; Schamberger, Beate; Pfister, Frederick; Amann, Kerstin Ute; Lutz, Jens (American Journal of Kidney Diseases, 2019)
Antibodies against THSD7A (thrombospondin type 1 domain-containing protein 7A) have been proposed to play a causal role in the development of nephrotic syndrome in patients with THSD7A antibody–positive membranous nephropathy. We hypothesized that removal of these antibodies from plasma could lead to a rapid reduction in proteinuria. Using immunoadsorption to reduce THSD7A antibodies led to a rapid reduction in proteinuria in 2 patients with THSD7A antibody–positive membranous nephropathy. Moreover, our findings support and strengthen the pathogenic role of the antibodies in the development of nephrotic syndrome in patients with THSD7A antibody–positive membranous nephropathy. Taken together, these 2 cases suggest that immunoadsorption could be a useful tool in the treatment of patients with THSD7A antibody–positive membranous nephropathy.
CRIS-Team Scopus Importer:2019-08-30
Keywords: autoantibodies; case report; immunoadsorption; kidney biopsy; malignancy-associated MN; membranous nephropathy (MN); nephrotic syndrome (NS); proteinuria; THSD7A (thrombospondin type 1 domain-containing protein 7A); urinary protein-creatinine ratio (UPCR)

Tumor grade-titude: XGBoost radiomics paves the way for RCC classification - Ellmann, Stephan; von Rohr, Felicitas; Komina, Selim; Bayerl, Nadine; Amann, Kerstin Ute; Polifka, Iris; Hartmann, Arndt; Sikic, Danijel; Wullich, Bernd; Uder, Michael; Bäuerle, Tobias (European Journal of Radiology, 2025)
This study aimed to develop and evaluate a non-invasive XGBoost-based machine learning model using radiomic features extracted from pre-treatment CT images to differentiate grade 4 renal cell carcinoma (RCC) from lower-grade tumours. A total of 102 RCC patients who underwent contrast-enhanced CT scans were included in the analysis. Radiomic features were extracted, and a two-step feature selection methodology was applied to identify the most relevant features for classification. The XGBoost model demonstrated high performance in both training (AUC = 0.87) and testing (AUC = 0.92) sets, with no significant difference between the two (p = 0.521). The model also exhibited high sensitivity, specificity, positive predictive value, and negative predictive value. The selected radiomic features captured both the distribution of intensity values and spatial relationships, which may provide valuable insights for personalized treatment decision-making. Our findings suggest that the XGBoost model has the potential to be integrated into clinical workflows to facilitate personalized adjuvant immunotherapy decision-making, ultimately improving patient outcomes. Further research is needed to validate the model in larger, multicentre cohorts and explore the potential of combining radiomic features with other clinical and molecular data.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Computed tomography (CT); Diagnostic performance; Feature extraction; Machine learning; Personalized immunotherapy; Radiomics; Renal cell carcinoma (RCC); Treatment decision-making; Tumor grading

Under-expression of ?8 integrin aggravates experimental atherosclerosis - Menendez-Castro, Carlos; Cordasic, Nada; Neureiter, Daniel; Amann, Kerstin Ute; Marek, Ines; Volkert, Gudrun; Stintzing, Sebastian; Jahn, Angelika; Rascher, Wolfgang; Hilgers, Karl Friedrich; Hartner, Andrea (Journal of Pathology, 2015)
Integrins play an important role in vascular biology. The ?8 integrin chain attenuates smooth muscle cell migration but its functional role in the development of atherosclerosis is unclear. Therefore, we studied the contribution of ?8 integrin to atherosclerosis and vascular remodelling. We hypothesized that ?8 integrin expression is reduced in atherosclerotic lesions, and that its under-expression leads to a more severe course of atherosclerosis. ?8 Integrin was detected by immunohistochemistry and qPCR and ?8 integrin-deficient mice were used to induce two models of atherosclerotic lesions. First, ligation of the carotid artery led to medial thickening and neointima formation, which was quantified in carotid cross-sections. Second, after crossing into ApoE-deficient mice, the formation of advanced vascular lesions with atherosclerotic plaques was quantified in aortic en face preparations stained with Sudan IV. Parameters of renal physiology and histopathology were assessed: ?8 integrin was detected in the media of human and murine vascular tissue and was down-regulated in arteries with advanced atherosclerotic lesions. In ?8 integrin-deficient mice (?8(-/-) ) as well as ?8(+/-) and ?8(+/+) littermates, carotid artery ligation increased media:lumen ratios in all genotypes, with higher values in ligated ?8(-/-) and ?8(+/-) compared to ligated ?8(+/+) animals. Carotid artery ligation increased smooth muscle cell number in the media of ?8(+/+) mice and, more prominently, of ?8(-/-) or ?8(+/-) mice. On an ApoE(-/-) background, ?8(+/-) and ?8(-/-) mice developed more atherosclerotic plaques than ?8(+/+) mice. ?8 Integrin expression was reduced in ?8(+/-) animals. Renal damage with increased serum creatinine and glomerulosclerosis was detected in ?8(-/-) mice only. Thus, under-expression of ?8 integrin aggravates vascular lesions, while a complete loss of ?8 integrin results in reduced renal mass and additional renal disease in the presence of generalized atherosclerosis. Our data support the hypothesis that integrin ?8?1 has a protective role in arterial remodelling and atherosclerosis. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
EVALuna2:3752

Update on monoclonal gammopathy of renal significance [Neues zur monoklonalen Gammopathie renaler Signifikanz] - Büttner-Herold, Maike; Pfister, F.; Amann, Kerstin Ute (Nephrologe, 2019)
The term monoclonal gammopathy of renal significance (MGRS) was recently introduced for glomerular or tubulointerstitial renal diseases that are induced by a monoclonal immunoglobulin (MIg) in the setting of a monoclonal gammopathy of uncertain significance (MGUS) which is regarded as a benign condition. Most of these MIg-associated renal diseases result from direct deposition of nephrotoxic immunoglobulins or their fragments, i. e. light and heavy chain fragments. Hereby, the nature and exact location of the immunoglobulin deposition defines the disease so that apart from light microscopy, immunohistochemistry and/or immunofluorescence and electron microscopy are of utmost importance in the workup of kidney biopsies. It is assumed that at least some members of the MGRS group of diseases, irrespective of the underlying disease, are associated with a higher progression rate which may be one reason for MGRS being considered as an indication for antineoplastic therapy.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Biopsy; Electron microscopy; Immunohistochemistry; Kidney; Paraproteinemias

Uremic mouse model to study vascular calcification and “inflamm-aging” - Tölle, Markus; Henkel, Cornelia; Herrmann, Jaqueline; Daniel, Christoph; Babic, Milen; Xia, Mengdi; Schulz, Anna M.; Amann, Kerstin Ute; van der Giet, Markus; Schuchardt, Mirjam (Journal of Molecular Medicine, 2022)
Calcification and chronic inflammation of the vascular wall is a high-risk factor for cardiovascular mortality, especially in patients with chronic uremia. For the reduction or prevention of rapid disease progression, no specific treatment options are currently available. This study aimed to evaluate an adenine-based uremic mouse model for studying medial vessel calcification and senescence-associated secretory phenotype (SASP) changes of aortic tissue to unravel molecular pathogenesis and provide a model for therapy testing. The dietary adenine administration induced a stable and similar degree of chronic uremia in DBA2/N mice with an increase of uremia blood markers such as blood urea nitrogen, calcium, creatinine, alkaline phosphatase, and parathyroid hormone. Also, renal fibrosis and crystal deposits were detected upon adenine feeding. The uremic condition is related to a moderate to severe medial vessel calcification and subsequent elastin disorganization. In addition, expression of osteogenic markers as Bmp-2 and its transcription factor Sox-9 as well as p21 as senescence marker were increased in uremic mice compared to controls. Pro-inflammatory uremic proteins such as serum amyloid A, interleukin (Il)-1β, and Il-6 increased. This novel model of chronic uremia provides a simple method for investigation of signaling pathways in vascular inflammation and calcification and therefore offers an experimental basis for the development of potential therapeutic intervention studies. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-08-12
Keywords: Calcification; Cardiovascular; Chronic inflammation; Chronic renal insufficiency; Inflammation; Vascular calcification

Urinary peptidomic liquid biopsy for non-invasive differential diagnosis of chronic kidney disease. - Mavrogeorgis, Emmanouil; He, Tianlin; Mischak, Harald; Latosinska, Agnieszka; Vlahou, Antonia; Schanstra, Joost P.; Catanese, Lorenzo; Amann, Kerstin Ute; Huber, Tobias B.; Beige, Joachim; Rupprecht, Harald D.; Siwy, Justyna (Nephrology Dialysis Transplantation, 2024)
BACKGROUND AND HYPOTHESIS: Specific urinary peptides hold information on disease pathophysiology, which, in combination with artificial intelligence, could enable non-invasive assessment of chronic kidney disease (CKD) aetiology. Existing approaches are generally specific for the diagnosis of single aetiologies. We present the development of models able to simultaneously distinguish and spatially visualize multiple CKD aetiologies. METHODS: The urinary peptide data of 1850 healthy control (HC) and CKD [diabetic kidney disease (DKD), immunoglobulin A nephropathy (IgAN) and vasculitis] participants were extracted from the Human Urinary Proteome Database. Uniform manifold approximation and projection (UMAP) coupled to a support vector machine algorithm was used to generate multi-peptide models to perform binary (DKD, HC) and multiclass (DKD, HC, IgAN, vasculitis) classifications. This pipeline was compared with the current state-of-the-art single-aetiology CKD urinary peptide models. RESULTS: In an independent test set, the developed models achieved 90.35% and 70.13% overall predictive accuracies, respectively, for the binary and the multiclass classifications. Omitting the UMAP step led to improved predictive accuracies (96.14% and 85.06%, respectively). As expected, the HC class was distinguished with the highest accuracy. The different classes displayed a tendency to form distinct clusters in the 3D space based on their disease state. CONCLUSION: Urinary peptide data present an effective basis for CKD aetiology differentiation using machine learning models. Although adding the UMAP step to the models did not improve prediction accuracy, it may provide a unique visualization advantage. Additional studies are warranted to further validate the pipeline's clinical potential as well as to expand it to other CKD aetiologies and also other diseases.
EVALuna2:540388

Vascular Calcification in Chronic Kidney Disease: The Role of Inflammation - Benz, Kerstin; Hilgers, Karl Friedrich; Daniel, Christoph; Amann, Kerstin Ute (International Journal of Nephrology, 2018)
Cardiovascular complications are extremely frequent in patients with chronic kidney disease (CKD) and death from cardiac causes is the most common cause of death in this particular population. Cardiovascular disease is approximately 3 times more frequent in patients with CKD than in other known cardiovascular risk groups and cardiovascular mortality is approximately 10-fold more frequent in patients on dialysis compared to the age- and sex-matched segments of the nonrenal population. Among other structural and functional factors advanced calcification of atherosclerotic plaques as well as of the arterial and venous media has been described as potentially relevant for this high cardiovascular morbidity and mortality. One potential explanation for this exceedingly high vascular calcification in animal models as well as in patients with CKD increased systemic and most importantly local (micro)inflammation that has been shown to favor the development of calcifying particles by multiple ways. Of note, local vascular upregulation of proinflammatory and proosteogenic molecules is already present at early stages of CKD and may thus be operative for vascular calcification. In addition, increased expression of costimulatory molecules and mast cells has also been documented in patients with CKD pointing to a more inflammatory and potentially less stable phenotype of coronary atherosclerotic plaques in CKD.
EVALuna2:35397

Vascular inflammation and media calcification are already present in early stages of chronic kidney disease - Benz, Kerstin; Varga, Ildiko; Neureiter, Daniel; Campean, Valentina; Daniel, Christoph; Heim, Christian; Reimann, Albrecht; Weyand, Michael; Hilgers, Karl Friedrich; Amann, Kerstin Ute (Cardiovascular Pathology, 2017)
While patients with chronic kidney disease (CKD) have a high prevalence of classical coronary risk factors, there is increasing evidence that atherosclerosis is different in renal compared to nonrenal patients. Therefore, the present study compares changes in different vessels obtained at cardiac surgery between patients with early and advanced CKD and nonrenal control patients.Fifty patients undergoing cardiac bypass surgery were divided into three groups: (i) 24 control patients with creatinine <1.3mg/dl, (ii) 14 patients with early CKD (creatinine 1.3-2.0mg/dl), and (iii) 12 patients with advanced CKD (creatinine >2.0mg/dl). Aorta, arteria mammaria interna, and vena saphena (V. saphena) were analyzed using morphometry, Kossa stain for vascular calcification, and immunohistochemistry for markers of inflammation and proosteogenic differentiation of vascular smooth muscle cells (VSMCs). Thereby, aortic wall thickness and calcification score of aortic intima and of V. saphena were significantly higher in advanced CKD patients than in nonrenal control patients, whereas significant vascular inflammation and proosteogenic dedifferentiation of VSMC and calcification of the aortic media were already present in early CKD. Interestingly, marked calcification of the V. saphena magna was seen in advanced CKD. Of note, calcium-phosphate product correlated well with markers of inflammation, but not with calcification itself.Early stages of CKD are already associated with local up-regulation of proinflammatory and proosteogenic molecules in the vascular wall and calcification of the aortic media. These findings point to the importance of local microinflammation in CKD and may shed new light on the potentially overestimated role of the calcium-phosphate product for vessel calcification.
EVALuna2:3941

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

Vasodilator-stimulated phosphoprotein-deficient mice demonstrate increased platelet activation but improved renal endothelial preservation and regeneration in passive nephrotoxic nephritis. - Hohenstein, Bernd; Kasperek, Laura; Kobelt, Dieter-Johannes; Daniel, Christoph; Gambaryan, Stepan; Renne, Thomas; Walter, Ulrich; Amann, Kerstin Ute; Hugo, Christian (Journal of the American Society of Nephrology, 2005)
Vasodilator-stimulated phosphoprotein (VASP), an actin cytoskeletal protein, is expressed in various cell types including renal cells. In vitro studies provide evidence for a role of VASP regarding platelet activation, cell adhesion, migration, and capillary formation. The in vivo role of VASP was investigated in experimental inflammatory renal disease. Kidneys of healthy VASP deficient (-/-) and wild-type (wt) mice were compared regarding morphology and functional parameters. Passive nephrotoxic nephritis was induced in 28 VASP -/- and 28 wt mice; kidneys were harvested; and tissues were analyzed by morphometric, immunohistochemical, and electron microscopic techniques on days 3, 7, 14, and 28. The time course of disease in VASP -/- mice differed substantially and biphasically from that in wt controls. Early on, VASP -/- mice demonstrated increased platelet influx associated with augmented glomerular and tubulointerstitial inflammation and sclerosis. Whereas renal disease continuously worsened up to day 28 in wt controls, renal disease in VASP -/- mice hardly progressed after day 3 as assessed by various injury indices. This long-term improvement of renal histology in VASP -/-compared with wt mice was associated with remarkable capillary preservation/regeneration up to day 28 mediated via an increased proliferative and a reduced apoptotic activity of VASP-negative peritubular endothelial cells. Despite an enhanced injury response early on, VASP -/- mice are protected from long-term progression of nephrotoxic nephritis, which is associated with improved renal endothelial cell preservation and regeneration. Copyright © 2005 by the American Society of Nephrology.
UnivIS-Import:2017-03-24:Pub.2005.med.MKIPIII.MKIPLA.vasodi

Vitamin D-dependent induction of cathelicidin in human macrophages results in cytotoxicity against high-grade B cell lymphoma - Bruns, Heiko; Büttner, Maike; Fabri, Mario; Mougiakakos, Dimitrios; Bittenbring, Joerg T.; Hoffmann, Markus; Beier, Fabian; Pasemann, Shirin; Jitschin, Regina; Hofmann, Andreas D.; Neumann, Frank; Daniel, Christoph; et al. (Science Translational Medicine, 2015)
Infiltration by macrophages represents a characteristic morphological hallmark in high-grade lymphatic malignancies such as Burkitt's lymphoma (BL). Although macrophages can, in principle, target neoplastic cells and mediate antibody-dependent cellular cytotoxicity (ADCC), tumor-associated macrophages (TAMs) regularly fail to exert direct cytotoxic functions. The underlying mechanisms responsible for this observation remain unclear. We demonstrate that inflammatory M1 macrophages kill proliferating high-grade B cell lymphoma cells by releasing the antimicrobial peptide cathelicidin in a vitamin D-dependent fashion. We show that cathelicidin directly induces cell death by targeting mitochondria of BL cells. In contrast, anti-inflammatory M2 macrophages and M2-like TAMs in BL exhibit an altered vitamin D metabolism, resulting in a reduced production of cathelicidin and consequently in inability to lyse BL cells. However, treatment of M2 macrophages with the bioactive form of vitamin D, 1,25D3, or a vitamin D receptor agonist effectively induces cathelicidin production and triggers tumoricidal activity against BL cells. Furthermore, rituximab-mediated cytotoxicity of vitamin D-treated M2 macrophages is cathelicidin-dependent. Finally, vitamin D treatment of 25-hydroxyvitamin D (25D)-deficient volunteers in vivo or primary TAMs in vitro improves rituximab-mediated ADCC against B cell lymphoma cells. These data indicate that activation of the vitamin D signaling pathway activates antitumor activity of TAMs and improves the efficacy of ADC
EVALuna2:13103

Whole-exome sequencing identifies mutations of TBC1D1 encoding a Rab-GTPase-activating protein in patients with congenital anomalies of the kidneys and urinary tract (CAKUT) - Kosfeld, Anne; Kreuzer, Martin; Daniel, Christoph; Brand, Frank; Schaefer, Anne-Kathrin; Chadt, Alexandra; Weiss, Anna-Carina; Riehmer, Vera; Jeanpierre, Cecile; Klintschar, Michael; Braesen, Jan Hinrich; Amann, Kerstin Ute; et al. (Human genetics, 2016)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are genetically highly heterogeneous leaving most cases unclear after mutational analysis of the around 30 causative genes known so far. Assuming that phenotypes frequently showing dominant inheritance, such as CAKUT, can be caused by de novo mutations, de novo analysis of whole-exome sequencing data was done on two patient-parent-trios to identify novel CAKUT genes. In one case, we detected a heterozygous de novo frameshift variant in TBC1D1 encoding a Rab-GTPase-activating protein regulating glucose transporter GLUT4 translocation. Sequence analysis of 100 further CAKUT cases yielded three novel or rare inherited heterozygous TBC1D1 missense variants predicted to be pathogenic. TBC1D1 mutations affected Ser237-phosphorylation or protein stability and thereby act as hypomorphs. Tbc1d1 showed widespread expression in the developing murine urogenital system. A mild CAKUT spectrum phenotype, including anomalies observed in patients carrying TBC1D1 mutations, was found in kidneys of some Tbc1d1 (-/-) mice. Significantly reduced Glut4 levels were detected in kidneys of Tbc1d1 (-/-) mice and the dysplastic kidney of a TBC1D1 mutation carrier versus controls. TBC1D1 and SLC2A4 encoding GLUT4 were highly expressed in human fetal kidney. The patient with the truncating TBC1D1 mutation showed evidence for insulin resistance. These data demonstrate heterozygous deactivating TBC1D1 mutations in CAKUT patients with a similar renal and ureteral phenotype, and provide evidence that TBC1D1 mutations may contribute to CAKUT pathogenesis, possibly via a role in glucose homeostasis.
EVALuna2:25497

WT1-dependent sulfatase expression maintains the normal glomerular filtration barrier - Schumacher, Valerie A.; Schlötzer-Schrehardt, Ursula; Karumanchi, S. Ananth; Shi, Xiaofeng; Zaia, Joseph; Jeruschke, Stefanie; Zhang, Dongsheng; Pavenstaedt, Hermann; Drenckhan, Astrid; Amann, Kerstin Ute; Ng, Carrie; Hartwig, Sunny; et al. (Journal of the American Society of Nephrology, 2011)
Paracrine signaling between podocytes and glomerular endothelial cells through vascular endothelial growth factor A (VEGFA) maintains a functional glomerular filtration barrier. Heparan sulfate proteoglycans (HSPGs), located on the cell surface or in the extracellular matrix, bind signaling molecules such as VEGFA and affect their local concentrations, but whether modulation of these moieties promotes normal crosstalk between podocytes and endothelial cells is unknown. Here, we found that the transcription factor Wilms' Tumor 1 (WT1) modulates VEGFA and FGF2 signaling by increasing the expression of the 6-O-endosulfatases Sulf1 and Sulf2, which remodel the heparan sulfate 6-O-sulfation pattern in the extracellular matrix. Mice deficient in both Sulf1 and Sulf2 developed age-dependent proteinuria as a result of ultrastructural abnormalities in podocytes and endothelial cells, a phenotype similar to that observed in children with WT1 mutations and in Wt1(+/-) mice. These kidney defects associated with a decreased distribution of VEGFA in the glomerular basement membrane and on endothelial cells. Collectively, these data suggest that WT1-dependent sulfatase expression plays a critical role in maintaining the glomerular filtration barrier by modulating the bioavailability of growth factors, thereby promoting normal crosstalk between podocytes and endothelial cell
EVALuna2:21045

Zoledronate causes a systemic shift of macrophage polarization towards M1 in vivo - Weber, Manuel; Homm, Andi; Müller, Stefan; Frey, Silke; Amann, Kerstin Ute; Ries, Jutta; Geppert, Carol-Immanuel; Preidl, Raimund; Möst, Tobias; Kämmerer, Peer W.; Kesting, Marco Rainer; Wehrhan, Falk (International Journal of Molecular Sciences, 2021)
Background: Immunomodulatory properties of bisphosphonates (BP) are suggested to contribute to the development of medication‐associated osteonecrosis of the jaw (MRONJ). Further-more, bisphosphonate‐derived immune modulation might contribute to the anti‐metastatic effect observed in breast cancer patients. Macrophages are potential candidates for the mediation of immunomodulatory effects of bisphosphonates. The study aimed to investigate the influence of bisphosphonates alone and in combination with surgical trauma on systemic macrophage polarization (M1 vs. M2) using an in vivo rat model. Methods: A total of 120 animals were divided into four groups. Groups 2 and 4 were treated with 8 × 40 μg/kg body weight of the BP Zoledronate i.p. (week 0–7). Groups 3 and 4 were exposed to surgical trauma (week 8, tooth extraction + tibia fracture), whereas in Group 1 neither medication nor surgical trauma was applied. After 8, 10, 12 and 16 weeks, skin, lung and spleen were immunohistochemically examined for macrophage polarization via expression analysis of CD68, CD163 and iNOS using a tissue microarray (TMA). Results: A significant shift of macrophage polarization towards M1 was observed in skin, spleen and lung tissue of animals, with and without surgical trauma, treated with BP when compared to those without BP application. Surgical trauma did not cause a significant increase towards M1 polarization. Conclusions: BP application leads to a systemic pro‐inflammatory situation in vivo, independent of surgical trauma, as evidenced by the shift in macrophage polarization towards M1 in various somatic tissues. This provides a possible explanation for the clinically observed anti‐tumor effect of bisphosphonates and might also contribute to pathogenesis of MRONJ.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Antiresorptives; Bisphosphonate; Immune modulation; M1; M2; Macrophage polarization; Zoledronate

Zoledronate Shifts Macrophage Polarization towards M1 in Vivo - An Animal Study on Wistar Rats - Weber, Manuel; Amann, Kerstin Ute; Homm, Andi; Müller, Stefan; Ries, Jutta; Geppert, Carol-Immanuel; Preidl, Raimund; Kesting, Marco Rainer; Wehrhan, Falk (2020)
EVALuna2:216186

Zymogen-locked mutant prostasin (Prss8) leads to incomplete proteolytic activation of the epithelial sodium channel (ENaC) and severely compromises triamterene tolerance in mice - Essigke, Daniel; Ilyaskin, Alexandr; Wörn, Matthias; Bohnert, Bernhard N.; Xiao, Mengyun; Daniel, Christoph; Amann, Kerstin Ute; Birkenfeld, Andreas L.; Szabo, Roman; Bugge, Thomas H.; Korbmacher, Christoph; Artunc, Ferruh (Acta physiologica (Oxford, England), 2021)
Aim: The serine protease prostasin (Prss8) is expressed in the distal tubule and stimulates proteolytic activation of the epithelial sodium channel (ENaC) in co-expression experiments in vitro. The aim of this study was to explore the role of prostasin in proteolytic ENaC activation in the kidney in vivo. Methods: We used genetically modified knockin mice carrying a Prss8 mutation abolishing proteolytic activity (Prss8-S238A) or a mutation leading to a zymogen-locked state (Prss8-R44Q). Mice were challenged with low sodium diet and diuretics. Regulation of ENaC activity by Prss8-S238A and Prss8-R44Q was studied in vitro using the Xenopus laevis oocyte expression system. Results: Co-expression of murine ENaC with Prss8-wt or Prss8-S238A in oocytes caused maximal proteolytic ENaC activation, whereas ENaC was activated only partially in oocytes co-expressing Prss8-R44Q. This was paralleled by a reduced proteolytic activity at the cell surface of Prss8-R44Q expressing oocytes. Sodium conservation under low sodium diet was preserved in Prss8-S238A and Prss8-R44Q mice but with higher plasma aldosterone concentrations in Prss8-R44Q mice. Treatment with the ENaC inhibitor triamterene over four days was tolerated in Prss8-wt and Prss8-S238A mice, whereas Prss8-R44Q mice developed salt wasting and severe weight loss associated with hyperkalemia and acidosis consistent with impaired ENaC function and renal failure. Conclusion: Unlike proteolytically inactive Prss8-S238A, zymogen-locked Prss8-R44Q produces incomplete proteolytic ENaC activation in vitro and causes a severe renal phenotype in mice treated with the ENaC inhibitor triamterene. This indicates that Prss8 plays a role in proteolytic ENaC activation and renal function independent of its proteolytic activity.
CRIS-Team Scopus Importer:2021-03-19
Keywords: ENaC; epithelial sodium channel; Prostasin; Prss8; Prss8-R44Q; Prss8-S238A

Zyxin is important for the stability and function of podocytes, especially during mechanical stretch - Kliewe, Felix; Siegerist, Florian; Hammer, Elke; Al-Hasani, Jaafar; Amling, Theodor Rolf Jakob; Hollemann, Jonas Zeno Eddy; Schindler, Maximilian; Drenic, Vedran; Simm, Stefan; Amann, Kerstin Ute; Daniel, Christoph; Lindenmeyer, Maja; et al. (Communications Biology, 2024)
Podocyte detachment due to mechanical stress is a common issue in hypertension-induced kidney disease. This study highlights the role of zyxin for podocyte stability and function. We have found that zyxin is significantly up-regulated in podocytes after mechanical stretch and relocalizes from focal adhesions to actin filaments. In zyxin knockout podocytes, we found that the loss of zyxin reduced the expression of vinculin and VASP as well as the expression of matrix proteins, such as fibronectin. This suggests that zyxin is a central player in the translation of mechanical forces in podocytes. In vivo, zyxin is highly up-regulated in patients suffering from diabetic nephropathy and in hypertensive DOCA-salt treated mice. Furthermore, zyxin loss in mice resulted in proteinuria and effacement of podocyte foot processes that was measured by super resolution microscopy. This highlights the essential role of zyxin for podocyte maintenance in vitro and in vivo, especially under mechanical stretch.
CRIS-Team Scopus Importer:2024-04-19